30 Years of Oliver-Pharr: Then, Now and the Future of Nanoindentation - Maier-Kiener, Verena; Lawrence, Samantha K.; Merle, Benoit (JOM Journal of the Minerals, Metals and Materials Society, 2022)
CRIS-Team WoS Importer:2022-05-20

3D Aspects of Fracture and Effects due to Crack Front Curvature - Bitzek, Erik; Baranova, Polina; Möller, Johannes (14th International Conference on Fracture (ICF 14), 2017)

A1-L1(2) structures in the Al-Co-Ni-Ti quaternary phase system - Minshull, James P.; Neumeier, Steffen; Tucker, Matthew G.; Stone, Howard J. (2011)
The phase constituents of alloys from the (Ni,Co)(85)(Al,Ti)(15) plane of the Ni-Co-Al-Ti quaternary system were investigated following prolonged exposure at 750 degrees C. Microstructural investigations confirmed the existence of a continuous A1-L1(2)) two-phase region in the Ni-Co-Al-Ti quaternary system between Ni-Ni3Al and Co-Co3Ti. The lattice misfits of alloys from this quaternary system were determined using neutron diffraction. With increasing contents of Ti the positive lattice misfit increases up to +0.79% in the Ti-containing alloys, which leads to an increasing tetragonal distortion of the gamma matrix phase due to the increasing coherency stresses.
Keywords: Lattice misfit; neutron diffraction; Phase diagrams; Ni-Co-superalloys

About the role of interfaces on the fatigue crack propagation in laminated metallic composites - Pohl, Philip; Kümmel, Frank; Schunk, Christopher; Serrano-Munoz, Itziar; Markötter, Henning; Göken, Mathias; Höppel, Heinz Werner (Materials, 2021)
The influence of gradients in hardness and elastic properties at interfaces of dissimilar materials in laminated metallic composites (LMCs) on fatigue crack propagation is investigated ex-perimentally for three different LMC systems: Al/Al-LMCs with dissimilar yield stress and Al/Steel-LMCs as well as Al/Ti/Steel-LMCs with dissimilar yield stress and Young’s modulus, respectively. The damage tolerant fatigue behavior in Al/Al-LMCs with an alternating layer structure is enhanced significantly compared to constituent monolithic materials. The prevalent toughening mechanisms at the interfaces are identified by microscopical methods and synchrotron X-ray computed tomography. For the soft/hard transition, crack deflection mechanisms at the vicinity of the interface are observed, whereas crack bifurcation mechanisms can be seen for the hard/soft transition. The crack propagation in Al/Steel-LMCs was studied conducting in-situ scanning electron microscope (SEM) experiments in the respective low cycle fatigue (LCF) and high cycle fatigue (HCF) regimes of the laminate. The enhanced resistance against crack propagation in the LCF regime is attributed to the prevalent stress redistribution, crack deflection, and crack bridging mechanisms. The fatigue properties of different Al/Ti/Steel-LMC systems show the potential of LMCs in terms of an appropriate selection of constituents in combination with an optimized architecture. The results are also dis-cussed under the aspect of tailored lightweight applications subjected to cyclic loading.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Fatigue crack growth; Fatigue crack prop-agation; Interfaces; Laminated metallic composites; Large chamber SEM; Toughening mechanisms

A Carbon-Stabilized Austenitic Steel with Lower Hydrogen Embrittlement Susceptibility - Khanchandani, Heena; Zeiler, Stefan; Strobel, Lucas; Göken, Mathias; Felfer, Peter (Steel Research International, 2023)
High-strength steels are susceptible to H-induced failure, which is typically caused by the presence of diffusible H in the microstructure. The diffusivity of H in austenitic steels with face-centered cubic (fcc) crystal structure is slow. The austenitic steels are hence preferred for applications in the hydrogen-containing atmospheres. However, the fcc structure of austenitic steels is often stabilized by the addition of Ni, Mn, or N, which are relatively expensive alloying elements to use. Austenite can kinetically also be stabilized using C. Herein, an approach is applied to a commercial cold work tool steel, where C is used to fully stabilize the fcc phase. This results in a microstructure consisting of only austenite and M7C3 carbide. An exposure to H by cathodic hydrogen charging exhibits no significant influence on the strength and ductility of the C-stabilized austenitic steel. While this material is only a prototype based on an existing alloy of different purposes, it shows the potential for low-cost H-resistant steels based on C-stabilized austenite.
CRIS-Team Scopus Importer:2023-11-03
Keywords: atom probe tomography; austenite stabilizations; diffusible hydrogen; electron backscatter diffractions; hydrogen embrittlements

Accelerated grain refinement during accumulative roll bonding by nanoparticle reinforcement - Schmidt, Christian; Knieke, Catharina; Maier, Verena; Höppel, Heinz Werner; Peukert, Wolfgang; Göken, Mathias (Scripta Materialia, 2011)
Ceramic nanoparticles produced by comminution are introduced homogeneously during accumulative roll bonding (ARB) in aluminium AA1050A by airgun spraying from a stabilized aqueous suspension. In the so-produced nanoparticle-reinforced ultrafine-grained material, acceleration of microstructural evolution during the early ARB cycles as well as reduced grain sizes at higher cycles are observed, both caused by additional local straining around the embedded nanoparticles and accompanied by further strengthening. The presented method of nanoparticle application allows homogeneous as well as graded particle distributio

A combined dislocation - Cohesive zone model for fracture in a confined ductile layer - Broedling, Nils C.; Hartmaier, Alexander; Gao, Huajian (International Journal of Fracture, 2006)
The collective dislocation behavior near a crack tip in a ductile layer sandwiched between two brittle solids is analyzed via two-dimensional dislocation dynamics (DD) simulations that incorporate a cohesive zone (CZ) model. The cohesive crack tip is treated as part of a much larger finite crack confined in the ductile layer. The underlying boundary value problem is formulated with a set of boundary integral equations and numerically evaluated with a collocation method. The fracture energy of the layered composite material is shown to be strongly correlated with the layer thickness and is directly influenced by the cohesive strength of the ductile layer (Hsia KJ et al. (1994) J Mech Phys Solids 6 877-896). © Springer Science+Business Media B.V. 2006.
Created from Fastlane, Scopus look-up
Keywords: Confinement effects; Constrained plasticity; Discrete dislocation dynamics; Layered material; Microscale plasticity; Thin films

A computational geometry framework for the optimisation of atom probe reconstructions - Felfer, Peter; Cairney, Julie (Ultramicroscopy, 2016)
In this paper, we present pathways for improving the reconstruction of atom probe data on a coarse ( > 10 nm) scale, based on computational geometry. We introduce a way to iteratively improve an atom probe reconstruction by adjusting it, so that certain known shape criteria are fulfilled. This is achieved by creating an implicit approximation of the reconstruction through a barycentric coordinate transform. We demonstrate the application of these techniques to the compensation of trajectory aberrations and the iterative improvement of the reconstruction of a dataset containing a grain boundary. We also present a method for obtaining a hull of the dataset in both detector and reconstruction space. This maximises data utilisation, and can be used to compensate for ion trajectory aberrations caused by residual fields in the ion flight path through a 'master curve' and correct for overall shape deviations in the data. (C) 2016 Elsevier B.V. All rights reserve
Keywords: Atom probe tomography; Atom probe reconstruction; Data analysis

Activation parameters for deformation of ultrafine-grained aluminium as determined by indentation strain rate jumps at elevated temperature - Wheeler, J. M.; Maier, Verena; Durst, Karsten; Göken, Mathias; Michler, Johann (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
The hardness and strain rate sensitivity of ultrafine-grained (UFG) aluminium was examined as a function of temperature using in situ strain rate jump indentation in a SEM at temperatures up to 250 °C. Measured strain rate sensitivities were in good agreement with earlier bulk compression measurements. Activation energies and volumes for deformation were extracted and discussed. Transitions in the deformation mechanism are observed at lower temperatures for smaller grain sizes.
WW1::952

Active Fuse - Berberich, Sven E. Berberich; März, Martin; Bauer, Alexander; Beuer, Susanne; Ryssel, Heiner (Symposium on Power Semiconductor Devices and IC's, 2006)
In this work, we propose an active fuse which is a novel power device to prevent serious hazards in power electronics in the case of a fault. Using this active fuse, power devices or parts of power electronic circuits which are in an undefined, uncontrollable condition can be disconnected reliable and irreversible from the power supply. Critical safety consequences of faults like overheating or fire will be avoided. The focus of this work was to develop a monolithic integrated crowbar circuit including a fusible element the active fuse - with an application range from 1A to 5A and 48V at an operating temperature of 175degC<br

Additional grain boundary strengthening in length-scale architectured copper with ultrafine and coarse domains - Hou, Xiaodong; Krauß, Sebastian; Merle, Benoit (Scripta Materialia, 2019)
The strength of polycrystals is known to increase with decreasing grain size, known as Hall-Petch effect. However, this relationship fails to predict the strength of samples with a non-uniform distribution of grain sizes. In this study, we purposely designed and fabricated copper micropillars with a strongly bimodal microstructure: half volume consisted of a large number of ultrafine grains, while the other half was predominantly single-crystalline. Micropillar compression evidenced that bimodal samples are 35% stronger than their counterparts containing only ultrafine grains. This paradoxical finding highlights the greater strengthening potential of microstructure distribution engineering, compared to the traditional grain refinement strategy. (C) 2019 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-04-16

Additive Manufacturing of 3D Luminescent ZrO2:Eu3+ Architectures - Winczewski, Jędrzej; Herrera, Manuel; Cabriel, Clément; Izeddin, Ignacio; Gabel, Stefan; Merle, Benoit; Susarrey Arce, Arturo; Gardeniers, Han (Advanced Optical Materials, 2022)
Implementation of more refined structures at the nano to microscale is expected to advance applications in optics and photonics. This work presents the additive manufacturing of 3D luminescent microarchitectures emitting light in the visible range. A tailor-made organo-metallic resin suitable for two-photon lithography is developed, which upon thermal treatment in an oxygen-rich atmosphere allows the creation of silicon-free tetragonal (t-) and monoclinic (m-) ZrO2. The approach is unique because the tailor-made Zr-resin is different from what is achieved in other reported approaches based on sol−gel resins. The Zr-resin is compatible with the Eu-rich dopant, a luminescent activator, which enables to tune the optical properties of the ZrO2 structures upon annealing. The emission characteristics of the Eu-doped ZrO2 microstructures are investigated in detail with cathodoluminescence and compared with the intrinsic optical properties of the ZrO2. The hosted Eu has an orange−red emission showcased using fluorescence microscopy. The presented structuring technology provides a new platform for the future development of 3D luminescent devices.
CRIS-Team Scopus Importer:2022-05-06
Keywords: additive manufacturing; europium; luminescence; two-photon lithography; zirconia

Additive manufacturing of 3D yttria-stabilized zirconia microarchitectures - Winczewski, J. P.; Zeiler, Stefan; Gabel, Stefan; Maestre, D.; Merle, Benoit; Gardeniers, J. G.E.; Susarrey Arce, A. (Materials and Design, 2024)
The additive manufacturing (AM) of yttria-stabilized zirconia (YSZ) microarchitectures with sub-micrometer precision via two-photon lithography (TPL), utilizing custom photoresin containing zirconium and yttrium monomers is investigated. YSZ 3D microarchitectures can be formed at low temperatures (600 °C). The low-temperature phase stabilization of ZrO2 doped with Y2O3 demonstrates that doping ZrO2 with ≈ 10 mol% Y2O3 stabilizes the c-ZrO2 phase. The approach does not utilize YSZ particles as additives. Instead, the crystallization of the YSZ phase is initiated after printing, i.e., during thermal processing in the air at 600 °C – 1200 °C for one and two hours. The YSZ microarchitectures are characterized in detail. This includes understanding the role of defect chemistry, which has been overlooked in TPL-enabled micro-ceramics. Upon UV excitation, defect-related yellowish-green emission is observed from YSZ microarchitectures associated with intrinsic and extrinsic centers, correlated with the charge compensation due to Y3+ doping. The mechanical properties of the microarchitectures are assessed with manufactured micropillars. Micropillar compression yields the intrinsic mechanical strength of YSZ. The highest strength is observed for micropillars annealed at 600 °C, and this characteristic decreased with an increase in the annealing temperature. The deformation behavior gradually changes from ductile to brittle-like, correlating with the Hall–Petch strengthening mechanism.
CRIS-Team Scopus Importer:2024-04-05
Keywords: 3D printing; Additive manufacturing; Micromechanics; Photoluminescence; Yttria-stabilized zirconia

Advanced concentration analysis of atom probe tomography data: Local proximity histograms and pseudo-2D concentration maps - Felfer, Peter; Cairney, Julie (Ultramicroscopy, 2018)
Analysing the distribution of selected chemical elements with respect to interfaces is one of the most common tasks in data mining in atom probe tomography. This can be represented by 1D concentration profiles, 2D concentration maps or proximity histograms, which represent concentration, density etc. of selected species as a function of the distance from a reference surface/interface. These are some of the most useful tools for the analysis of solute distributions in atom probe data. In this paper, we present extensions to the proximity histogram in the form of 'local' proximity histograms, calculated for selected parts of a surface, and pseudo-2D concentration maps, which are 2D concentration maps calculated on non-flat surfaces. This way, local concentration changes at interfaces or and other structures can be assessed more effectively. (C) 2018 Elsevier B.V. All rights reserved.

Advanced Polycrystalline γ′-Strengthened CoNiCr-Based Superalloys - Neumeier, Steffen; Freund, Lisa; Bezold, Andreas; Köbrich, Manuel; Vollhüter, Jan; Hausmann, D.; Solis, C.; Stark, A.; Schell, N.; Pyczak, F.; Felfer, Peter; Gilles, R.; et al. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
Novel compositionally complex CoNiCr-based superalloys with excellent mechanical properties have been developed, which combine the multiprincipal element nature of high-entropy alloys with the precipitation strengthening in superalloys. A series of advanced polycrystalline γ′-strengthened CoNiCr-based superalloys, called CoWAlloys, with varying contents of Al, W, Ti, Ta, Mo, and Nb are investigated in terms of microstructure, thermophysical properties, yield, and creep strength. The microstructure of all CoWAlloys consists of an fcc solid solution matrix phase (approximate γ composition in at. pct: 50Co–20Ni–20Cr–10X (X = other alloying elements)), which is strengthened by a multicomponent γ′ (Ni,Co)3(Al,Ti,Ta,W,Nb)-based precipitate phase with a very high-volume fraction of around 60 vol pct (approximate γ′ composition in at. pct: 45Ni–30Co–25X). These alloys have high solidus temperatures above 1300 °C and moderate γ′ solvus temperature between 985 °C and 1080 °C leading to a large processing window. The increasing content of γ′-forming elements Ti, Ta, W, and Nb decreases this window, but increases the γ/γ′ lattice misfit and the anti-phase boundary energy, which contribute to a significantly higher yield and creep strength. Their properties are discussed in comparison with conventional polycrystalline Ni-base superalloys and so-called L12-strengthened high-entropy alloys, revealing that the creep strengths of the CoWAlloys are significantly higher. This is due to the reduced strain rate sensitivity of the CoWAlloys due to different underlying deformation mechanisms: By increasing the anti-phase boundary energy, a transition to stacking fault shearing and microtwinning occurs, which leads to the enhanced creep strength. Based on these results, guidelines and strategies for the design of next-generation advanced high-temperature polycrystalline superalloys are proposed. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-03-15

Advanced Rietveld refinement and SEM analysis of tobermorite in chemically diverse autoclaved aerated concrete - Schreiner, Jürgen; Götz-Neunhoeffer, Friedlinde; Neubauer, Jürgen; Bergold, Sebastian; Webler, Ralf; Volkmann, Stephan; Jansen, Daniel (Powder Diffraction, 2019)
Changes of structural properties of tobermorite in autoclaved aerated concrete (AAC) for various compositions were characterized and the disadvantages of SEM analysis in this context are discussed. The influence of variations in the chemical composition of raw materials on lattice parameters, morphology and domain sizes of tobermorite was investigated by XRD and for comparison by SEM analysis. Particularly the effect of substitution by Al3+ and (SO4)2− in tobermorite structure was examined. The dimensions of coherently scattering domains were calculated based on the refinement of anisotropic peak broadening of tobermorite in XRD diffractograms using a Rietveld compatible approach. No effect of (SO4)2− on the domain sizes and lattice parameters of tobermorite could be observed. The amount of anhydrite detected by quantitative XRD analysis indicates that all of the available (SO4)2− is present as anhydrite. Lath-like shapes of domains and a larger c parameter are calculated whenever Al3+ is incorporated in a considerable amount. Formation of katoite can be observed very clearly in SEMmicrographs whenever the amount of available Al3+ exceeds a distinct value in the dry mix. The effect of Al3+ and (SO4)2− on tobermorite morphology could not be observed clearly by SEM analysis in AAC samples.<br

Advancements in metal additive manufacturing: In-situ heat treatment of aluminium alloys during the laser powder bed fusion process - Schimbäck, D.; Kaserer, L.; Mair, P.; Mohebbi, M. S.; Staron, P.; Maier-Kiener, V.; Letofsky-Papst, I.; Kremmer, T.; Palm, F.; Montes, I.; Höppel, Heinz Werner; Leichtfried, G.; et al. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2024)
The high design freedom of laser powder bed fusion (LPBF) additive manufacturing enables new integrated structures, which in turn demand advances in the process conditions and material design to exploit the full potential of this process. A computational multi-scale thermal simulation and metallurgical analysis of the aluminium alloy Scalmalloy® were used to develop and present a specific process window to enable an in-situ heat treatment during LPBF. High resolution analysis and synchrotron experiments on specimens manufactured in this process window revealed a major proportion of nano-sized Al3(ScxZr1−x) solute-clusters were already present in the as-built state, as predicted by simulation. Supported by this experimental research, the new processing concept of in-situ heat treatment yielded the highest recorded strength values combined with high ductility directly after LPBF for Scalmalloy®. This advancement in LPBF enables highly complex, thin-walled structures directly made from a high-strength, lightweight material, which is not possible with conventional processes that require a subsequent heat treatment cycle.
CRIS-Team Scopus Importer:2024-06-07

A finite element modelling study of strain localization in the vicinity of near-surface cavities as a cause of subsurface fatigue crack initiation - Mughrabi, Hael; Höppel, Heinz Werner; et al. (International Journal of Fracture, 2002)
Recently, several observations of subsurface fatigue crack initiation in the vicinity of cavities in cast and in powder metallurgical (PM) alloys have been reported. In an attempt to explain these rather unexpected observations, an FE (finite element) modelling study of the stress and strain fields around spherical cavities of radius r lying at different distances below the surface of a tensile-stressed material has been performed. The results show that, due to the local stress enhancement in the 'bridge' of material between the cavity and the surface, an increasingly severe strain localization develops, as the distance d between the centre of the cavity and the free surface decreases and as the ratio rl(r + d) approaches 0.5 for a cavity located just underneath the surface (r = d). It is concluded that, under conditions of cyclic stressing, the strain localization in the immediate near-surface vicinity of a cavity lying just beneath the surface can be severe enough to cause the initiation of subsurface fatigue cracks. Depending on the detailed situation, these fatigue cracks can be initiated at the pore or at the adjacent outer surface.
UnivIS-Import:2015-03-09:Pub.2002.tech.IW.LWAW.afinit
Keywords: (Cylic) strain localization; Cavities; Finite element (FE) modelling; Subsurface fatigue crack initiation

A flexible method for the preparation of thin film samples for in situ TEM characterization combining shadow-FIB milling and electron beam-assisted etching - Liebig, Jan Philipp; Göken, Mathias; Richter, Gunther; Mackovic, Mirza; Przybilla, Thomas; Spiecker, Erdmann; Pierron, O. N.; Merle, Benoit (Ultramicroscopy, 2016)
A new method for the preparation of freestanding thin film samples for mechanical testing in transmission electron microscopes is presented. It is based on a combination of focused ion beam.(FIB) milling and electron-beam-assisted etching with xenon difluoride (XeF2) precursor gas. The use of the FIB allows for the target preparation of microstructural defects and enables well-defined sample geometries which can be easily adapted in order to meet the requirements of various testing setups. In contrast to existing FIB-based preparation approaches, the area of interest is never exposed to ion beam irradiation which preserves a pristine microstructure. The method can be applied to a wide range of thin film material systems compatible with XeF2 etching. Its feasibility is demonstrated for gold and alloyed copper thin films and its practical application is discussed. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Thin films; FIB; Electron-beam-assisted etching; XeF2; Micromechanical testing

Ag2Cu2O3- a catalyst template material for selective electroreduction of CO to C(2+)products - Marti, Nemanja; Reller, Christian; Macauley, Chandra; Löffler, Mario; Reichert, Andreas; Reichbauer, Thomas; Vetter, Kim-Marie; Schmid, Bernhard; Mclaughlin, David; Leidinger, Paul; Reinisch, David; Vogl, Christoph; et al. (Energy and Environmental Science, 2020)
Although recent years have brought significant progress within the field of electrochemical conversion of CO(2)and CO to value-added chemicals, many more challenges need to be overcome for this technology to be implemented on an industrial level. Rational design of catalyst materials that would enable selective production of desired products at industrially relevant current densities (>200 mA cm(-2)) is most certainly one of them. Here, we introduce Ag2Cu2O3, a mixed-metal oxide, as a starting template material for efficient electroreduction of CO to C(2+)products. By combining results from electrochemical real-time mass spectrometry (EC-RTMS), XRD and XPS we confirmed the template nature of Ag(2)Cu(2)O(3)andin situformation of a fully reduced CuAg bimetallic material during the first minutes of electrolysis. Electrochemical screening of the catalyst revealed significantly varying product distributions when CO2(CO2RR) and CO (CORR) where used as feed gases. During CORR, a faradaic efficiency close to 92% towards C(2+)products at 600 mA cm(-2)was achieved. On the other hand, during CO2RR, CO was found to be the main product under all tested current densities, reaching a maximum faradaic efficiency of 68%. XPS valence band spectra of the bimetallic surface originating from Ag(2)Cu(2)O(3)showed that its d-band electronic structure is noticeably different compared to metallic Ag and Cu, a finding we link to the observed product distributions. Finally, additional microscopy characterization techniques were used to investigate the observed surface reconstruction of the catalyst material under reaction conditions.
CRIS-Team WoS Importer:2020-10-02

A hierarchical multi-scale model for hexagonal materials taking into account texture evolution during forming simulation - He, W. J.; Zhang, S. H.; Prakash, Aruna; Helm, Dirk (Computational Materials Science, 2014)
Due to the absence of sufficient number of slip systems in hexagonal close packed (hcp) metals to accommodate arbitrary plastic deformation, mechanical twinning occupies an important role in the mechanical behavior of these metals. Twinning causes a significant and abrupt change in the orientation of crystals, whilst simultaneously affecting the hardening and plastic flow behavior of the material considerably. Modeling of forming processes of hexagonal close packed metals thus requires accounting for the evolution of texture and texture induced anisotropy, especially due to twinning. Additionally, the computational framework for the simulation of forming processes must be reliable and efficient in order to guarantee results in realistic time frames. In the present work, a phenomenological constitutive model consisting of an anisotropic yield function, associate flow rule and isotropic hardening, is coupled with the viscoplastic self-consistent polycrystal model in order to capture the slip and twinning activity, texture evolution and the evolving anisotropy during plastic deformation of hcp materials, similar to a hierarchical multi-scale modeling framework proposed by Van Houtte et al. [41] for cubic metals. To account for texture evolution during plastic deformation, the parameters involved in the anisotropic yield function are regularly updated based on mechanical test data obtained from the polycrystal model at the micro-scale. The parameter update is performed at discrete steps instead of every increment. The developed model is applied to describe the behaviors of pure zirconium at liquid nitrogen temperature. The results of the numerical simulations were found to be good agreement with experimental results, and at acceptable computation time.© 2013 Elsevier B.V. All rights reserved.
Keywords: Embedded model; Hexagonal materials; Hierarchical multi-scale model; Non-orthotropic yield function; Texture evolution; Visco-plastic self-consistent scheme

Allotropic transformation induced stacking faults and discontinuous coarsening in a γ-γ′ Co-base alloy - Bhowmik, Ayan; Neumeier, Steffen; Rhode, Sneha; Stone, Howard J. (Intermetallics, 2015)
The stability of a Co-based alloy designed to possess a microstructure comprising of L1, γ′ CoTi-type precipitates embedded in an A1, γ Co solid solution matrix has been investigated. The alloy showed acute microstructural instabilities upon ageing at 700 °C, resulting in the degeneration of the γ-γ′ aggregate into i) a faulted Co-based martensite and CoTi and ii) a lamellar aggregate of A3-Co and CoTi. The faulted Co-based phase was formed by isothermal diffusionless transformation of the metastable A1-phase, whilst the lamellar aggregate was a discontinuous reaction produc
WW1::1042
Keywords: A. Intermetallics; B. Diffusion; B. Phase transformation; D. Planar faults; F. Electron microscopy transmission

A low-cycle fatigue life predication model of ultrafine-grained metals - Mughrabi, Hael; Höppel, Heinz Werner; et al. (Fatigue & Fracture of Engineering Materials & Structures, 2002)
UnivIS-Import:2015-03-09:Pub.2002.tech.IW.LWAW.alowcy

A Modular and Automated Serial Section Collection System for Ultramicrotomy and Subsequent Imaging - Böhm, Thomas; Felfer, Peter; Thiele, Simon (Microscopy and Microanalysis, 2023)
Ultramicrotomy with automated section collection enables a reliable collection of sequential sections for 3D imaging. Here, we introduce a system for collecting several hundred ultra-thin sections on tape as a flexible polymeric substrate. The tape is stored within a portable cassette, which can be used as a modular platform for different applications. The motorized cassette with its retractable section collection cantilever is installed in front of an ultramicrotome for section collection. Section collection and imaging of the sections can be conducted without requiring any manual handling of the tape, which reduces the risk of specimen contamination and offers various options for automatization and cross-compatibility. For instance, processing steps such as a plasma glow-discharge of the substrate can be performed on the tape while it is enclosed in the cassette. As a proof of concept, more than 300 sequential sections at a thickness of 150 nm were cut from a polymer blend sample and collected on a metal-coated tape. Finally, a subset of 15 × 15 × 15 µm3 of the original sample volume was successfully imaged by confocal Raman microscopy and reconstructed at submicron resolution. The serial section cassette harbors the potential to standardize, simplify, and automate sample library collection, imaging, and storage.
CRIS-Team Scopus Importer:2023-12-29
Keywords: imaging; Raman microscopy; serial sectioning; tomography; ultramicrotomy

A Molecular Simulation Approach to Bond Reorganization in Epoxy Resins: From Curing to Deformation and Fracture - Konrad, Julian; Meißner, Robert H.; Bitzek, Erik; Zahn, Dirk (ACS Polymers Au, 2021)
We model bond formation and dissociation processes in thermosetting polymer networks from molecular dynamics simulations. For this, a coarsened molecular mechanics model is derived from quantum calculations to provide effective interaction potentials that enable million-atoms scale simulations. The importance of bond (re)organization is demonstrated for (i) simulating epoxy resin formation─for which our approach leads to realistic network models which can now account for degrees of curing up to 98%. Moreover, (ii) we elucidate the competition of bond dissociation and bond reformation during plastic deformation and fracture. On this basis, we rationalize the molecular mechanisms that account for the irreversible nature of damaging epoxy polymers by mechanical load.
Keywords: epoxy resin; reactive force-field; molecular dynamics; curing fracture; tensile testing

Amorphous Carbon Coatings for Total Knee Replacements—Part I: Deposition, Cytocompatibility, Chemical and Mechanical Properties - Rothammer, Benedict; Neusser, Kevin; Marian, Max; Bartz, Marcel; Krauß, Sebastian; Böhm, Thomas; Thiele, Simon; Merle, Benoit; Detsch, Rainer; Wartzack, Sandro (Polymers, 2021)
Diamond-like carbon (DLC) coatings have the potential to reduce implant wear and thus to contribute to avoiding premature failure and to increasing service life of total knee replacements (TKAs). This two-part study addresses the development of such coatings for ultrahigh molecular weight polyethylene (UHMWPE) tibial inlays as well as cobalt-chromium-molybdenum (CoCr) and titanium (Ti64) alloy femoral components. While a detailed characterization of the tribological behavior is the subject of part II, part I focusses on the deposition of pure (a-C:H) and tungsten-doped hydrogen-containing amorphous carbon coatings (a-C:H:W) and the detailed characterization of their chemical, cytological, mechanical and adhesion behavior. The coatings are fabricated by physical vapor deposition (PVD) and display typical DLC morphology and composition – as verified by focused ion beam scanning electron microscopy and Raman spectroscopy. Their roughness is higher than that of the plain substrates. Initial screening with contact angle and surface tension as well as in vitro testing by indirect and direct application indicate favorable cytocompatibility. The DLC coatings feature excellent mechanical properties with a substantial enhancement of indentation hardness and elastic modulus ratios. The adhesion of the coatings as determined in modified scratch tests can be considered as sufficient for the use in TKAs.<br
Keywords: DLC coating; Biomedical applications; Biotribology; UHMWPE; CoCr; Ti64; Total knee arthroplasty; Cytocompatibility; Hardness; Adhesion

Amorphous Carbon Coatings for Total Knee Replacements—Part II: Tribological Behavior - Rothammer, Benedict; Marian, Max; Neusser, Kevin; Bartz, Marcel; Böhm, Thomas; Krauß, Sebastian; Schroeder, Stefan; Uhler, Maximilian; Thiele, Simon; Merle, Benoit; Kretzer, J. Philippe; Wartzack, Sandro (Polymers, 2021)
Diamond-like carbon coatings may decrease implant wear, therefore, they are helping to reduce aseptic loosening and increase service life of total knee arthroplasties (TKAs). This two-part study addresses the development of such coatings for ultrahigh molecular weight polyethylene (UHMWPE) tibial inlays as well as cobalt-chromium-molybdenum (CoCr) and titanium (Ti64) alloy femoral components. While the deposition of a pure (a-C:H) and tungsten-doped hydrogen-containing amorphous carbon coating (a-C:H:W) as well as the detailed characterization of mechanical and adhesion properties were the subject of Part I, the tribological behavior is studied in Part II. Pin-on-disk tests are performed under artificial synovial fluid lubrication. Numerical elastohydrodynamic lubrication modeling is used to show the representability of contact conditions for TKAs and to assess the influence of coatings on lubrication conditions. The wear behavior is characterized by means of light and laser scanning microscopy, Raman spectroscopy, scanning electron microscopy and particle analyses. Although the coating leads to an increase in friction due to the considerably higher roughness, especially the UHMWPE wear is significantly reduced up to a factor of 49% (CoCr) and 77% (Ti64). Thereby, the coating shows continuous wear and no sudden failure or spallation of larger wear particles. This demonstrated the great potential of amorphous carbon coatings for knee replacements.
Keywords: DLC coating; Biomedical applications; Biotribology; UHMWPE; CoCr; Ti64; Total knee arthroplasty; Pin-on-disk; Friction; Wear

A multiscale simulation framework of the accumulative roll bonding process accounting for texture evolution - Prakash, Aruna; Nöhring, Wolfram Georg; Lebensohn, R. A.; Höppel, Heinz Werner; Bitzek, Erik (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2015)
The accumulative roll bonding process is one of the most prominent severe plastic deformation processes for obtaining sheet materials with ultra-fine-grained microstructures and high strength. The properties of such sheets differ significantly from those of conventionally rolled sheets. It is hence desirable to have a simulation framework that can accurately predict the material properties, including the evolving texture and anisotropy during processing. Here, we propose such a framework for multiple pass rolling using explicit finite elements and embedding the visco-plastic self-consistent (VPSC) polycrystal texture model for the material response. To facilitate multiple pass rolling, we propose a novel solution mapping scheme that transfers the material state from the deformed finite element mesh to a new one. Additionally, we implement a two-level parallelization scheme – with decomposition of the FE domain using message passing interface (MPI) and thread based parallelization of the material response using OPENMP – to ensure reduced simulation times. The predictive capabilities of the proposed framework are demonstrated by simulating the accumulative roll bonding of aluminum alloy AA5754 sheets. The simulations validate the working of the solution mapping scheme, and clearly show the development of a through thickness gradient of texture and anisotropy in the roll-bonded sheet after two passes.
WW1::1018

Analyzing the Precipitation Effects in Low-Alloyed Copper Alloys Containing Hafnium and Chromium - Dölling, Julia; Kuglstatter, Moritz; Prahl, Ulrich; Höppel, Heinz Werner; Ortner, Patrick; Ott, Benedict; Kracun, Stefanie Felicia; Fehlbier, Martin; Zilly, Andreas (Metals, 2024)
Copper alloys containing chromium and hafnium combine elevated mechanical strength and high electrical and thermal conductivity. For the simultaneous enhancement of both material properties, precipitation hardening is the utilized mechanism. Therefore, the aim is to analyze the influence of chromium and hafnium in binary and ternary low-alloyed copper alloys and to compare the precipitation processes during temperature exposure. Atom probe tomography (APT) and differential scanning calorimetry (DSC) measurements enable to understand the precipitation sequence in detail. CuCr0.7 starts to precipitate directly, whereas CuHf0.7 is highly influenced by prior diffusion facilitating cold rolling. Within the ternary alloy, hafnium atoms accumulate at the shell of mainly Cr-containing precipitates. Increasing the local hafnium concentration results in the formation of intermetallic CuHf precipitates at the sites of mainly Cr-containing precipitates. Indirect methods are utilized to investigate the materials’ properties and show the impact of cold rolling prior to an aging treatment on binary alloys CuCr and CuHf. Finally, ternary alloys combine the benefits of facilitated precipitation processes and decelerated growing and coarsening, which classifies the alloys to be applicable for usage at elevated temperatures.
CRIS-Team Scopus Importer:2024-04-05
Keywords: atom probe tomography APT; cold rolling; cold working; conduction materials; conductivity improvement; copper–chromium CuCr; copper–hafnium CuHf; CuHfCr; differential scanning calorimetry DSC; electrical and automotive engineering; high-performance copper alloy; precipitation hardening; precipitation mechanism

Analyzing the Precipitation Effects in Low-Alloyed Copper Alloys Containing Hafnium and Chromium - Dölling, Julia; Kuglstatter, Moritz; Prahl, Ulrich; Höppel, Heinz Werner; Ortner, Patrick; Ott, Benedict; Kracun, Stefanie Felicia; Fehlbier, Martin; Zilly, Andreas (Metals, 2024)
Copper alloys containing chromium and hafnium combine elevated mechanical strength and high electrical and thermal conductivity. For the simultaneous enhancement of both material properties, precipitation hardening is the utilized mechanism. Therefore, the aim is to analyze the influence of chromium and hafnium in binary and ternary low-alloyed copper alloys and to compare the precipitation processes during temperature exposure. Atom probe tomography (APT) and differential scanning calorimetry (DSC) measurements enable to understand the precipitation sequence in detail. CuCr0.7 starts to precipitate directly, whereas CuHf0.7 is highly influenced by prior diffusion facilitating cold rolling. Within the ternary alloy, hafnium atoms accumulate at the shell of mainly Cr-containing precipitates. Increasing the local hafnium concentration results in the formation of intermetallic CuHf precipitates at the sites of mainly Cr-containing precipitates. Indirect methods are utilized to investigate the materials’ properties and show the impact of cold rolling prior to an aging treatment on binary alloys CuCr and CuHf. Finally, ternary alloys combine the benefits of facilitated precipitation processes and decelerated growing and coarsening, which classifies the alloys to be applicable for usage at elevated temperatures.<br
Keywords: copper–hafnium CuHf; copper–chromium CuCr; CuHfCr; atom probe tomography APT; differential scanning calorimetry DSC; precipitation hardening; precipitation mechanism; cold working; cold rolling; conductivity improvement; high-performance copper alloy; conduction materials; electrical and automotive engineering

An Atom Probe with Ultra-Low Hydrogen Background - Felfer, Peter; Ott, Benedict; Monajem, Mehrpad; Dalbauer, Valentin; Heller, Martina; Josten, Jan; Macaulay, Chandra (Microscopy and Microanalysis, 2021)
Atom probe tomography (APT) is a single-ion sensitive time-of-flight mass spectrometry method with near-atomic spatial resolution. In principle, it can be used to detect any chemical element, but so far hydrogen in the form of protium (H-1) had to be largely excluded. This is owing to the residual H emitted from the stainless-steel chambers and in-vacuum parts commonly used in atom probe instrumentation. This residual H is then picked up in the APT experiment. In this paper, we show that by replacing the stainless-steel chamber and in-vacuum parts with titanium parts, this residual H can largely be removed, thus enabling the direct imaging of H using APT. We show that besides the drastic reduction of H, also other contaminants such as O, OH, and H2O are reduced by employing this instrument. In the current set-up, the instrument is equipped with high-voltage pulsing limiting the application to conductive materials.
CRIS-Team WoS Importer:2021-12-31

A new approach to the determination of concentration profiles in atom probe tomography - Felfer, Peter; Gault, Baptiste; Sha, Gang; Stephenson, Leigh; Ringer, Simon P.; Cairney, Julie M. (Microscopy and Microanalysis, 2012)
Abstract Atom probe tomography (APT) provides three-dimensional analytical imaging of materials with near-atomic resolution using pulsed field evaporation. The processes of field evaporation can cause atoms to be placed at positions in the APT reconstruction that can deviate slightly from their original site in the material. Here, we describe and model one such process-that of preferential retention of solute atoms in multicomponent systems. Based on relative field evaporation probabilities, we calculate the point spread function for the solute atom distribution in the "z," or in-depth direction, and use this to extract more accurate solute concentration profiles. © 2012 Microscopy Society of Americ
Keywords: atom probe tomography; concentration profiles; grain boundaries; interfaces; preferential retention; quantitative

A New Approach to Understand the Adsorption of Thiophene on Different Surfaces: An Atom Probe Investigation of Self-Assembled Monolayers - Eder, Katja; Felfer, Peter; Gault, Baptiste; Ceguerra, Anna V.; La Fontaine, Alexandre; Masters, Anthony F.; Maschmeyer, Thomas; Cairney, Julie M. (Langmuir, 2017)
Atom probe tomography was used to analyze self assembled monolayers of thiophene on different surfaces, including tungsten, platinum, and aluminum, where the tungsten was examined in both pristine and oxidized forms. A glovebag with controlled atmospheres was used to alter the level of oxidation for tungsten. It was shown that different substrates lead to substantial changes in the way thiophene adsorbs on the surface. Furthermore, the oxidation of the surface strongly influenced the adsorption behavior of the thiophene molecules, leading to clear differences in the amounts and compositions of field evaporated ions and molecular ions.

A new method for microscale cyclic crack growth characterization from notched microcantilevers and application to single crystalline tungsten and a metallic glass - Gabel, Stefan; Merle, Benoit; Bitzek, Erik; Göken, Mathias (Journal of Materials Research, 2022)
Keywords: kernfusionsrelevant

An improved long-term nanoindentation creep testing approach for studying the local deformation processes in nanocrystalline metals at room and elevated temperatures - Maier, Verena; Merle, Benoit; Göken, Mathias; Durst, Karsten (Journal of Materials Research, 2013)
The strain-rate sensitivity of ultrafine-grained aluminum (Al) and nanocrystalline nickel (Ni) is studied with an improved nanoindentation creep method. Using the dynamic contact stiffness thermal drift influences can be minimized and reliable creep data can be obtained from nanoindentation creep experiments even at enhanced temperatures and up to 10 h. For face-centered cubic (fcc) metals it was found that the creep behavior is strongly influenced by the microstructure, as nanocrystalline (nc) as well as ultrafine-grained (ufg) samples show lower stress exponents when compared with their coarse-grained (cg) counterparts. The indentation creep behavior resembles a power-law behavior with stress exponents n being ; 20 at room temperature. For higher temperatures the stress exponents of ufg-Al and nc-Ni decrease down to n ; 5. These locally determined stress exponents are similar to the macroscopic exponents, indicating that similar deformation mechanisms are acting during indentation and macroscopic deformation. Grain boundary sliding found around the residual indentations is related to the motion of unconstrained surface grains.
WW1::953

An improved method for point deflection measurements on rectangular membranes - Merle, Benoit; Nicholson, Kyle S.; Herbert, Erik G.; Göken, Mathias (Materials & Design, 2016)
In this work, the recent theoretical advances for evaluating point deflection experiments are reviewed and further refined. An improved experimental approach based on measuring the contact stiffness during nanoindentation is implemented and applied to the evaluation of the residual stress in SiNx and gold membranes. The accuracy of the point deflection experiments is assessed by evaluating the same set of samples with the bulge test reference technique and comparing the residual stress results. It is shown that the new experimental method greatly improves the reproducibility of the measurement and that the updated evaluation scheme leads to a more reliable residual stress value. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Point deflection; Nanoindentation; Continuous stiffness measurement; Bulge test; Thin film; Residual stress

Annealing treatments to enhance thermal and mechanical stability of ultrafine-grained metals produced by severe plastic deformation - Mughrabi, Hael; Höppel, Heinz Werner; Kautz, Martin; Valiev, Ruzlan (Zeitschrift für Metallkunde, 2003)
Ultrafine-grained (UFG) metals produced by techniques of severe plastic deformation, such as equal channel angular pressing (ECAP), exhibit extraordinary strength properties. However, in the as-ECAP-processed state, the heavily deformed microstructure of such UFG metals is rather unstable and is prone to undergo grain coarsening (recrystallization) at moderate temperatures. This microstructural instability is enhanced in the presence of modest mechanical stressing as, for example, in cyclic deformation. Thus, all measures to enhance the thermal stability are also considered as beneficial for the improvement of the mechanical stability. One main objective of the present work is to analyse the thermal and mechanical stability of ECAP-processed metals during specific annealing and cyclic deformation tests. As a by-product, some conclusions relating to the separate effects of dislocation density, grain size (in the UFG regime) and internal stresses on the (micro)yielding behaviour will be drawn. Another goal is to explore the potential of different annealing treatments with respect to the stabilization of the microstructure and the optimization of the mechanical properties of ECAP-processed UFG metals in terms of an optimal combination of strength and ductility. In order to demonstrate the potential and the limitations of this approach, experimental work performed on UFG copper, aluminium and α-brass produced by ECAP will be reported and discussed. The results presented indicate strongly that a heat treatment leading to a bimodal grain size distribution provides the best compromise between strength and ductilit
UnivIS-Import:2015-03-09:Pub.2003.tech.IW.LWAW.anneal
Keywords: Annealing; Ductility; Low-cycle fatigue; Microstructural stability; Recovery/recrystallization; Strength; Ultrafine-grained metals

Anomalous Work Hardening Behavior of a Single Crystalline Co-Base Superalloy - Bezold, Andreas; Volz, Nicklas; Xue, Fei; Neumeier, Steffen; Göken, Mathias (Alloys, 2022)
The defect evolution associated with an anomalous work hardening behavior of a single crystalline quaternary Co-Al-W-Ta superalloy at 950 °C was investigated by transmission electron microscopy. As plastic deformation is initially confined to the γ matrix channels, a plateau arises in the stress-strain curve after yielding. At about 1% plastic strain, extensive shearing of the γ′ precipitates under superlattice stacking fault formation occurs leading to extreme work hardening rates up to 12 GPa and a total increase in stress of about 200 MPa. Additional investigations on the temperature and strain-rate dependence of the anomalous work hardening behavior reveal the significance of diffusion and segregation processes on the stress-strain curve and the work hardening behavior.
Keywords: superalloy; yielding behavior; work hardening; transmission electron microscopy (TEM); high-temperature deformation

Anomalous yielding in the complex metallic alloy Al13Co4 - Walter, C.; Wheeler, J. M.; Barnard, J. S.; Raghavan, Rejin; Korte, Sandra; Gille, P.; Michler, Johann; Clegg, W. J. (Acta Materialia, 2013)
The single crystal deformation behaviour of orthorhombic Al13Co4 has been studied below the brittle-ductile transition temperature observed in bulk material from room temperature to 600° C, using indentation, microcompression and transmission electron microscopy. At room temperature, slip occurred most easily by dislocation motion on the (001)[010] slip system, as observed in the ductile regime at high temperatures. However, as the temperature was increased towards 600° C, the slip pattern changed to one consisting of linear defects running perpendicular to the loading axis. Serrated flow was observed at all temperatures, although at 600° C the magnitude of the serrations decreased. Anomalous yielding behaviour was also observed above 226° C, where both the yield and the 2% flow stress increased with temperature, almost doubling between 226 and 600° C. It has been suggested that this might arise due to the increasing stability of orthorhombic Al13Co4 with respect to the monoclinic form with increasing temperature. This is shown to be consistent with the theoretical predictions that exist.
EAM Import::2019-03-13

A novel type of Co-Ti-Cr-base γ/γ′ superalloys with low mass density - Zenk, Christopher; Povstugar, Ivan; Li, Rui; Rinaldi, Fernando; Neumeier, Steffen; Raabe, Dierk; Göken, Mathias (Acta Materialia, 2017)
A gamma' strengthened Co-Ti-Cr superalloy is presented with a mass density similar to 14 % below that of typical Co-Al-W-based alloys. The lattice misfit is sufficiently low to form coherent cuboidal gamma' precipitates. Atom probe tomography shows that Cr partitions to the gamma phase, but increases the gamma' volume fraction compared to a binary Co-Ti alloy to more than 60 %. The solubility of Cr in the gamma' phase is significantly higher than expected from previously published values. The gamma' solvus temperature is above 1100 degrees C. The yield strength shows a distinct increase above 600 degrees C surpassing that of Co-9Al-8W (at.%) and conventional Co-base superalloys, even more so when it is normalized by the mass density. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Co-base superalloys; Atom probe tomography (APT); High-temperature deformation; X-ray diffraction (XRD); Phase diagram calculation

An overview: Fatigue behaviour of ultrafine-grained metals and alloys - Höppel, Heinz Werner; Kautz, Martin; Xu, Cheng; Murashkin, Maxim; Langdon, Terence G.; Valiev, R. Z.; Mughrabi, Hael (International Journal of Fatigue, 2006)
The objectives of the present study were to assess and to optimize the fatigue behaviour in strain-controlled tests of different ultrafine-grained (UFG) metals and alloys (Cu, Al, AA6061, α-brass) prepared by equal channel angular pressing (ECAP). Quite generally, the UFG materials investigated exhibited shorter fatigue lives in the low-cycle fatigue (LCF) regime than corresponding conventional grain (CG) size specimens. In all cases, the fatigue lives could be enhanced appreciably by a suitable heat treatment following ECAP without, however, paralleling the fatigue lives of the CG specimens. The microstructural reasons for this behaviour are discussed, and a microstructure-based fatigue life model for UFG materials is presented.
Created from Fastlane, Scopus look-up
Keywords: α-Brass; AA6061; Aluminium; Annealing; Copper; ECAP; Fatigue life; Modelling; Ultrafine-grained materials

Applicability of focused Ion beam (FIB) milling with gallium, neon, and xenon to the fracture toughness characterization of gold thin films - Preiß, Eva; Merle, Benoit; Xiao, Yuan; Gannott, Florentina; Liebig, Jan Philipp; Wheeler, Jeffrey M.; Göken, Mathias (Journal of Materials Research, 2021)
Abstract: Focused ion beam (FIB) milling is an increasingly popular technique for fabricating micro-sized samples for nanomechanical characterization. Previous investigations have cautioned that exposure to a gallium ion beam can significantly alter the mechanical behavior of materials. In the present study, the effects of gallium, neon, and xenon ions are scrutinized. We demonstrate that fracture toughness measurements on freestanding gold thin films are unaffected by the choice of the ion species and milling parameters. This is likely because the crack initiation is controlled by the local microstructure and grain boundaries at the notch, rather than by the damaged area introduced by FIB milling. Additionally, gold is not susceptible to chemical embrittlement by common FIB ion species. This confirms the validity of microscale fracture measurements based on similar experimental designs. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2021-03-05

Application of change-point analysis to the selection of representative data in creep experiments - Zomorodpoosh, Setareh; Volz, Nicklas; Neumeier, Steffen; Roslyakova, Irina (Journal of Physics Communications, 2020)
The high volume of data resulting from a rapidly increasing number of experiments in materials science necessitates an efficient preparing of the data before any analysis. In addition, due to the large datasets in some experiments, it is essential to reduce the data sample to a small number of representative data points. In this study, three statistical methods for the change-point analysis are tested for the automated selection of representative creep data which provides large possibilities to speed up the data preparation for their further analysis. Moreover, this approach aids the practitioner to produce consistent and unique representative data for each experiment more efficiently.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Automated data selection; Change-point analysis; Creep; Non-stationary time series

Applying computational geometry techniques for advanced feature analysis in atom probe data - Felfer, Peter; Ceguerra, Anna; Ringer, Simon; Cairney, Julie (Ultramicroscopy, 2013)
In this paper we present new methods for feature analysis in atom probe tomography data that have useful applications in materials characterisation. The analysis works on the principle of Voronoi subvolumes and piecewise linear approximations, and feature delineation based on the distance to the centre of mass of a subvolume (DCOM). Based on the coordinate systems defined by these approximations, two examples are shown of the new types of analyses that can be performed. The first is the analysis of line-like-objects (i.e dislocations) using both proxigrams and line-excess plots. The second is interfacial excess mapping of an InGaAs quantum dot. (C) 2013 Elsevier B.V. All rights reserve
Keywords: Atom probe tomography; Data analysis; Proxigram; Interfacial excess; Interfacial excess mapping

A quantitative atom probe study of the Nb excess at prior austenite grain boundaries in a Nb microalloyed strip-cast steel - Felfer, Peter; Killmore, Chris R.; Williams, Jim G.; Carpenter, Kristin R.; Ringer, Simon P.; Cairney, Julie M. (Acta Materialia, 2012)
Most modern HSLA steels rely on the effect of Nb in steels to achieve the properties desired for a specific application. While the role of Nb in forming precipitates has been well characterized, its role in a solid solution is less well understood due to the difficulty of obtaining quantitative experimental data. In the current work, site-specific atom probe tomography was used to quantify the amount of Nb present at prior austenite grain boundaries in a commercial strip-cast steel, produced via the Castrip process. This was compared to the amount of Nb found at ferrite-ferrite grain boundaries that had formed during the transformation from austenite to ferrite. With the interfacial excess Nb measured, thermodynamic calculations were carried out and compared to the change in transformation temperature obtained by dilatometry, with reference to a comparable Nb free, strip-cast steel. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Atom probe tomography; Bainitic steel; Grain boundary segregation; Nucleation of phase transformations; Strip-casting

Architecture of β-lactoglobulin coating modulates bioinspired alginate dialdehyde-gelatine/polydopamine scaffolds for subchondral bone regeneration - Ghorbani, Farnaz; Kim, Myong-Ho; Ghalandari, Behafarid; Zhang, Mingjing; Varma, Swastina Nath; Schöbel, Lisa; Liu, Chaozong; Boccaccini, Aldo R. (Acta Biomaterialia, 2024)
In this study, we developed polydopamine (PDA)-functionalized alginate dialdehyde-gelatine (ADA-GEL) scaffolds for subchondral bone regeneration. These polymeric scaffolds were then coated with β-Lactoglobulin (β-LG) at concentrations of 1 mg/ml and 2 mg/ml. Morphological analysis indicated a homogeneous coating of the β-LG layer on the surface of network-like scaffolds. The β-LG-coated scaffolds exhibited improved swelling capacity as a function of the β-LG concentration. Compared to ADA-GEL/PDA scaffolds, the β-LG-coated scaffolds demonstrated delayed degradation and enhanced biomineralization. Here, a lower concentration of β-LG showed long-lasting stability and superior biomimetic hydroxyapatite mineralization. According to the theoretical findings, the single-state, representing the low concentration of β-LG, exhibited a homogeneous distribution on the surface of the PDA, while the dimer-state (high concentration) displayed a high likelihood of uncontrolled interactions. β-LG-coated ADA-GEL/PDA scaffolds with a lower concentration of β-LG provided a biocompatible substrate that supported adhesion, proliferation, and alkaline phosphatase (ALP) secretion of sheep bone marrow mesenchymal stem cells, as well as increased expression of osteopontin (SPP1) and collagen type 1 (COL1A1) in human osteoblasts. These findings indicate the potential of protein-coated scaffolds for subchondral bone tissue regeneration. Statement of Significance: This study addresses a crucial aspect of osteochondral defect repair, emphasizing the pivotal role of subchondral bone regeneration. The development of polydopamine-functionalized alginate dialdehyde-gelatine (ADA-GEL) scaffolds, coated with β-Lactoglobulin (β-LG), represents a novel approach to potentially enhance subchondral bone repair. β-LG, a milk protein rich in essential amino acids and bioactive peptides, is investigated for its potential to promote subchondral bone regeneration. This research explores computationally and experimentally the influence of protein concentration on the ordered or irregular deposition, unravelling the interplay between coating structure, scaffold properties, and in-vitro performance. This work contributes to advancing ordered protein coating strategies for subchondral bone regeneration, providing a biocompatible solution with potential implications for supporting subsequent cartilage repair.
CRIS-Team Scopus Importer:2024-06-07
Keywords: 3D printing; Alginate dialdehyde-gelatine; Polydopamine; Tissue engineering; β-Lactoglobulin

A reproducible method for damage-free site-specific preparation of atom probe tips from interfaces - Felfer, Peter; Alam, Talukder; Ringer, Simon Peter; Cairney, Julie Marie (Microscopy Research and Technique, 2012)
Atom probe tomography (APT) is a mass spectrometry method with atomic-scale spatial resolution that can be used for the investigation of a wide range of materials. The main limiting factor with respect to the type of problems that can be addressed is the small volume investigated and the randomness of common sample preparation methods. With existing site-specific specimen preparation methods it is still challenging to rapidly and reproducibly produce large numbers of successful samples from specifically selected grain boundaries or interfaces for systematic studies. A new method utilizing both focused ion beam (FIB) and transmission electron microscopy (TEM) is presented that can be used to reproducibly produce damage-free atom probe samples with features of interest at any desired orientation with an accuracy of better than 50 nm from samples that require very little prior preparation. © 2011 Wiley-Liss, In
Keywords: Atom probe; Atom probe tomography; Focused ion beam; Grain boundaries; Interface; Ion damage; Lift-out; Site specific

A review of experimental approaches to fracture toughness evaluation at the micro-scale - Ast, J.; Ghidelli, M.; Durst, K.; Göken, Mathias; Sebastiani, M.; Korsunsky, A. M. (Materials and Design, 2019)
The discipline of fracture mechanics was born almost a century ago through the pioneering work of A.A. Griffith, and saw particularly rapid growth in the second half of 20th century when it became an indispensable tool in the development of advanced transportation, civil construction, and energy systems. Forty years ago, Materials & Design published a series of papers devoted to the state-of-the-art in the field of Fracture Mechanics. The present review reflects the lasting legacy and surviving importance of this theme: it is associated with the Virtual Special Issue on nanoscale materials testing and characterisation, and focuses on the modern experimental approaches to fine scale fracture toughness evaluation, with particular emphasis on micro-cantilever bending and micro-pillar splitting. The fundamental aspects of these approaches are overviewed, and their application to a range of systems is described. Implications for further development of these methods are discussed.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Focused ion beam milling; Fracture toughness; Material characterisation; Micro-mechanics; Micro-scale

A scale-bridging study of the influence of TCP phases on the mechanical properties of an additive manufactured Ni-base superalloy combining microcompression testing, X-ray nanotomography and TEM - Sommerschuh, Michael; Wirth, Janis; Englisch, Silvan; Przybilla, Thomas; Apeleo Zubiri, Benjamin; Pistor, Julian; Merle, Benoit; Körner, Carolin; Göken, Mathias; Spiecker, Erdmann (Microscopy and Microanalysis, 2021)

A simple approach to atom probe sample preparation by using shadow masks - Felfer, Peter; Mccarroll, Ingrid; Macauley, Chandra; Cairney, Julie M. (Ultramicroscopy, 2016)
Here, we present a new method that utilises shadow masks in a broad ion beam system to prepare atom probe samples. It is particularly suited to non-conductors and materials with surface layers such as surface oxides, implanted layers or thin films. This new approach bypasses the focused ion beam (FIB) lift-out step, increasing the sample throughput, dramatically reducing the required FIB beam time and decreasing the complexity of sample preparation. (C) 2015 Elsevier By. All rights reserve
Keywords: Atom probe tomography; Sample preparation; Focused ion beam; Broad ion beam

A simple dislocation model of deformation resistance of ultrafine-grained materials explaining Hall-Petch strengthening and enhanced strain rate sensitivity - Blum, Wolfgang; Zeng, Xiaohui (Acta Materialia, 2009)
WW1::794

A simple method for residual stress measurements in thin films by means of focused ion beam milling and digital image correlation - Krottenthaler, Markus; Schmid, Christoph; Schaufler, Jens; Durst, Karsten; Göken, Mathias (Surface & Coatings Technology, 2013)
Hydrogenated amorphous carbon (a-C:H) coatings contain substantial residual stresses which particularly influence the failure behaviour of the coating system. However, measuring their residual stresses with conventional methods is not trivial. In this work, a simple method is presented to determine residual stresses of thin films locally by using stress relaxation tests by means of focused ion beam (FIB) milling and digital image correlation (DIC). It is shown, that the H-bar geometry, as it is used for TEM lamella preparation, is especially suitable for such measurements. Displacements due to relaxation of residual stresses are tracked using DIC and the stresses are obtained by correlation with finite element analysis. The method is applied to determine residual stresses of two a-C:H coatings processed with different deposition processes and parameters. It was found, that the coatings differ in their mechanical properties as well as in their residual stress state. The proposed method offers therefore a simple way for analysing residual stresses in thin amorphous coatings.
WW1::951

Assessment and optimization of the fast inertial relaxation engine (FIRE) for energy minimization in atomistic simulations and its implementation in LAMMPS - Guénolé, Julien; Nöhring, Wolfram G.; Vaid, Aviral; Houlle, Frederic; Xie, Zhuocheng; Prakash, Aruna; Bitzek, Erik (Computational Materials Science, 2020)
In atomistic simulations, pseudo-dynamical relaxation schemes often exhibit better performance and accuracy in finding local minima than line-search-based descent algorithms like steepest descent or conjugate gradient. Here, an improved version of the fast inertial relaxation engine (FIRE ) and its implementation within the open-source atomistic simulation code LAMMPS is presented. It is shown that the correct choice of time integration scheme and minimization parameters is crucial for the performance of FIRE.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Atomistic simulation; FIRE; IMD; LAMMPS; Pseudo-dynamics; Relaxation

Assessment of fatigue damage in heterogeneous materials by application of a novel compliancen technique - Mughrabi, Hael; Höppel, Heinz Werner (Solid Mechanics and Its Applications, 2008)
WW1::752

Assessment of stress relaxation experiments on diamond coatings analyzed by digital image correlation and micro-Raman spectroscopy - Ahmed, Furqan; Krottenthaler, Markus; Schmid, Christoph; Durst, Karsten (Surface & Coatings Technology, 2013)
The analysis and control of residual stresses are important for understanding the fracture and delamination behavior of coatings and thin films. In this work, the stress relaxation in microcrystalline diamond coatings after focused ion beam (FIB) milling was assessed by micro-Raman spectroscopy and digital image correlation. Using the FIB, the so called H-Bar geometry was milled in the diamond coating. The cutting introduced a strain relief in the coating perpendicular to the longer sides of the bar. The relaxation strains were recorded from high resolution scanning electron microscopy images of the H-Bar before and after FIB cutting. Using finite element modeling of the milled geometry, the residual stress level in the coating is evaluated from the relaxation strains. Furthermore, extgreekm-Raman spectroscopy was used to assess the biaxial residual stress level in the coating before and after FIB cutting. The extgreekm-Raman signal inside the bar showed strong incidence for stress relaxation and confirmed to some extent the applicability of the FIB–DIC method.
WW1::954

Asymmetric accumulative roll bonding of aluminium-titanium composite sheets - Hoi Pang Ng,; Przybilla, Thomas; Schmidt, Christian; Lapovok, Rimma; Orlov, Dmitry; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
Aluminium–titanium (Al/Ti) composite sheets were fabricated via asymmetric accumulative roll bonding (AARB), which capitalises on additional shear to enhance plastic deformation. Multi-layers of Al alloy (AA1050) and commercially-pure Ti sheets were alternatively stacked and rolled-bonded with varied roll diameter ratios (dr) ranging from 1 to 2, for up to four passes. Annealing of selected composite sheets was subsequently carried out at 600 °C for 24 h to compare the rates of solid-state diffusion reactions between Al and Ti components. Mechanical tests revealed that both tensile strength and ductility of the sheets increase systematically with dr. The microstructures and the Al/Ti interfaces of the sheets were analysed in detail using TEM, SEM and FIB techniques. It is shown that not only does AARB lead to a more refined grain size of the Al matrix but also it promotes the development of a nanostructured surface layer on Ti that comprises crystallites of 50–100 nm in size, which is otherwise absent in the case of symmetric ARB (i.e. dr=1). The AARB-processed sheets exhibit a larger thickness of the interdiffusion layer at the Al/Ti interfaces than the counterparts processed via the symmetric ARB route, the difference being in excess of 15%. The effects and the implications of AARB processing on mechanical behaviour and diffusion kinetics are discussed with respect to the microstructural evolutions.
WW1::955

Asymmetric accumulative roll bonding of aluminium–titanium composite sheets - Hoi Pang Ng,; Przybilla, Thomas; Schmidt, Christian; Lapovok, Rimma; Orlov, Dmitry; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
Keywords: Transmission electron microscopy; Asymmetric accumulative roll bonding; Al–Ti; Mechanical properties; Diffusion

ATI718PLUS® - New nickel based disc alloy and its capability - Huenert, Daniela; Pröbstle, Martin; Casanova, Ana; Schlütter, Regina; Krakow, Robert; Büscher, M.; Randelzhofer, Peter; Evans, A.; Löhnert, Katja; Witulski, T.; Neumeier, Steffen; Rae, Catherine M. F. (Superalloys 2016: Proceedings of the 13th Intenational Symposium of Superalloys, 2016)
Two extreme microstructural variants of alloy ATI718PLUS® were investigated regarding their tensile strength, creep resistance, long-term stability, oxidation and crack growth properties. The variants were produced by supersolvus and subsolvus forging procedures. A subsolvus forging produces fine-grained microstructure with aligned blocky secondary η-phase. The supersolvus forging generated a coarser grain size with improved creep performance and non-aligned lamellar η-phase. The oxidation behavior has been characterized showing superior performance of ATI718PLUS® relative to alloy 718 and 720LI. The results have been used to design optimized microstructures balancing the properties required for critical rotating parts. The analysis of several test conditions show, that key properties can be altered over a wide rang
Keywords: ATI718Plus® alloy; Creep; FCG; Long term stability; Oxidation; Tensile

Atomic-scale insights into surface species of electrocatalysts in three dimensions - Li, Tong; Kasian, Olga; Cherevko, Serhiy; Zhang, S.; Geiger, S.; Scheu, C.; Felfer, Peter; Raabe, Dierk; Gault, Baptiste; Mayrhofer, Karl (Nature Catalysis, 2018)
The topmost atomic layers of electrocatalysts determine the mechanism and kinetics of reactions in many important industrial processes, such as water splitting, chlor-electrolysis or fuel cells. Optimizing the performance of electrocatalysts requires a detailed understanding of surface-state changes during the catalytic process, ideally at the atomic scale. Here, we use atom probe tomography to reveal the three-dimensional structure of the first few atomic layers of electrochemically grown iridium oxide, an efficient electrocatalyst for the oxygen evolution reaction. We unveil the formation of confined, non-stoichiometric Ir-O species during oxygen evolution. These species gradually transform to IrO2, providing improved stability but also a decrease in activity. Additionally, electrochemical growth of oxide in deuterated solutions allowed us to trace hydroxy-groups and water molecules present in the regions of the oxide layer that are favourable for the oxygen evolution and iridium dissolution reactions. Overall, we demonstrate how tomography with near-atomic resolution advances the understanding of complex relationships between surface structure, surface state and function in electrocatalysis.

Atomic-scale modeling of elementary processes during the fatigue of metallic materials: from crack initiation to crack-microstructure interactions - Möller, Johannes; Bitzek, Erik (Fatigue of Materials at Very High Numbers of Loading Cycles - Experimental Techniques, Mechanisms, Modeling and Fatigue Life Assessment, 2018)
It is well known that the fatigue of metallic materials is governed by the accumulation of plastic slip, which ultimately leads to the initiation and propagation of cracks. Whether a material exhibits an infinite fatigue life or not is therefore determined by the complex interplay between plastic deformation processes, the formation of small crack nuclei and the direct and indirect interactions of cracks with the surrounding microstructure. It is this complex interplay with the microstructure that makes predictive modeling of fatigue in metals such a arduous task, even though the first empirical expressions for the fatigue life have been developed more than hundred years ago. For this reason, most macroscale material models for large-scale computer simulations are still directly parameterized through costly fatigue experiments instead of considering microstructural information and lower-scale deformation mechanisms. The focus of this work is therefore to investigate the fundamental mechanisms that are of relevance to metal fatigue: crack nucleation by slip accumulation at grain boundaries (GBs), crack propagation along GBs, dislocation-crack interactions, and the influence of crack front curvature, which is especially important as long as the cracks are very small. Studying the direct defect-defect interactions characteristic for these processes require atomic-scale resolution. Atomistic modelling methods, such as molecular dynamics (MD) simulations, are therefore ideally suited for their close and detailed investigation. Since atomistic simulations come with their own challenges in terms of limited time and length scale, it is important to note that the present work is intended to lay the foundations for the future developments of predictive, mechanism-based and microstructure-sensitive material models for large-scale fatigue simulations, rather than being by itself quantitatively predictive. Instead, we present several qualitative and semi-quantitative observations, which should also hold true in real materials. I.e., that dislocation pile ups are more critical for crack nucleation at GBs than homogeneously distributed dislocations and vacancies; that furthermore, the fracture behavior and toughness is markedly influenced by (i) crystal orientations, (ii) GB structures, (iii) pre-existing dislocations, and (iv) crack front curvature.Finally, future directions for atomistic modeling of fatigue damage are presente
Keywords: Atomistic simulations; fracture; fatigue; grain boundaries; dislocations

Atomic Structure and Chemical Composition of Planar Fault Structures in Co-Base Superalloys - Lenz, Malte; Wu, Mingjian; He, Junyang; Makineni, Surendra K.; Gault, Baptiste; Raabe, Dierk; Neumeier, Steffen; Spiecker, Erdmann (Minerals, Metals and Materials Series, 2020)
We report atomic structures and chemical compositions of defects associated to planar faults in a creep deformed Co-base superalloy and discuss their formation and contribution to plastic deformation. The multinary single crystalline Co-base superalloy was creep deformed under tension along [ 001 ] -direction at 850 °C and 400 MPa. The creep microstructure comprises a high density of planar defects. Solute segregation to superlattice intrinsic stacking faults (SISF) is characterized via EDXS analysis of a statistically relevant number of faults and compared at different creep stages. The amount of solute segregation shows negligible difference at different creep stages indicating that segregation directly occurs during planar fault formation and does not significantly evolve afterward. Based on the observation and analysis of Frank partial dislocations with a/3⟨111⟩ Burgers vectors terminating SISF, we discuss a new route to SISF formation via dislocation climb. Additionally, two more complex fault structures are analyzed, and potential formation mechanisms are discussed. The first of these structures is a terminating end of an SISF where an a/3⟨112⟩ partial dislocation splits up into two closely spaced a/6⟨112⟩ partials separated by an SESF. The second structure consists of two parallel SISFs connected by an anti-phase boundary (APB). All deformation mechanisms described in this study show an involvement of solute segregation directly affecting formation and propagation of creep defects by changing planar fault energies and chemical environments of dislocations. Solute segregation is therefore expected to be a key to future alloy design by enabling control of creep deformation mechanisms in specific temperature and stress regimes.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Co-base superalloy; Creep; Frank dislocation; Segregation; Stacking faults

Atomistic insights into the mixed-alkali effect in phosphosilicate glasses - Atila, Achraf; Ouldhnini, Youssef; Ouaskit, Said; Hasnaoui, Abdellatif (Physical Review B, 2022)
Oxide glasses have proven useful as bioactive materials, owing to their fast degradation kinetics and tunable properties. Hence, in recent years tailoring the properties of bioactive glasses through compositional design have become the subject of widespread interest for their use in medical application, e.g., tissue regeneration. Understanding the mixed alkali effect (MAE) in oxide glasses is of fundamental importance for tailoring the glass compositions to control the mobility of ions and, therefore, the glass properties that depend on it, such as ion release, glass transition temperature, and ionic conductivity. However, most of the previously designed bioactive glasses were based on trial-and-error, which is due to the complex glass structure that is nontrivial to analyze and, thus, the lack of a clear picture of the glass structure at short- and medium-range order. Accordingly, we use molecular dynamics simulations to study whether using the MAE can control the bioactivity and properties of 45S5 glass and its structural origins. We showed that the network connectivity, a structural parameter often used to access the bioactivity of silicate glasses, does not change with Na substitution with Li or K. On the contrary, the elastic moduli showed a strong dependence on the type of the modifier as they increased with increasing mean field strength. Similarly, the mobility of the glass elements was significantly affected by the type of modifier used to substitute Na. The change of the properties is further discussed and explained using changes at the short- and medium-range structure by giving evidence of previous experimental findings. Finally, we highlight the origin of the nonexistence of the MAE, the effect of the modifier on the bioactivity of the glasses, the importance of dynamical descriptors in predicting the bioactivity of oxide glasses, and we provide the necessary insights, at the atomic scale, needed for further development of bioactive glasses.
CRIS-Team Scopus Importer:2022-04-29

Atomistic insights into the structure and elasticity of densified 45S5 bioactive glasses - Ouldhnini, Youssef; Atila, Achraf; Ouaskit, Said; Hasnaoui, Abdellatif (Physical Chemistry Chemical Physics, 2021)
Glasses have applications in regenerative medicine due to their bioactivity, enabling interactions with hard and soft tissues. Soda-lime phosphosilicate glasses, such as 45S5, represent a model system of bioactive glasses. Regardless of their importance as bioactive materials, the relationship between the structure, density, and cooling process has not been studied in detail. This hinders further development of glasses as biomaterials. We used molecular dynamics simulations to study the elastic and structural properties of densified 45S5 bioactive glass and liquids over a wide range of densities. We performed a systematic analysis of the glass structure to density relationship to correlate the change in the properties with the structural change to enhance the mechanical properties of bioactive glasses while preserving their bioactive nature. The results show that the glass structure tends to be repolymerized, as indicated by increased network connectivity and a tetrahedral to octahedral polyhedral transition. We were able to tailor the elastic properties while keeping the bioactivity of the glass. The results presented here will provide some guidance to develop bioactive glasses with enhanced mechanical properties.
CRIS-Team WoS Importer:2021-07-23

Atomistic Model Analysis of Local and Global Instabilities in Crystals at Finite Temperature - Umeno, Yoshitaka; Nöhring, Wolfram Georg; Iskandarov, Albert; Bitzek, Erik (Key Engineering Materials, 2013)

Atomistic model analysis of local and global instabilities in crystals at finite temperature - Umeno, Yoshitaka; Nöhring, Wolfram Georg; Iskandarov, Albert; Bitzek, Erik (Key Engineering Materials, 2014)
WW1::985

Atomistic Simulation of Cracks versus Generalized Continua - Mousavi, Mahmoud; Guenole, Julien; Baranova, Polina; Bitzek, Erik; Korsunsky, Alexander M. (14th International Conference on Fracture (ICF 14), 2017)

Atomistic simulations of basal dislocations in Mg interacting with Mg17Al12 precipitates - Vaid, Aviral; Guenole, Julien; Prakash, Aruna; Korte-Kerzel, Sandra; Bitzek, Erik (Materialia, 2019)
The mechanical properties of Mg-Al alloys are greatly influenced by the complex intermetallic phase Mg17Al12, which is the most dominant precipitate found in this alloy system. The interaction of basal edge and 30∘ dislocations with Mg17Al12 precipitates is studied by molecular dynamics and statics simulations, varying the inter-precipitate spacing (L), and size (D), shape and orientation of the precipitates. The critical resolved shear stress τc to pass an array of precipitates follows the usual ln((1/D+1/L)−1) proportionality. In all cases but the smallest precipitate, the dislocations pass the obstacles by depositing dislocation segments in the disordered interphase boundary rather than shearing the precipitate or leaving Orowan loops in the matrix around the precipitate. An absorbed dislocation increases the stress necessary for a second dislocation to pass the precipitate also by absorbing dislocation segments into the boundary. Replacing the precipitate with a void of identical size and shape decreases the critical passing stress and work hardening contribution while an artificially impenetrable Mg17Al12 precipitate increases both. These insights will help improve mesoscale models of hardening by incoherent particles.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Atomistic simulations; Magnesium alloys; Mg; Molecular dynamics/statics; Precipitation strengthening

Atomistic Simulations of Compression Tests on gamma-Precipitate Containing Ni3Al Nanocubes - Houlle, Frederic; Walsh, Flynn; Prakash, Aruna; Bitzek, Erik (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2018)
The influence of gamma precipitates on the deformation behavior of gamma' Ni3Al nanocubes with 100 side surfaces is investigated by molecular dynamics simulations of uniaxial compression tests at 300 K. The plastic deformation of the nanocubes is caused by the nucleation of Shockley partial dislocations near the cube corners followed by the formation of pseudo-twins. While the dominant deformation mechanisms and the flow stress are not affected by the presence of precipitates, the precipitates reduce the yield stress by up to 10 pct and determine the location of dislocation nucleation. These findings can be rationalized by accounting for the misfit stresses caused by the presence of the gamma precipitates. Within the simulated ranges, the results are independent of cube size, rounding of the cube or precipitate corners, surface roughness, and strain rate. The observed precipitate softening in the dislocation-nucleation-controlled deformation of gamma' NiAl nanocubes is in stark contrast to the strengthening effect caused by the presence of a gamma phase in the gamma' precipitates in the microstructure of typical Ni- and Co-based superalloys.

Atomistic Simulations of Dislocation-Void Interactions in Concentrated Solid Solution Alloys - Vaid, Aviral; Zaiser, Michael; Bitzek, Erik (Metals, 2023)
This paper investigates the interaction of edge dislocations with voids in concentrated solid solution alloys (CSAs) using atomistic simulations. The simulation setup consists of edge dislocations with different periodicity lengths and a periodic array of voids as obstacles to dislocation motion. The critical resolved shear stress (CRSS) for dislocation motion is determined by static simulations bracketing the applied shear stress. The results show that shorter dislocation lengths and the presence of voids increase the CRSS for dislocation motion. The dislocation–void interaction is found to follow an Orowan-like mechanism, where partial dislocation arms mutually annihilate each other to overcome the void. Solute strengthening produces a ‘friction stress’ that adds to the Orowan stress. At variance with classical theories of solute pinning, this stress must be considered a function of the dislocation line length, in line with the idea that geometrical constraints synergetically enhance the pinning action of solutes. Modifying the equation by Bacon, Kocks and Scattergood for void strengthening to account for the solute hardening in CSAs allows one to quantitatively predict the CRSS in the presence of voids and its dependency on void spacing. The predictions show good agreement with the simulation data without invoking any fit parameters.
CRIS-Team Scopus Importer:2023-11-03
Keywords: atomistic simulations; concentrated solid solution alloys (CSA); dislocations; dislocation–void interaction; high-entropy alloys (HEA); superposition of strengthening; void strengthening

Atomistic simulations of focused ion beam machining of strained silicon - Guenole, Julien; Prakash, Aruna; Bitzek, Erik (Applied Surface Science, 2017)
focused ion beam (FIB) technique has established itself as an indispensable tool in the material science community, both to analyze samples and to prepare specimens by FIB milling. In combination with digital image correlation (DIC), FIB milling can, furthermore, be used to evaluate intrinsic stresses by monitoring the strain release during milling. The irradiation damage introduced by such milling, however, results in a change in the stress/strain state and elastic properties of the material; changes in the strain state in turn affect the bonding strength, and are hence expected to implicitly influence irradiation damage formation and sputtering. To elucidate this complex interplay between strain, irradiation damage and sputtering, we perform TRIM calculations and molecular dynamics simulations on silicon irradiated by Ga+ ions, with slab and trench-like geometries, whilst simultaneously applying uniaxial tensile and compressive strains up to 4%. In addition we calculate the threshold displacement energy (TDE) and the surface binding energy( SBE) for various strain states. The sputter rate and amount of damage produced in the MD simulations show a clear influence of the strain state. The SBE shows no significant dependence on strain, but is strongly affected by surface reconstructions. The TDE shows a clear strain-dependence, which, however, cannot explain the influence of strain on the extent of the induced irradiation damage or the sputter rate. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Irradiation demage; Strain; Atomistic simulation; Silicon; TRIM

Atomistic Study of Twinning in Gold Nanowhiskers - Bitzek, Erik (Journal of Solid Mechanics and Materials Engineering, 2012)
Twinning can become an important deformation mechanism in fcc metals once the crystal size is reduced to the sub-micron scale, e.g., in nanocrystals or nanowhiskers. The study of the twinning process, the interactions between propagating twins and between dislocations and twins is therefore important for a better understanding of the mechanical properties of metallic nanostructures. Here we show the results of atomistic simulations of defect-free nanowhiskers under tensile load using different EAM potentials for Au. The mechanisms of twin propagation and twin-stacking fault interaction are described and a modification to the criterion by Chen et al. [M. Chen et al., Science 300, 1275, 2003] for predicting twinning and its size dependence is presented.<br

Atom Probe Analysis of Nanoparticles through Pick and Coat Sample Preparation - Josten, Jan; Felfer, Peter (Microscopy and Microanalysis, 2021)
The ability to analyze nanoparticles in the atom probe has often been limited by the complexity of the sample preparation. In this work, we present a method to lift-out single nanoparticles in the scanning electron microscope. First, nanoparticles are dispersed on a lacey carbon grid, then positioned on a sharp substrate tip and coated on all sides with a metallic matrix by physical vapor deposition. Compositional and structural insights are provided for spherical gold nanoparticles and a segregation of silver and copper in silver copper oxide nanorods is shown in 3D atom maps. Using the standard atom probe reconstruction algorithm, data quality is limited by typical standard reconstruction artifacts for heterogeneous specimens (trajectory aberrations) and the choice of suitable coatings for the particles. This approach can be applied to various unsupported free-standing nanoparticles, enables preselection of particles via correlative techniques, and reliably produces well-defined structured samples. The only prerequisite is that the nanoparticles must be large enough to be manipulated, which was done for sizes down to 50 nm.
CRIS-Team Scopus Importer:2021-06-25
Keywords: atom probe tomography; micromanipulation; nanoparticles; pick and place

Atom probe informed simulations of dislocation-precipitate interactions reveal the importance of local interface curvature - Prakash, Aruna; Guenole, Julien; Wang, J.; Müller, Johannes; Spiecker, Erdmann; Mills, M. J.; Povstugar, Ivan; Choi, P.; Raabe, Dierk; Bitzek, Erik (Acta Materialia, 2015)
The interaction of dislocations with precipitates is an essential strengthening mechanism in metals, as exemplified by the superior high-temperature strength of Ni-base superalloys. Here we use atomistic simulation samples generated from atom probe tomography data of a single crystal superalloy to study the interactions of matrix dislocations with a γ′ precipitate in molecular dynamics simulations. It is shown that the precipitate morphology, in particular its local curvature, and the local chemical composition significantly alter both, the misfit dislocation network which forms at the precipitate interface, and the core structure of the misfit dislocations. Simulated tensile tests reveal the atomic scale details of many experimentally observed dislocation-precipitate interaction mechanisms, which cannot be reproduced by idealized simulation setups with planar interfaces. We thus demonstrate the need to include interface curvature in the study of semicoherent precipitates and introduce as an enabling method atom probe tomography-informed atomistic simulation
Keywords: Atom probe tomography (APT); Atomistic simulation; Misfit dislocation network; Ni-base superalloys; Precipitation hardening

Atom probe microscopy characterization of as quenched Zr-0.8 wt% Fe and Zr-0.15 wt% Cr binary alloys - Gault, Baptiste; Felfer, Peter; Ivermark, Maria; Bergqvist, Hans; Cairney, Julie M.; Ringer, Simon P. (Materials Letters, 2013)
Two binary Zr-alloys with a β-quenched structure were analysed by atom probe tomography to provide a better understanding of how Fe and Cr perform in industrial Zr alloys. In a Zr-0.8 Fe (wt%) alloy, we observed a dispersion of precipitates with a composition close to ZrFe, and Fe segregated to a grain boundary. In a Zr-0.15 Cr (wt%) alloy, Cr was observed in solid solution in the Zr-matrix and segregated to grain boundary where it formed small spherical particles or elongated atmospheres. © 2012 Elsevier B.V. All rights reserve
Keywords: Atom probe tomography; FIB specimen preparation; Grain boundary; Precipitation; Zr-alloys

Atom probe specimen preparation and 3D interfacial study of Ti-Al-N thin films - Rachbauer, Richard; Massl, S.; Stergar, E.; Felfer, Peter; Mayrhofer, P. H. (Surface & Coatings Technology, 2010)
3D-atom probe tomography is used to study the atomistic morphology of Ti-Al-N thin films in the as deposited and annealed states. We present results on modification of a focused ion beam based lift-out technique to meet the challenges for specimen preparation of substrate-free thin film material, which allows to avoid substrate interference during post-deposition annealing. We further emphasize the influence of doped silicon and low-carbon steel posts on the measurement performance during atom probe tomography of Ti(0.46)Al(0.54)N films. Pre-sharpened silicon posts ensure the preparation of equally shaped specimens, whereas steel posts reach a better mass resolution. Taking these results into account, we moreover examined the decomposition of Ti(0.46)Al(0.54)N towards TiN and AlN with respect to determination and distribution of oxygen impurities as a function of temperature. Thereby we observe an enrichment of these oxygen impurities in AIN with increasing annealing temperature to 1350 degrees C, from an originally random distribution in the as-deposited state. (C) 2009 Elsevier B.V. All rights reserve
Keywords: Ti-Al-N; TiAlN; Atom probe; 3DAPT; Thermal stability; Oxygen impurities

Atom probe study of chromium oxide spinels formed during intergranular corrosion - La Fontaine, Alexandre; Yen, Hung-Wei; Felfer, Peter; Ringer, Simon P.; Cairney, Julie M. (Scripta Materialia, 2015)
Atom probe microscopy has been used to study the inhomogeneous nature of chromium oxide spinels in intergranular corrosion of a 253 MA austenitic stainless steel after thermal cycling up to 970 °C in air. The results indicate that the non-continuous character of the spinel layers originates from nanoscale phases such as iron-rich oxides along the chromite grain boundaries and silicate particles. Their role in the rate of intergranular corrosion is discusse
Keywords: Atom probe tomography; Chromium oxide spinels; Corrosion; Oxidation; Stainless steel

Atom Probe Tomography - Felfer, Peter; Stephenson, L. T.; Li, T. (Praktische Metallographie, 2018)

Automated 3D assembly of periodic alumina-epoxy composite structures - Biggemann, Jonas; Diepold, Benedikt; Pezoldt, Marc; Stumpf, Martin; Greil, Peter; Fey, Tobias (Journal of the American Ceramic Society, 2018)
Keywords: Brick and mortar; Periodic structures; Pick and place; Building blocks; Interlocking

A versatile cryo-transfer system, connecting cryogenic focused ion beam sample preparation to atom probe microscopy - Macauley, Chandra; Heller, Martina; Rausch, Alexander; Kümmel, Frank; Felfer, Peter (PLoS ONE, 2021)
Atom probe tomography (APT) is a powerful technique to obtain 3D chemical and structural information, however the ‘standard’ atom probe experimental workflow involves transfer of specimens at ambient conditions. The ability to transfer air- or thermally-sensitive samples between instruments while maintaining environmental control is critical to prevent chemical or morphological changes prior to analysis for a variety of interesting sample materials. In this article, we describe a versatile transfer system that enables cryogenic- or room-temperature transfer of specimens in vacuum or atmospheric conditions between sample preparation stations, a focused ion beam system (Zeiss Crossbeam 540) and a widely used commercial atom probe system (CAMECA LEAP 4000X HR). As an example for the use of this transfer system, we present atom probe data of gallium- (Ga)-free grain boundaries in an aluminum (Al) alloy specimen prepared with a Ga-based FIB.
CRIS-Team Scopus Importer:2021-02-12

Between defects and inclusions: The fate of tellurium in pyrite - Börner, Frederik; Keith, Manuel; Fougerouse, Denis; Macauley, Chandra; Felfer, Peter; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann (Chemical Geology, 2023)
Tellurium (Te) is a critical commodity, essential for renewable energy technologies and other high-tech applications. Most Te is currently recovered from anode slimes, i.e., waste arising from copper refining. Rising demand and the key role for the green transition make the diversification and extension of the Te supply important. However, the nature of Te incorporation into ores is still poorly understood and hinders their economic potential. Here, we investigate the distribution of Te in pyrite from a high-grade Au-Ag-Te epithermal-type ore, where pyrite is already processed for ‘invisible’ Au, to inform metallurgical extraction methods, and secure future Te supply. Current models of Te incorporation into pyrite suggest a solid-solution limit in relation to As, similar as for ‘invisible’ Au. In this study, we identified three distinct modes of Te incorporation in pyrite, which challenge previous solubility models: (1) Te solid-solution, at concentrations (up to 285 ppma) that significantly exceed the previously suggested solubility limit. (2) Nano-telluride inclusions along cracks that formed by intra-grain remobilization. (3) Crystal defects, enriched in Te through pipe diffusion hosting up to 0.5 at. % Te. Our results therefore provide new fundamental insights into the chemical and structural coordination of Te in pyrite, which may guide future efforts for its direct recovery.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Atom probe tomography (APT); Defects; Inclusions; Low sulfidation epithermal; Pyrite; Solid solution; Tellurium (Te); Vatukoula

Between defects and inclusions: The fate of tellurium in pyrite - Börner, Frederik; Keith, Manuel; Fougerouse, Denis; Macauley, Chandra; Felfer, Peter; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann (Chemical Geology, 2023)
Tellurium (Te) is a critical commodity, essential for renewable energy technologies and other high-tech applications. Most Te is currently recovered from anode slimes, i.e., waste arising from copper refining. Rising demand and the key role for the green transition make the diversification and extension of the Te supply important. However, the nature of Te incorporation into ores is still poorly understood and hinders their economic potential. Here, we investigate the distribution of Te in pyrite from a high-grade Au-Ag-Te epithermal-type ore, where pyrite is already processed for ‘invisible’ Au, to inform metallurgical extraction methods, and secure future Te supply. Current models of Te incorporation into pyrite suggest a solid-solution limit in relation to As, similar as for ‘invisible’ Au. In this study, we identified three distinct modes of Te incorporation in pyrite, which challenge previous solubility models: (1) Te solid-solution, at concentrations (up to 285 ppma) that significantly exceed the previously suggested solubility limit. (2) Nano-telluride inclusions along cracks that formed by intra-grain remobilization. (3) Crystal defects, enriched in Te through pipe diffusion hosting up to 0.5 at. % Te. Our results therefore provide new fundamental insights into the chemical and structural coordination of Te in pyrite, which may guide future efforts for its direct recovery.<br
Keywords: Pyrite; Tellurium (Te); Atom probe tomography (APT); Low sulfidation epithermal; Solid solution; Inclusions; Defects; Vatukoula

Bimodal grain size distributions in UFG materials produced by SPD: Their evolution and effect on mechanical properties - Höppel, Heinz Werner; Korn, Matthias; Lapovok, R.; Mughrabi, Hael (2010)
The mechanical properties of bulk ultrafine-grained materials produced by severe plastic deformation can be modified (sometimes enhanced) by a mild annealing treatment which leads, in some cases, to a bimodal grain size distribution, characterized by a good combination of strength and ductility. Bimodal grain size distributions can also evolve during cyclic deformation at rather low homologous temperature. Here, the conditions under which bimodal grain size distributions evolve and how they affect the mechanical properties, as studied by the authors and as reported so far in the literature, will be reviewed and discussed

Bimodal grain size distributions in UFG materials produced by SPD - Their evolution and effect on the fatigue and monotonic strength properties - Korn, Matthias; Lapovok, R.; Böhner, A.; Höppel, Heinz Werner; Mughrabi, Hael (Kovove Materialy-Metallic Materials, 2011)
WW1::863

Bovine serum albumin-modified 3D printed alginate dialdehyde-gelatin scaffolds incorporating polydopamine/SiO2-CaO nanoparticles for bone regeneration - Kim, Myong-Ho; Schöbel, Lisa; Geske, Michael; Boccaccini, Aldo R.; Ghorbani, Farnaz (International Journal of Biological Macromolecules, 2024)
Three-dimensional (3D) printing allows precise manufacturing of bone scaffolds for patient-specific applications and is one of the most recently developed and implemented technologies. In this study, bilayer and multimaterial alginate dialdehyde-gelatin (ADA-GEL) scaffolds incorporating polydopamine (PDA)/SiO2-CaO nanoparticle complexes were 3D printed using a pneumatic extrusion-based 3D printing technology and further modified on the surface with bovine serum albumin (BSA) for application in bone regeneration. The morphology, chemistry, and in vitro bioactivity of PDA/SiO2-CaO nanoparticle complexes were characterized (n = 3) and compared with those of mesoporous SiO2-CaO nanoparticles. Successful deposition of the PDA layer on the surface of the SiO2-CaO nanoparticles allowed better dispersion in a liquid medium and showed enhanced bioactivity. Rheological studies (n = 3) of ADA-GEL inks consisting of PDA/SiO2-CaO nanoparticle complexes showed results that may indicate better injectability and printability behavior compared to ADA-GEL inks incorporating unmodified nanoparticles. Microscopic observations of 3D printed scaffolds revealed that PDA/SiO2-CaO nanoparticle complexes introduced additional topography onto the surface of 3D printed scaffolds. Additionally, the modified scaffolds were mechanically stable and elastic, closely mimicking the properties of natural bone. Furthermore, protein-coated bilayer scaffolds displayed controllable absorption and biodegradation, enhanced bioactivity, MC3T3-E1 cell adhesion, proliferation, and higher alkaline phosphatase (ALP) activity (n = 3) compared to unmodified scaffolds. Consequently, the present results confirm that ADA-GEL scaffolds incorporating PDA/SiO2-CaO nanoparticle complexes modified with BSA offer a promising approach for bone regeneration applications.
CRIS-Team Scopus Importer:2024-03-22
Keywords: 3D printing; Alginate dialdehyde-gelatin; Bovine serum albumin; Polydopamine; Silica-calcia; Tissue engineering

Breakdown of the superplastic deformation behavior of heterogeneous nanomaterials at small length scales - Feldner, Patrick; Merle, Benoit; Göken, Mathias (Materials Research Letters, 2021)
Ultrafine-grained and nanocrystalline materials frequently show an enhanced rate sensitivity of their mechanical behavior, which is generally assumed to be the consequence of interface sliding or thermally activated dislocation processes at the boundaries. Although this has been well documented on many different materials, the underlying mechanisms and their effect on the ductility of the material are still not well understood. Therefore, here, the deformation behavior of the ultrafine-grained, heterogeneous superplastic alloy Zn-22% Al was analyzed by small-scale nanoindentation and micropillar testing. The results show a breakdown of the superplastic deformation behavior in terms of a reduced strain rate sensitivity at small scales, which has not been reported before, although grain boundary sliding is still prevalent at the nanoscale. These results suggest that grain boundary sliding does not necessarily result in a high strain rate sensitivity and high ductility. Instead, a pronounced strain rate dependent flow behavior requires grain boundary sliding to be controlled by dislocation creep. Impact statement Superplastic flow is shown to persist down to a small material volume corresponding to a few grains. This has far-reaching consequences for the production of small-scale devices with complex geometries by superplastic forming.
CRIS-Team Scopus Importer:2020-10-09
Keywords: micropillar; nanoindentation; size effect; strain rate sensitivity; Superplasticity

Breaking the continuity of the Al2O3 oxide scale by additions of Cr in Co-Al-W-based superalloys - Liang, Zhida; Pyczak, Florian; Stark, Andreas; Rao, Ziyuan; Neumeier, Steffen; Göken, Mathias (Corrosion Science, 2021)
The paper presents the effect of small amounts of Cr alloying on the oxidation behavior of a Co-9Al-9W-2Si alloy. A small amount of Cr alloying inhibits the formation of a continuous Al2O3 scale in the oxide layers. The exact mechanism is explained by studying the transient oxidation stages. Cr addition can increase the diffusion rate of oxygen in the oxidation scale. Al is consumed very fast by forming Co(Al,Cr)2O4. This impedes the formation of Al2O3. As a result, the few formed Al2O3 particles do not merge to a continuous scale in the oxide layer.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Co-based superalloys; Oxidation; Synchrotron radiation; TEM

Bulge fatigue testing of freestanding and supported gold films - Merle, Benoit; Göken, Mathias (Journal of Materials Research, 2014)
The bulge test was used to investigate the fatigue properties of gold thin films with a thickness between 100 and 300 nm. The membranes were pressurized at a rate of 0.2 Hz up to 105 times, during which their stress and strain states were continuously recorded. Gold films on a silicon nitride substrate were cyclically loaded into tension and compression. Due to the presence of the substrate, no membrane failure was observed, but the residual stress shifted from an initially tensile state to an increasingly compressive one. Typical fatigue damage mechanisms consisting of extrusions were found in some large grains. Freestanding films were cyclically loaded in pure tension until failure occurred. The data acquired during the fatigue tests show a strong ratcheting of the films, which is indicative of cyclic plastic creep. Microstructural investigations clearly show grain boundary sliding in very thin films with columnar grains extending through the thickness.
WW1::987

CALPHAD informed design of multicomponent CoNiCr-based superalloys exhibiting large lattice misfit and high yield stress - Liang, Zhida; Neumeier, Steffen; Rao, Ziyuan; Göken, Mathias; Pyczak, Florian (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
Usually, Co-based superalloys contain a high fraction of W and/or Mo. The refractory elements stabilize the precipitate phase, but cause a high density. In this work, new L12-phase hardened, low-density CoNiCr-based superalloys were developed with the assistance of CALPHAD calculations. Several alloys were studied experimentally and their microstructures, elemental distributions, lattice parameters and the lattice misfit between the γ and γ′ phases were evaluated using scanning electron microscopy, transmission electron microscopy, atom probe tomography and high energy X-ray diffraction. The alloys exhibit a very high misfit, good phase stability and excellent mechanical strength. It was found by hardness tests that a two-step heat treatment improves the strength of the new alloys even further. In comparison with conventional Co-based superalloys, Co–Al–W based superalloys and Co–Ti based superalloys, as well as Ni-based superalloys, i.e. Udimet 720Li, they have a low mass density and high yield stress. They also overcome the problem of a generally low lattice misfit of previous L12-phase hardened CoNiCr-based superalloys with high Ni and Cr contents. As a result, they show cuboidal-shaped precipitates similar to Co–Al–W and Co–Al–Mo based superalloys.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Atom probe tomography; CALPHAD; Co-based superalloys; HEXRD; Lattice misfit; Yield stress

Castability and Recrystallization Behavior of γ′-Strengthened Co-Base Superalloys - Volz, Nicklas; Zenk, Christopher; Halvaci, Timur; Matuszewska, Katarzyna; Neumeier, Steffen; Göken, Mathias (Springer International Publishing, 2020)
Casting of single-crystalline superalloys is known to be difficult due to a variety of challenges. Co-based superalloysCo-base superalloys, however, promise to show quite good castability compared to Ni-based superalloys, as documented in this manuscript. Therefore, an alloy series, which is designed by changing only the Co-to-Ni ratio, is used to address this topic. In addition to the castingCasting behavior, segregationSegregation and recrystallizationRecrystallization behavior were also investigated, since these are closely related to castingCasting challenges. It was found that in the as-cast state, all alloying elements distribute more homogeneously in the Co-rich alloys which is beneficial for castingCasting. CastingCasting of directionally solidified tubes revealed that the Co-rich alloys show a lower susceptibility to hot tearing and predominantly develop cold cracks. Since cold cracking can be addressed by component design, Co-base superalloysCo-base superalloys are suggested to show a better castability compared to Ni-based superalloys. RecrystallizationRecrystallization, however, is more pronounced for the Co-rich alloys. This might become a problem during castingCasting of single-crystalline Co-base components, if high deformation is introduced in the solidified component.

CBED-Measurement of Residual Internal Strains in the Neighbourhood of TCP-Phases in Ni-Base Superalloys - Pyczak, Florian; Biermann, Horst; Mughrabi, Hael; Volek, Andreas; Singer, Robert (Superalloys 2000: Proceedings of the 9th Intenational Symposium of Superalloys, 2000)
UnivIS-Import:2015-04-16:Pub.2000.tech.IW.LWWTM.cbedme

Cell-based resurfacing of large cartilage defects: Long-term evaluation of grafts from autologous transgene-activated periosteal cells in a porcine model of osteoarthritis - Gelse, Koja; Muehle, Christiane; Franke, Oliver; Park, Jung; Jehle, Marc; Durst, Karsten; Göken, Mathias; Hennig, Friedrich; Mark, Klaus; Schneider, Holm (Arthritis & Rheumatism-Arthritis Care & Research, 2008)
WW1::753

Characterization of oxidation protection coatings for high temperature applications by means of nanoindentation and scanning electron microscopy methods - Webler, Ralf; Neumeier, Steffen; Göken, Mathias (Praktische Metallographie, 2014)
Oxidation protection coatings are required for thermally highly stressed components such as turbine blades in aircraft engines Cyclic oxidation experiments were performed on a NiCoCrAlY protective coating of a nickel-based superalloy and hardness and modulus of elasticity (mechanical properties) were determined by nanoindentation before and after the experiments Microstructure and chemical composition were characterized by means of scanning electron microscopy. Here, the focus is on the © Carl Hanser Verla
WW1::988

Characterization of phases of aluminized nickel base superalloys - Göken, Mathias; et al. (Surface & Coatings Technology, 2003)
Aluminum rich coatings, built up by a diffusion zone and a NiAl-cover layer, can protect the surface of turbine blades against oxidation. Within the single crystalline substrate and the adjacent layer, phases in the range of several tens of nanometers up to a few micrometers develop during production and operation of the turbine blade, were characterized. Investigations with transmission electron microscopy, nanoindentation and local crystal orientation mapping with a scanning electron microscope have been carried out in order to determine composition, morphology and distribution of the different phases. The diffusion zone has in general a defined orientation relative to the superalloy substrate and is built up by at least three phases embedded in a softer matrix, with significant differences in nanohardness. Local internal stress states in the diffusion zone are estimated. The NiAl-cover layer is a coarse columnar grained, non-textured B2 ordered intermetallic NiAl-phase. © 2002 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.tech.IW.LWAW.charac
Keywords: Electron back scattered diffraction; Nanoindentation; Nanostructure; Nickel alloy; Phase transitions; Transmission electron microscopy

Characterization of γ and γ′ Phases in 2nd and 4th Generation Single Crystal Nickel-Base Superalloys - Zietara, Maciej; Neumeier, Steffen; Göken, Mathias; Czyrska-Filemonowicz, Aleksandra (Metals and Materials International, 2017)
WW1::1088
Keywords: High Temperature

Close up on crystal plasticity - Mughrabi, Hael; Ungár, Tamas (Nature Materials, 2006)
A technique of X-ray diffraction was applied to investigate deformation-induced dislocation microstructures with submicrometer resolution. X-ray microscopy allows measurements of residual long-range internal stresses in deformed single crystals of copper with a spatial resolution of a few hundred nanometers. X-ray diffraction shows that long-range internal back-stresses prevailed in the cell interiors of their specimens that had been deformed in tension or in compression. The magnitude of the internal back-stresses varied from one cell interior to the next and shows that fluctuations are an inherent feature in deformed microstructures. The average diffraction profiles, obtained from large volumes of small crystal, exhibit characteristic asymmetrically broadened line profiles. The techniques provided advanced microstructural analysis of deformed crystalline materials.
Created from Fastlane, Scopus look-up

Coarsening of precipitates and degradation of creep resistance in tempered martensite steels - Chilukuru, Hemambar; Durst, Karsten; Wadekar, S.; Schwienheer, M.; Scholz, A.; Berger, C.; Mayer, K. H.; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::796
Keywords: kernfusionsrelevant

Combining Experiments and Atom Probe Tomography-Informed Simulations on γ′ Precipitation Strengthening in the Polycrystalline Ni-Base Superalloy A718Plus - Kirchmayer, Andreas; Lyu, Hao; Pröbstle, Martin; Houlle, Frederic; Förner, Andreas; Huenert, Daniela; Göken, Mathias; Felfer, Peter; Bitzek, Erik; Neumeier, Steffen (Advanced Engineering Materials, 2020)
The strength of superalloys is strongly influenced by γ′ precipitates, whose size and volume fraction which can be adjusted by heat treatments. According to classical precipitation strengthening models, an increasing precipitate diameter should lead to a transition from weak to strong coupling of the dislocation pairs that form superdislocations in the γ′ phase. We show that long-term annealing of the Ni-base superalloy A718Plus at 670 and 680 °C increases the alloy's strength without significantly changing the grain size and η fraction. To understand the effect of the slight increase in γ′ size, detailed atom probe tomography (APT) was performed. Here, different field evaporation rates of the phases strongly affect the determination of the volume fraction when using the usual isosurface construction. This can be mitigated by considering the number density of atoms inside and outside the γ′ precipitates. Using an approximation of the precipitate shapes and arrangements from the APT data in atomistic simulations revealed that precipitate shearing by both, weakly and strongly coupled dislocations can occur in the same sample due to the wide distribution of precipitate sizes. These results highlight the need for advanced strengthening models that take into account the γ′ size distribution.
CRIS-Team Scopus Importer:2020-06-02
Keywords: atom probe tomography; atomistic simulations; Ni-base superalloys; precipitation strengthening; weak–strong pair coupling

Combining multi-scale surface texturing and DLC coatings for improved tribological performance of 3D printed polymers - Marian, Max; Zambrano, Dario; Rothammer, Benedict; Waltenberger, Valentin; Boidi, Guido; Krapf, Anna; Merle, Benoit; Stampfl, Juergen; Rosenkranz, Andreas; Gachot, Carsten; Grützmacher, Philipp (Surface & Coatings Technology, 2023)
Polymer components fabricated by additive manufacturing typically show only moderate strength and low temperature stability, possibly leading to severe wear and short lifetimes especially under dry tribological sliding. To tackle these shortcomings, we investigated the combination of single- and multi-scale textures directly fabricated by digital light processing with amorphous diamond-like carbon (DLC) coatings. The topography of the samples and conformity of the coatings on the textures are assessed and their tribological behaviour under dry conditions is studied. We demonstrate that the surface textures have a detrimental tribological effect on the uncoated samples. This changes with the application of DLC coatings since friction substantially reduces and wear of the textures is not observed anymore. These trends are attributed to the protection of the underlying polymer substrate by the coatings and a reduced contact area. The best tribological performance is found for a coating with highest hardness and hardness-to-elasticity ratios. Moreover, multi-scale textures perform slightly better than single-scale textures due to a smaller real contact area. Summarizing, we verified that the high flexibility and low production costs of 3D printing combined with the excellent mechanical and tribological properties of DLC results in synergistic effects with an excellent performance under dry sliding conditions.<br

Comment to paper "penetration depth and tip radius dependence on the correction factor in nanoindentation measurements" by J.M. Meza et al. [J. Mater. Res. 23(3), 725 (2008)] - Durst, Karsten; Rehman, Hamad Ur; Merle, Benoit (Journal of Materials Research, 2012)
WW1::914

Comment to paper "Penetration depth and tip radius dependence on the correction factor in nanoindentation measurements" by JM Meza et al. [J. Mater. Res. 23(3), 725 (2008)] - Merle, Benoit; Durst, Karsten; Hamad-Ur-Rehman, - (2012)
[Meza et al. J. Mater. Res. 23(3), 725 (2008)] recently claimed that the correction factor beta for the Sneddon equation, used for the evaluation of nanoindentation load-displacement data, is strongly depth-and tip-shape-dependent. Meza et al. used finite element (FE) analysis to simulate the contact between conical or spheroconical indenters, and an elastic material. They calculated the beta factor by comparing the simulated contact stiffness with Sneddon's prediction for conical indenters. Their analysis is misleading, and it is shown here that by applying the general Sneddon equation, taking into account the true contact area, an almost constant and depth-independent beta factor is obtained for conical, spherical and spheroconical indenter geometries.

Comparative study of embedded atom potentials for atomistic simulations of fracture in α-iron - Möller, Johannes; Bitzek, Erik (Modelling and Simulation in Materials Science and Engineering, 2014)
Atomistic simulations play a crucial role in advancing our understanding of the crack-tip processes that take place during fracture of semi-brittle materials like extgreeka-iron. As with all atomistic simulations, the results of such simulations however depend critically on the underlying atomic interaction model. Here, we present a systematic study of eight extgreeka-iron embedded atom method potentials used to model cracks subjected to plane strain mode-I loading conditions in six different crystal orientations. Molecular statics simulations are used to determine the fracture behavior (cleavage, dislocation emission, twinning) and the critical stress intensity factor KIc. The structural transformations in front of the crack tips, and in particular the occurrence of [1 1 0] planar faults, are analyzed in detail and related to the strain-dependent generalized stacking fault energy curve. The simulation results are discussed in terms of theoretical fracture criteria and compared to recent experimental data. The different potentials are ranked according to their capability to model the experimentally observed fracture behavior.
EAM Import::2019-03-13
Keywords: atomistic simulation; EAM potential; fracture; iron

Comparison of the monotonic and cyclic mechanical properties of ultrafine-grained low carbon steels processed by continuous and conventional equal channel angular pressing - Niendorf, Thomas; Boehner, A.; Höppel, Heinz Werner; Göken, Mathias; Valiev, R. Z.; Maier, H. J. (Materials & Design, 2013)
WW1::956

Composition and cooling-rate dependence of plastic deformation, densification, and cracking in sodium borosilicate glasses during pyramidal indentation - Malchow, P.; Johanns, K. E.; Moencke, D.; Korte-Kerzel, Sandra; Wondraczek, Lothar; Durst, Karsten (Journal of Non-Crystalline Solids, 2015)
WW1::1021

Compression moduli of foamed films of fluorinated ethylene propylene copolymers determined by nanoindentation - Zirkel, Larissa; Maier, Verena; Durst, Karsten; Münstedt, Helmut (Polymer Testing, 2011)
Nanoindentation was applied to determine the elastic moduli in the compression mode of films of fluorinated ethylene propylene copolymers (FEP) foamed by means of supercritical carbon dioxide. For this purpose, a flat punch indenter with a diameter larger than the average cell size of the foams was found to be appropriate. The dependence of the mechanical properties of the films on their cellular structure was investigated by varying material and process parameters: molar mass of the FEP, the magnitude of the pressure drop and the temperature during the foaming process. The elastic modulus showed a strong influence of the cellular structure of the films. A decrease of the molar mass of FEP as well as an increase of pressure drop and foaming temperature considerably reduced the elastic modulus of the foams generated. This lowering of the stiffness correlated with the decrease of foam density. In addition, a significant contribution of the cellular morphology and the thickness of the compact skin layers of the foams could be noted. A further reduction of the foam stiffness was achieved by a biaxial stretching of the foams, which deformed the cells into a lens shape.
WW1::864

Confined recrystallization of high-purity aluminium during accumulative roll bonding of aluminium laminates - Chekhonin, Paul; Beausir, Benoit; Scharnweber, Juliane; Oertel, Carl-Georg; Hausöl, Tina; Höppel, Heinz Werner; Brokmeier, Heinz-Guenter; Skrotzki, Werner (Acta Materialia, 2012)
WW1::915

Conical nanoindentation allows azimuthally independent hardness determination in geological and biogenic minerals - Böhm, Corinna; Feldner, Patrick; Merle, Benoit; Wolf, Stephan (Materials, 2019)
The remarkable mechanical performance of biominerals often relies on distinct crystallographic textures, which complicate the determination of the nanohardness from indentations with the standard non-rotational-symmetrical Berkovich punch. Due to the anisotropy of the biomineral to be probed, an azimuthal dependence of the hardness arises. This typically increases the standard deviation of the reported hardness values of biominerals and impedes comparison of hardness values across the literature and, as a result, across species. In this paper, we demonstrate that an azimuthally independent nanohardness determination can be achieved by using a conical indenter. It is also found that conical and Berkovich indentations yield slightly different hardness values because they result in different pile-up behaviors and because of technical limitations on the fabrication of perfectly equivalent geometries. For biogenic crystals, this deviation of hardness values between indenters is much lower than the azimuthal variation in non-rotational-symmetrical Berkovich indentations.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Biomineralization; Hardness anisotropy; Mollusks; Nanoindentation

Contributions to understanding catalysis by using atom probe tomography - Cairney, Julie; Eder, Katja; Felfer, Peter; Masters, Anthony (AMER CHEMICAL SOC, 2016)

Control of dynamic recovery and strength by subgrain boundaries - Insights from stress-change tests on CaF2 single crystals - Mekala, Subba Rao; Eisenlohr, Philip; Blum, Wolfgang (Philosophical Magazine, 2011)
WW1::865

Correlation between constitution, properties and machining performance of TiN/ZrN multilayers - Göken, Mathias; et al. (Surface & Coatings Technology, 2004)
A concept for wear protective coatings on saw blades for metal cutting applications based on nanoscale titanium nitride/zirconium nitride (TiN/ZrN) multilayers is presented, which comprises the adjustment of columnar morphology for the cavities between the columns being used as a reservoir of cooling lubricants. The challenge consisted in optimizing the deposition conditions such that adhesion is increased to values that are normally reached by a compact morphology only (critical load of failure in the scratch test >40 N). Nanoscale TiN/ZrN multilayer were deposited by reactive dc-magnetron sputtering of metallic titanium and zirconium targets in argon/nitrogen plasma. These multilayers are a model system for a comprehensive characterization of both multilayers and their interfaces from the micrometer down to the nanometer-scale to correlate their constitution (X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM)), their properties (hardness: 2000-2600 HV0.015, reduced elastic modulus: 330-420 GPa, internal stress <1 GPa, critical load of failure in the scratch test: 30-85 N) and their performance in cutting screws made of freecutting steel of quality 11SMnPb30 (AISI 12L13, DIN 1.0718) at a cutting speed of 125 mm/min with coated high speed steel (HSS) saw blades (AISI M2, DIN 1.3343). In addition, the small angle cross-section method was developed for use in depth-resolved investigations of mechanical properties of multilayers and first results will be presented. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.correl
Keywords: Interfaces; Machining performance; Multilayer; Nano-indentation; Titanium nitride; Zirconium nitride

Correlation Between Local Chemical Composition and Formation of Different Types of Ordered Phases in the Polycrystalline Nickel-Base Superalloy A718Plus - Hausmann, Daniel; Förner, Andreas; Pröbstle, Martin; Huenert, Daniela; Felfer, Peter; Göken, Mathias; Neumeier, Steffen (Advanced Engineering Materials, 2021)
Allvac 718Plus is a derivative of alloy 718 for applications at higher temperatures in rotating and static components of gas turbines. According to literature, various phases as γ, γ′, η, δ, and γ″ can form with so far contradicting results. Herein, the precipitation behavior in different alloy conditions is investigated using transmission electron microscopy and atom probe tomography. The aim is to clarify how local variations in chemical composition alter the sequence of precipitation and type of precipitates that form. Material conditions with a minor volume fraction of η/δ phase and a high fraction of primary γ′ precipitates form γ″ phase due to excess of available Nb. Spherical γ′ precipitates with disc-shaped γ″ precipitates at γ′ interfaces are observed. During discontinuous coarsening of η/δ plates mainly Nb is consumed which leads to an enrichment of γ′ forming elements and hence the heterogeneous nucleation of γ′ at the η/γ interface. The coexistence of thin η plates embedded in δ phase in grain boundary pinning precipitates could additionally be confirmed. These results show under which conditions certain primary phases form and how the resulting consumption and redistribution of phase promoting elements trigger the formation of other secondary phases.
CRIS-Team Scopus Importer:2021-08-06
Keywords: atom probe tomography; Ni-base superalloys; precipitation behavior; scanning electron microscopy; transmission electron microscopy

Correlative Microscopy-Novel Methods and Their Applications to Explore 3D Chemistry and Structure of Nanoscale Lattice Defects: A Case Study in Superalloys - Makineni, S. K.; Lenz, M.; Kontis, P.; Li, Z.; Kumar, A.; Felfer, Peter; Neumeier, Steffen; Herbig, M.; Spiecker, Erdmann; Raabe, Dierk; Gault, Baptiste (JOM Journal of the Minerals, Metals and Materials Society, 2018)
Nanoscale solute segregation to or near lattice defects is a coupled diffusion and trapping phenomenon that occurs in superalloys at high temperatures during service. Understanding the mechanisms underpinning this crucial process will open pathways to tuning the alloy composition for improving the high-temperature performance and lifetime. Here, we introduce an approach combining atom probe tomography with high-end scanning electron microscopy techniques, in transmission and backscattering modes, to enable direct investigation of solute segregation to defects generated during high-temperature deformation such as dislocations in a heat-treated Ni-based superalloy and planar faults in a CoNi-based superalloy. Three protocols were elaborated to capture the complete structural and compositional nature of the targeted defect in the alloy.

Correlative Microscopy—Novel Methods and Their Applications to Explore 3D Chemistry and Structure of Nanoscale Lattice Defects: A Case Study in Superalloys - Makineni, Surendra Kumar; Lenz, Malte; Kontis, Paraskevas; Li, Zhuangming; Kumar, Ankit; Felfer, Peter; Neumeier, Steffen; Herbig, Michael; Spiecker, Erdmann; Raabe, Dierk; Gault, Baptiste (JOM Journal of the Minerals, Metals and Materials Society, 2018)
Nanoscale solute segregation to or near lattice defects is a coupled diffusion and trapping phenomenon that occurs in superalloys at high temperatures during service. Understanding the mechanisms underpinning this crucial process will open pathways to tuning the alloy composition for improving the high-temperature performance and lifetime. Here, we introduce an approach combining atom probe tomography with high-end scanning electron microscopy techniques, in transmission and backscattering modes, to enable direct investigation of solute segregation to defects generated during high-temperature deformation such as dislocations in a heat-treated Ni-based superalloy and planar faults in a CoNi-based superalloy. Three protocols were elaborated to capture the complete structural and compositional nature of the targeted defect in the alloy. <p

Corrigendum to Revealing atomic-scale vacancy-solute interaction in nickel(Scripta Materialia (2021) 203, (114036) (S135964622100316X), (10.1016/j.scriptamat.2021.114036)) - Morgado, Felipe F.; Katnagallu, Shyam; Freysoldt, Christoph; Klaes, Benjamin; Vurpillot, Francois; Neugebauer, Joerg; Raabe, Dierk; Neumeier, Steffen; Gault, Baptiste; Stephenson, Leigh T. (Scripta Materialia, 2021)
The authors regret there was an error in the affiliations for the authors of this article. The correct affiliations are now shown above. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2021-09-24

Crack-Free Welding of a Co-Base Superalloy with High γ' Precipitate Fraction - Haußmann, Lukas; Burbaum, Bernd; Stoehr, Britta; Förner, Andreas; Freund, Lisa; Göken, Mathias; Neumeier, Steffen (Advanced Engineering Materials, 2022)
Laser cladding of superalloys provides an attractive and cost-efficient technique for near-net shape manufacturing, remanufacturing, or individualized repair of components. While the weldability of γ' hardened Ni-base superalloys is limited, Co-base superalloys should have a lower susceptibility for cracking during welding due to a lower γ' solvus temperature and less segregation than Ni-base superalloys. The weldability of the Co-base superalloy CoWAlloy2Mod and the resulting mechanical properties at 950 °C are investigated. In the as-welded condition of CoWAlloy2Mod, a fine dendritic microstructure without forming cracks and limited porosity is found. After a three-step heat treatment, recrystallized, equiaxed grains and a high γ' volume fraction are obtained leading to a very good strength. CoWAlloy2Mod shows a significantly higher strength and creep strength than the conventional weld filler Co-alloy PWA795.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Co-base superalloy; compression test; creep; laser cladding; laser metal deposition

Crack Healing in Ti2Al0.5Sn0.5C-Al2O3 Composites - Bei, Guo Ping; Pedimonte, Birgit Joana; Pezoldt, Marc; Ast, Johannes; Fey, Tobias; Göken, Mathias; Greil, Peter (Journal of the American Ceramic Society, 2015)
Oxidation induced crack healing of Al2O3 composites loaded with a MAX phase based repair filler (Ti2Al0.5Sn0.5C) was examined. The fracture strength of 20 vol% repair filler loaded composites containing artificial indent cracks recovered fully to the level of the virgin material upon isothermal annealing in air atmosphere after 48 h at 700 degrees C and 0.5 h at 900 degrees C. SEM-EBSD analysis of crack microstructure indicates two different oxidation reaction regimes to govern the crack filling: near the surface SnO2, TiO2, and Al2O3 were formed whereas deeply inside the cracks Al2O3 and TiO2 and metallic Sn were detected. The presence of elemental Sn was attributed to partial oxidation of aluminum and titanium which lowered the local oxygen concentration below a threshold value required for Sn oxidation to SnO2. Thus, Ti2Al0.5Sn0.5C may represent an efficient repair filler system to trigger oxidation induced crack healing in ceramic composites at temperatures below 1000 degrees

Cracking during High-Temperature Deformation of a High-Strength Polycrystalline CoNi-Base Superalloy - Hausmann, Daniel; Freund, Lisa; Solis, Cecilia; Giese, Sven; Göken, Mathias; Gilles, Ralph; Neumeier, Steffen (Metals, 2022)
The crack susceptibility during processing has a crucial influence on the workability of wrought alloys. In particular, the processing of high-strength alloys that are prone to cracking is challenging and various process parameters have to be optimized to achieve a good formability. The polycrystalline CoNi-base superalloy CoWAlloy1 provides a high potential for high-temperature applications due to it having a large forging window, a high gamma ' fraction and excellent creep properties. In order to study its formability during hot rolling, its deformation behavior and susceptibility to cracking were characterized by sub- and supersolvus compression tests at temperatures between 1000-1150 degrees C. At temperatures around the gamma ' solvus temperature, no cracks formed during the compression testing, while at lower temperatures, cracking occurred. Additionally, an in-situ high-temperature small-angle neutron scattering revealed the phase fractions and the precipitate size distributions at different processing temperatures. It was found that a high fraction of gamma ' forms during cooling and cracking starts at the surface of the bar, when the hot bar encounters the cold rolls during hot rolling. Apparently, the precipitation of gamma ', which causes a high strength and reduced ductility, and the absent recrystallization leads to pronounced crack propagation and limited formability below the gamma ' solvus temperature.
CRIS-Team WoS Importer:2022-09-30

Crack initiation mechanisms in AA6082 fatigued in the VHCF-regime - Bach, Jochen; Höppel, Heinz Werner; Prell, M.; Göken, Mathias (International Journal of Fatigue, 2014)
WW1::992

Crack nucleation and elastic / plastic deformation of TiAl alloys investigated by in-situ loaded atomic force microscopy - Iqbal, Farasat; Pyczak, Florian; Neumeier, Steffen; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2017)
The crack propagation mechanisms of gamma-titanium aluminides with fully lamellar microstructure have been studied using in-situ deformation in the Atomic Force Microscope (AFM). AFM demonstrated the unique capability to detect elastic as well as plastic deformation during in-situ tests from topography changes on the surface. It was found that the crack nucleation, which can occur at gamma/gamma and alpha 2/y interfaces as well as inside the gamma-phase, is always preceded by strong local elastic deformation. No cracking inside the alpha 2-phase was observed. The elastic and plastic deformation was confined inside the gamma-phase and especially pronounced near interfaces which can be explained by the differences of the elastic and plastic deformation behavior of the gamma-and alpha 2-phase.
Keywords: TiAl; Crack nucleation; In-situ observation; AFM; Elastic/plastic deformation

Creep Behavior of Bulk Nanostructured Materials - Time-Dependent Deformation and Deformation Kinetics - Blum, Wolfgang; Eisenlohr, Philip; Sklenička, Vaclav (Bulk Nanostructured Materials, 2009)
Created from Fastlane, Scopus look-up
Keywords: Bulk nanostructured materials; Creep behavior; Deformation kinetics; Deformation resistance; Time-dependent deformation

Creep behavior of compact γ′-γ′′ coprecipitation strengthened in718-variant superalloy - Mukhopadhyay, Semanti; Sriram, Hariharan; Zenk, Christopher; Didomizio, Richard; Detor, Andrew J.; Hayes, Robert W.; Viswanathan, Gopal B.; Wang, Yunzhi; Mills, Michael J. (Metals, 2021)
The development of high-temperature heavy-duty turbine disk materials is critical for improving the overall efficiency of combined cycle power plants. An alloy development strategy to this end involves superalloys strengthened by ‘compact’ γ′-γ” coprecipitates. Compact morphology of coprecipitates consists of a cuboidal γ′ precipitate such that γ” discs coat its six 001 faces. The present work is an attempt to investigate the microstructure and creep behavior of a fully aged alloy exhibiting compact coprecipitates. We conducted heat treatments, detailed microstructural characterization, and creep testing at 1200◦ F (649◦ C) on an IN718-variant alloy. Our results indicate that aged IN718-27 samples exhibit a relatively uniform distribution of compact coprecipitates, irrespective of the cooling rate. However, the alloy ruptured at low strains during creep tests at 1200◦ F (649◦ C). At 100 ksi (689 MPa) load, the alloy fails around 0.1% strain, and 75 ksi (517 MPa) loading causes rupture at 0.3% strain. We also report extensive intergranular failure in all the tested samples, which is attributed to cracking along grain boundary precipitates. The results suggest that while the compact coprecipitates are indeed thermally stable during thermomechanical processing, the microstructure of the alloy needs to be optimized for better creep strength and rupture life.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Compact; Coprecipitates; Creep; ECCI; Grain boundary; IN718; Microstructure; Superalloy

Creep behavior of gold thin films investigated by bulge testing at room and elevated temperature - Merle, Benoit (Journal of Materials Research, 2019)
Keywords: strength; thin film

Creep-dominated fatigue of freestanding gold thin films studied by bulge testing - Krapf, Anna; Gebhart, David D.; Gammer, Christoph; Cordill, Megan J.; Merle, Benoit (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2023)
Although metallic thin films are widely used in microelectronics, their high-cycle fatigue properties are not well-understood. Cyclic testing was conducted on 150-nm thick freestanding gold thin films using nominal stress amplitudes between 50 and 150 MPa at 23–100 °C. As expected, lifetime decreases with increasing stress amplitude and temperature. The strain at failure hardly exceeds 1.5%, which is in agreement with previous studies on metallic thin films. The hysteresis stress-strain curves suggest that strain accumulates mostly due to cyclic creep. Based on this observation, we calculated the stress exponent n and activation energy Q – which are typical creep parameters – from the apparent steady-state strain rate observed during cyclic testing. Comparison to preexisting creep bulge tests show that the higher the temperature, the more pronounced the influence of creep on the fatigue behavior. Especially at 100 °C, creep mechanisms clearly dominate. At lower temperatures (23 °C) the data indicate that creep still plays a role, but intrinsic cycling effects become more pronounced. That leads us to postulate that the fatigue lifetime of gold thin films is closely connected to their creep properties.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Bulge test; Cyclic creep; Freestanding; Gold thin film; High-cycle fatigue

Creep properties and deformation mechanisms of single-crystalline gamma '-strengthened superalloys in dependence of the Co/Ni ratio - Volz, N.; Zenk, Carolin; Karpstein, Nicolas; Lenz, Malte; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Philosophical Magazine, 2021)
Co-base superalloys are considered as promising high temperature materials besides the well-established Ni-base superalloys. However, Ni appears to be an indispensable alloying element also in Co-base superalloys. To address the influence of the base elements on the deformation behaviour, high-temperature compressive creep experiments were performed on a single crystal alloy series that was designed to exhibit a varying Co/Ni ratio and a constant Al, W and Cr content. Creep tests were performed at 900 degrees C and 250 MPa and the resulting microstructures and defect configurations were characterised via electron microscopy. The minimum creep rates differ by more than one order of magnitude with changing Co/Ni ratio. An intermediate CoNi-base alloy exhibits the overall highest creep strength. Several strengthening contributions like solid solution strengthening of the gamma phase, effective diffusion coefficients or stacking fault energies were quantified. Precipitate shearing mechanisms differ significantly when the base element content is varied. While the Ni-rich superalloys exhibit SISF and SESF shearing, the Co-rich alloys develop extended APBs when the gamma ' phase is cut. This is mainly attributed to a difference in planar fault energies, caused by a changing segregation behaviour. As a result, it is assumed that the shearing resistivity and the occurring deformation mechanisms in the gamma ' phase are crucial for the creep properties of the investigated alloy series.
CRIS-Team WoS Importer:2022-01-07

Creep properties of different γ'-strengthened Co-base superalloys - Bauer, Alexander; Neumeier, Steffen; Pyczak, Florian; Singer, Robert; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2012)
The influence of various alloying elements on the creep properties of polycrystalline Co-base superalloys hardened by a ternary L1 compound, Co (Al,W) (γ'-phase), was investigated. A Ti containing quaternary alloy shows creep strength similar to Ni-base superalloys IN100 and IN713C at 850°C and strongly superior to conventional Co-base superalloys as Haynes188. The activation energy for creep between 850 and 950°C is similar to the polycrystalline Ni-base superalloy IN100 in the same temperature range. Strengthening of the grain boundaries by third phase precipitates was found to be crucial for the mechanical properties. This can be achieved either by precipitation of borides or by additional intermetallic phases which precipitate due to oversaturation. During compressive creep at 850°C only a slight tendency for directional coarsening occurs, while at 950°C distinct γ/γ'-rafts perpendicular to the external compressive stress axis are formed which indicate a positive lattice misfit even at 950°C. © 2012 Elsevier B.
Keywords: Boron; Cobalt; Creep; Grain boundary strengthening; Superalloy

Creep Strength and Microstructure of Polycrystalline γ′ - Strengthened Cobalt-Base Superalloys - Bauer, Alexander; Neumeier, Steffen; Pyczak, Florian; Göken, Mathias (John Wiley and Sons, 2012)
The influence of several alloying elements on the microstructure and creep properties of polycrystalline Co-base superalloys hardened with the ternary Ll2 compound, γ'-Co3(Al,W), are presented in this work. The stability of the γ/γ'-microstructure was investigated by long term aging at temperatures of 750 C° and 900 C°. High contents of chromium and iron destabilize the γ/γ'- microstructure. Additions of nickel widen the γ/γ'- two phase field. Discontinuous precipitation is observed only in the iridiumcontaining alloy during aging. In all other alloys no formation of further intermetallic phases are found even after 1000 hrs aging at 750 C° and 900 C°. Boron has been added for the formation of grain boundary strengthening intermetallic phases which leads to an adjacent γ'-depleted zone. Nanoindentation shows that titanium improves its hardness. The creep strength of the studied alloys is sufficiently better than that of commercial carbide hardened polycrystalline Co-base superalloys and already close to γ'- hardened Ni-base superalloys. An alloy containing 2 at.% titanium exhibited a creep strength comparable with the Ni-base alloy IN 100. The microstructure after creep tests at 950 C° showed rafting perpendicular to the compressive load axis, confirming the positive lattice misfit of the alloys at high temperatures which was determined with high energy X-ray diffraction. © 2012 The Minerals, Metals, & Materials Society. All rights reserved.
Keywords: Boron; Cobalt; Creep; Grain boundary strengthening; Superalloy

Creep transients during stress changes in ultrafine-grained copper - Kapoor, R.; Li, Yujiao; Wang, J. T.; Blum, Wolfgang (Scripta Materialia, 2006)
Stress change tests were conducted on ultrafine-grained Cu in a region where the grain size is smaller than the steady state subgrain size. After stress reduction the normal creep transients were absent, confirming subgrain strengthening in conventional grain-sized materials and a lack of steady state subgrain structure in the ultrafine-grained materials. © 2006 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Equal channel angular pressing (ECAP); Severe plastic deformation; Subgrain boundary; Transients; Ultrafine-grained Cu

Critical issues in conducting constant strain rate nanoindentation tests at higher strain rates - Merle, Benoit; Higgins, Wesley H.; Pharr, George M. (Journal of Materials Research, 2019)
Constant strain rate nanoindentation is a popular technique for probing the local mechanical properties of materials but is usually restricted to strain rates ≤0.1 s-1. Faster indentation potentially results in an overestimation of the hardness because of the plasticity error associated with the continuous stiffness measurement (CSM) method. This can have significant consequences in some applications, such as the measurement of strain rate sensitivity. The experimental strain rate range can be extended by increasing the harmonic frequency of the CSM oscillation. However, with commercial instruments, this is achievable only by identifying higher CSM frequencies at which the testing system is dynamically well behaved. Using these principles, a commercial system operated at the unusually high harmonic frequency of 1570 Hz was successfully used to characterize of the strain rate sensitivity of a Zn22Al superplastic alloy at strain rates up to 1 s-1, i.e., an order of magnitude higher than with standard methods.
CRIS-Team Scopus Importer:2019-10-25
Keywords: continuous stiffness measurement; nanoindentation; strain rate

Cumulate olivine: A novel host for heavy rare earth element mineralization - Brandt, Sönke; Faßbender, Marc Lorin; Klemd, Reiner; Macauley, Chandra; Felfer, Peter; Haase, Karsten (Geology, 2020)

Current trends in nanomechanical testing research - Merle, Benoit; Maier-Kiener, Verena; Rupert, Timothy J.; Pharr, George M. (Journal of Materials Research, 2021)
CRIS-Team WoS Importer:2021-07-16

Cyclic deformation and fatigue behaviour of the magnesium alloy AZ91 - Mughrabi, Hael; Höppel, Heinz Werner; et al. (Proc. of 12th Int. Conf. on Strength of Materials (ICSMA 12), 2001)
UnivIS-Import:2015-04-16:Pub.2001.tech.IW.LWAW.cyclic_5

Cyclic deformation and fatigue behaviour of the magnesium alloy AZ91: temperature effects and two-step fatigue tests - Höppel, Heinz Werner; Mughrabi, Hael; et al. (Proc. of 8th Int. Fatigue Congress (FATIGUE 2002), 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IW.LWAW.cyclic_33

Cyclic deformation and fatigue properties of very fine-grained metals and alloys - Mughrabi, Hael; Höppel, Heinz Werner (International Journal of Fatigue, 2010)
WW1::836

Cyclic deformation behavior and fatigue lives of ultrafine-grained Ti-6AL-4V ELI alloy for medical use - Saitova, L. R.; Höppel, Heinz Werner; Göken, Mathias; Semenova, I. P.; Valiev, R. Z. (International Journal of Fatigue, 2009)
Keywords: Fatigue strength; Damage; Ti-6Al-4V; S-N curves; Ultrafine-grained material

Cyclic deformation behavior and fatigue lives of ultrafine-grained Ti-6AL-4V ELI alloy for medical use - Saitova, L. R.; Höppel, Heinz Werner; Göken, Mathias; Semenova, I. P.; Valiev, R. Z. (International Journal of Fatigue, 2009)
It was shown that introducing an ultrafine-grained (UFG) microstructure in pure metals as well as some alloys leads to strongly enhanced fatigue properties. The cyclic deformation behavior of UFG Ti-6Al-4V ELI (extra low interstitials) alloy is studied by both strain and stress controlled fatigue tests using plastic strain amplitudes between 3 x 10(-4) and 5 x 10(-3) and stress amplitudes ranging from 550 to 670 MPa. The UFG microstructures were obtained by equal channel angular pressing (ECAP) with different number of passes followed by a subsequent thermomechanical treatment (TMT). When compared to the conventional grain (CG) size counterpart, the UFG alloy exhibited a pronounced enhancement in the fatigue life in the S-N (Wohler) diagram. It was also shown that additional UFG processing prior to TMT did not result in any further improvement of the fatigue resistance. Furthermore, microstructural investigations revealed a high cyclic stability of the UFG microstructure. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Ti-6Al-4V; Ultrafine-grained material; Fatigue strength; S-N curves; Damage

Cyclic deformation behavior and fatigue lives of ultrafine-grained Ti-6AL-4V ELI alloy for medical use - Saitova, L. R.; Höppel, Heinz Werner; Göken, Mathias; Semenova, I. P.; Valiev, R. Z. (International Journal of Fatigue, 2009)
WW1::798

Cyclic Deformation Behaviour and Damage Mechanisms in CuAgZr Alloys - Kommer, Martin; Schwub, Sigrid; Göken, Mathias; Höppel, Heinz Werner; Freudenberger, Jens (Proceedings of the 7th International Conference on Low Cycle Fatigue, 2013)

Cyclic deformation behaviour and fatigue lives of ultrafine-grained aluminium-magnesium alloys - Höppel, Heinz Werner; May, Johannes; Göken, Mathias (Materials Science Forum, 2008)
The fatigue behaviour of aluminium-magnesium alloys has been investigated in the recrystallized CG state and in an ultrafine-grained (UFG) state after equal channel angular pressing (ECAP). A strong improvement of the fatigue behaviour up to 12 ECAP passes has been found for an AlMg0.5 alloy. The results have been interpreted in consideration of the microstructure of the different states. Additionally, for an investigation of the influence of impurities on the cyclic stability of Aluminium, 3 different AlMg alloys with Magnesium contents of 0.5, 1, and 2 wt.-% have been compared. Total strain controlled fatigue tests have shown an improvement of the cyclic stability with increasing Mg content. © 2008 Trans Tech Publications.
Created from Fastlane, Scopus look-up
Keywords: Aluminium-magnesium alloys; Equal channel angular pressing; Fatigue; Severe plastic deformation; Ultrafine-grained metals

Cyclic deformation behaviour and possibilities for enhancing the fatigue properties of ultrafine-grained metals - Höppel, Heinz Werner; Mughrabi, Hael; et al. (Proc. of the Conf. "Nanomaterials by Severe Plastic Deformation NANOSPD2, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IW.LWAW.cyclic

Cyclic deformation behaviour of ultrafine grain size copper produced by equal channel angular extrusion; - Höppel, Heinz Werner; Mughrabi, Hael; et al. (Materials Week 2000 Proceedings, 2001)
UnivIS-Import:2015-04-16:Pub.2001.tech.IW.LWAW.cyclic

Cyclic Failure of a Cr–Au Bilayer on Polyimide: In Situ Transmission Electron Microscopy Observations of Interfacial Dislocation Mechanisms - Gebhart, David D.; Krapf, Anna; Schretter, Lukas; Lassnig, Alice; Merle, Benoit; Cordill, Megan J.; Gammer, Christoph (Advanced Engineering Materials, 2024)
This work presents in situ transmission electron microscopy observations of dislocation activities and associated fatigue properties in a cross-sectional sample of a Cr–Au bilayer on a polyimide substrate under cyclic loading. Dislocation structures in the Au layer are observed to evolve into a geometrically necessary boundary parallel to the Cr–Au interface, which significantly impedes dislocation motion and plays a crucial role in enhancing the fatigue resistance of the studied sample. While a comparison to the damage in a conventional blanket film testing geometry reveals some differences in the accumulation of plastic flow, the findings can provide insights into the underlying mechanisms governing fatigue in nanostructured multilayer materials on polymer substrates.
CRIS-Team Scopus Importer:2024-05-03
Keywords: cyclic loading; dislocation activities; fatigue resistance; geometrically necessary boundaries; in situ transmission electron microscopy; metal bilayer; polyimide substrates

Cycling of ultrafine-grained Ti-6Al-4V ELI alloy: Microstructural changes and enhanced fatigue limit - Saitova, Lilia R.; Höppel, Heinz Werner; Göken, Mathias; Kilmametov, A. R.; Semenova, Irina P.; Valiev, Ruslan Z. (4th International Conference on Nanomaterials by Severe Plastic Deformation, 2008)
Ti-6Al-4V ELI (extra low interstitials) was processed by equal channel angular pressing in order to obtain an ultrafine-grained (UFG) microstructure which is known to enhance the fatigue behavior of metallic materials. Fatigue properties of UFG Ti-6Al-4V ELI were studied by strain and stress controlled fatigue tests. UFG Ti-6Al-4V ELI shows an improvement of the fatigue behavior compared to conventional grain (CG) size counterpart. Microstructural investigations prior to and after fatigue testing confirm a high structural stability of the UFG material. Hence, the UFG alloy has a high potential for prospective use in biomedical and engineering applications. © 2008 Trans Tech Publications.
Created from Fastlane, Scopus look-up
Keywords: Cyclic deformation; Fatigue limit; Softening; Ti-6Al-4V; Ultrafine-grained microstructure

Damage evolution during thermo-mechanical fatigue of a coated monocrystalline nickel-base superalloy - Nützel, Ralf; Affeldt, E.; Göken, Mathias (International Journal of Fatigue, 2008)
WW1::758

Deformation and ultrafine dynamic recrystallization of quartz in pseudotachylyte-bearing brittle faults: A matter of a few seconds - Bestmann, Michel; Pennacchioni, Giorgio; Nielsen, Stefan; Göken, Mathias; de Wall, Helga (Journal of Structural Geology, 2012)
Tectonic pseudotachylytes, i.e. quenched friction-induced silicate melts, record coseismic slip along faults and are mainly reported from the brittle crust in association with cataclasites. In this study, we document the occurrence of recrystallization of quartz to ultrafine-grained (grain size 1-2 mu m) aggregates along microshear zones (50-150 mu m thick) in the host rock adjacent to pseudotachylytes from two different faults within quartzite (Schneeberg Normal Fault Zone, Eastern Alps), and tonalite (Adamello fault, Southern Alps) in the brittle crust. The transition from the host quartz to microshear zone interior includes: (i) formation of high dislocation densities; (ii) fine (0.3-0.5 mu m) polygonization to subgrains defined by disordered to well-ordered dislocation walls; (iii) development of a mosaic aggregate of dislocation-free new grains. The crystallographic preferred orientation (CPO) of quartz towards the microshear zone shows a progressive misorientation from the host grain, by subgrain rotation recrystallization, to a nearly random CPO possibly related to grain boundary sliding. These ultrafine aggregates appear to be typically associated with pseudotachylytes in nature. We refer the crystal plastic deformation of quartz accompanied by dramatic grain size refinement to the coseismic stages of fault slip due to high differential stress and temperature transients induced by frictional heating. Microshear zones localized on precursory fractures developed during the stages of earthquake rupture propagation and the very initial stages of fault slip. Thermal models indicate that the process of recrystallization, including recovery processes, occurred in a time lapse of a few tens of seconds. (C) 2011 Elsevier Ltd. All rights reserved.
WW1::919
Keywords: Earthquakes; Pseudotachylyte; Crystal plastic deformation; Quartz; Microstructure; TEM; EBSD

Deformation behaviour, microstructure and processing of accumulative roll bonded aluminium alloy AA6016 - Topic, Irena; Höppel, Heinz Werner; Göken, Mathias (International Journal of Materials Research, 2007)
The technologically relevant aluminium alloy AA6016 was successfully processed using accumulative roll bonding to 8 cycles (ε von Mises = 6.4) in order to obtain an ultrafine-grained microstructure with an average grain size of approximately 200 nm. With the aim of optimising the accumulative roll bonding process detailed investigations on the robustness, the type of rolling mill, the influence of temperature, the microstructural evolution and the mechanical properties have been carried out. Processing at 230°C provided a good compromise between thermal stability and interlamellar bonding. Samples strained up to 6 cycles (εvon Mises = 4.8) showed an increase in the yield strength by a factor of 3 in comparison to the as-received material. The ductility of the roll bonded samples was slightly sacrificed, although an increase in ductility can be achieved by increasing the number of accumulative roll bonding cycles. The mechanical properties depend on the strain rate, as has also been found for many other ultrafine-grained materials. Annealing of ultrafine-grained samples revealed a stability limit of approximately 200°C.
Created from Fastlane, Scopus look-up
Keywords: Accumulative roll bonding (ARB); Interlamellar bonding; Strain rate sensitivity; Thermal stability; Ultrafine-grained microstructure

Deformation behaviour of accumulative roll bonded and friction stir welded aluminium alloys - Topic, Irena; Höppel, Heinz Werner; Göken, Mathias (Materials Science Forum, 2008)
Commercial purity aluminium AA1050 and aluminium alloy AA6016 were accumulative roll bonded and subsequently friction stir welded. The microstructure of the conventional and ultrafine-grained materials produced by accumulative roll bonding is strongly affected by friction stir welding. The elongated ultrafine-grained microstructure of roll bonded sheets becomes coarser and equiaxed in the nugget region. Hydraulic bulge tests showed that higher burst pressure can be achieved for samples without friction stir welding than for the ones with friction stir welding. Localised deformation, crack initiation and propagation, as well as the final fracture occurred within the nugget. Friction stir welded AA1050 sheet showed similar achievable burst pressures and von Mises equivalent strains compared to the as-received conventionally grained sheets. On the other hand, significantly higher burst pressures and at the same time higher von Mises equivalent strains were observed for the friction stir welded ultrafine-grained material than for the friction stir welded conventionally grained material. © 2008 Trans Tech Publications.
Created from Fastlane, Scopus look-up
Keywords: Accumulative roll bonding (ARB); Bulge tests; Friction stir welding (FSW); Ultrafine-grained microstructure (UFG)

Deformation behaviour of nanocrystalline al alloy, processed by severe plastic deformation - Vevecka-Priftaj, Afërdita; Höppel, Heinz Werner; Göken, Mathias (7th International Conference of the Balkan Physical Union, 2010)
Keywords: Nanocrystalline metals; Equal Channel Angular Pressing (ECAP); Strain rate sensitivity; Severe plastic deformation; Ultrafine - Grain materials

Deformation-induced long-range internal stresses and lattice plane misorientations and the role of geometrically necessary dislocations - Mughrabi, Hael (Philosophical Magazine, 2006)
The goal of this study is to develop a unified picture of the role of geometrically necessary dislocations (GNDs) in the evolution of long-range internal stresses and lattice plane misorientations in the heterogeneous dislocation pattern of deformed crystals. For this purpose, X-ray diffraction techniques are considered as the pertinent experimental tools. On the modelling side, the composite models of single/multiple slip serve to interpret the experimentally measured long-range internal stresses quantitatively in terms of densities of GNDs. However, in order to be able to deduce from experiment the evolution of those GNDs that are responsible for the observed lattice plane misorientations, the composite model must be refined. Quite generally, the same GND array can give rise to both long-range internal stresses and lattice plane misorientations. On this basis, available experimental data obtained on cyclically and tensile-deformed copper (and copper-manganese) single crystals were analyzed quantitatively. The stresses acting locally in the "hard" dislocation cell walls and in the "soft" cell interiors and the magnitude of the internal stresses are found to increase approximately linearly with the applied stress. In spite of the fact that the density of the GNDs always amounts to only a few per cent of the total dislocation density, they are responsible for the long-range internal stresses and/or for the misorientations. An analysis of the evolution of the lattice plane misorientations shows that the kink walls and the dislocation sheets/grids in stage II are geometrically necessary boundaries (GNBs), whereas the dislocation cell walls formed by multiple slip are incidental dislocation boundaries (IDBs).
Created from Fastlane, Scopus look-up

Deformation kinetics of coarse-grained and ultrafine-grained commercially pure Ti - Blum, Wolfgang; Li, Yujiao; Breutinger, Falk (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2007)
The elevated temperature deformation kinetics of ultrafine-grained (UFG) Ti of commercial purity (grade 2) produced by equal channel angular pressing (ECAP) at elevated temperature was measured and compared to that of coarse-grained (CG) Ti. Like CG Ti, the UFG Ti exhibits dynamic strain aging effects related to transition between jerky glide of dislocations without solute cloud and viscous glide with cloud. In the jerky region the yield stress of UFG Ti is distinctly enhanced compared to CG Ti. The steady state deformation resistances of CG and UFG Ti are not significantly different. The jerky → viscous transition results in a relative maximum of deformation resistance as function of strain, which is explained by the opposing effects of cloud formation and coarsening of dislocation structure. The high content of grain boundaries and dislocations in the initial state of UFG Ti stabilizes the material against break-away of dislocations from their clouds. © 2006 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Deformation kinetics; Dislocation model; Dynamic strain aging; Solute clouds; Transition; UFG Ti

Deformation kinetics of nanocrystalline nickel - Li, Yujiao; Müller, Johannes; Höppel, Heinz Werner; Göken, Mathias; Blum, Wolfgang (Acta Materialia, 2007)
The work hardening and the strain rate sensitivity of flow stress were studied in the temperature range from 298 to 473 K for nanocrystalline (NC) nickel with average grain sizes of about 25 and 80 nm produced by pulsed electrodeposition. The rate of work hardening, the maximum flow stress and the strain rate sensitivity of flow stress increase with decreasing grain size. The data are compared to published data for NC Ni and found to be consistent. The common analysis of strain rate sensitivity in terms of thermal activation is critically discussed. It is proposed that the activation analysis gives information about thermally activated processes at grain boundaries which may be related with recovery of dislocations.
Created from Fastlane, Scopus look-up
Keywords: Activation volume; Grain boundaries; Nanocrystalline Ni; Strain rate sensitivity; Work hardening

Deformation mechanisms and strain rate sensitivity of bimodal and ultrafine-grained copper - Bach, Jochen; Stoiber, Marco; Schindler, L.; Höppel, Heinz Werner; Göken, Mathias (Acta Materialia, 2020)
Materials with ultrafine grain size in the range from 100 nm to 1 µm exhibit very high strength paired with a satisfactory ductility when compared to their coarse grained (CG) counterparts. Although this typical behavior is already well known, the dominating deformation mechanisms are still controversially discussed in literature. One idea to explain the deformation behavior of ultrafine-grained metals is that deformation is mainly triggered by grain boundary sliding. Another explanation is that deformation in ultrafine-grained materials is controlled by the thermally activated dislocation annihilation of dislocations at grain boundaries. To gain deeper insights to the relevant deformation mechanisms in UFG metals a systematic study was conducted where the deformation behavior of UFG and bimodal copper (consisting of UFG and CG grains) is compared to the behavior of their CG counterparts. The UFG microstructure was obtained by equal channel angular pressing (ECAP). To achieve a bimodal or coarsened microstructure, specimens were annealed at 125 °C or, respectively, at 140 °C subsequent to the ECAP-process. Mechanical characterization and investigation on the strain-rate sensitivity were done by compression strain-rate jump tests at room-temperatures and elevated temperatures. It turned out clearly that the degree of bimodality determines the dominant deformation mechanism and the strain-rate sensitivity. In the UFG-state thermally activated annihilation of dislocations at the grain boundaries govern the mechanical behavior. For the bimodal microstructure the annihilation of dislocation at the interface of coarsened grains to the surrounding ultrafine-grained matrix dominate the mechanical behavior. For the fully coarsened state plastic deformation is mainly governed by dislocation interaction in the grain interior. In this regime, annihilation at grain boundaries plays only a minor role.
CRIS-Team Scopus Importer:2020-01-28
Keywords: Bimodal grain structure; Deformation mechanisms; Strain rate sensitivity; Ultrafine-grained copper

Deformation Mechanisms in Compositionally Complex Polycrystalline CoNi-Base Superalloys: Influence of Temperature, Strain-Rate and Chemistry - Bezold, Alexander; Freund, Lisa; Förner, Andreas; Völkl, Johannes; Huber, Laura-Kristin; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
Recent studies revealed the excellent high temperature properties of polycrystalline CoNi-base superalloys. However, their underlying deformation behavior has been reported only scarcely so far. In this work, the deformation mechanisms of four polycrystalline compositionally complex CoNi-base superalloys with slightly varying chemical compositions were investigated by compression and creep experiments at temperatures between 750 degrees C and 850 degrees C and strain-rates between 10 (3) and 10 (8) s(-1). In the two (Ta + Ti)-rich alloys, a transition of the deformation mechanism from shearing by APB-coupled dislocation pairs to stacking fault shearing and finally also to microtwinning is observed with decreasing strain-rate and increasing temperature. In contrast, APB-based shearing mechanisms represent the dominant mechanism in both (Al + W)-rich alloys in all conditions. At high temperatures and low strain-rates, dislocation glide-climb processes also contribute to plastic deformation in all alloys. By correlating the underlying defect structures with the mechanical properties of these alloys, it becomes evident that a transition to stacking fault shearing and microtwinning leads to a lower strain-rate dependency and superior high-temperature strength in comparison with APB-based mechanisms. Reasons for the different deformation mechanisms, the influence of segregation processes, the consequences for mechanical properties and implications for a mechanism-based alloy design are discussed.
CRIS-Team WoS Importer:2023-01-06

Deformation mechanisms in Ni-based superalloys at room and elevated temperatures studied by in Situ neutron diffraction and electron microscopy - Kümmel, Frank; Kirchmayer, Andreas; Solís, Cecilia; Hofmann, Michael; Neumeier, Steffen; Gilles, Ralph (Metals, 2021)
Polycrystalline Ni-based superalloys are one of the most frequently used materials for high temperature load-bearing applications due to their superior mechanical strength and chemical resistance. In this paper, we presented an in situ diffraction study on the tensile deformation behavior of the polycrystalline Ni-based superalloy VDM® Alloy 780 at temperatures up to 500 °C performed at the STRESS-SPEC neutron diffractometer at the Heinz Maier-Leibnitz Zentrum. A detailed microstructural investigation was carried out by electron microscopy before and after testing. The results of these studies allowed us to determine the deformation mechanism in the differently orientated grains. It is shown that the deformation behavior, which is mainly dislocation motion and shearing of the γ′-precipitates, does not change at this temperature range. The deformation is strongly anisotropic and depends on the grain orientation. The macroscopic hardening can mainly be attributed to plastic deformation in grains, where the (200) lattice planes were orientated perpen-dicular to the loading direction. Accordingly, a remaining lattice strain and high dislocation density were detected predominantly in these grains.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Deformation behavior; Lattice strain; Micro-structural investigation; Neutron diffraction; Ni-based superalloy; Transmission electron microscopy; kernfusionsrelevant

Deformation of WC-Co Hardmetals During Scratch Testing - Ndlovu, Siphilisiwe; Durst, Karsten; Göken, Mathias (Wiley-VCH, 2011)
Keywords: WC-Co hardmetal deformation; Scratch testing

Density-Diffusion Relationship in Soda-Lime Phosphosilicate - Ouldhnini, Youssef; Atila, Achraf; Ouaskit, Said; Hasnaoui, Abdellatif (Journal of Non-Crystalline Solids, 2022)
Bioactive glasses release ions such as sodium when implanted in the human body. However, an excess of the released ions can cause problems related to cytotoxicity. The ion release control is considered one of the primary challenges in developing new bioactive glasses. Here, we use molecular dynamics simulations to investigate the effect of the density on atoms’ dynamics in an archetypal phosphosilicate bioactive system. The diffusion coefficient displays three main regimes with increasing density. The mobility of the modifiers is significantly affected by the increase of the density, especially Na, compared to other elements. We use a modified Arrhenian model to access the complex dynamic behavior of 45S5 melts and correlate it to the structural changes by evaluating the network connectivity and pair-excess entropy. Overall, our results present a step toward the rational design of bioactive glasses and a key to controlling the ion release of bioactive glasses.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Bioactive glasses; Diffusion; Molecular dynamics; Structural properties

Density-functional investigation of the (113) [-110] twin grain boundary in Co-doped anatase Ti O2 and its influence on magnetism in dilute magnetic semiconductors - Gemming, S.; Janisch, Rebecca; Schreiber, M.; Spaldin, N. A. (Physical Review B - Condensed Matter and Materials Physics, 2007)
Density-functional calculations were carried out for the (113) [-110] tilt grain boundary in the anatase modification of Ti O2, with and without magnetic Co dopants. The boundary exhibits a low energy of 0.88 J/m2 and no rigid translation of the grains. It is composed from four distinct structural units, and a deviation from the mirror-symmetric atom arrangement due to local relaxation is found. The analysis of the electronic structure indicates that the grain boundary is electronically inactive, because it introduces no boundary-specific states in the bulk band gap, and only minor differences between the valence band structures of the grain boundary and the pure bulk are obtained. The regular arrangement of the quite open structural units provides the possibility of doping the grain boundary with electronically or magnetically active elements, which is explored by doping the supercell with Co. In this diluted magnetic semiconductor, the (113) [-110] grain boundary can enhance the ferromagnetic interaction by providing convenient bond angles for ferromagnetic superexchange. © 2007 The American Physical Society.
Created from Fastlane, Scopus look-up

Describing mechanical damage evolution through in situ electrical resistance measurements - Gebhart, David D.; Krapf, Anna; Merle, Benoit; Gammer, Christoph; Cordill, Megan J. (Journal of Vacuum Science & Technology A, 2023)
The fatigue properties of metallizations used as electrical conductors in flexible electronic devices have been thoroughly studied over the years. Most studies use time-intensive characterization methods to evaluate mechanical damage. For their ease of access, in situ electrical resistance measurements are often performed along with other characterization methods. However, the data are mostly used as an indicator of failure and a thorough analysis is usually missing. This work presents some deeper analysis methods of such datasets, using gold films on polyimide, with and without a chromium interlayer, revealing that grain growth, through-thickness cracking, and more general fatigue behavior can be determined from electrical resistance data alone. A case is made for increased utilization of such easily obtained data, reducing the time required for the evaluation of experiments.
CRIS-Team Scopus Importer:2023-03-17

Design and Characterization of a Novel NiAl–(Cr,Mo) Eutectic Alloy - Titz, Katharina; Vollhüter, Jan; Randelzhofer, Peter; Neumeier, Steffen; Göken, Mathias; Wahlmann, Benjamin; Körner, Carolin (Advanced Engineering Materials, 2024)
To enhance the mechanical properties of NiAl–(Cr,Mo) in situ composites for high-temperature structural use, achieving a regular eutectic microstructure is crucial. A novel alloy with a composition of Ni30.6Al36Cr31.4Mo2 is developed that exhibits a significantly reduced solidification interval compared to well-studied alloys such as Ni33Al33Cr28Mo6. This advancement results from using the in-house developed alloy design tool PyMultOpt and Calculation of Phase Diagrams analysis to minimize the solidification interval. The refined alloy demonstrates a theoretical solidification interval of 0 K. These results are verified with differential scanning calorimetry measurements at different heating rates for the new alloy and compared with the established alloy Ni33Al33Cr28Mo6. The small solidification interval leads to a uniform eutectic microstructure consisting of a (Cr,Mo) phase embedded in the NiAl matrix without primary NiAl dendrites present. This indicates that deviating from the stoichiometric NiAl composition results in a significantly lower solidification interval and thus in an actual eutectic composition of the NiAl–(Cr,Mo) system.
CRIS-Team Scopus Importer:2024-04-05
Keywords: alloy development; eutectics; intermetallics; nickel aluminides

Designing bulk metallic glass and glass matrix composites in martensitic alloys - Das, Jayanta; Pauly, S.; Bostroem, M.; Durst, Karsten; Göken, Mathias; Eckert, J. (Journal of Alloys and Compounds, 2009)
WW1::800

Design of a Co–Al–W–Ta Alloy Series with Varying γ′ Volume Fraction and Their Thermophysical Properties - Volz, Nicklas; Xue, Fei; Bezold, Andreas; Zenk, Carolin; Fries, Suzana G.; Schreuer, Juergen; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2021)
The γ′ volume fraction is a key parameter in precipitation-strengthened Co- and Ni-base superalloys and mainly determines the alloys’ properties. However, systematic studies with varying γ′ volume fractions are rare and the influence on thermal expansion has not been studied in detail. Therefore, a series of six Ta-containing Co-based alloys was designed with compositions on a γ–γ′ tie-line, where the γ′ volume fraction changes systematically. During solidification, Laves (C14-type) and µ (D85-type) phases formed in alloys with high levels of W and Ta. Single-phase γ or two-phase γ/γ′ microstructures were obtained in four experimental alloys after heat treatment as designed, whereas secondary precipitates, such as χ (D019-type), Laves, and μ, existed in alloys containing high levels of γ′-forming elements. However, long-term heat treatments for 1000 hours revealed the formation of the χ phase also in the former χ-free alloys. The investigation of the thermal expansion behavior revealed a significant anomaly related to the dissolution of γ′, which can be used to determine the γ′ solvus temperature with high accuracy. Compared to thermodynamic calculations, differential scanning calorimetry (DSC) and thermal expansion analysis revealed a larger increase of the γ′ solvus temperatures and a lesser decline of the solidus temperatures when the alloy composition approached the composition of the pure γ′ phase.

Design of graded materials by particle reinforcement during accumulative roll bonding - Schmidt, Christian; Ruppert, Mathis; Höppel, Heinz Werner; Nachtrab, Frank; Dietrich, Anja; Hanke, Randolf; Göken, Mathias (Advanced Engineering Materials, 2012)
Graded distributions of copper particles in ultrafine-grained aluminium sheets are produced by accumulative roll bonding and particle reinforcement. The metallic copper particles are sprayed on the sheet surfaces under variation of spray distance and/or relative velocity of the spray gun to the sheet. Therewith, the particle content could be varied by a factor of three. After solutionizing, the successful gradation is clearly proven by tensile tests showing a steady and monotonous gradient along the rolling direction. By a systematic analysis of the spraying process, the particle content profile is calculated. Accuracy of the calculation is confirmed by electrical resistivity measurements. The presented method enables the production of tailored sheets by graded particle reinforcement. The graded sheets are also used for basic investigation of materials properties along graded compositions.
WW1::920

Detecting and extracting clusters in atom probe data: A simple, automated method using Voronoi cells - Felfer, Peter; Ceguerra, A. V.; Ringer, S. P.; Cairney, J. M. (Ultramicroscopy, 2015)
The analysis of the formation of clusters in solid solutions is one of the most common uses of atom probe tomography. Here, we present a method where we use the Voronoi tessellation of the solute atoms and its geometric dual, the Delaunay triangulation to test for spatial/chemical randomness of the solid solution as well as extracting the clusters themselves. We show how the parameters necessary for cluster extraction can be determined automatically, i.e without user interaction, making it an ideal tool for the screening of datasets and the pre-filtering of structures for other spatial analysis techniques. Since the Voronoi volumes are closely related to atomic concentrations, the parameters resulting from this analysis can also be used for other concentration based methods such as iso-surfaces. (C) 2014 Elsevier B.V. All rights reserve
Keywords: Atom probe tomography; Clustering; Voronoi tessellation; Point cloud; Spatial filter

Detection and effects of lack of fusion defects in Hastelloy X manufactured by laser powder bed fusion - Palm, M. S.; Diepold, Benedikt; Neumeier, Steffen; Höppel, Heinz Werner; Göken, Mathias; Zaeh, M. F. (Materials & Design, 2023)
Laser Powder Bed Fusion (L-PBF) is increasingly used for the manufacturing of complex metal parts. A major hurdle for L-PBF to manufacture critical parts is the lack of knowledge about the effects of inner material defects on the material properties. This paper presents a new method to manufacture specimens with inner lack of fusion (LOF) defects and to detect and localize them simultaneously by the in-process monitoring tool Optical Tomography (OT). The presence of defects at locations indicated by OT was verified through Computed Tomography analyses. Correlative metallographic preparation of the processed specimens showed LOF defects with their main extent within the build plane and sharp edges. Moreover, microstructural investigations revealed a fine globular grain structure and coarse dendritic segregations in the area, influenced by the defect. Correlations between the LOF defects analyzed in the microstructure and corresponding OT indications were established. Tensile tests and high cycle fatigue tests were performed on defective and non-defective material to evaluate the effects of LOF defects on the material properties of Hastelloy® X manufactured by L-PBF. While a minor influence of the LOF defects on static material properties was identified, the fatigue life of the defective specimens was significantly reduced.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Effects of defects; Hastelloy X; High cycle fatigue; Laser powder bed fusion; Optical tomography

Determination of plastic properties of polycrystalline metallic materials by nanoindentation: Experiments and finite element simulations - Backes, Björn; Durst, Karsten; Göken, Mathias (Philosophical Magazine, 2006)
Nanoindentation experiments at low indentation depths are strongly influenced by micromechanical effects, such as the indentation size effect, pile-up or sink-in behaviour and crystal orientation of the investigated material. For an evaluation of load-displacement data and a reconstruction of stress-strain curves from nanoindentations, these micromechanical effects need to be considered. The influence of size effects on experiments were estimated by comparing the results of finite element simulation and experiments, using uniaxial stress-strain data of the indented material as input for the simulations. The experiments were performed on conventional and ultrafine-grained copper and brass, and the influence of the indentation size effect and pile-up formation is discussed in terms of microstructure. Applying a pile-up correction on Berkovich and cube-corner indentation data, a piecewise reconstruction of stress-strain curves from load-displacement data is possible with Tabor's concept of representative strain. A good approximation of the slope of the stress-strain curve from the indentation experiments is found for all materials down to an indentation depth of 800∈nm.
Created from Fastlane, Scopus look-up

Determination of the interfacial strength and fracture toughness of a-C:H coatings by in-situ microcantilever bending - Schaufler, Jens; Schmid, Christoph; Durst, Karsten; Göken, Mathias (Thin Solid Films, 2012)
The interfacial fracture strength and toughness of two hydrogenated amorphous carbon coatings (a-C:H) with Cr-adhesion layers on steel substrate have been determined directly by in-situ deformation tests using microcantilever bending experiments. The coating conditions for the two systems were essentially the same, only slight differences have been introduced in the adhesion layer. These changes resulted in a totally different delamination behavior, from excellent to poor adhesion. The well adherent interface between the adhesion layer and the a-C:H has a fracture strength and toughness value close to the a-C:H coating itself. For bulk a-C:H a bending strength close to the theoretical strength was found, indicating that the tested volume was defect free. Changing the process conditions reduced the bending strength by 40%, leading to strong delamination and a catastrophic behavior during Rockwell C testing. An interfacial fracture toughness value of 2.18 MPa m0.5 was found for the well adherent coating, exceeding even that of pure a-C:H.
WW1::921

Determination of the strain-rate sensitivity of ultrafine-grained materials by spherical nanoindentation - Feldner, Patrick; Merle, Benoit; Göken, Mathias (Journal of Materials Research, 2017)
The strain-rate sensitivity of the flow stress represents a crucial parameter for characterizing the deformation kinetics of a material. In this work a new method was developed and validated for determining the local strain-rate sensitivity of the flow stress at different plastic strains. The approach is based on spherical nanoindentation strain-rate jump tests during one deformation experiment. In the case of ultrafine-grained Al and ultrafine-grained Cu good agreement between this technique and macroscopic compression tests has been achieved. In contrast to this, individual spherical nanoindentation experiments at constant strain-rates resulted in unrealistically high strain-rate sensitivities for both materials because of drift influences. Microstructural investigations of the residual spherical imprints on ultrafine-grained Al and ultrafine-grained Cu revealed significant differences regarding the deformation structure. For ultrafine-grained Cu considerably less activity of grain boundary sliding has been observed compared to ultrafinegrained A

Determination of the true projected contact area by in situ indentation testing - Guillonneau, Gaylord; Wheeler, Jeffrey M.; Wehrs, Jun; Philippe, Laetitia; Baral, Paul; Höppel, Heinz Werner; Göken, Mathias; Michler, Johann (Journal of Materials Research, 2019)
A major limitation in nanoindentation analysis techniques is the inability to accurately quantify pile-up/sink-in around indentations. In this work, the contact area during indentation is determined simultaneously using both contact mechanical models and direct in situ observation in the scanning electron microscope. The pile-up around indentations in materials with low H/E ratios (nanocrystalline nickel and ultrafine-grained aluminum) and the sink-in around a material with a high H/E ratio (fused silica) were quantified and compared to existing indentation analyses. The in situ projected contact area measured by scanning Eelectron Mmicroscopy using a cube-corner tip differs significantly from the classical models for materials with low H/E modulus ratio. Using a Berkovich tip, the in situ contact area is in good agreement with the contact model suggested by Loubet et al. for materials with low H/E ratio and in good agreement with the Oliver and Pharr model for materials with high H/E ratio.
CRIS-Team WoS Importer:2019-09-17

Development of a new alloy for directional solidification of large industrial gas turbine blades - Bürgel, Ralf; Grossmann, Jörn; Lüsebrink, Oliver; Mughrabi, Hael; Pyczak, Florian; Singer, Robert; Volek, Andreas (SUPERALLOYS 2004 - Tenth International Symposium on Superalloys, 2004)
A nickel-base superalloy for directional solidification (DS) of industrial gas turbine blades was developed based on alloy IN792 with approximately 12 mass % Cr. From preliminary test results a temperature gain in stress-rupture strength of 30 K can be expected compared to Re-free aero engine alloys with columnar grains. This significant strength improvement can be achieved by adding 2 to 3 mass % Re in the group of 12 mass % Cr alloys. With balanced Cr-, Al-, and Ti- contents they also exhibit superior hot corrosion resistance compared to typical high Al / low Cr / low Ti aero engine alloys. The castability for large blades was prove
Keywords: Cobalt; Directional solidification; Hot corrosion; Industrial gas turbine; Nickel-base superalloy; Phase stability; Rhenium; Stress-rupture

Development of Microstructure and Mechanical Properties of TiAl6V4 Processed by Wire and Arc Additive Manufacturing - Elitzer, Daniel; Jäger, Stefan; Höll, Clara; Baier, Daniel; Varga, Rosa; Zaeh, Michael F.; Göken, Mathias; Höppel, Heinz Werner (Advanced Engineering Materials, 2022)
Wire and arc additive manufacturing (WAAM) has the potential to significantly reduce material waste due to the milling of components made of TiAl6V4 (Ti-64). To keep up with the market development, this resource-efficient technology is becoming increasingly important to achieve climate policy goals. Therefore, this study not only focuses on the influence of different process parameters, such as torch and wire feed speed, but also different gas mixtures on the microstructure and related mechanical properties, as well as on the scalability by investigating single- to multilayer welded structures. The wire feed speed is found to have a major influence on the geometry and mechanical properties. The use of different process gases, i.e., argon (Ar), helium (He), and a mixture of 70% He and 30% Ar neither significantly affect the microstructure nor the mechanical properties. It is also found that a solution heat treatment followed by an annealing step degrades mechanical properties, while an ordinary stress-relief heat treatment leads to improved mechanical properties. It is shown that by adapting WAAM process and heat treatment parameters, mechanical properties of additively produced specimens can be achieved, which are fully comparable to milled components.
CRIS-Team Scopus Importer:2022-09-30
Keywords: additive manufacturing; alpha-beta alloys; heat treatments; mechanical properties; microstructures; Ti-64; WAAM

Development of new 11%Cr heat resistant ferritic steels with enhanced creep resistance for steam power plants with operating steam temperatures up to 650 °C - Wang, Y.; Mayer, K. -H.; Scholz, A.; Berger, C.; Chilukuru, Hemambar; Durst, Karsten; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::801
Keywords: kernfusionsrelevant

DFG Research Training Group 1229 "Stable and Metastable Multi-Phase Systems for Elevated Service Temperatures" - Göken, Mathias; Glatzel, Uwe (Advanced Engineering Materials, 2015)
WW1::1047
Keywords: High Temperature

Diffusion brazing of single crystalline nickel base superalloys using boron free nickel base braze alloys - Heinz, Paul; Volek, Andreas; Singer, Robert; Dinkel, Markus; Pyczak, Florian; Göken, Mathias; Ott, Michael; Affeldt, Ernst; Vossberg, A. (Defect and Diffusion Forum, 2008)
Brazing is a well established repair technique for high temperature components in both industrial gas turbines and aero engines. Conventional nickel base braze alloys contain boron or silicon as melting point depressing elements. The major benefit of boron and silicon compared to other melting point depressants is its large effect on the melting point and its high diffusion coefficient in nickel base superalloys. However these elements promote precipitation of undesired brittle phases during the brazing process. To avoid these phases, transient liquid phase bonding in combination with boron and silicon free brazing alloys will be examined in this work. The influence of the brazing temperature on solidification and diffusion behaviour during transient liquid phase bonding for a single crystalline first generation and a second generation superalloy will be reported. Our experiments show that isothermal solidification without precipitation of brittle phases in the braze joint or the base material can be achieved. The brazed joint consists of fine gamma/gamma' microstructure. EBSD measurements demonstrated that the single crystalline orientation of the base material was maintained throughout the joint. Electron probe micro analysis is used to characterize the diffusion behaviour. Solidification velocity will be compared with the theory of transient liquid phase bonding established by Tuah-Poku [1
Keywords: diffusion brazing; single crystalline; nickel base superalloy; boron free

Diffusion of solutes in fcc Cobalt investigated by diffusion couples and first principles kinetic Monte Carlo - Neumeier, Steffen; Rehman, H. U.; Neuner, J.; Zenk, Carolin; Michel, Sabine; Schuwalow, S.; Rogal, J.; Drautz, Ralf; Göken, Mathias (Acta Materialia, 2016)
WW1::1058
Keywords: High Temperature; Simulation and Modeling

Digitalisation in Materials Science – Combining Experiments and Simulation Across Length Scales - Felfer, Peter; Sandfeld, Stefan (Praktische Metallographie, 2018)
CRIS-Team Scopus Importer:2021-05-18

Directed energy deposition of gamma/gamma' Co-Al-W superalloys - Yoo, Boryung; Jung, Chanwon; Ryou, Kenhee; Choi, Won Seok; Haußmann, Lukas; Yang, Sangsun; Boll, Torben; Neumeier, Steffen; Choi, Pyuck-Pa (Additive Manufacturing, 2022)
In this study, Co-Al-W superalloys forming gamma/gamma' microstructures were fabricated by laser-directed energy depo-sition and investigated with respect to their susceptibility to hot-cracking during manufacturing. Two alloys of different nominal compositions (Co-12Al-8W, Co-7Al-8W (at.%)) were deposited to characterize their micro-structures on multiple length scales. While the as-deposited Co-12Al-8W alloy was free of cracks, the Co-7Al-8W alloy exhibited numerous cracks, particularly along high-angle grain boundaries due to internal oxidation cracking. The former Al-rich alloy showed a continuous and dense-packed Al2O3 scale on its surface, preventing internal oxidation. After homogenization heat-treatment at 1300 degrees C for 24 h and subsequent aging at 900 degrees C for 24 h, the Co-12Al-8W alloy revealed a homogeneous gamma/gamma' microstructure without hot-cracking. By contrast, the Co-7Al-8W alloy did not exhibit a passivation layer but only internal Al2O3 particles due to the reduced Al content and insufficiently fast transport of Al to the oxidation front. These particles acted as stress concentration and crack initiation sites during directed energy deposition, thereby limiting the printability of the Co-7Al-8W alloy. The compressive creep results reveal a similar creep resistance of crack-free Co-12Al-8W alloy compared to conventionally processed ternary Co-Al-W alloys.
CRIS-Team WoS Importer:2022-12-23

Directed energy deposition of γ/γ' Co-Al-W superalloys - Haußmann, Lukas; Yoo, Boryung; Jung, Chanwon; Ryou, Kenhee; Choi, Won Seok; Haußmann, Lukas; Yang, Sangsun; Boll, Torben; Neumeier, Steffen; Choi, Pyuck-Pa (Additive Manufacturing, 2022)
In this study, Co-Al-W superalloys forming γ/γ' microstructures were fabricated by laser-directed energy deposition and investigated with respect to their susceptibility to hot-cracking during manufacturing. Two alloys of different nominal compositions (Co-12Al-8W, Co-7Al-8W (at.%)) were deposited to characterize their microstructures on multiple length scales. While the as-deposited Co-12Al-8W alloy was free of cracks, the Co-7Al-8W alloy exhibited numerous cracks, particularly along high-angle grain boundaries due to internal oxidation cracking. The former Al-rich alloy showed a continuous and dense-packed Al2O3 scale on its surface, preventing internal oxidation. After homogenization heat-treatment at 1300 °C for 24 h and subsequent aging at 900 °C for 24 h, the Co-12Al-8W alloy revealed a homogeneous γ/γ' microstructure without hot-cracking. By contrast, the Co-7Al-8W alloy did not exhibit a passivation layer but only internal Al2O3 particles due to the reduced Al content and insufficiently fast transport of Al to the oxidation front. These particles acted as stress concentration and crack initiation sites during directed energy deposition, thereby limiting the printability of the Co-7Al-8W alloy. The compressive creep results reveal a similar creep resistance of crack-free Co-12Al-8W alloy compared to conventionally processed ternary Co-Al-W alloys. © 2022 Elsevier B.V.
Keywords: Additives; Alumina; Aluminum alloys; Aluminum oxide; Cobalt alloys; Creep; Creep resistance; Deposition; Grain boundaries; Heat treatment; Microstructure; Passivation; Superalloys; Ternary alloys; Co-based superalloys; Directed energy; Directed energy deposition; Energy depositions; Free of cracks; High angle grain boundaries; Hot-cracking; Length scale; Nominal composition; γ/ microstructure; 3D printers; Additive manufacturing; Co-based superalloys; Creep; Directed energy deposition; Hot-cracking

Discontinuous precipitation and phase stability in Re- and Ru-containing nickel-base superalloys - Heckl, Astrid; Cenanovic, S.; Göken, Mathias; Singer, Robert (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2012)
The phase stability of nickel-base superalloys has been investigated using a new in-house-designed alloy series with stepwise increased additions of Re and Ru at otherwise fixed atomic fractions of alloying elements. Results presented in this study are focused on the lesser-known topologically closed packed (TCP) formation of columnar colonies or so-called discontinuous precipitation. A detailed investigation of these colonies allowed for identifying compositional changes during the growth process and for providing a three-dimensional (3-D) illustration of the TCP phases within these colonies. The results were used to compare the colony growth process with existing growth models. Furthermore, the influence of Re and Ru on the appearance of discontinuous precipitation has been investigated by means of colony width and the effect on creep properties. Larson-Miller plots are given to illustrate the creep strength of directionally solidified samples with and without TCP colonies compared with single crystalline samples free from TCP colonies. © 2011 The Minerals, Metals & Materials Society and ASM Internationa

Does copper undergo surface roughening during fatigue in the VH regime? - Stanzl-Tschegg, Stefanie; Mughrabi, Hael; Schuller, Reinhard (Fracture of Nano and Engineering Materials and Structures - Proceedings of the 16th European Conference of Fracture, 2006)
Extensive studies have been performed on nature and formation of persistent slip bands (PSBs) in the past. They have been identified as sites of localized cyclic plastic deformation, which are typically found in fcc metals, like copper, nickel or solid solutions of these metals. These sites of plastic deformation become visible as extrusions and microcracks (intrusions) on the specimen surface and as “ladder”, “vein” or cell structures of the dislocations in the interior of the specimen. The stresses and plastic strains for their formation are determined by a plateau stress in the cyclic stress strain curve (CSS curves) [1] with a typical plateau stress at approximately 28 MPa and a resolved shear strain between approximately 10−4 and 8×10−3 for copper single crystals. Additional investigations have been performed at stresses below the plateau regime at stresses between 3 and 26 MPa and number of cycles up to several 107 in order to study the evolution of sliding and dislocation characteristics [2].<br
Created from Fastlane, Scopus look-up

Double minimum creep in the rafting regime of a single-crystal Co-base superalloy - Xue, Fei; Zenk, Christopher; Freund, Lisa; Hoelzel, M.; Neumeier, Steffen; Göken, Mathias (Scripta Materialia, 2018)
To investigate whether the formation of rafts in Co-base superalloys has a hardening or softening effect, the single crystal deformation behavior was studied in the high temperature/low stress creep regime. The large positive lattice misfit of the investigated Co-base superalloy led to a pronounced directional coarsening of the microstructure normal to the stress axis during compressive creep at 950 degrees C/150 MPa. Two creep minima were observed similar to Ni-base superalloys under tensile creep. Rafting was accompanied by a decreasing creep rate indicating a hardening effect, although cutting of gamma' rafts by partial dislocations under the formation of stacking faults occurred. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Co-base superalloys; Lattice misfit; Directional coarsening; Creep; Neutron diffraction

Dry reforming of methane over gallium-based supported catalytically active liquid metal solutions - Wolf, Moritz; de Oliveira, Ana; Taccardi, Nicola; Maisel, Sven; Heller, Martina; Khan Antara, Sharmin; Soegaard, Alexander; Felfer, Peter; Görling, Andreas; Haumann, Marco; Wasserscheid, Peter (Communications Chemistry, 2023)
Gallium-rich supported catalytically active liquid metal solutions (SCALMS) were recently introduced as a new way towards heterogeneous single atom catalysis. SCALMS were demonstrated to exhibit a certain resistance against coking during the dehydrogenation of alkanes using Ga-rich alloys of noble metals. Here, the conceptual catalytic application of SCALMS in dry reforming of methane (DRM) is tested with non-noble metal (Co, Cu, Fe, Ni) atoms in the gallium-rich liquid alloy. This study introduces SCALMS to high-temperature applications and an oxidative reaction environment. Most catalysts were shown to undergo severe oxidation during DRM, while Ga-Ni SCALMS retained a certain level of activity. This observation is explained by a kinetically controlled redox process, namely oxidation to gallium oxide species and re-reduction via H2 activation over Ni. Consequentially, this redox process can be shifted to the metallic side when using increasing concentrations of Ni in Ga, which strongly suppresses coke formation. Density-functional theory (DFT) based ab initio molecular dynamics (AIMD) simulations were performed to confirm the increased availability of Ni at the liquid alloy-gas interface. However, leaching of gallium via the formation of volatile oxidic species during the hypothesised redox cycles was identified indicating a critical instability of Ga-Ni SCALMS for prolonged test durations.
CRIS-Team Scopus Importer:2023-10-27

Dual role of deformation-induced geometrically necessary dislocations with respect to lattice plane misorientations and/or long-range internal stresses - Mughrabi, Hael (Acta Materialia, 2006)
This work is part of a continuing effort to develop a unified picture of the role of geometrically necessary dislocations (GNDs) in the evolution of the dislocation distribution of unidirectionally and cyclically deformed crystals. In particular, the dual role of the GNDs in the development of long-range internal stresses and lattice plane misorientations which arise because of the heterogeneity of the dislocation substructure is explored. Available experimental data of cyclically and tensile-deformed copper single crystals were evaluated as quantitatively as possible in the framework of the composite model. Valuable complementary information to TEM was obtained from well-designed X-ray diffraction experiments (line broadening, broadening of rocking curves, Berg-Barrett X-ray topography). The evolution of the long-range internal stresses and of the density of the GNDs with increasing deformation could be determined quantitatively as a function of deformation for cases of both single and multiple slip. In all cases studied, the GND density was found to be small and amounted only to some per cent of the total dislocation density. From the rate of evolution of the misorientations of different types of dislocation boundaries, the latter could be classified either as so-called geometrically necessary boundaries or incidental dislocation boundaries. A number of semi-empirical relationships between the microstructural parameters on a mesoscale and the parameters of deformation that were derived in this study can provide valuable guidance in future modelling. © 2006 Acta Materialia Inc.
Created from Fastlane, Scopus look-up
Keywords: Deformed crystals; Dislocation distribution; Geometrically necessary dislocations; Lattice plane misorientations; Long-range internal stresses

Dynamic mechanical characterization of poly(glycerol sebacate)/poly (butylene succinate-butylene dilinoleate) blends for cardiac tissue engineering by flat punch nanoindentation - Merle, Benoit; Kraus, X.; Tallawi, Marwa; Scharfe, B.; El Fray, Miroslawa; Aifantis, K. E.; Boccaccini, Aldo R.; Göken, Mathias (Materials Letters, 2018)
The viscoelastic properties of polymer blends of poly(glycerol sebacate) (PGS) and poly(butylene succinate-dilinoleate) (PBS-DLA) copolymer intended for cardiac tissue patches are investigated by dynamic flat punch nanoindentation at frequencies ranging from 1 to 45 Hz. The storage modulus is found to depend weakly on the testing frequency, the lowest value being for 1 Hz, which corresponds to the usual heart rate. More significantly, it is found that varying the PGS content between 40 and 70 wt% allows tuning the storage modulus of the blends between 11 and 39 MPa. The reliability of the nanoindentation method is validated by reference dynamic mechanical measurements on thicker PBS-DLA samples using a tensile testing machine. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Nanoindentation; Dynamic mechanical analysis; Cardiac tissue engineering

Dynamic nanoindentation of articular porcine cartilage - Franke, O.; Göken, Mathias; Meyers, M. A.; Durst, Karsten; Hodge, A. M. (Materials Science and Engineering C, 2011)
Articular cartilage is a poroelastic (biphasic) material with a complex deformation behavior, which can be considered elastic–viscoelastic. In this article, articular porcine cartilage is tested in vitro using dynamic nanoindentation and is analyzed using the frequency domain. The testing and data analysis are presented as a function of the strain rate and frequency, which allows for the results to be compared for various load amplitudes over the same frequency range. In addition, a new approach to correct the contact area during dynamic nanoindentation is presented and the effects of sample freezing on the mechanical properties are also discussed.
WW1::870

Dynamic nanoindentation testing for studying thermally activated processes from single to nanocrystalline metals - Durst, Karsten; Maier, Verena (Current Opinion in Solid State & Materials Science, 2014)
WW1::993

Editorial in special issue of the ocassion of Prof. Mughrabi's 65th Birthday, Haël Mughrabi 65 years - Höppel, Heinz Werner; et al. (Zeitschrift für Metallkunde, 2002)
UnivIS-Import:2015-03-09:Pub.2002.tech.IW.LWAW.editor

Effective usage of 2D MXene nanosheets as solid lubricant – Influence of contact pressure and relative humidity - Marian, Max; Song, Gui Cheng; Wang, Bo; Fuenzalida, Victor M.; Krauß, Sebastian; Merle, Benoit; Tremmel, Stephan; Wartzack, Sandro; Yu, Jinhong; Rosenkranz, Andreas (Applied Surface Science, 2020)
Newly emerging Ti3C2Tx–nanosheets (MXenes) have attracted considerable attention in energy storage, catalysis and, more recently, tribology. MXene nanosheets are characterized by a weakly-bonded multi-layered structure with self-lubricating ability, making them a suitable candidate for solid lubrication. This contribution aims at addressing for the first time their application in higher loaded steel/steel dry sliding contacts by investigating the influence of contact pressure and relative humidity on friction and wear performance. Compared to the uncoated reference, a 2.3-fold friction reduction and a 2.7-fold reduction of the wear volume were verified for MXene-coated specimens for moderate contact pressures and low relative humidity. This was due to the in-situ formation of a compacted tribo-film consisting of densified Ti3C2Tx–nanosheets. In contrast, too high pressures induced a partial rupture of the wear-protecting tribo-layer, thus reducing its beneficial effects. Additionally, no beneficial effects regarding friction and/or wear were found at higher relative humidities, which was correlated with the expansion of the basal spacings. Therefore, this study summarizes favorable operating conditions for MXene nanosheets when used as solid lubricant to improve friction and/or wear thus making them excellent candidates for advanced, next-generation solid lubricants.<br
Keywords: MXene-nanosheets; Contact pressure; Relative humidity; Friction reduction; Wear reduction

Effect of cold sintering process (CSP) on the electro-chemo-mechanical properties of Gd-doped ceria (GDC) - Kabir, Ahsanul; Espineira-Cachaza, Martin; Fiordaliso, Elisabetta Maria; Ke, Daoyao; Grasso, Salvatore; Merle, Benoit; Esposito, Vincenzo (Journal of the European Ceramic Society, 2020)
In this report, the effect of the cold sintering process (CSP) on the electro-chemo-mechanical properties of 10 mol% Gd-doped ceria (GDC) is investigated. High purity nanoscale GDC powder is sintered via a cold sintering process (CSP) in pure water followed by post-annealing at 1000 °C. The resultant ceramics exhibits high relative density (∼90 %) with a fine grain size of ∼100 nm. This sample illustrates comparable electrochemical properties at intermediate-high temperatures and electromechanical properties at room temperature to the material prepared via conventional firing, i.e., sintering in the air at 1450 °C. Moreover, a large creep constant, as well as a low elastic modulus and hardness, are also observed in the CSP sample.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Cold sintering; Creep; Electrostriction; Gd-doped ceria; Oxygen defects

Effect of C on the Martensitic Transformation in Fe-C Alloys in the Presence of Pre-Existing Defects: A Molecular Dynamics Study - Karewar, Shivraj; Sietsma, Jilt; Santofimia, Maria J. (Crystals, 2019)
Molecular dynamics simulations are used to investigate the atomic effects of carbon (C) addition in Fe on the martensitic phase transformation in the presence of pre-existing defects such as stacking faults and twin boundaries. The pre-existing defect structures in Fe-C alloys have the same effect on the atomistic mechanisms of martensitic transformation as in pure Fe. However, C addition decreases the martensitic transformation temperature. This effect is captured by characterizing three parameters at the atomic level: atomic shear stresses, atomic energy, and total energy as a function of temperature for face-centered-cubic (fcc) and body-centered-cubic (bcc) phases. The thermodynamic effect of fcc phase stabilization by C addition is revealed by the atomic energy at a particular temperature and total energy as a function of temperature. The barrier for fcc-to-bcc transformation is revealed by analysis of atomic shear stresses. The analysis indicates that addition of C increases the atomic shear stresses for atomic displacements during martensitic transformation, which in turn decreases the martensitic transformation temperature.
CRIS-Team WoS Importer:2019-03-26

Effect of elastic anisotropy on strain relief and residual stress determination in cubic systems by FIB-DIC experiments - Krottenthaler, Markus; Benker, Lisa; Mughal, M. Z.; Sebastiani, Marco; Durst, Karsten; Göken, Mathias (Materials & Design, 2016)
Focused Ion Beam milling and Digital Image Correlation analysis (FIB-DIC) method has been shown to offer an effective measure of residual stresses in coatings and bulk materials. In the present work the effect of elastic anisotropy on the residual stress interpretation from FIB-DIC measurements is studied for single crystals with cubic symmetry. Crystal orientation-dependent, elastically anisotropic 3D finite element models of the double slot milling geometry were developed and verified against FIB-DIC measurements performed on in situ four point bent samples of nanocrystalline nickel and single crystal CMSX-6 alloy. A discussion is presented of the limitations of the simplified assumptions vs full anisotropic modelling. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Focused ion beam milling assisted digital image correlation; Residual stress; Elastic anisotropy; Finite element modelling; Four point bending

Effect of ion irradiation on tensile ductility, strength and fictive temperature in metallic glass nanowires - Magagnosc, D. J.; Kumar, Golden; Schroers, J.; Felfer, Peter; Cairney, J. M.; Gianola, D. S. (Acta Materialia, 2014)
Ion irradiation of thermoplastically molded Pt57.5CU14.3Ni5.7P22.5 metallic glass nanowires is used to study the relationship between glass structure and tensile behavior across a wide range of structural states. Starting with the as-molded state of the glass, ion fluence and irradiated volume fraction are systematically varied to rejuvenate the glass, and the resulting plastic behavior of the metallic glass nanowires probed by in situ mechanical testing in a scanning electron microscope. Whereas the as-molded nanowires exhibit high strength, brittle-like fracture and negligible inelastic deformation, ion-irradiated nanowires show tensile ductility and quasi-homogeneous plastic deformation. Signatures of changes to the glass structure owing to ion irradiation as obtained from electron diffraction are subtle, despite relatively large yield strength reductions of hundreds of megapascals relative to the as-molded condition. To reconcile changes in mechanical behavior with glass properties, we adapt previous models equating the released strain energy during shear banding to a transit through the glass transition temperature by incorporating the excess enthalpy associated with distinct structural states. Our model suggests that ion irradiation increases the fictive temperature of our glass by tens of degrees the equivalent of many orders of magnitude change in cooling rate. We further show our analytical description of yield strength to quantitatively describe literature results showing a correlation between severe plastic deformation and hardness in a single glass system. Our results highlight not only the capacity for room temperature ductile plastic flow in nanoscaled metallic glasses, but also processing strategies capable of glass rejuvenation outside of the realm of traditional thermal treatments. (C) 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Metallic glass; Nanowire; Tensile ductility; Ion irradiation; Fictive temperature

Effect of Mg content on microstructure, texture and strength of severely equal channel angular pressed aluminium-magnesium alloys - Kalsar, R.; Yadav, D.; Sharma, A.; Brokmeier, H. G.; May, Johannes; Höppel, Heinz Werner; Skrotzki, W.; Suwas, S. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2020)
Equal channel angular pressing was carried out on Al–Mg alloys to study the effect of Mg addition on the microstructure, texture and strength after severe plastic deformation by 8 passes of equal channel angular pressing (ECAP) through route Bc. The increase in Mg content enhanced the propensity of continuous dynamic recrystallization and simultaneously decreased the average grain size of the alloy. The microstructure and local texture was heterogeneous across the billet thickness for all the samples, irrespective of composition. All the samples showed a shear-type bulk texture generally observed in face-centred cubic metals with strong BE/‾BE components. The weakening of the texture with increase in Mg content is attributed to the substructure evolution during the ECAP process. The grain size and dislocation density have been determined by X-ray diffraction line profile analysis. The experimentally determined yield strength of the ultrafine grained samples can be explained by a combination of solid solution, dislocation and grain size strengthening, the latter being predominant.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Al-Mg alloys; ECAP; Microstructure; Strengthening mechanisms; Texture; X-ray line profile analysis

Effect of thermal annealing on the mechanical properties of low-emissivity physical vapor deposited multilayer-coatings for architectural applications - Meszaros, Robert; Merle, Benoit; Wild, Michael; Durst, Karsten; Göken, Mathias; Wondraczek, Lothar (Thin Solid Films, 2012)
Low-emissivity (low-E) coatings comprising a stack of multiple physical vapor deposited metallic and dielectric layers play an important role in energy management of modern buildings. The production process of such architectural glazings often requires that the coatings withstand a short-term thermal load of up to 700 °C. Here, we report on thermally-induced variations in the mechanical properties of representative large-area magnetron-sputtered low-E stacks on glass, developed specifically for high temperature stability. Coatings are investigated before and after heat treatment by bulge testing, curvature analyses using Stoney's equation, and nanoindentation. For as-deposited coatings, an in-plane residual compressive stress about 48 MPa and Young's modulus of 120 GPa are found, depending on the type of substrate. Short-term exposure to up to 700 °C converts this situation to in-plane residual tensile stress of > 400 MPa, while Young's modulus decreases to about 105 GPa. These changes in the residual stress state are explained on the basis of structural, topological and dimensional changes in the coating stack. They identified as one of the primary factors governing temperature-resistance of low-E coatings.
WW1::923

Effects of interatomic potential on fracture behaviour in single- and bicrystalline tungsten - Hiremath, Praveenkumar; Melin, Solveig; Bitzek, Erik; Olsson, Pär A.T. (Computational Materials Science, 2022)
In the present work, we have evaluated the performance of different embedded atom method (EAM) and second-nearest neighbour modified embedded atom method (2NN-MEAM) potentials based on their predictive capabilities for modelling fracture in single- and bicrystalline tungsten. As part of the study, a new 2NN-MEAM was fitted with emphasis on reproducing surface, unstable stacking fault and twinning energies as derived from density functional theory (DFT) modelling. The investigation showed a systematic underestimation of surface energies by most EAM potentials, and a significant variation in unstable stacking and twinning fault energies. Moreover, the EAM potentials in general lack the ability to reproduce the DFT traction–separation (TS) curves. The shorter interaction length and higher peak stress of the EAM TS curves compared to the 2NN-MEAM and DFT TS curves result in one order of magnitude higher lattice trapping than for cracks studied with 2NN-MEAM. These differences in lattice trapping can lead to significant qualitative differences in the fracture behaviour. Overall, the new 2NN-MEAM potential best reproduced fracture-relevant material properties and its results were consistent with fracture experiments. Finally, the results of fracture simulations were compared with analytical predictions based on Griffith and Rice theories, for which emerging discrepancies were discussed.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Critical stress intensity factor; Density functional theory; Fracture mechanisms; Grain-boundary cohesion; Molecular statics; Tungsten

Elastic moduli and hardness of c- Zr2.86 (N0.88 O0.12) 4 having Th3 P4 -type structure - Dzivenko, Dmytro A.; Zerr, Andreas; Schweitzer, Elmar; Göken, Mathias; Boehler, Reinhard; Riedel, Ralf (Applied Physics Letters, 2007)
The equation of state of the recently discovered oxygen-bearing cubic zirconium (IV) nitride, c- Zr2.86 (N0.88 O0.12) 4, was measured at room temperature in a diamond anvil cell using x-ray powder diffraction combined with synchrotron radiation. From these studies the bulk modulus B0 =219 (13) GPa and its first pressure derivative B0′ =4.4 (1.0) [or B0 =223 (5) GPa, for B0′ fixed at 4] were obtained. Applying nanoindentation techniques the reduced modulus Er ≈220 GPa and hardness H≈18 GPa were measured for porous c- Zr2.86 (N0.88 O0.12) 4. The shear modulus of c- Zr2.86 (N0.88 O0.12) 4 was estimated to be at least G0 =96 (13) GPa using the experimental data of B0 and Er, exclusively.
Created from Fastlane, Scopus look-up
Keywords: Diamond anvil cells; Equations of state; Hertzian contact; Elastic modulus; Bulk modulus; Polycrystalline material; Powder diffraction; Shear modulus; Nano-indentation; Synchrotron radiation

Elemental partitioning and mechanical properties of Ti- and Ta-containing Co-Al-W-base superalloys studied by atom probe tomography and nanoindentation - Povstugar, Ivan; Choi, Pyuck-Pa; Neumeier, Steffen; Bauer, Alexander; Zenk, Christopher; Göken, Mathias; Raabe, Dierk (Acta Materialia, 2014)
Elemental partitioning and hardness in Ti- and Ta-containing Co-base superalloys, strengthened by γ′-Co(Al, W) precipitates, have been studied by local measurements. Using atom probe tomography, we detect strong partitioning of W (partitioning coefficients from 2.4 to 3.4) and only slight partitioning of Al (partitioning coefficients ≤1.1) to the γ′-Co(Al, W) phase. Al segregates to the γ/γ′ phase boundaries, whereas W is depleted at the γ side of the boundaries after aging at 900 °C and slow air cooling. This kind of Al segregation and W depletion is much less pronounced when water quenching is applied. As a result, these effects are considered to be absent at high temperatures and therefore should not influence the creep properties. Ti and Ta additions are found to strongly partition to the γ′ phase and greatly increase the γ′ volume fraction. Our results indicate that the alloying elements Al, W, Ti and Ta all occupy the B sublattice of the A B structure (L1 type) and affect the partitioning behavior of each other. Nanoindentation measurements show that Ta also increases the hardness of the γ′ phase, while the hardness of the γ channels remains nearly constant in all alloys. The change in hardness of the γ′ phase can be ascribed to the substitution of Al and W atoms by Ti and/or Ta. © 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Atom probe tomography (APT); Cobalt-base superalloys; Nanoindentation

Elemental partitioning, lattice misfit and creep behaviour of Cr containing γ′ strengthened Co base superalloys - Povstugar, I.; Zenk, Carolin; Li, R.; Choi, P. -P.; Neumeier, Steffen; Dolotko, O.; Hoelzel, M.; Göken, Mathias; Raabe, D. (Materials Science and Technology, 2016)
Novel Cr containing Co-Al-W base superalloys were studied by atom probe tomography and neutron diffraction. Cr is found to predominantly partition to the γ matrix and decrease partitioning of W to γ′. Furthermore, Cr significantly enhances the γ′ volume fraction, decreases the γ/γ′ lattice misfit and deteriorates the creep resistance. Addition of Ni to the Cr containing alloys affects partitioning of W and Al, further decreases the lattice misfit and results in the formation of irregularly shaped precipitates. Al, W and Cr tend to occupy the ‘B' sublattice in the γ′-A3B phase (L12 type), while Co and Ni reside in the ‘A' sublattice.<br
WW1::1068
Keywords: Cobalt base superalloys; Creep; Atom probe tomography; Partitioning; Lattice misfit; Neutron diffraction

Elemental segregation to antiphase boundaries in a crept CoNi-based single crystal superalloy - Makineni, Surendra Kumar; Lenz, Malte; Neumeier, Steffen; Spiecker, Erdmann; Raabe, Dierk; Gault, Baptiste (Scripta Materialia, 2018)
We report on the full three-dimensional compositional partitioning among the features of a planar imperfection comprising a superlattice intrinsic stacking fault (SISF) with its leading and trailing partials, as well as the antiphase boundary (APB) in the wake of the trailing partial formed in the L12-ordered γ′ phase of a CoNi-based single crystal superalloy. The partial dislocations and the APB are found to be Cr/Co rich relative to the surrounding γ′ and richer in W/Ta/Ti compared to the γ matrix phase. Solute diffusion mechanisms are derived from the compositional gradients in the vicinity of the imperfection.
Keywords: Superalloys; Planar Defects; Antiphase Boundaries; Stacking Faults; Atom Probe Tomography

Element-resolved local lattice distortion in complex concentrated alloys: An observable signature of electronic effects - Oh, Hyun Seok; Odbadrakh, Khorgolkhuu; Ikeda, Yuji; Mu, Sai; Körmann, Fritz; Sun, Cheng Jun; Ahn, Heh Sang; Yoon, Kook Noh; Ma, Duancheng; Tasan, Cemal Cem; Egami, Takeshi; Park, Eun Soo (Acta Materialia, 2021)
Complex concentrated alloys (CCAs) are of growing interest due to their outstanding mechanical properties that exceed the property limits of conventional alloys. Whereas the superior properties are often attributed to severe lattice distortion, to date it is not clear what controls the lattice distortion and how it affects the mechanical properties of CCAs. In this work, we study the element-resolved local lattice distortion (ELLD) in CCAs of 3d transition-metal elements (3d CCAs) by the extended X-ray absorption fine structure experiment and the density-functional theory calculations. We show that ELLD is primarily dependent upon charge transfer among elements and affects the properties through atomic-level pressure and orbital transition. The ELLD provides a qualitative measure of the effective atomic size for explaining element-specific properties and macroscopic properties.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Charge transfer; Complex concentrated alloy; Element-resolved local lattice distortion; Magnetism; Short-range order

Energy-storage-efficient 0.9Pb(Mg1/3Nb2/3)O3–0.1PbTiO3 thick films integrated directly onto stainless steel - Sadl, Matej; Condurache, Oana; Bencan, Andreja; Dragomir, Mirela; Prah, Uros; Malic, Barbara; Deluca, Marco; Eckstein, Udo; Hausmann, Daniel; Khansur, Neamul Hayet; Webber, Kyle Grant; Ursic, Hana (Acta Materialia, 2021)
The integration of functional ceramics with metals remains challenging due to the thermally activated processes and the incompatibilities that arise during the high-temperature ceramic sintering process. In order to overcome this, low-temperature processing methods can be employed. In this work, dense 0.9Pb(Mg1/3Nb2/3)O3–0.1PbTiO3 thick films were deposited on low-cost, stainless-steel substrates at room temperature using an aerosol-deposition method. The key material parameters for a successful aerosol deposition of the powder were identified and used in the process, which resulted in homogeneous 15-µm-thick films. The as-deposited films can withstand electric fields of 900 kV⋅cm−1 and exhibit promising room-temperature energy-storage properties: the recoverable energy density reaches 7.0 J⋅cm−3 with an energy-storage efficiency of ∼70%. A post-deposition stress relaxation by annealing at 500°C further improves the recoverable energy density, leading to 9.8 J⋅cm−3 at 900 kV⋅cm−1 with an energy-storage efficiency of ∼80%. The energy-storage performance exhibits excellent temperature stability up to 200°C and an electric-field cycling stability up to 16 million cycles. The low-temperature integration of energy-storage-efficient thick films onto stainless steel opens up possibilities for numerous new, pulsed-power and power-conditioning electronic applications.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Aerosol deposition; Energy storage; Low-temperature processing; PMN–PT; Relaxor-ferroelectric; Stainless steel; Thick film

Enhanced fatigue lives in AA1050A/AA5005 laminated metal composites produced by accumulative roll bonding - Kümmel, Frank; Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias (Acta Materialia, 2016)
In this work laminated metal composites with alternating layers of commercial pure aluminum AA1050A and aluminum alloy AA5005 were produced by ARB. In order to vary the layer thickness and the number of interfaces different numbers of ARB cycles (4, 8 and 12) were applied. Subsequently, fatigue tests were performed and the related deformation and damage mechanisms were investigated. At high amplitudes crack growth occurs very straight through the whole sheet and is more or less unaffected by the interfaces of the individual layers in the composite. At lower amplitudes, where pronounced grain coarsening of the AA1050A layers occurs, the cracks deflect in front of the AA5005 layers and propagate in the coarsened AA1050A layers parallel to the bonding plane and the loading direction. Contrary to the composite, in both conventionally ARB processed AA1050A and AA5005 mono-material sheets grains are only locally coarsened around the crack tip and the fatigue cracks propagate very straight through the sheet width. Compared to AA1050A mono-material ARB sheets fatigue life and the cyclic stability are clearly enhanced in all composites. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Accumulative roll bonding (ARB); Ultrafine-grained (UFG); Laminated metal composites (LMCs); Fatigue behavior; Dynamic grain coarsening

Enhanced monotonic and cyclic mechanical properties of ultrafine-grained laminated metal composites with strong and stiff interlayers - Kümmel, Frank; Diepold, Benedikt; Prakash, Aruna; Höppel, Heinz Werner; Göken, Mathias (International Journal of Fatigue, 2018)
The accumulative roll bonding process allows to produce multilayered composites in which substantially dissimilar metals, both in terms of Young's modulus as well as mechanical strength, can be brought together. For the optimization of such laminated metal composites a fundamental understanding of the microstructural interactions and deformation processes at the internal material interfaces is necessary. The influence of a gradient in hardness and Young's modulus in ultrafine-grained laminated metal composites on the monotonic and cyclic mechanical properties is investigated in this paper. Special attention is put on aluminum/steel composites, as a high gradient in hardness and Young's modulus is present at the layer interfaces. The mechanical properties are determined in monotonic and cyclic three-point bending tests. By scanning electron microscopy, the influence of the meso- and microstructure on the fatigue properties is intensively studied. Furthermore, the internal stresses during elastic straining are calculated using finite element simulations. The results are that for the aluminum/steel composites the monotonic and cyclic properties are drastically increased compared to aluminum mono material sheets, as well as to composites based on two different aluminum alloys, in which only a gradient in hardness at the material interface exists and the gradient in elastic properties is absent. This is related to a pronounced crack deviation at the material interface as well as to an effective load transfer in the composites.
Keywords: Accumulative Roll Bonding (ARB); Ultrafine-grained (UFG) materials; Laminated metal composites (LMCs); FE-simulation; Monotonic mechanical properties; Fatigue life; Fatigue crack path

Enhanced strength and ductility in ultrafine-grained aluminium produced by accumulative roll bonding (ARB) - Göken, Mathias; Höppel, Heinz Werner; May, Johannes (Advanced Engineering Materials, 2004)
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.nhance

Enhanced superplastic deformation behavior of ultrafine-grained Ti-6Al-4V alloy - Saitova, L.; Semenova, I.; Höppel, Heinz Werner; Valiev, R.; Göken, Mathias (Materialwissenschaft und Werkstofftechnik, 2008)
WW1::762

Enhancing mechanical properties of ultrafine-grained tungsten for fusion applications - Wurmshuber, Michael; Doppermann, Simon; Wurster, Stefan; Jakob, Severin; Balooch, Mehdi; Alfreider, Markus; Schmuck, Klemens; Bodlos, Rishi; Romaner, Lorenz; Hosemann, Peter; Clemens, Helmut; Maier-Kiener, Verena; et al. (International Journal of Refractory Metals & Hard Materials, 2023)
Keywords: Ultrafine-grained; Grain boundary segregation engineering; Small-scale testing; Tungsten; Mechanical properties; Nuclear fusion

Enhancing the high-temperature strength of a Co-base superalloy by optimizing the γ/γ' microstructure - Hausmann, Daniel; Solís, C.; Freund, Lisa; Volz, Nicklas; Heinemann, A.; Göken, Mathias; Gilles, R.; Neumeier, Steffen (Metals, 2020)
Compositionally complex polycrystalline γ/γ' CoNi-base superalloys, such as CoWAlloy2 (Co41-Ni32-Cr12-Al9-W5-Ti0.3-Ta0.2-Si0.4-Hf0.1-C-B-Zr) are interesting candidates for new high-temperature materials. To maximize their high-temperature strength, the γ/γ' microstructure has to be optimized by adjusting the multi-step heat treatments. Various microstructures after different heat treatments were analyzed by scanning and transmission electron microscopy and especially in-situ small-angle neutron scattering during heat treatment experiments. The corresponding mechanical properties were determined by compression tests and hardness measurements. From this, an optimum γ' precipitate size was determined that is adjusted mainly in the first precipitation heat treatment step. This is discussed on the basis of the theory of shearing of γ' precipitates by weak and strong pair-couplings of dislocations. A second age hardening step leads to a further increase in the γ' volume fraction above 70% and the formation of tertiary γ' precipitates in the γ channels, resulting in an increased hardness and yield strength. A comparison between two different three-step heat treatments revealed an increase in strength of 75 MPa for the optimized heat treatment.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Compositionally complex alloy; CoNi-base superalloy; Electron microscopy; Hardness; Precipitation behavior; Scanning electron microscopy transmission; Small-angle neutron scattering; Yield stress

Enhancing the lifetime and vacuum tribological performance of PVD-MoS2 coatings by nitrogen modification - Seynstahl, Armin; Köbrich, Manuel; Rosnitschek, Tobias; Göken, Mathias; Tremmel, Stephan (Surface & Coatings Technology, 2024)
As a solid lubricant, MoS2 is used for reducing friction and wear in machine elements under challenging operating conditions. In application, service life is thus a decisive factor that depends on the coating. Here, the effect of gaseous nitrogen modification on the performance of physical vapor deposited MoS2 coatings has been studied under vacuum conditions. The coatings were modified chemically or in their structural design by varying the bias voltage alternately. Tribologically induced changes were identified in short-running and long-running intermittent ball-on-disc tests, while the lifetime was evaluated in ball-on-disc tests until coating failure, with a coefficient of friction value exceeding 0.3 defined as the failure criterion. Furthermore, the microstructure was investigated before and after tribological loading. It appeared from scanning electronic microscopic imaging, that nitrogen modification reduced the initial degree of porosity and material compacting occurred after a short tribological loading. Nanoindentation measurements in the wear track of the compacted coating supported these results by a significant increase in indentation hardness and indentation modulus. Overall, the improvement in lubrication performance due to nitrogen modification led to a significant extension of service life, whereas the chemical and structural modification exhibited the highest service life of the coating.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Compaction; Lifetime tests; MoS; Nitrogen modification; Physical vapor deposition (PVD); Tribological behavior

Ermüdungslebensdauer der Magnesiumlegierung AZ91: Experiment und Modellierung - Mughrabi, Hael; Höppel, Heinz Werner; et al. (Materialwissenschaft und Werkstofftechnik, 2002)
UnivIS-Import:2015-03-09:Pub.2002.tech.IW.LWAW.ermdun_14

Ermüdungslebensdauer der Magnesiumlegierung AZ 91: Expriment und Modellierung - Höppel, Heinz Werner; Mughrabi, Hael; et al. (Mechanismenorientierte Lebensdauervorhersage für zyklisch beanspruchte metallische Werkstoffe, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IW.LWAW.ermdun

Erratum: Progressive changes in crystallographic textures of biominerals generate functionally graded ceramics (Mater. Adv. (2022) DOI: 10.1039/d1ma01031j) - Wallis, David; Harris, Joseph; Böhm, Corinna; Wang, Di; Zavattieri, Pablo; Feldner, Patrick; Merle, Benoit; Pipich, Vitaliy; Hurle, Katrin; Leupold, Simon; Hansen, Lars N.; Marin, Frederic; et al. (Materials Advances, 2022)
The authors regret that the affiliation details in the original article for the authors Simon Leupold, Lars N. Hansen, and Frederic Marin were incorrect. The full and corrected list of affiliations are given in this document. The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers.
CRIS-Team Scopus Importer:2022-04-15

Erratum to “Optimization of KOH etching parameters for quantitative defect recognition in n- and p-type doped SiC”: [J. Crystal Growth 289 (2006) 520–526] - Sakwe, Aloysius; Müller, Robin; Wellmann, Peter (Journal of Crystal Growth, 2007)

Eu2+ and Eu3+ based "concentrated phosphors" as converters for UV LED light: two approaches and two new examples - Batentschuk, Miroslaw; Geisler, R.; Hum, Jasmin; Iqbal, Farasat; Meister, Frank; Osvet, Andres; Stiegelschmitt, Alfons; Winnacker, Albrecht (Applied Physics B-Lasers and Optics, 2012)
The absolute majority of phosphors are composed of a host lattice and some percentage of an activator. At higher activator concentrations the concentration quenching occurs. However, there are phosphors in which only minor quenching of the emission occurs with increasing of the activator content. Based on the existence of two different valence states of the Eu ion (2+ and 3+), two approaches for the development of "concentrated phosphors", i.e. light emitting materials in which the activator ion is a main part of the crystal lattice, are discussed. In both approaches, reduced energy migration leading to the luminescence quenching is considered as a main condition to reach a high quantum efficiency of a concentrated phosphor. Two kinds of phosphors-Eu2+-doped alumosilicate and Eu3+-doped oxyfluoride-are used as an experimental basis for this discussion. Starting from the stoichiometric Ca1-x Eu-x(2+) A1(2)si(2)O8 anorthite and Eu3+OF oxyfluorides, the non-stoichiometric powders with Eu-0.92(2+) A1(1.76)Si(2.24)O(8), Eu3+(O, F)(2,35) and Eu3+(O, F)(2,16) compositions were synthesized by a solid state reaction and investigated. It was shown that-in spite of the almost 100% Eu concentration-light converters with high quantum efficiency of more than 45% can be realized. A possible application of these materials as UV LED light converters for white light emitting diodes are discussed as well.

Evaluation of the surface fatigue behavior of amorphous carbon coatings through cyclic nanoindentation - Weikert, Tim; Wartzack, Sandro; Baloglu, Maximilian Volkan; Willner, Kai; Gabel, Stefan; Merle, Benoit; Pineda, Fabiola; Walczak, Magdalena; Marian, Max; Rosenkranz, Andreas; Tremmel, Stephan (Surface & Coatings Technology, 2021)
Diamond-like carbon (DLC) coatings, frequently used to reduce wear and friction in machine components as well as on forming tools, are often subjected to cyclic loading. Doping of DLC coatings with metals or metal carbides as well as the usage of multilayer architectures represent promising approaches to enhance toughness, which is beneficial for the coatings’ behavior under cyclic loading. In this study, we utilized cyclic nanoindentation to characterize the tribologically induced surface fatigue behavior of single-layer tungsten-doped (a-C:H:W) and multilayer silicon oxide containing (a-C:H:Si:O/a-C:H)25 amorphous carbon coatings under cyclic loading. Columnar growth was observed for both coatings by focused ion beam microscopy and scanning electron microscopy, while the multilayer architecture of the (a-C:H:Si:O/a-C:H)25 coating was verified by the silicon content using glow-discharge optical emission spectroscopy. In cyclic nanoindentation of the (a-C:H:Si:O/a-C:H)25 multilayer coating, stepwise small changes in indentation depth were observed over several indentation cycles. The surface fatigue process of the single-layer a-C:H:W covered a smaller number of indentation cycles and was characterized by an early steep increase of the static displacement signal. Microscopical analyses hint at grain deformation, sliding at columnar boundaries, and grain detachment as underlying fatigue mechanisms of the a-C:H:W coating, while the (a-C:H:Si:O/a-C:H)25 multilayer coating showed transgranular crack propagation and gradual fracturing. In case of the (a-C:H:Si:O/a-C:H)25 multilayer coating, superior indentation hardness (HIT) and indentation modulus (EIT) as well as a higher HIT3/EIT2 ratio suggest a higher resistance to plastic deformation. A high HIT3/EIT2 ratio, being an indicator for hindered crack initiation, combined with the capability of stress relaxation in soft layers contributed to the favorable surface fatigue behavior of the (a-C:H:Si:O/a-C:H)25 multilayer coating observed in this cyclic nanoindentation studies.
Keywords: Diamond-like carbon; Cyclic nanoindentation; Surface fatigue; Multilayer architecture

Evolution of an industrial-grade Zr-based bulk metallic glass during multiple laser beam melting - Yang, Zerong; Wang, Hongcai; Krauß, Sebastian; Huber, Florian; Merle, Benoit; Schmidt, Michael; Markl, Matthias; Körner, Carolin (Journal of Non-Crystalline Solids, 2022)
Selective laser melting (SLM), taking advantage of its inherent rapid cooling rates and near-net-shape forming ability, has been employed to fabricate bulk metallic glasses (BMGs). However, crystallization is frequently triggered during the SLM process, which results in the loss of advantageous properties of BMGs, such as extremely high hardness and near-theoretical yield strength. Although many studies have been conducted to investigate SLM of BMGs, there is still a lack of knowledge about the microstructural and compositional evolution during the laser beam processing, particularly the micromechanical property response upon crystallization. In the present work, a systematic investigation is performed to gain a much better understanding about the evolution of microstructure and composition as well as the corresponding micromechanical property change during multiple laser beam melting. The material used in this study is an industrial-grade Zr-based BMG Zr59.3Cu28.8Al10.4Nb1.5 (AMZ4) with two different oxygen levels. AMZ4 demonstrates its good thermal stability by the fact that observable crystalline structure appears around the melt pool only after more than once laser beam treatment. The compositional stability of AMZ4 is manifested by the homogeneous elemental distribution on the melt pool area after even twenty-five laser beam remelting. The laser-metal interaction, melting and subsequent solidification are not effectively influenced by the emerging and expanding of crystallization zone (or heat affected zone, HAZ). Higher oxygen content results in not only a larger HAZ but also more quenched-in nuclei at the melt pool bottom. The HAZ does not exhibit a fully crystallized structure, but rather has a mixture of amorphous and crystalline phases. Crystallization of AMZ4 leads to an increase in hardness and Young’s modulus of the materia
Keywords: Bulk metallic glass; Crystallization; Laser beam melting; Selective laser melting; Additive manufacturing

Evolution of dislocation structure and deformation resistance in creep exemplified on single crystals of CaF2 - Sadrabadi, Peiman; Eisenlohr, Philip; Wehrhan, G.; Staeblein, J.; Parthier, L.; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::804

Evolution of microstructure and deformation resistance in creep of tempered martensitic 9-12%Cr-2%W-5%Co steels - Agamennone, Roberto; Blum, Wolfgang; Gupta, Chiradeep; Chakravartty, Jayanta K. (Acta Materialia, 2006)
The microstructural evolution during creep at 923 K of four tempered martensite 9-12%Cr-steels modified with 2%W and 5%Co was quantified by electron microscopy. Coarsening of subgrains with strain towards the stress dependent steady state was confirmed. The evolution of the precipitate structure is similar with regard to M23C6 (M: metallic element, X: N, C) and Laves phase (Fe,Cr)2(W,Mo) but differs strongly with regard to V-bearing precipitates. Low temper temperatures promote precipitation of V as M2X instead of VX. This appears to be critical in causing anomalously fast breakdown of initially high creep resistance. Dissolution of small V-bearing precipitates and corresponding loss of precipitation hardening in the subgrain interior is proposed to be the reason for this breakdown. The dissolution is caused by fast coarsening of M2X precipitates and precipitation of Z-phase at subgrain boundaries. Large M2X precipitates at subgrain boundaries are proposed to be nucleation sites of Z-phase. © 2006 Acta Materialia Inc.
Created from Fastlane, Scopus look-up
Keywords: Creep; Precipitates; Subgrains; Tempered martensite steels; Z-phase

Evolution of microstructure and mechanical properties of coated Co-base superalloys during heat treatment and thermal exposure - Webler, Ralf; Ziener, Marco; Neumeier, Steffen; Terberger, Philipp J.; Vassen, Robert; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2015)
WW1::1024
Keywords: High Temperature; Nanomechanics

Ex and in situ investigations on the role of persistent slip bands and grain boundaries in fatigue crack initiation - Höppel, Heinz Werner; Goik, Philip; Krechel, Christian; Göken, Mathias (Journal of Materials Research, 2017)
Polycrystalline copper (99.9%) was fatigued at a total strain amplitude of 0.1 and 0.2%, respectively. The tests were performed in situ under vacuum in a Large Chamber-Scanning Electron Microscope. By a repeated combination of in situ fatigue testing and ex situ focused ion beam milling, a deep insight into the mechanism of fatigue crack initiation and early stages of crack initiation at persistent slip bands (PSBs) and their interaction with grain boundaries was obtained. The EBSD-technique showed early slip activation and the exclusive formation of extrusions in favorably oriented grains until a certain extrusion height was reached. At the total strain amplitude of 0.2%, extrusions are formed not only in favorably oriented grains but also in grains with a lower Schmid factor due to high compatibility stresses at the grain boundaries. Extrusion growth through grain boundaries is affected by the orientation of the primary slip systems in the neighboring grains and the additional anisotropy stresses. It is concluded that early stages of crack initiation are the consequence of the formation of extrusions at PSBs in combination with the clustering of vacancies along the PSB boundaries, as it was proposed by the well-known Essmann-Gosele-Mughrabi model.
Keywords: fatigue; microstructure; Cu

Experimental and theoretical confirmation of the scaling exponent 2 in pyramidal load displacement data for depth sensing indentation - Merle, Benoit; Maier, Verena; Durst, Karsten (Scanning, 2014)
A series of articles by Kaupp et al. have recently been published in ,containing erroneous claims about the curvature of pyramidal nanoindentation loading curves. The present paper recalls the theoretical reasons why, for self-similar indenter shapes like pyramidal or conical indentations, the load scales with the indentation depth squared. Furthermore, experimental evidence for that behavior is provided for a wide variety of materials, ranging from ceramics to metals and polymers.
WW1::996

Experimental determination of the effective indenter shape and epsilon-factor for nanoindentation by continuously measuring the unloading stiffness - Merle, Benoit; Maier, Verena; Göken, Mathias; Durst, Karsten (Journal of Materials Research, 2012)
The Oliver and Pharr method for evaluating nanoindentation load-displacement data is based on the measurement of the contact stiffness, which is usually determined at the very beginning of the unloading sequence, or, using dynamic nanoindentation, continuously during the whole loading segment. A new experimental method has been developed to continuously monitor the contact stiffness throughout the unloading sequence. It provides supplementary information about the shape and area of the residual impression, as well as a direct measurement of the shape of the effective indenter previously introduced by Pharr and Bolshakov. The new method was applied to indentations on fused silica, sapphire, nanocrystalline nickel, and ultrafin e-grained aluminum. Lastly, the new procedure was adapted to directly measure the epsilon factor used in the Oliver and Pharr method. A value of 0.76 was found from indentation into fused silica, in close agreement with literature values.

Experimental determination of the effective indenter shape and ε-factor for nanoindentation by continuously measuring the unloading stiffness - Merle, Benoit; Maier, Verena; Göken, Mathias; Durst, Karsten (Journal of Materials Research, 2012)
The Oliver and Pharr method for evaluating nanoindentation load–displacement data is based on the measurement of the contact stiffness, which is usually determined at the very beginning of the unloading sequence, or, using dynamic nanoindentation, continuously during the whole loading segment. A new experimental method has been developed to continuously monitor the contact stiffness throughout the unloading sequence. It provides supplementary information about the shape and area of the residual impression, as well as a direct measurement of the shape of the effective indenter previously introduced by Pharr and Bolshakov. The new method was applied to indentations on fused silica, sapphire, nanocrystalline nickel, and ultrafine-grained aluminum. Lastly, the new procedure was adapted to directly measure the epsilon factor used in the Oliver and Pharr method. A value of 0.76 was found from indentation into fused silica, in close agreement with literature values.
EAM Import::2019-03-14

Experimental Validation of Property Models and Databases for Computational Superalloy Design - Gaag, Tobias; Weidinger, Julius; Bandorf, Jakob; Lux, Valeska; Wahlmann, Benjamin; Neumeier, Steffen; Zenk, Christopher; Körner, Carolin (Advanced Engineering Materials, 2024)
Computational superalloy development is a powerful alternative to the conventional experimental approach. Based on thermodynamic databases and the CALPHAD method, it is possible to estimate the properties of a large number of potential alloys and select the most promising ones. However, the accuracy of the databases and complementary property models can be unsatisfying. The accuracy of two mass density and (Formula presented.) lattice parameter models and the TTNI8 and TCNI10 databases is analyzed in detail on the experimental basis of computationally optimized single-crystalline superalloys. Various properties are measured and compared to the results of the property models and databases. Neither of the databases is superior to the other and especially the (Formula presented.) solvus temperature is not accurately described in both. The new mass density model, a linear regression based on the molar mass, is more reliable for low-density alloys. Both lattice parameter model versions slightly overestimate the room-temperature (Formula presented.) lattice parameter. The (Formula presented.) lattice parameter, however, is more accurately calculated using the new model version. The results of this study can be readily used to improve a multicriteria alloy optimization tool for computational superalloy design.
CRIS-Team Scopus Importer:2024-07-19
Keywords: CALPHAD; computational alloy developments; differential scanning calorimetry; optimizations; superalloys

Exploring the mechanical properties of additively manufactured carbon-rich zirconia 3D microarchitectures - Winczewski, J. P.; Zeiler, Stefan; Gabel, Stefan; Susarrey-Arce, A.; Gardeniers, J. G.E.; Merle, Benoit (Materials & Design, 2023)
Two-photon lithography (TPL) is a promising technique for manufacturing ceramic microstructures with nanoscale resolution. The process relies on tailor-made precursor resins rich in metal–organic and organic constituents, which can lead to carbon-based residues incorporated within the ceramic microstructures. While these are generally considered unwanted impurities, our study reveals that the presence of carbon-rich residues in the form of graphitic and disordered carbon in tetragonal (t-) ZrO2 can benefit the mechanical strength of TPL microstructures. In order to achieve a better understanding of these effects, we deconvolute the structural and materials contributions to the strength of the 3D microarchitectures by comparing them to plain micropillars. We vary the organic content by different thermal treatments, resulting in different crystal structures. The highest compression strength of 3.73 ± 0.21 GPa and ductility are reached for the t-ZrO2 micropillars, which also contain the highest carbon content. This paradoxical finding opens up new perspectives and will foster the development of “brick and mortar”-like ceramic microarchitectures.
CRIS-Team Scopus Importer:2023-07-28
Keywords: 3D printing; Additive manufacturing; Micromechanics; Micropillar compression; Zirconia

Extending Estimating Hydrogen Content in Atom Probe Tomography Experiments Where H 2 Molecule Formation Occurs - Meier, Martin S.; Jones, Megan E.; Felfer, Peter; Moody, Michael P.; Haley, Daniel (Microscopy and Microanalysis, 2022)
We investigated a new method for estimating specimen hydrogen content in atom probe tomography (APT) in experiments where molecular hydrogen ions originating from the measurement environment can overlap with deuterium (D+) in the mass-to-charge-state spectrum, thus preventing the direct application of isotopic marking for unambiguous hydrogen analysis. First, we applied an existing method for hydrogen content estimation, using ratios obtained from paired deuterated/nondeuterated experiments. These measurements demonstrated sufficient residual uncertainty to motivate exploring an alternative method to accurately estimate hydrogen content. By varying the time between evaporation events, it is then shown that a highly correlated relationship between field evaporation rate and hydrogen content exists and can also be used to predict hydrogen content. This leads to a new method for measuring hydrogen content within the specimen. We combine this extrapolation technique with continuous cycling of the evaporation rate or pulse frequency during an APT experiment. This could enable spatially resolved imaging of hydrogen concentrations despite the presence of a contaminant background hydrogen signal, without the need for deuteration.
CRIS-Team Scopus Importer:2022-12-09
Keywords: atom probe tomography; deuterium; evaporation rate; hydrogen; hydrogen peak height ratio; hydrogen/deuterium mass-to-charge spectrum overlap

Extending the range of constant strain rate nanoindentation testing - Merle, Benoit; Higgins, Wesley H.; Pharr, George M. (Journal of Materials Research, 2020)
Constant strain rate nanoindentation hardness measurements at high sustained strain rates cannot be made in conventional nanoindentation testing systems using the commonly employed continuous stiffness measurement technique (CSM) because of the "plasticity error" recently reported by Merle et al. [Acta Mater.134, 167 (2017)]. To circumvent this problem, here we explore an alternative testing and analysis procedure based on quasi-static loading and an independent knowledge of the Young's modulus, which is easily obtained by standard nanoindentation testing. In theory, the method applies to any indentation strain rate, but in practice, an upper limit on the rate arises from hardware limitations in the testing system. The new methodology is developed and applied to measurements made with an iMicro nanoindenter (KLA, Inc.), in which strain rates up to 100 s-1 were successfully achieved. The origins of the hardware limitations are documented and discussed.
CRIS-Team Scopus Importer:2020-02-04
Keywords: high strain rate; high velocity; nanoindentation

External stress as a way to control Au(111) reconstruction - Chauraud, Dimitri; Durinck, J.; Vernisse, L.; Smalley, S.; Drouet, M.; Coupeau, C. (Surface Science, 2021)
We report investigations on gold single crystals carried out with the help of an original experimental set-up, combining a scanning tunneling microscope and a compression device under ultra high vacuum, that allows for in situ observations of stressed surfaces at the atomic scale. It is observed that a macroscopic compression strain may induce a reorganization of the Au(111) surface reconstruction, known as the chevron-like pattern. Molecular dynamics simulations using a modified embedded atom method potential have been carried out to highlight the elementary dislocation mechanisms at the origin of such an evolution.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Molecular Dynamics; Scanning Tunneling Microscopy; Surface Reconstruction

Fabrication and Characterization of a Magnetic 3D-printed Microactuator - Rothermel, Florian; Thiele, Simon; Jung, Chris; Krapf, Anna; Ilse, Sven Erik; Merle, Benoit; Giessen, Harald; Herkommer, Alois M. (Advanced Materials Technologies, 2024)
Conventional MEMS microactuators have, in recent years, been complemented by 3D-printed actuatable microstructures fabricated via two-Photon-Polymerization (2PP). Herein, a novel compact 3D-printed magnetically actuatable microactuator with a diameter of 500µm is demonstrated, originally designed for micro-optical systems. It is fabricated by incorporating a composite of NdFeB microparticles and epoxy resin into a designated reservoir of the printed mechanical structure within a simple post-processing step. The microactuator structure features mechanical springs, allowing for continuous positioning with large displacement. Mechanical studies by nanoindentation of IP-S bulk structures reveal a viscoelastic material behavior, described by a two-element General Kelvin-Voigt viscoelasticity model. The obtained material parameters are then used to simulate and characterize the spring behavior of the microactuator. Actuation experiments are conducted using an external microcoil. The actuator displacement is measured for triangular current pulses with a peak current of 106 mA and durations of 1 to 100 s, resulting in displacements of 69.1 to 88.9 µm. Hysteretic behavior of the actuator is observed, attributable to viscoelasticity and magnetic properties of the core material. Numerical simulations of the experiment demonstrate this behavior as well. On-the-fly demagnetization and the implementation of closed-loop control allow for both high repeatability and precise positioning.
CRIS-Team Scopus Importer:2024-04-19
Keywords: 3D-printing; magnetic microactuator; nanoindentation; two-photon polymerization; viscoelasticity

Failure mechanisms of a hydrogenated amorphous carbon coating in load-scanning tests - Hetzner, Harald; Schaufler, Jens; Tremmel, Stephan; Durst, Karsten; Wartzack, Sandro (Surface & Coatings Technology, 2012)
A diamond-like carbon (DLC) coating with a top layer of pure hydrogenated amorphous carbon (a-C:H) and an interlayer of tungsten-modified hydrogenated amorphous carbon (a-C:H:W) was deposited onto polished cylindrical specimens of a hardened and tempered cold work tool steel. On a load-scanning test rig, tribological-mechanical tests under dry conditions with DLC coated specimens sliding against identical, but uncoated specimens were performed. Additionally, comparative tests with DLC sliding against DLC and tool steel sliding against tool steel were carried out. During each test cycle, the normal load was gradually increased from 13 to 350. N, corresponding to a Hertzian contact pressure of 1.0 to 3.0. GPa. The coefficient of friction was monitored as a function of the normal load, with a significant increase in friction indicating failure of the coating. The tests were repeated and stopped at different total numbers of load cycles. After the tests, a FIB-assisted microscopical analysis in terms of wear and damage of the DLC coating was performed, revealing the (subsurface) failure mechanisms. For DLC sliding against steel, the coating fails within only few load cycles; first tribologically and after that mechanically. Failure is initiated by adherence and subsequent transfer of steel of the counter body. Below adhered steel flakes, tensile cracks form in the a-C:H top layer, with sharp crack edges removing even more steel from the counter body. In following load cycles, coating fragments are being pulled out at these spots, representing the final failure mode. In contrast, for DLC sliding against DLC, no coating failure and also no significant wear are observed, even after a considerably higher number of load cycles. © 2012 Elsevier B.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.failur
Keywords: a-C:H; Coating failure; Diamond-like carbon; Load-scanning test

Failure mechanisms of a tungsten-modified hydrogenated amorphous carbon coating in load-scanning tests - Hetzner, Harald; Schaufler, Jens; Tremmel, Stephan; Durst, Karsten; Wartzack, Sandro (Surface & Coatings Technology, 2012)
Polished cylindrical specimens of a hardened and tempered cold work steel were coated with a tungsten-modified hydrogenated amorphous carbon coating (a-C:H:W). On a load-scanning test rig, tribological-mechanical tests under dry conditions with coated specimens sliding against identical, but uncoated specimens were performed. Additionally, comparative tests with a-C:H:W coated specimens sliding against a-C:H:W coated specimens were carried out. During each test cycle, the normal load was gradually increased from 13 to 350. N (Hertzian contact pressure of 1.0 to 3.0. GPa). The coefficient of friction was monitored as a function of the normal load, with a significant increase in friction indicating failure of the coating. These tests were repeated and stopped at different total numbers of load cycles. After the tests, a FIB-assisted microscopical analysis in terms of wear and damage of the coating was performed, revealing the (subsurface) failure mechanisms. The results obtained show that at Hertzian pressures of more than 2. GPa and after about eight load cycles, failure of the a-C:H:W coating is initiated by locally accumulated adhesion of steel flakes, repeatedly occurring at random contact pressures in this load range. The adherence of steel goes along with a local increase in friction, inducing the formation of small shear cracks in the coating top layer. Continued crack formation finally results in partial delamination of coating material and disruption of the surface, in affected areas only. Reference tests with the pairing a-C:H:W/a-C:H:W underline that, very much unlike pure hydrogenated amorphous carbon (a-C:H), a-C:H:W is a rather ductile material with the ability to stick to itself. A discussion of this study's results against the background of a similarly conducted previous study of an a-C:H-based coating system reveals some similarities, but also significant differences in the tribological and mechanical behaviour of both types of amorphous carbon. © 2012 Elsevier B.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.failur_1
Keywords: a-C:H:W; Coating failure; Diamond-like carbon; Load-scanning test

Fatigue and microstructure of ultrafine-grained metals produced by severe plastic deformation - Mughrabi, Hael; Höppel, Heinz Werner; et al. (Scripta Materialia, 2004)
The cyclic deformation and fatigue behaviour of ultrafine-grained metals produced by the severe plastic deformation technique ECAP (equal channel angular pressing) is discussed briefly with respect to cyclic softening, macroscopic shear banding and fatigue lives. Possibilities to enhance the LCF fatigue resistance by annealing are indicated. © 2004 Acta Materialia Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.fatigu_4
Keywords: Annealing; ECAP; Fatigue damage; Fatigue life; Microstructure; Ultrafine-grained metals

Fatigue behavior of calcium containing AZ91 magnesium alloys - Amberger, Dorothea; Blickle, Tina; Höppel, Heinz Werner; Göken, Mathias (MP Materials Testing, 2015)
WW1::1025

Fatigue Behavior of Calcium Containing AZ91 Magnesium Alloys - Amberger, Dorothea; Blickle, Tina; Höppel, Heinz Werner; Göken, Mathias (Proceedings of the 7th International Conference on Low Cycle Fatigue, 2013)

Fatigue behavior of ultrafine-grained Ti-6Al-4V 'ELI' alloy for medical applications - Saitova, L. R.; Höppel, Heinz Werner; Göken, Mathias; Semenova, I. P.; Raab, G. I.; Valiev, R. Z. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
Keywords: Ultrafine-grained materials; Fatigue life; Ti-6Al-4V; Fatigue damage; Equal channel angular pressing

Fatigue behavior of ultrafine-grained Ti-6Al-4V 'ELI' alloy for medical applications - Saitova, L. R.; Höppel, Heinz Werner; Göken, Mathias; Semenova, I. P.; Raab, G. I.; Valiev, R. Z. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::805

Fatigue behaviour in nanostructured metals - Göken, Mathias; Höppel, Heinz Werner (Elsevier Ltd., 2011)
Keywords: Ultrafine-grained (UFG) materials; Aluminium alloys; Damage mechanisms; Copper microstructure; Fatigue behaviour; ECAP; Magnesium alloys; Fatigue life; Severe plastic deformation; Nanocrystalline materials; Titanium alloys; Steels

Fatigue crack initiation in nickel-based superalloys studied by microstructure-based FE modeling and scanning electron microscopy - Fried, M.; Krechel, Christian; Affeldt, E. E.; Eckert, B.; Kimmig, S.; Retze, U.; Höppel, Heinz Werner; Göken, Mathias (MATEC Web of Conferences, 2014)
WW1::997

Fatigue damage evolution in a particulate-reinforced metal matrix composite determined by acoustic emission and compliance method - Biermann, Horst; Vinogradov, Alexei; Hartmann, Oliver; Hartmann, Oliver (International Journal of Materials Research, 2021)
The damage evolution during fatigue of a particulate-reinforced metal matrix composite was investigated experimentally by two methods, i. e., by the measurement of the samples' stiffness values within individual stress - strain hysteresis loops and by the measurement and evaluation of the acoustic emission during cyclic deformation. Both methods indicate that the first damage occurs during the first loading cycle, in tension as well as in compression. After a short period of a high damage rate which is due to fracture of large particles, a longer range of a smaller damage rate follows, in which smaller particles break. Finally, both methods indicate the growth of the main (and final) fatigue crack.
CRIS-Team WoS Importer:2022-01-14

Fatigue damage in copper polycrystals subjected to ultrahigh-cycle fatigue below the PSB threshold - Weidner, Anja; Amberger, Dorothea; Pyczak, Florian; Schoenbauer, Bernd; Stanzl-Tschegg, Stefanie; Mughrabi, Hael (International Journal of Fatigue, 2010)
WW1::838

Fatigue Life, Cyclic Deformation Behaviour and Damage Mechanisms of Ultrafine-Grained AA5754 Aluminum Alloy Produced by Accumulative Roll Bonding - Göken, Mathias; Hausöl, Tina; Höppel, Heinz Werner (Proceedings of the 7th International Conference on Low Cycle Fatigue, 2013)

Fatigue Life Optimized Layer Architecture of Ultrafine-Grained Al-Ti Laminates Under Bending Stresses - Diepold, Benedikt; Schunk, Christopher; Kümmel, Frank; Fey, Tobias; Prakash, Aruna; Höppel, Heinz Werner; Göken, Mathias (Advanced Engineering Materials, 2022)
Fatigue of metallic components is an important aspect in mechanical engineering. For example, the repeated pressure differences result in the fatigue of the fuselage of aircrafts. These high demands require the application of endurable and lightweight materials. In this context, laminated metal composites produced by the accumulative roll bonding process can fulfill both aspects: outstanding mechanical strength of lightweight materials, due to an ultrafine-grained microstructure, combined with the possibility to produce fatigue-resistant materials by varying the stacking order of the laminated metal composites. This work investigates laminated metal composites consisting of aluminum AA2024 and titanium grade 1 layers with different stacking orders in respect to their three-point bending fatigue properties. Additional finite element method (FEM) calculations of the stress distributions in the laminated metal composites are used to explain the results. The mechanical properties of the laminates with an outer aluminum or titanium layer are discussed based on the investigations of nanohardness and crack propagations. Although maximum bending stresses at the sheet surface of laminates with outer Titanium layer are higher than in monolithic materials, these laminates exhibit good lightweight potentials due to the weight reducing aluminum in inner layers.
CRIS-Team WoS Importer:2022-01-21

Fatigue lives and cyclic deformation behaviour of ultrafine grained materials - Höppel, Heinz Werner; Mughrabi, Hael; Kautz, Martin; et al. (Mechanismenorientierten Lebensdauervorhersage für zyklisch beanspruchte metallische Werkstoffe, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IW.LWAW.fatigu

Fatigue lives and cyclic deformation behaviour of ultrafine-grained metals and alloys - Höppel, Heinz Werner; Mughrabi, Hael; et al. (DVM/DFG-Abschlusskolloquium "Lebensdauervorhersage, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IW.LWAW.fatigu

Fatigue of low alloyed carbon steels in the HCF/VHCF-regimes - Bachmann, Jonas; Göken, Mathias; Höppel, Heinz Werner (Fatigue of Materials at Very High Numbers of Loading Cycles, 2018)
The fatigue behaviour and damage evolution in body centered cubic low alloyed steels in the high cycle and very high cycle fatigue regimes (HCF/VHCF) were in focus of this work. For this purpose, the steels C15E, C45E and C60E, with different ferritic-pearlitic microstructures were investigated. Due to the different carbon contents the ratio of ferrite to pearlite decreased from C15E to C60E. C15E mainly consist of ferrite grains. The ferrite grains deform plastically under cyclic loading. With decreasing stress amplitudes plastic deformation becomes more and more localized in particular ferrite grains. During further cyclic loading plastic deformation accumulates in those grains and finally leads to crack initiation and fatigue failure. The accumulation of irreversible plastic deformation in the ferrite grains and the strength of microstructural barriers in the vicinity of the plastically deformed grains are mainly determining the total fatigue life. In order to assess quantitatively the contribution of irreversible plastic deformation a new method was developed. By determining the dissipated energy per fatigue cycle, which was derived from the power input of the ultrasonic fatigue machine, it is possible to account for the amount of irreversibility during one loading pulse. Based on these results a prediction of the fatigue life can be made at a very early stage of the fatigue experiment. It also allows distinguishing very early whether the specimen will become a runout or if it will fail at a given amplitude. It also turned out that the interaction of localized plastic deformation with microstructural barriers in the direct vicinity is the key for understanding the occurrence of late fatigue failure. If specimens showed macroscopic crack growth and fatigue failure, critical cracks always initiated at interfaces. On the other hand, runout specimens showed some crack nuclei, but they were not able to overcome the next microstructural barrier.<br

Fatigue Properties of Bulk Nanostructured Materials - Höppel, Heinz Werner; Mughrabi, Hael; Vinogradov, Alexei (John Wiley and Sons, 2009)
Keywords: Bulk nanostructured materials; Damage mechanisms; Cyclic deformation behavior; Fatigue properties

FE2AT - Finite element informed atomistic simulations - Möller, Johannes; Prakash, Aruna; Bitzek, Erik (Modelling and Simulation in Materials Science and Engineering, 2013)
Atomistic simulations play an important role in advancing our understanding of the mechanical properties of materials. Currently, most atomistic simulations are performed using relatively simple geometries under homogeneous loading conditions, and a significant part of the computer time is spent calculating the elastic response of the material, while the focus of the studies lies usually on the mechanisms of plastic deformation and failure. Here we present a simple but versatile approach called FE2AT to use finite element calculations to provide appropriate initial and boundary conditions for atomistic simulations. FE2AT allows us to forgo the simulation of large parts of the elastic loading process, even in the case of complex sample geometries and loading conditions. FE2AT is open source and can be used in combination with different atomistic simulation codes and methods. Its application is demonstrated using the bending of a nano-beam and the determination of the displacement field around a crack tip as examples.
WW1::963

Finite element simulation of spherical indentation in the elastic / plastic transition - Göken, Mathias; Durst, Karsten; et al. (Zeitschrift für Metallkunde, 2002)
Finite element simulations were conducted to examine spherical indentation in the elastic-plastic transition regime. Various elastic-perfectly plastic materials were studied by varying the ratio of the elastic modulus to the yield stress in the range 25-1000. Special attention was given to the influence of residual stress and friction on the indentation load-displacement behavior and development of the plastic zone. A new method for measuring yield strengths from indentation load-displacement curves is proposed, and a recently developed experimental method for measuring biaxial residual stresses by nanoindentation methods is assessed. In the appropriate limits, the simulations show good agreement with the theoretical descriptions of spherical indentation given by Hertz and Tabor.
UnivIS-Import:2015-03-09:Pub.2002.tech.IW.LWAW.finite
Keywords: Constraint; Elastic plastic transition; Finite element simulation; Friction; Hardness; Hertzian contact; Residual stress; Spherical indentation; Yield strength

Finite element study for nanoindentation measurements on two-phase materials - Göken, Mathias; Durst, Karsten; et al. (Journal of Materials Research, 2004)
Finite element simulations of conical indentations in two-phase elastic-plastic materials were used to investigate the influence of the shape and the aspect ratio of particles embedded in a matrix material on the deformation behavior and hardness during depth-sensing indentation. Starting with single-phase materials, pile-up behavior and its influence on the contact area was studied. Particle-matrix systems were simulated for elastic-perfectly plastic particles embedded in a matrix, with a yield-strength ratio of 2 or 0.5, respectively. The simulations were motivated by indentation experiments in precipitation hardened nickel-base superalloy with a nanoindenting atomic force microscope. In the studied alloys, the matrix formed channels with a thickness of about 100 nm around the precipitates with diameters of about 500 nm. The simulations explained an experimentally observed transition from particle to matrix deformation behavior during indentation. Depth limits in hardness testing in particle-matrix systems were evaluated. Depending on the aspect ratio, soft and hard particles were tested reliably up to a normalized contact radius of about 70% particle diameter. © 2004 Materials Research Society.
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.finite

Flexural strength of PVD coated float glass for architectural applications - Meszaros, Robert; Wild, Michael; Merle, Benoit; Wondraczek, Lothar (Glass Technology-European Journal of Glass Science and Technology Part A, 2011)
The effect of PVD coatings on the ring-on-ring flexural strength of soda lime silica float glass was studied. A 70% increase from 280 +/- 8 to 478 +/- 10 MPa was observed on the air-side of the glass after applying a multilayer low emissivity coating of 100 nm total thickness. A similar but less pronounced effect could be obtained with a TiO(2) single layer of 50 nm. At the same time, for both coatings, the Weibull modulus was found to approximately double. Results are interpreted on the basis of two assumptions: initial defects on the glass surface are covered by the coating, and their growth is prevented due to the protective function of the coating, especially as a humidity barrier. Both assumptions were confirmed by atomic force microscopy and micromechanical analyses. This barrier function leads to significantly improved resistance to long term fatigue and stress corrosion, respectively.

Flow stress and creep rate of nanocrystalline Ni - Blum, Wolfgang; Li, Yujiao (Scripta Materialia, 2007)
Stress-strain curves of nanocrystalline Ni are compared to reported creep rate-strain curves at 298 and 373 K. Both show a limited range of strong work hardening followed by a steady-state. The stress dependence of the steady-state creep rate explains the continuous decrease in creep rate found in tests at constant load. The stress exponent of strain rate, n, decreases markedly with decreasing stress, but does not reach the low level commonly expected for Coble creep or grain boundary sliding.
Created from Fastlane, Scopus look-up
Keywords: Creep rate; Flow stress; Nanocrystalline Ni; Steady-state; Stress exponent

Formability of accumulative roll bonded aluminum AA1050 and AA6016 investigated using bulge tests - Topic, Irena; Höppel, Heinz Werner; Staud, Detlev; Merklein, Marion; Geiger, Manfred; Göken, Mathias (Advanced Engineering Materials, 2008)
The paper reports one of the very first attempts to investigate the formability of ultrafine- grained aluminum sheets produced by a severe plastic deformation process known as accumulative roll bonding. During hydraulic bulge testing the samples showed a tendency to higher achievable burst pressures and/or von Mises equivalent strains with increasing number of accumulative roll bonding cycles, indicating promising deformation behaviour and good formability.
WW1::765

Formability of ultrafine-grained AA6016 sheets processed by accumulative roll bonding - Hausöl, Tina; Schmidt, Christian; Maier, Verena; Böhm, Wolfgang; Nguyen, Manh Hung; Merklein, Marion; Höppel, Heinz Werner; Göken, Mathias (Key Engineering Materials, 2012)
Aluminium alloy AA6016 was accumulative roll bonded up to eight cycles in order to produce an ultrafine-grained microstructure. The formability of these sheets was investigated by means of bending tests. Furthermore the influence of a local laser heat treatment at the bending edge is observed. The strength of the UFG samples is increased by a factor of around two compared to the conventionally grained T4 condition which also results in up to 50 % higher punch forces needed for bending of ARB processed samples. An anisotropic bending behaviour is observed. By applying a tailored laser heat treatment along the bending edge prior to the bending tests a local recrystallization and recovery at the deformation zone of the samples is achieved. Thus, ductility is increased locally whereby bending to an angle of 80° is possible with lower forming forces compared to the non-heat treated specimens. The results are compared to previous studies on mechanical properties and formability investigations of ARB processed AA6016.
WW1::929

Formation of Cuboidal Co3AlC Precipitates in Carbon-Containing Co-Al-W-Based Superalloys - Freund, Lisa; Bauer, Alexander; Benker, Lisa; Neumeier, Steffen; Göken, Mathias (Advanced Engineering Materials, 2015)
WW1::1048
Keywords: High Temperature

Formation of Die Soldering and the Influence of Alloying Elements on the Intermetallic Interface - Kohlhepp, Marius; Uggowitzer, Peter J.; Hummel, Marc; Höppel, Heinz Werner (Materials, 2021)
Die soldering of die castings is a serious problem in the aluminum casting industry. The precise mechanism, the influence of the alloy composition, and the options for prevention have not yet been fully elaborated. A well-established solution for alloys with low iron content is the addition of manganese. However, up to 0.8 wt.% is necessary, which increases the amount of brittle phases in the material and consequently reduces ductility. Immersion tests with 1.2343 tool steel and pure aluminum as well as a hypoeutectic AlSi-alloy with Mn, Mo, Co, and Cr additions were carried out to systematically investigate the formation of die soldering. Three different intermetallic layers and a scattered granular intermetallic phase formed at the interface between steel and Al-alloy after immersion into the melt for a duration of 6 min at 710 °C. The combined presence of the irregular, needle-shaped β-Al5FeSi phase and the surrounding alloy was responsible for the bond between the two components. Mn and Mo inhibited the formation of the β-phase, and instead promoted the αC-Al15(Fe,X)3Si2 phase. This led to an evenly running boundary to the AlSi-alloy and thus prevented bonding. Cr has proven to be the most efficient addition against die soldering, with 0.2 wt.% being sufficient. Contrary to the other elements investigated, Cr also reduced the thickness of the intermetallic interface.<br
Keywords: aluminum; die soldering; intermetallic phases; high-pressure die casting; chromium; manganese; molybdenum; cobalt

Formation of Peripheral Coarse Grain in Thin-Walled Al–Mg–Si Extrusion Profiles - Goik, Philip; Schiffl, A.; Höppel, Heinz Werner (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
Investigations on microstructure and texture development during processing of Al–Mg–Si sheet and extrusion profiles focused on describing and modelling the changes in the bulk. However, understanding the evolution of microstructure in the sub-surface region is highly relevant, as this governs material performance under corrosion and bending deformation, which are crucial applications in mobility and transportation. The aim of this study was to correlate the effect of alloy composition and extrusion parameters to the formation of texture and peripheral coarse grain (PCG) layer. For this, five alloys of the AA6xxx class with varying content of dispersoid forming elements were extruded at increasing extrusion speeds into thin-walled hollow profiles. The microstructure at a plane section was investigated by means of EBSD and characterized in terms of distinct texture component distribution. It was shown that with increasing grain boundary mobility, through adapting dispersoid content and extrusion speed, the PCG layer grows into a fine-grained bulk. This growth of the PCG layer is only counter-acted upon, when the grain boundary mobility in the bulk is high enough, so that extensive growth of Cube oriented grains occurs. The PCG layer shows distinct orientations related to ⟨ 101 ⟩ | | TD , so that a possible mechanism for the orientation selection during grain growth is proposed.
CRIS-Team Scopus Importer:2023-08-11

Fracture ab initio: A force-based scaling law for atomistically informed continuum models - Möller, Johannes; Bitzek, Erik; Janisch, Rebecca; ul Hassan, Hamad; Hartmaier, Alexander (Journal of Materials Research, 2018)
In fracture mechanics, established methods exist to model the stability of a crack tip or the kinetics of crack growth on both the atomic and the macroscopic scale. However, approaches to bridge the two scales still face the challenge in terms of directly converting the atomic forces at which bonds break into meaningful continuum mechanical failure stresses. Here we use two atomistic methods to investigate cleavage fracture of brittle materials: (i) we analyze the forces in front of a sharp crack and (ii) we study the bond breaking process during rigid body separation of half crystals without elastic relaxation. The comparison demonstrates the ability of the latter scheme, which is often used in ab initio density functional theory calculations, to model the bonding situation at a crack tip. Furthermore, we confirm the applicability of linear elastic fracture mechanics in the nanometer range close to crack tips in brittle materials. Based on these observations, a fracture mechanics model is developed to scale the critical atomic forces for bond breaking into relevant continuum mechanical quantities in the form of an atomistically informed scale-sensitive traction separation law. Such failure criteria can then be applied to describe fracture processes on larger length scales, e.g., in cohesive zone models or extended finite element models.

Fracture resistance of yttria stabilized zirconia manufactured from stabilizer-coated nanopowder by micro cantilever bending tests - Giese, Sven; Kern, F.; Macauley, Chandra; Neumeier, Steffen; Göken, Mathias (Journal of the European Ceramic Society, 2019)
Yttria stabilized tetragonal zirconia polycrystal (Y-TZP)owes its high toughness to transformation toughening, a mechanism that requires the development of a process zone. It is important to measure if and to what extent the size of components can be reduced. In this study, tests were carried out using focused ion beam or picosecond milled pre-notched, 3 mol percent Y 2 O 3 (3Y-)TZP micro-cantilever (10–250 μm)beams. The tests show clearly that the maximum fracture resistance is size dependent and the plateau toughness was not reached in any of the small-scale samples. A correlation between transformability of the tetragonal phase and the measured fracture resistance became visible only for the largest micro cantilever but did not reach the values measured in macroscopic samples. Based on these results, it is not advantageous to use very tough zirconia materials in components with dimensions smaller than ∼0.25 mm, as the high toughness is not fully realized.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Ceramic; Fracture toughness; Micro cantilever; Small scale; TZP

Fracture toughness evaluation of a cracked au thin film by applying a finite element analysis and bulge test - Tinoco, Hector A.; Hutař, Pavel; Merle, Benoit; Göken, Mathias; Kruml, Tomas (Key Engineering Materials, 2020)
This paper presents a finite element analysis of a pre-cracked freestanding gold thin film subjected to bulge test. These tests were conducted in order to determine the elasto-plastic properties and fracture toughness of the gold films. For the experimental tests, a pre-crack was introduced in the center of the film by focused ion beam (FIB) milling with a length of 10 µ m and a width of 100nm. For the numerical fracture analysis, the problem was divided into two stages; the first stage was the development of the numerical model on the whole film without pre-crack (elasto-plastic analysis) and the second one was performed on a film portion that included the pre-crack (sub-modeling stage). Three different notches (rounded, sharp and V-sharp) were applied to calculate the stress intensity factor around the crack tip using path independent J-integral. The obtained results show that the load-deflection curves for non-cracked and pre-cracked film reproduced the experiments using the calculated elasto-plastic properties. This indicates that the proposed models presented a good correlation and robustness. Additionally, fracture toughness values were calculated between 0.288 0.5 and 0.303 MPa. m0.5 with J-integral values 1.037 J/m2 (elastic) and 1.136 J/m2 (elasto-plastic) which correspond with other calculations available in the literature.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Bulge test; Finite element analysis; Fracture toughness; Gold film; Thin films

Fracture toughness evaluation of NiAl single crystals by microcantilevers-a new continuous J-integral method - Ast, Johannes; Merle, Benoit; Durst, Karsten; Göken, Mathias (Journal of Materials Research, 2016)
The fracture toughness of NiAl single crystals is evaluated with a new method based on the J-integral concept. The new technique allows the measurement of continuous crack resistance curves at the microscale by continuously recording the stiffness of the microcantilevers with a nanoindenter. The experimental procedure allows the determination of the fracture toughness directly at the onset of stable crack growth. Experiments were performed on notched microcantilevers which were prepared by focused ion beam milling from NiAl single crystals. Stoichiometric NiAl crystals and NiAl crystals containing 0.14 wt% Fe were investigated in the so-called "hard" orientation. The fracture toughness was evaluated to be 6.4 +/- 0.5 MPa m(1/2) for the stoichiometric sample and 7.1 +/- 0.5 MPa m(1/2) for the iron containing sample, indicating that the addition of iron enhances the ductility. This effect is intensified with ongoing crack propagation where the Fe-containing sample exhibits a stronger crack resistance behavior than the stoichiometric NiAl single crystal. These findings are in good agreement with macroscopic fracture toughness measurements, and validate the new micromechanical testing approach.

Fracture toughness of GIC—A mechanistic approach on the nanoscale - Brandt, B; Durst, Karsten; Belli, Renan; Göken, Mathias; Lohbauer, Ulrich (Dental Materials, 2010)
Objectives: To investigate the fracture toughness KIc of a dental glassionomer (GI) cement in terms of terms of different storage intervals and to correlate the development of macroscopic data with findings on the nanoscale. Materials and methods: Bars with dimensions of 25 mm × 2 mm × 2 mm were produced out of a model GI cement (Schott/Evonik, Germany) and stored for 24 h, 7 d, and 21 d in water of 37 °C. Sharp notches were cut into the bars using a diamond wheel saw blade and a razor blade. Fracture toughness (n = 15) was measured using the SENB (single-edge-notched-bending) method. The actual notch depth for each specimen was measured after fracture under a light microscope. A Nano Indenter (G200, Agilent Tech., USA) was used to observe the elastic modulus and local hardness on the nanoscale. Therefore, flat specimens were produced, surface polished using the lapping technique, and stored as described above. Local mechanical properties were measured on glass particles and matrix of the set cement. Load-control (LCM) and Continuous Stiffness (CSM) measurements were performed. Results: An increasing fracture toughness was measured with extended storage times. The KIc increased from 0.22 MPa m0.5 after 24 h up to 0.24 MPa m0.5 (7 d) and finally to 0.27 MPa m0.5 after 21 d. The elastic modulus of the GI composite increased from 12.2 GPa (7 d) up to 16.1 GPa after 21 d. Hardness increased from 0.27 GPa (7 d) up to 0.43 GPa after 21 d. The glass particles showed an elastic modulus of 65.5 GPa and a hardness of 0.69 GPa. Conclusions: Mechanical properties on the nanoscale reflect the macroscopic data without any disturbing influence from material inhomogeneities, porosity, etc. Over time, the elastic modulus showed a higher increase compared to the macroscopic fracture toughness measurements. The material performance was found to be determined by the matrix behaviour. On the nanoscale, a viscoplastic response of the matrix component could be proved. Nanoindentation is a very useful technique for improving the macroscopic behaviour of a GI cement and suitable for localizing the weakest link in the composite structur

Fracture toughness of silicon nitride thin films of different thicknesses as measured by bulge tests - Merle, Benoit; Göken, Mathias (Acta Materialia, 2011)
A bulge test setup was used to determine the fracture toughness of amorphous low-pressure chemical vapor deposited (LPCVD) silicon nitride films with various thicknesses in the range 40–108 nm. A crack-like slit was milled in the center of each free-standing film with a focused ion beam, and the membrane was deformed in the bulge test until failure occurred. The fracture toughness KIC was calculated from the pre-crack length and the stress at failure. It is shown that the membrane is in a transition state between pure plane-stress and plane-strain which, however, had a negligible influence on the measurement of the fracture toughness, because of the high brittleness of silicon nitride and its low Young's modulus over yield strength ratio. The fracture toughness KIC was found to be constant at 6.3 ± 0.4 MPa m1/2 over the whole thickness range studied, which compares well with bulk values. This means that the fracture toughness, like the Young's modulus, is a size-independent quantity for LPCVD silicon nitride. This presumably holds true for all amorphous brittle ceramic materials.
WW1::875

Fretting fatigue of carbon steels in the high cycle fatigue regime - Neuner, Frank; Nützel, Ralf; Höppel, Heinz Werner (Materials Testing, 2004)
Fretting fatigue can be a serious problem for many engineering applications. Relative motions between components in contact can generate surface and subsurface damage, which leads to failure of the component. Hence, it is very reason that the microstructural condition strongly influences the so-called fretting fatigue behaviour. Nevertheless, the microstructural influence on the fretting fatigue behaviour has not been very well investigated up to now. To investigate systematically the influence of specific microstructural parameters on the fretting fatigue behaviour, a broad variety of different iron-base materials were selected for this study. Based on a variation of the grain size and of the ferrite /pearlite morphologies, a detailed understanding of microstructural, effects on the fretting fatigue behaviour can be derived. In general, a reduction of the fatigue life compared to uniaxial fatigue tests by up to 50 %, depending on the respective microstructure, normal load and strain amplitude, was observed.
Created from Fastlane, Scopus look-up

Fretting fatigue of low carbon steels in the high cycle fatigue regime - Höppel, Heinz Werner; et al. (MP Materials Testing, 2004)
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.fretti

Fretting fatigue of low carbon steels in the high cycle fatigue regime - Höppel, Heinz Werner; Neuner, Frank; Nützel, Ralf (5th Int. Conf on Low Cycle Fatigue, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IW.LWAW.fretti_6

Friction stir welding of accumulative roll-bonded commercial-purity aluminium AA1050 and aluminium alloy AA6016 - Topic, Irena; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::807

Fundamental Investigations of Aluminium Matrix Composite Brake Rotors for the Use in Passenger Cars - Gulden, Florian; Höppel, Heinz Werner; Göken, Mathias; Stich, Anton; Gramstat, Sebastian (EuroBreak 2017 (EB2017-MDS-026), 2017)

Funktionelle Beschichtungen in der Nanotechnologie - Ein Kooperationsprojekt Schule-Hochschule. - Heinzerling, Peter; Dräger, Gerald; Kometz, Andreas; Preiß, Eva (Praxis der Naturwissenschaften - Chemie in der Schule, 2015)
Es werden Experimente zur Funktionalisierung von Oberflächen vorgestellt. Neben der Beschichtung kommt es auch zu chemischen Reaktionen an der Oberfläche, was zu veränderten Eigenschaften führ
Keywords: Schule; Experiment; Beschichtung; Chemieunterricht; Kunststoff; Nanochemie; Partikel; Projekt; Nanotechnologie; Hochschule; Kooperation; Deutschland

Fused Filament Fabrication-Based Additive Manufacturing of Commercially Pure Titanium - Thompson, Yvonne; Polzer, Markus; Gonzalez-Gutierrez, Joamin; Kasian, Olga; Heckl, Johannes Philipp; Dalbauer, Valentin; Kukla, Christian; Felfer, Peter (Advanced Engineering Materials, 2021)
Fabrication of titanium components is very cost intensive, partly due to the complex machining and limited recyclability of waste material. For electrochemical applications, the excellent corrosion resistance of pure titanium is of high importance, whereas medium mechanical strength of fabricated parts is sufficient for such a use case. For smaller parts, metal fused filament fabrication (MF3) enables the fabrication of complex metallic structures densified during a final sintering step. Pure titanium can be processed to near-net-shape geometries for electrochemical applications if the parameters and the atmosphere during sintering are carefully monitored. Herein, the influence of thermal debinding and sintering parameters on the fabrication of high-density pure titanium using MF3 is investigated. Particular focus is placed on enhancing sintered density while limiting impurity uptake to conserve the high chemical purity of the initial powder material. Relative densities of 95% are repeatedly reached inside the bulk of the samples. An oxygen content of 0.56 wt% as a result of vacuum processing induces the formation of the retained α-Ti phase (925 HV0.2) inside the α matrix (295 HV0.2). Fabricated parts exhibit high mechanical strength, albeit reduced elongation due to remaining pores, and, in terms of electrochemistry, enhanced stability toward anodic dissolution.
CRIS-Team Scopus Importer:2021-10-01
Keywords: additive manufacturing; highly filled filaments; material extrusion; powder metals; sintering

Fused filament fabrication, debinding and sintering as a low cost additive manufacturing method of 316L stainless steel - Thompson, Yvonne; Gonzalez-Gutierrez, Joamin; Kukla, Christian; Felfer, Peter (Additive Manufacturing, 2019)
By using filaments comprising metal or ceramic powders and polymer binders, solid metal and ceramic parts can be created by combining low-cost fused filament fabrication (FFF) with debinding and sintering. In this work, we explored a fabrication route using a FFF filament filled with 316 L steel powder at 55 vol.-%. We investigated the printing, debinding and sintering parameters and optimized them with respect to the mechanical properties of the final part. Special focus was placed on debinding and sintering in order to obtain components of low residual porosity. Solvent debinding of the printed green bodies created an internal network of interconnected pores and was followed by thermal debinding. Thermal debinding allowed for complete removal of the remaining binder and produced mechanically stable brown parts. Sintering at 1360 °C provided densification of the parts and generated nearly isotropic linear shrinkage of about 20%. Using optimized parameters, it was possible to fabricate 316 L steel components with a density greater than 95% via the material extrusion additive manufacturing, debinding and sintering route, with achievable deflections in a 3-point bending test similar to rolled sheet material, albeit at lower strength.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Additive manufacturing; Highly filled filaments; Material extrusion; Powder metals; Sintering

GaPt Supported Catalytically Active Liquid Metal Solution Catalysis for Propane Dehydrogenation-Support Influence and Coking Studies - Raman, Narayanan; Wolf, Moritz; Heller, Martina; Heene-Würl, Nina; Taccardi, Nicola; Haumann, Marco; Felfer, Peter; Wasserscheid, Peter (ACS Catalysis, 2021)
Supported catalytically active liquid metal solutions (SCALMS) of Pt in Ga (2 at.-% Pt) were studied in the temperature range of 500 to 600 °C for propane dehydrogenation. A facile synthesis procedure using ultrasonication was implemented and compared to a previously reported organo-chemical route for gallium deposition. The procedure was applied to synthesize GaPt-SCALMS catalyst on silica (SiO2), alumina (Al2O3), and silicon carbide (SiC) to investigate the effect of the support material on the catalytic performance. The SiC-based SCALMS catalyst showed the highest activity, while SiO2-based SCALMS showed the highest stability and lowest cracking tendency at higher temperatures. The selectivity toward propene for the SiO2-based catalyst remained above 93% at 600 °C. The catalysts were analyzed for coke content after use by temperature-programmed oxidation (TPO) and Raman spectroscopy. While the SiC- and SiO2-supported SCALMS systems showed hardly any coke formation, the Al2O3-supported systems suffered from pronounced coking. SEM-EDX analyses of the catalysts before and after reaction indicated that no perceivable morphological changes occur during reaction. The SCALMS catalysts under investigation are compared with supported Pt and supported GaPt solid-phase catalyst, and possible deactivation pathways are discussed.
CRIS-Team Scopus Importer:2021-11-19
Keywords: coking; dehydrogenation; gallium; platinum; SCALMS; supported liquid catalysis

Gaseous nitriding of Co-10 at% and -15 at% Cr alloys at 400 °C and 450 °C - Akhlaghi, Maryam; Hock, Rainer; Dallmann, Johannes; Krapf, Anna; Merle, Benoit; Hofsäss, Hans; Körner, Carolin; Leineweber, Andreas (Journal of Alloys and Compounds, 2022)
Co-10 at% and -15 at% Cr with the stable hexagonal close packed (hcp) crystal structure at room temperature have been subjected to gaseous nitriding treatment using nitriding temperatures of 400 °C and 450 °C far below the austenite start temperature. Using X-ray and electron backscatter diffraction (EBSD), structural changes as a result of nitrogen incorporation into the initial hcp lattice can be divided into the following steps: (i) expansion of the lattice due to N uptake yielding hcp (hcpexp) at nitriding temperature of 400 °C, (ii) gradual transformation of hcpexp into an expanded face-centered cubic phase (fccexp) by increasing time at 400 °C/ or temperature to 450 °C (mixture of two phases), (iii) development of stable nitrided layer containing fccexp using moderate nitriding times up to 3 h at 450 °C and (iv) decomposition of fccexp layer into CrN nitrides and less expanded austenite and the reverse transformation from fcc to hcp at near-surface regions at 450 °C after prolonged nitriding time of 24 h. Due to occurrence of step (iv), the square-root treatment-time dependence of the nitrided layer thickness breaks down. Nitrogen-depth profiles obtained for Co-15 at% Cr by glow-discharge optical emission spectroscopy (GDOES) along with the Non-Rutherford MeV proton backscattering spectrometry reveal a nitrogen supersaturation of around 20 at% at surface-adjacent areas in hcpexp. A relatively large unit volume expansion has been recognized for hcpexp with a change of c/a ratio of around 0.6%. Hardness-depth profiles obtained for nitrided Co-10 at% and -15 at% Cr alloys using nanoindentation evidence an increase in hardness inside the nitrided layer, compared to the untreated core.
Keywords: Nitride materials; Precipitation; Phase transitions; Rutherford backscattering; scanning electron microscopy; SEM; X-ray diffraction

Global and local strain rate sensitivity of bimodal Al-laminates produced by accumulative roll bonding - Ruppert, Mathis; Schunk, Christopher; Hausmann, Daniel; Höppel, Heinz Werner; Göken, Mathias (Acta Materialia, 2016)
Laminated metallic composites of 5 mm thickness, with a bimodal grain size distribution and alternating layers of commercial purity aluminum (Al99.5) and high purity aluminum (Al99.999) were successfully processed by accumulative roll bonding at room temperature up to 8 cycles. With increasing number of ARB cycles the layers of commercial purity aluminum become ultrafine-grained, whereas the grain size in the high purity aluminum remains clearly above 1 extgreekmm. The mechanical properties of the laminates were investigated by compression testing with strain rate jumps and by nanoindentation using continuous stiffness method and nanoindentation strain rate jump tests. Thereby the strain rate sensitivity was determined both globally, proving the bulk laminate material, and locally, proving the single layers of the laminate. It was found that the local strain rate sensitivity of the ultrafine-grained Al99.5-layers is increasing up to 4 ARB cycles, while the local strain rate sensitivity of the coarse grained Al99.999-layers remains rather constant independently of the number of cycles. In contrast to that, the global strain rate sensitivity of the bulk laminate increases up to 8 cycles without saturation. Thermally activated annihilation of dislocations at the grain boundaries and interfaces between the coarse grained and ultrafine-grained layers is proposed in order to interpret the findings.
WW1::1056
Keywords: Nanomaterials

Grain boundary engineering in roll-bonded copper to overcome the strength-ductility dilemma - Taali, Saeed; Toroghinejad, Mohammad Reza; Kuglstatter, Moritz; Höppel, Heinz Werner (Journal of Materials Research and Technology, 2022)
Copper sheets with graded and fine-grained (FG) microstructures were processed by accumulative roll bonding (ARB) and subsequent annealing to evaluate the effect of structural heterogeneities on the strength-ductility relationship. By an appropriate design of the individual ARB-process-steps, two types of graded structures (GSs) have been achieved where the grain size gradually changes from a more refined grain structure at the surface to a coarser one in the interior (CGC) or a coarser one at the surface to a finer one in the interior (FGC). For both types, the grains size gradually changes between 4 and 19 microns across the thickness of samples. In terms of the uniform tensile work, GSs exhibited a superior combination of strength and elongation owing to the heterodeformation induced strengthening. In addition to a good strain delocalization capability compared to their coarse-grained (CG) counterpart, the graded microstructures affect the crack paths in the non-uniform deformation regime.(c) 2022 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
CRIS-Team WoS Importer:2022-05-13

Grain boundary mediated plasticity: A blessing for the ductility of metallic thin films? - Liebig, Jan Philipp; Mackovic, Mirza; Spiecker, Erdmann; Göken, Mathias; Merle, Benoit (Acta Materialia, 2021)
The limited ductility of metallic thin films (< 1%) poses a challenge to MEMS and flexible electronics applications. Here, we report on freestanding gold specimens with the remarkable ability to accommodate ≥10% plastic deformation while retaining a high strength. Using in situ nanomechanical testing in a transmission electron microscope, this exceptionally high ductility is traced back to the combination of an ultrathin thickness, a columnar microstructure and a (111) fiber texture. Under such conditions, the deformation is largely mediated by grain boundaries through grain boundary sliding and shear coupled grain boundary migration. Because these non-conventional mechanisms preserve the cross-sectional thickness of the specimens, necking is postponed and the samples can reach a high ductility. Since the mechanisms were evidenced at room temperature and under strain-rate conditions typical of most applications, the findings open up promising outlooks for developing ductile metallic films by microstructural engineering.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Deformation mechanisms; Ductility; Nanomechanical testing; Thin films; Transmission electron microscopy

Grain refinement and deformation mechanisms in heterogeneous ultrafine-grained materials processed by accumulative roll bonding - Göken, Mathias; Höppel, Heinz Werner; Hausöl, Tina; Bach, Jochen; Maier, Verena; Schmidt, Christian; et al. (Nanometals - status and perspective, 2012)
Grain refinement by severe plastic deformation is nowadays intensively used to process pure metals and alloys. These ultrafine-grained and homogeneous materials show already a great potential concerning their mechanical properties. Recently, heterogeneous ultrafine-grained materials consisting of different metals or different alloys became also very attractive. A very promising production process for such multicomponent materials is accumulative roll bonding (ARB) which allows producing laminates with finely distributed micrometer-sized layers. Interesting heterogeneous materials can also be produced by particle incorporation in the ARB process. Hard ceramic particles lead to additional grain refinement of the surrounding metal matrix by flow around the spherical particles. Similar extra grain refinement processes occur also at the interfaces in heterogeneous laminates. Although the deformation mechanisms in such UFG materials have been investigated quite intensively, a generally accepted view is still missing. Especially the question if grain boundary sliding or thermally activated dislocation processes are the dominant deformation mechanism has to be clearly answered. It is generally accepted that the strain rate sensitivity of nanomaterials is significantly enhanced compared to coarse grained materials, which probably is the dominant contribution to the often reported enhanced ductility. In the literature some indications can be found that also grain boundary sliding occurs under specific conditions and is sometimes considered as the dominant deformation mechanism in nanomaterials. Here, different arguments based on macroscopic deformation experiments such as strain rate jump tests and fatigue tests are discussed. The results show that thermally activated dislocation processes at the grain boundaries are the dominant deformation mechanisms in UFG materials. In addition nanoindentation experiments and focused ion beam investigations indicate that grain boundary sliding occurs only at free surfaces but not in the bulk volume of ultrafine-grained materials. This leads to the suggestion that thermally activated deformation processes at grain boundaries are dominant in ultrafinegrained materials with grain size of some hundred nanometers.
EAM Import::2019-03-13

GRAIN REFINEMENT AND DEFORMATION MECHANISMS IN HETEROGENEOUS ULTRAFINE-GRAINED MATERIALS PROCESSED BY ACCUMULATIVE ROLL BONDING - Göken, Mathias; Höppel, Heinz Werner; Hausöl, Tina; Bach, Jochen; Maier, Verena; Schmidt, Christian; Amberger, D. (2012)
Grain refinement by severe plastic deformation is nowadays intensively used to process pure metals and alloys. These ultrafine-grained and homogeneous materials show already a great potential concerning their mechanical properties. Recently, heterogeneous ultrafine-grained materials consisting of different metals or different alloys became also very attractive. A very promising production process for such multicomponent materials is accumulative roll bonding (ARB) which allows producing laminates with finely distributed micrometer-sized layers. Interesting heterogeneous materials can also be produced by particle incorporation in the ARB process. Hard ceramic particles lead to additional grain refinement of the surrounding metal matrix by flow around the spherical particles. Similar extra grain refinement processes occur also at the interfaces in heterogeneous laminates. Although the deformation mechanisms in such UFG materials have been investigated quite intensively, a generally accepted view is still missing. Especially the question if grain boundary sliding or thermally activated dislocation processes are the dominant deformation mechanism has to be clearly answered. It is generally accepted that the strain rate sensitivity of nanomaterials is significantly enhanced compared to coarse grained materials, which probably is the dominant contribution to the often reported enhanced ductility. In the literature some indications can be found that also grain boundary sliding occurs under specific conditions and is sometimes considered as the dominant deformation mechanism in nanomaterials. Here, different arguments based on macroscopic deformation experiments such as strain rate jump tests and fatigue tests are discussed. The results show that thermally activated dislocation processes at the grain boundaries are the dominant deformation mechanisms in UFG materials. In addition nanoindentation experiments and focused ion beam investigations indicate that grain boundary sliding occurs only at free surfaces but not in the bulk volume of ultrafine-grained materials. This leads to the suggestion that thermally activated deformation processes at grain boundaries are dominant in ultrafine-grained materials with grain size of some hundred nanometers.

Grain size stability in Al-Sc alloys processed by severe plastic deformation - Eder, K.; Felfer, Peter; Ferry, M.; Xia, K.; Cairney, J. M. (Scripta Materialia, 2016)

Graphene quantum dots: wave function mapping by scanning tunneling spectroscopy and transport spectroscopy of quantum dots prepared by local anodic oxidation - Morgenstern, Markus; Freitag, Nils; Vaid, Aviral; Pratzer, Marco; Liebmann, Marcus (Physica Status Solidi-Rapid Research Letters, 2016)
3D view of STM image of graphene supported by SiO2 [1, 2]; Insets (from left to right): STM image of graphene nanoislands on Ir(111) and scanning tunneling spectroscopy images of the three low energy wave functions of a particular nano-island [3]. (C) 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhe
Keywords: graphene; quantum dots; edge states; scanning tunneling microscopy; local anodic oxidation; metallic substrates

Growth and mechanical properties of a MoC precipitate at a Mo grain boundary: An ab initio density functional theory study - Janisch, Rebecca; Elsässer, Christian (Physical Review B - Condensed Matter and Materials Physics, 2008)
Atomic-scale stages of the growth of an interfacial precipitate film of tetragonal molybdenum carbide at a Σ5 (310) [001] symmetrical tilt grain boundary in body-centered cubic molybdenum were investigated by means of atomistic supercell calculations on the basis of ab initio density functional theory. The structural development of the precipitate with increasing carbon concentration is analyzed qualitatively and quantitatively. The structurally optimized atomistic model for the fully developed precipitate is compared to experimental high-resolution images from transmission electron microscopy. Characteristic interface energies are calculated to evaluate the influence of the precipitate on the mechanical stability of the material. Finally, an atomic-scale twinning mechanism in the MoC precipitate is proposed. © 2008 The American Physical Society.
Created from Fastlane, Scopus look-up

Hardening and thermal stability of nanocrystalline AlMg4.8 powder - Hueller, M.; Vlcek, J.; Dinkel, Markus; Höppel, Heinz Werner; Göken, Mathias (Philosophical Magazine, 2008)
WW1::768

Helium-induced swelling and mechanical property degradation in ultrafine-grained W and W-Cu nanocomposites for fusion applications - Wurmshuber, Michael; Balooch, Mehdi; Huang, Xi; Hosemann, Peter; Kiener, Daniel (Scripta Materialia, 2022)

Hetero-deformation induced (HDI) hardening does not increase linearly with strain gradient - Wang, Y. F.; Huang, C. X.; Fang, X. T.; Höppel, Heinz Werner; Göken, Mathias; Zhu, Y. T. (Scripta Materialia, 2020)
Hetero-deformation induced (HDI) hardening has been attributed to geometrically necessary dislocations (GNDs) that are needed to accommodate strain gradient near the interfaces of heterostructured domains. Here we report that HDI hardening does not increase linearly with increasing strain gradient in the interface-affected zone. This is because some GND pileups may be absorbed by the interface and consequently does not contribute to HDI hardening with increasing strain gradient. Higher mechanical incompatibility across interface produces higher strain gradient. The strain gradient-dependent strengthening effect of heterostructured interface mainly originates from the development of HDI stress.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Geometrically necessary dislocations; Hetero-deformation induced stress; Heterostructures; Interface; Strain gradient

Hierarchical and heterogeneous multiphase metallic nanomaterials and laminates - Misra, Amit; Göken, Mathias; Mara, Nathan A.; Beyerlein, Irene J. (Mrs Bulletin, 2021)
The strength and plasticity of metallic composites is reviewed in terms of (1) hierarchical morphologies in metallic nanocomposites, such as Cu–Mo, Zr–Nb, Al–Si, and (2) heterogeneous interface behavior and compositionally graded interfaces in metallic laminates, such as Cu/bronze, Ti/Al, Fe/Cu, Cu/Nb. Hierarchical architectures of multiple phases with varying sizes and morphologies are particularly effective in enhancing yield strength, due to the strong glide dislocation interactions with their nanoscale features; plastic deformability, due to increased strain hardening from microstructure hierarchy. Enhanced toughening is attributed to impedance of crack growth via deflection along interfaces that have relatively low shear strength and bridging via relatively softer microscale composite domains. In laminates, the constraint from an interface affected zone arising from geometrically necessary dislocations can lead to enhanced strain hardening and plasticity.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Dislocations; Microstructure; Multiscale; Strength

High-Energy Computed Tomography as a Prospective Tool for In Situ Monitoring of Mass Transfer Processes inside High-Pressure Reactors-A Case Study on Ammonothermal Bulk Crystal Growth of Nitrides including GaN - Schimmel, Saskia; Salamon, Michael; Tomida, Daisuke; Neumeier, Steffen; Ishiguro, Tohru; Honda, Yoshio; Chichibu, Shigefusa F.; Amano, Hiroshi (Materials, 2022)
For the fundamental understanding and the technological development of the ammonothermal method for the synthesis and crystal growth of nitrides, an in situ monitoring technique for tracking mass transport of the nitride throughout the entire autoclave volume is desirable. The feasibility of using high-energy computed tomography for this purpose was therefore evaluated using ex situ measurements. Acceleration voltages of 600 kV were estimated to yield suitable transparency in a lab-scale ammonothermal setup for GaN crystal growth designed for up to 300 MPa operating pressure. The total scan duration was estimated to be in the order of 20 to 40 min, which was sufficient given the comparatively slow crystal growth speed in ammonothermal growth. Even shorter scan durations or, alternatively, lower acceleration voltages for improved contrast or reduced X-ray shielding requirements, were estimated to be feasible in the case of ammonoacidic growth, as the lower pressure requirements for this process variant allow for thinned autoclave walls in an adapted setup designed for improved X-ray transparency. Promising nickel-base and cobalt-base alloys for applications in ammonothermal reactors with reduced X-ray absorption in relation to the maximum operating pressure were identified. The applicability for the validation of numerical simulations of the growth process of GaN, in addition to the applicability of the technique to further nitride materials, as well as larger reactors and bulk crystals, were evaluated.
CRIS-Team WoS Importer:2022-09-16
Keywords: X-ray computed tomography; gallium nitride; high-pressure reactor; in situ monitoring of crystal growth; ammonothermal growth of nitrides

High Lightweight Potential of Ultrafine-Grained Aluminum/Steel Laminated Metal Composites Produced by Accumulative Roll Bonding - Kümmel, Frank; Diepold, Benedikt; Sauer, Kim Florian; Schunk, Christopher; Prakash, Aruna; Höppel, Heinz Werner; Göken, Mathias (Advanced Engineering Materials, 2018)
Keywords: Laminated metal composites (LMCs); Monotonic mechanical properties; Accumulative roll bonding (ARB); Fatigue life; Fatigue crack path

Highly resolved analysis of the chemistry and mechanical properties of an a-C:H coating system by nanoindentation and auger electron spectroscopy - Schmid, Christoph; Maier, Verena; Schaufler, Jens; Butz, Benjamin; Spiecker, Erdmann; Meier, S.; Göken, Mathias; Durst, Karsten (Thin Solid Films, 2013)
The small-angle cross-section method was applied to a multi-layered hydrogenated amorphous carbon coating (a-C:H) system deposited by plasma enhanced chemical vapour deposition. The investigated system consists of a silicon rich adhesion layer and an adjacent ramp layer with a graded chemical composition to the a-C:H coating. The mechanical properties and the corresponding chemical gradients of the coating system were analysed by a combination of the small-angle cross-section method together with auger electron spectroscopy and nanoindentation. Furthermore, energy filtered transmission electron microscopy on a thin lamella was used to check the reliability of the auger electron spectroscopy results. It was found that local gradients in the chemical composition within the coating relate well to gradients observed in the local mechanical properties. The used combination of the different methods enables to resolve the correlation between the microstructure, chemical composition and mechanical properties of thin film systems with high spatial resolution. (c) 2012 Elsevier B.V. All rights reserve
Keywords: a-C:H; Nanoindentation; Small-angle cross-section; Focused ion beam; Adhesion layer; Chemical composition; DLC

High-performance direct conversion X-ray detectors based on sintered hybrid lead triiodide perovskite wafers - Shrestha, Shreetu; Fischer, Rene; Matt, Gebhard; Feldner, Patrick; Michel, Thilo; Osvet, Andres; Levchuk, Ievgen; Merle, Benoit; Golkar, Saeedeh; Chen, Haiwei; Tedde, Sandro F.; Schmidt, Oliver; et al. (Nature Photonics, 2017)
Lead halide perovskite semiconductors are in general known to have an inherently high X-ray absorption cross-section and a significantly higher carrier mobility than any other low-temperature solution-processed semiconductor. So far, the processing of several-hundred-micrometres-thick high-quality crystalline perovskite films over a large area has been unresolved for efficient X-ray detection. In this Article, we present a mechanical sintering process to fabricate polycrystalline methyl ammonium lead triiodide perovskite (MAPbI(3)) wafers with millimetre thickness and well-defined crystallinity. Benchmarking of the MAPbI(3) wafers against state-of-the-art CdTe detectors reveals competitive conversion efficiencies of 2,527 mu C Gy(air)(-1) cm(-2) under 70 kV(p) X-ray exposure. The high ambipolar mobility-lifetime product of 2 x 10(-4) cm(2) V-1 is suggested to be responsible for this exceptionally high sensitivity. Our findings inform a new generation of highly efficient and low-cost X-ray detectors based on perovskite wafer

High-pressure synthesis of ultraincompressible hard rhenium nitride pernitride Re2(N2)(N)2 stable at ambient conditions - Bykov, Maxim; Chariton, Stella; Fei, Hongzhan; Fedotenko, Timofey; Aprilis, Georgios; Ponomareva, Alena V.; Tasnádi, Ferenc; Abrikosov, Igor A.; Merle, Benoit; Feldner, Patrick; Vogel, Sebastian; Schnick, Wolfgang; et al. (Nature Communications, 2019)
High-pressure synthesis in diamond anvil cells can yield unique compounds with advanced properties, but often they are either unrecoverable at ambient conditions or produced in quantity insufficient for properties characterization. Here we report the synthesis of metallic, ultraincompressible (K0 = 428(10) GPa), and very hard (nanoindentation hardness 36.7(8) GPa) rhenium nitride pernitride Re2(N2)(N)2. Unlike known transition metals pernitrides Re2(N2)(N)2 contains both pernitride N24− and discrete N3− anions, which explains its exceptional properties. Re2(N2)(N)2 can be obtained via a reaction between rhenium and nitrogen in a diamond anvil cell at pressures from 40 to 90 GPa and is recoverable at ambient conditions. We develop a route to scale up its synthesis through a reaction between rhenium and ammonium azide, NH4N3, in a large-volume press at 33 GPa. Although metallic bonding is typically seen incompatible with intrinsic hardness, Re2(N2)(N)2 turned to be at a threshold for superhard materials.
CRIS-Team Scopus Importer:2019-07-16

High strength and retained ductility achieved in a nitrided strip cast Nb-microalloyed steel - Xie, Kelvin Y.; Shrestha, Sachin L.; Felfer, Peter; Cairney, Julie M.; Killmore, Chris R.; Carpenter, Kristin R.; Kaul, Harold R.; Ringer, Simon P. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2013)
The current study investigates the strengthening of an Nb-microallyed CASTRIP steel at 798 K (525 C) by nitriding in a KNO salt bath. Nitriding up to 1 hour dramatically increased the yield strength of the steel by ∼35 pct (from 475 to 645 MPa) with no sacrifice of ductility (∼16 pct). Further nitriding led to brittle fracture. Hardness profiles of the nitrided steels through the thickness reveal hard surfaces and a relatively softer core. The hardening of the shell in the nitrided steels is thought to be the combined effect of solid solution strengthening from nitrogen and dispersion strengthening from clusters and precipitates. The retained ductility is attributed to the hard-shell-soft-core structure through nitriding. © 2012 The Minerals, Metals & Materials Society and ASM Internationa

High-Temperature CoNi-Based Superalloys Strengthened by γ′-(Ni,Co)3(Cr,Al,Ti,X): The Effect of Refractory Elements - Liang, Zhida; Paul, Jonathan D. H.; Stark, Andreas; Bezold, Andreas; Neumeier, Steffen; Göken, Mathias; Pyczak, Florian (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
Recent research on Co-based and CoNi-based alloys revealed that the Co–Al–W-system provides interesting properties, however, the high content of W addition triggers high mass density of alloys which limits its industrial application. Therefore, new high temperature superalloys based on the Co–Ni–Al–Ti-system with high content Cr and strengthened by γ′-(Ni,Co)3(Cr,Al,Ti) precipitates, have been developed, and the effect of different refractory element additions was investigated. STEM-EDS and HEXRD were employed to determine the elemental partitioning behavior and the lattice misfit between the γ and γ′ phases. Ta and Nb strongly concentrate within the γ′ phase, whereas Mo weakly partitions to the γ phase. W distributes equally between the γ and γ′ phases. These new superalloys have an unexpectedly high positive misfit compared with some conventional Ni-based superalloys and Co-based superalloys. Nb and Ta additions increase the lattice misfit further, while Mo and W decrease the lattice misfit. The effect of refractory elements alloying on the yield stress at room temperature was evaluated by analyzing the contributions of different strengthening mechanisms. Alloying with Nb or Ta significantly improves precipitation strengthening by increasing the antiphase boundary energy. Mo has the highest solid solution strengthening effect in the γ phase, followed by W. Compared with some conventional Ni-based superalloys, the investigated new CoNi-based superalloys exhibited better mechanical properties at high temperature, which indicates that these compositionally complex alloys are possible candidates for high temperature applications. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-09-30

High-temperature corrosion of Inconel (R) Alloy 718, Haynes (R) 282 (R) Alloy and CoWAlloy1&2 in supercritical ammonia/ammonium chloride solutio - Kimmel, Anna-Carina; Malkowski, Thomas F.; Griffiths, Steven; Hertweck, Benjamin; Steigerwald, Thomas; Freund, Lisa; Neumeier, Steffen; Göken, Mathias; Speck, James S.; Schlücker, Eberhard (Journal of Crystal Growth, 2018)
Corrosion of process equipment during ammonothermal synthesis at high temperature and pressure is still one of the big limitations of this process because of reduced crystal quality and safety issues. In this paper we present preliminary ammonothermal corrosion experiments with two Ni-base superalloys (Inconel (R) Alloy 718 and Haynes (R) 282 (R) Alloy) and two newly developed Co-base superalloys (CoWAlloy1&2) in a supercritical NH3/NH4Cl-solution (24 h/550 degrees C/105 MPa). After the experiment, the samples were analyzed by their mass change per initial surface area (specific weight change). Additionally, the morphological and elemental changes of the corrosion layers were evaluated. None of the investigated alloys developed a passivation layer and the corrosion layers were very fragile. In agreement with previous studies, the Ni-base alloys showed intergranular attack with severe general corrosive degeneration. Despite their high potential for high-pressure at high-temperature applications and in contrast to a ternary Co-Al-W-alloy, the investigated multinary Co-base alloys were strongly attacked, too. However, CoWAlloy2 presented the lowest specific weight change of the investigated alloys. Thus, it shows the best potential for application in acidic environment of the investigated alloys. Additionally, CoWAlloy2 proved good stability in a supercritical NH3/Na-solution (24 h/550 degrees C/93 MPa).
Keywords: Ammonothermal crystal growth (A2.); Supercritical corrosion (B1.); Nickel-base superalloys (B1.); Cobalt-base superalloys (B1.); Acidic mineralizer NH4Cl (A2.)

High temperature corrosion of the nickel-based alloy Inconel 617 in helium containing small amounts of impurities - Christ, Hans-Jürgen; Künecke, Ulrike; Meyer, K; Sockel, Hans-Georg (Materials Science and Engineering, 1987)
Application of the technical nickel-based alloy Inconel 617 as a material for gas tubes in the primary circuit of the high temperature gas-cooled reactor is limited essentially by the chemical reactions of the alloying elements with the impurities (CO, CO2, H2, CH4 and H2O) in the helium coolant. Depending on the temperature and gas composition, carburization or decarburization as well as oxidation occur. In this work the interaction of the alloy with the reactive impurities in different simulated cooling gases were investigated by thermogravimetry in a gas-tight microbalance and by simultaneous measurements of the changes in the gas composition by a continuous sensitive mass spectrometry analysis of the gas. The results demonstrate that the occurrence of the various reactions is determined essentially by temperature. For a standardized helium gas (HHT-He), three temperature regions can be distinguished between. Below a critical temperature (about 1105 K) the presence of CO can cause simultaneous oxidation and carburization. Above about 1105 K, this reaction does not reverse itself. Rather, oxidation by CO2 and H2O takes place which shows, after a transient state, the same kinetics as those observed in undiluted oxygen-containing gases. At temperatures above about 1205 K, decarburization of the alloy accompanied by the production of CO takes place, leading to severe destruction of the carbide microstructure and therefore limiting the applicability of the materia
Keywords: Inconel 617; high temperature corrosion

High-temperature mechanical behavior of end-of-life cryomilled NiCrAlY bond coat materials - Göken, Mathias; Hemker, K. J.; Eberl, Christoph; Ma, Kaka; Schoenung, J. M.; Funk, M. (2011)
WW1::877

High-temperature nanoindentation of an advanced nano-crystalline W/Cu composite - Burtscher, Michael; Zhao, Mingyue; Kappacher, Johann; Leitner, Alexander; Wurmshuber, Michael; Pfeifenberger, Manuel; Maier-Kiener, Verena; Kiener, Daniel (Nanomaterials, 2021)
Keywords: Nanoindentation; W/Cu composite; Microstructure; Nanocrystalline; High-pressure torsion; kernfusionsrelevant

High temperature oxidation of γ/γ′-strengthened Co-base superalloys - Klein, Leonhard; Bauer, Alexander; Neumeier, Steffen; Göken, Mathias; Virtanen, Sannakaisa (Corrosion Science, 2011)
Keywords: A. Alumina; A. Co-base superalloy; A. Boron; C. Oxide layer; C. High-temperature oxidation

High temperature oxidation of γ/γ′-strengthened Co-base superalloys - Klein, Leonhard; Bauer, Alexander; Neumeier, Steffen; Göken, Mathias; Virtanen, Sannakaisa (Corrosion Science, 2011)
WW1::876

High temperature oxidation resistance of physical vapor deposited Hf-Si-B-2 +/- z thin films - Glechner, T.; Bahr, A.; Hahn, R.; Wojcik, T.; Heller, Martina; Kirnbauer, A.; Ramm, J.; Kolozsvari, S.; Felfer, Peter; Riedl, H. (Corrosion Science, 2022)
Within physical vapor deposited Hf-Si-B-2 +/- z thin films, selective diffusion-driven oxidation of Si is identified to cause outstanding oxidation resistance at temperatures up to 1500 degrees C. After 60 h at 1200 degrees C, the initially 2.47 mu m thin Hf0.20Si0.23B0.57 thin film exhibits a dense oxide scale of only 1.56 mu m. The thermally induced decomposition of metastable Hf-Si-B-2 +/- z leads not only to the formation of Si precipitates within the remaining thin film (related to a non-homogenous Si distribution after the deposition) but also to pure Si layers on top and bottom of the Hf-Si-B-2 +/- z coatings next to the excellent adherend SiO2 based scales.
CRIS-Team WoS Importer:2022-07-15

High-temperature oxidation resistance of ternary and quaternary Cr-(Mo)-Si-B2-z coatings — Influence of Mo addition - Bahr, A.; Glechner, T.; Grimmer, A.; Wojcik, T.; Kutrowatz, P.; Podsednik, M.; Limbeck, A.; Heller, Martina; Ramm, J.; Hunold, O.; Kolozsvári, S.; Polcik, P.; et al. (Surface & Coatings Technology, 2023)
The Si-based alloying of transition metal diborides is a promising strategy to improve their limited oxidation resistance in high-temperature environments. In this study, we investigate the oxidation resistance of ternary and quaternary Cr-(Mo)-Si-B2-z coatings sputter-deposited from alloyed CrB2/TMSi2 targets (TM = Cr, Mo). The as-deposited Cr-(Mo)-Si-B2-z coatings are stabilized in the single-phased hexagonal AlB2-structure, except the high-Si containing Cr0.26Mo0.11Si0.24B0.39 presenting amorphous character. The Mo-containing Cr-Mo-Si-B2-z films exhibit relatively high hardness compared to their ternary Cr-Si-B2-z counterparts, obtaining up to 26 GPa due to the formation of (Cr,Mo)B2 solid solutions. The Si-alloying in ternary and quaternary coatings provides oxidation resistance up to 1200 °C, owing to the formation of highly protective double-layered scales consisting of SiO2 with a Cr2O3 layer on top, inhibiting oxygen inward diffusion. The quaternary Cr0.31Mo0.07Si0.15B0.47 coating is distinguished by superior oxidation resistance with lower porosity and void formation compared to the ternary Cr0.37Si0.16B0.47. Mo proved to be the key element for the higher stability and enhanced oxidation resistance due to the evolution of the MoSi2 phase at 600 °C. This phase formation controls the Si diffusion and mobility within the microstructure, thus reducing the porosity and governing the Si supply to form SiO2 scale. The quaternary Cr0.31Mo0.07Si0.15B0.47 coating maintained an oxidation resistance up to 30 h at 1200 °C by forming a 2.5 μm dense amorphous Si-based oxide scale with a thin Cr2O3 on top.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Chromium diboride; Disilicides; Oxidation resistance; Sputtering; Thin films

High temperature properties and fatigue strength of novel wrought gamma/gamma' Co-base superalloys - Freund, Lisa; Giese, Sven; Schwimmer, Daniel; Höppel, Heinz Werner; Neumeier, Steffen; Göken, Mathias (Journal of Materials Research, 2017)
This paper presents the high temperature yield and fatigue strength as well as thermophysical properties of two polycrystalline wrought gamma/gamma' Co-base superalloys developed for application in a temperature regime above 700 degrees C. The alloys CoW Alloy1 (Co42Ni32Cr12Al6W3Ti2.5Ta1.5 1 Si,C,B,Zr,Hf) and CoW Alloy2 (Co41Ni32Cr12Al9W5 1 Ti,Ta,Si,C,B,Zr,Hf) exhibited solidus temperatures of 1070 degrees C and 1030 degrees C, respectively, and a gamma' fraction of about 50%. CoW Alloy2 displayed a rather high Young's modulus of 250 GPa. The two Co-base superalloys showed a good high temperature strength exceeding Ni-base disc alloys U720Li and Waspaloy at temperatures above 800 degrees C. When comparing the yield strength from tensile and compression tests, no asymmetry could be found. The low-cycle fatigue life of CoW Alloy2 at a total strain amplitude of 0.5% is similar to that of U720Li and Waspaloy (about 370 cycles, R = -1). During long-term aging for 1024 h at 750 degrees C, no additional phases were formed and the room temperature hardness barely changed.
Keywords: Co; fatigue; strength

How Will Your Tweet Be Received? Predicting the Sentiment Polarity of Tweet Replies - Tayebi Arasteh, Soroosh; Monajem, Mehrpad; Christlein, Vincent; Heinrich, Philipp; Nicolao, Anguelos; Boldaji, Hamidreza Naderi; Lotfinia, Mahshad; Evert, Stephanie (2021 IEEE 15th International Conference on Semantic Computing (ICSC), 2021)
Twitter sentiment analysis, which often focuses on predicting the polarity of tweets, has attracted increasing attention over the last years, in particular with the rise of deep learning (DL). In this paper, we propose a new task: predicting the predominant sentiment among (first-order) replies to a given tweet. Therefore, we created RETwEET, a large dataset of tweets and replies manually annotated with sentiment labels. As a strong baseline, we propose a two-stage DL-based method: first, we create automatically labeled training data by applying a standard sentiment classifier to tweet replies and aggregating its predictions for each original tweet; our rationale is that individual errors made by the classifier are likely to cancel out in the aggregation step. Second, we use the automatically labeled data for supervised training of a neural network to predict reply sentiment from the original tweets. The resulting classifier is evaluated on the new ReTweeT dataset, showing promising results, especially considering that it has been trained without any manually labeled data. Both the dataset and the baseline implementation are publicly available.<br
Keywords: Deep Learning; Sentiment Analysis; Tweet Reply Prediction; Natural Language Processing

Hydrogen embrittlement of twinning-induced plasticity steels: Contribution of segregation to twin boundaries - Khanchandani, Heena; Rolli, Rolf; Schneider, Hans-Christian; Kirchlechner, Christoph; Gault, Baptiste (Scripta Materialia, 2023)

Idealized vs. Realistic Microstructures: An Atomistic Simulation Case Study on γ/γ′ Microstructures - Prakash, Aruna; Bitzek, Erik (Materials, 2017)
WW1::1087
Keywords: Simulation and Modeling

Imaging individual solute atoms at crystalline imperfections in metals - Katnagallu, Shyam; Stephenson, Leigh T.; Mouton, Isabelle; Freysoldt, Christoph; Subramanyam, Aparna P. A.; Jenke, Jan; Ladines, Alvin N.; Neumeier, Steffen; Hammerschmidt, Thomas; Drautz, Ralf; Neugebauer, Joerg; Vurpillot, Francois; et al. (New Journal of Physics, 2019)
Directly imaging all atoms constituting a material and, maybe more importantly, crystalline defects that dictate materials' properties, remains a formidable challenge. Here, we propose a new approach to chemistry-sensitive field-ion microscopy (FIM) combining FIM with time-of-flight mass-spectrometry (tof-ms). Elemental identification and correlation to FIM images enabled by data mining of combined tof-ms delivers a truly analytical-FIM (A-FIM). Contrast variations due to different chemistries is also interpreted from density-functional theory (DFT). A-FIM has true atomic resolution and we demonstrate how the technique can reveal the presence of individual solute atoms at specific positions in the microstructure. The performance of this new technique is showcased in revealing individual Re atoms at crystalline defects formed in Ni-Re binary alloy during creep deformation. The atomistic details offered by A-FIM allowed us to directly compare our results with simulations, and to tackle a long-standing question of how Re extends lifetime of Ni-based superalloys in service at high-temperature.
CRIS-Team WoS Importer:2020-03-03

Impact of interfaces on the radiation response and underlying defect recovery mechanisms in nanostructured Cu-Fe-Ag - Wurmshuber, Michael; Frazer, David; Bachmaier, Andrea; Wang, Yongquiang; Hosemann, Peter; Kiener, Daniel (Materials & Design, 2018)
Keywords: Nanostructured materials; Radiation resistant materials; Defect-interface interactions; Nanoindentation; Severe plastic deformation; kernfusionsrelevant

Impact of Mn on the precipitate structure and creep resistance of Ca containing magnesium alloys - Lamm, Steffen; Matschkal, Dorothea; Göken, Mathias; Felfer, Peter (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2019)
The reason for the enhanced creep resistance of Ca-modified magnesium alloys is investigated based on their microstructure and precipitate morphology. It is known from literature that the creep resistance of commercial AZ91 is improved by the addition of Calcium through the formation of a skeleton-like intermetallic phase (IP) at the grain boundaries. Compared to AZ91 + Ca, the alloy MRI230D, which is a Mg–Al–Ca–Sn based alloy with similar Ca content, shows a significantly better creep resistance. This is probably caused by small precipitates in the α-Mg grain interior that were found in earlier TEM investigations of as-cast MRI230D alloy. For this work, we have investigated the evolution of the precipitate structure from as-cast to crept conditions via atom probe tomography (APT). Based on the APT data, an intensive cluster analysis for all deformation states was performed using Voronoi cluster search algorithm. Cluster analysis revealed that Ca atoms show an especially high grade of clustering in as-cast conditions. This changes in the crept states, where co-clustering of Ca and Mn atoms was observed. Further analysis revealed that the number density of clusters is generally higher in MRI230D than in AXZ931 and clusters tend to be smaller and enriched with Mn. All of this led to the conclusion that a minimum amount of Mn is necessary for a stabilization of the clusters in the Mg matrix, leading to an improvement of the creep resistance.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Clusters; Creep; Magnesium alloys; Precipitate structure

Impact of n-type versus p-type doping on mechanical properties and dislocation evolution during SiC crystal growth - Wellmann, Peter; Hens, Philip; Sakwe, Aloysius; Queren, Desiree; Müller, Ralf; Durst, Karsten; Göken, Mathias (Materials Science Forum, 2007)
The origin of dislocation evolution during SiC crystal growth is usually related to lattice relaxation mechanisms caused by thermal stress. In this paper we discuss dislocation generation and dislocation propagation related to doping and suppression of basal plane dislocations, the latter being of particular interest for bipolar electronic devices. We have prepared alternating p-/n-/p-doped SiC crystals using the donor nitrogen and the acceptors aluminum or boron. In addition we determined the mechanical properties of n-type and p-type SiC; in particular we measured the critical shear stress by nano-indentation on c-plane and a-plane 6H-SiC surfaces. A considerably lower basal plane dislocation density is found in aluminum as well as in boron doped p-type SiC compared to nitrogen doped n-type SiC. It is concluded that the explanation of the reduced basal plane dislocation density in p-type SiC needs the consideration of electronic as well as mechanical effect
Keywords: Basal Plane Dislocation (BPD); Doping; PVT Growth; SiC

Impact of the Co/Ni-Ratio on Microstructure, Thermophysical Properties and Creep Performance of Multi-Component γ′-Strengthened Superalloys - Zenk, Christopher; Volz, Nicklas; Zenk, Carolin; Felfer, Peter; Neumeier, Steffen (Crystals, 2020)
The Ni content is a crucial factor for the development of γ′-strengthened Co-based superalloys and some studies have systematically addressed its influence on various properties in model superalloys. In this paper, we report for the first time the influence of the Co/Ni ratio in the more advanced nine-component superalloy ERBOCo-1: exchanging Co and Ni in this Co/Ni-based superalloy while keeping the other alloying elements constants has a big influence on a variety of material properties. The elemental segregation after casting is slightly more pronounced in the alloy with higher Ni-content. Microstructural characterization of this alloy termed ERBOCo-1X after heat-treatment reveals that the precipitates are cuboidal in the Co- and spherical in the Ni-rich alloy, indicating a decrease in the γ/γ′ lattice misfit. Analyzing the elemental partitioning behavior by atom probe tomography suggests that the partitioning behavior of W is responsible for that. Furthermore, it is found that even though Ni exhibits the highest overall concentration, the γ matrix phase is still Co-based, because Ni is strongly enriched in the γ′ precipitates. Creep tests at 900 °C reveal that even though the microstructure looks less favorable, the creep resistance of the Ni-rich alloy is slightly superior to the Co-rich variant.<br

Implications of linear relationships between local and macroscopic flow stresses in the composite model - Mughrabi, Hael (Zeitschrift für Metallkunde, 2006)
Earlier results obtained by X-ray diffraction studies on tensile-deformed [001]-orientated copper single crystals have recently been re-assessed with respect to the evolution of the long-range internal stresses and the local flow stresses of the dislocation cell walls and the cell interiors. It was noted that the magnitudes of the long-range internal stresses and of the local flow stresses increase in good approximation linearly with the applied macroscopic flow stress. In the present work, the results of a similar analysis of earlier published X-ray data, which were obtained on tensile-deformed [001]-orientated Cu-Mn single crystals, are reported. When the friction stress of the alloy is taken into account, similar linear relationships to the case of deformed [001]-orientated copper single crystals were obtained. The implications of these results are analyzed in the framework of the composite model of crystal plasticity. It is shown that linear relationships of the type considered imply, in terms of the composite model, that the ratio between the local dislocation densities in the dislocation cell walls and the cell interiors must remain constant during deformation. This result is discussed with respect to the experimentally obtained data on local dislocation densities.
Created from Fastlane, Scopus look-up
Keywords: Composite model; Local flow stresses; Longrange internal stresses; Plastic deformation

Improved creep strength of nickel-base superalloys by optimized γ/γ′ partitioning behavior of solid solution strengthening elements - Pröbstle, Martin; Neumeier, Steffen; Feldner, Patrick; Rettig, Ralf; Helmer, Harald; Singer, Robert; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2016)
Solid solution strengthening of the γ matrix is one key factor for improving the creep strength of single crystal nickel-base superalloys at high temperatures. Therefore a strong partitioning of solid solution hardening elements to the matrix is beneficial for high temperature creep strength. Different Rhenium-free alloys which are derived from CMSX-4 are investigated. The alloys have been characterized regarding microstructure, phase compositions as well as creep strength. It is found that increasing the Titanium (Ti) as well as the Tungsten (W) content causes a stronger partitioning of the solid solution strengtheners, in particular W, to the γ phase. As a result the creep resistance is significantly improved. Based on these ideas, a Rhenium-free alloy with an optimized chemistry regarding the partitioning behavior of W is developed and validated in the present study. It shows comparable creep strength to the Rhenium containing second generation alloy CMSX-4 in the high temperature / low stress creep regime and is less prone to the formation of deleterious topologically close packed (TCP) phases. This more effective usage of solid solution strengtheners can enhance the creep properties of nickel-base superalloys while reducing the content of strategic elements like Rheniu
WW1::1077
Keywords: Creep; Element partitioning; Nickel-base superalloys; Solid solution strengthening

Improving the Effectiveness of the Solid-Solution-Strengthening Elements Mo, Re, Ru and W in Single-Crystalline Nickel-Based Superalloys - Gaag, Tobias; Ritter, Nils; Peters, Alexandra; Volz, Nicklas; Gruber, Daniel; Neumeier, Steffen; Zenk, Christopher; Körner, Carolin (Metals, 2021)
Tailoring the partitioning behavior of solid solution strengtheners is a crucial design strategy for advanced Ni-based superalloys. The goal of this study was to maximize the enrichment of Mo, Re, Ru and W in the γ-matrix phase. To determine the composition dependency of the partitioning behavior, a set of polycrystalline superalloys with varying contents of these solid solution-strengthening elements and a W-containing single-crystalline alloy series with varying concentrations of the γ′-forming elements Ta and Ti was produced. Assessed properties include phase compositions by electron-probe micro-analysis, phase transformation temperatures by differential scanning calorimetry and creep behavior. Re exhibits the most pronounced enrichment in the γ-matrix, followed by Mo, Ru and W. Due to the preference of the Al-sites in the γ′-phase in the order Ta > Ti > W > Mo > Re, the solid solution strengthening elements Mo, Re and W are displaced from the γ′-phase by increasing Ti and Ta contents. The investigated solutes do not directly influence the partitioning behavior of Ru as it prefers Ni-sites in the γ′-phase. Compressive creep experiments reveal a correlation between the content of solid solution strengtheners in the γ-phase and creep performanc
CRIS-Team Scopus Importer:2021-11-05
Keywords: Ni-based superalloys; creep; solid solution strengthening; partitioning behavior; DSC; CALPHAD

Indentation size effect in metallic materials: Modeling strength from pop-in to macroscopic hardness using geometrically necessary dislocations - Durst, Karsten; Backes, Björn; Franke, Oliver; Göken, Mathias (Acta Materialia, 2006)
The indentation size effect observed during indentation testing of crystalline materials is modeled in terms of geometrically necessary dislocations using a corrected Nix/Gao model. Considering the size of the plastic zone underneath the indenter, the density of geometrically necessary dislocations is calculated for Berkovich and cube-corner indenters. The statistically stored dislocation density is derived from uniaxial stress-strain data applying the Tabor concept of the representative strain. The depth dependence of hardness is obtained from the Taylor relation, considering the statistically stored and geometrically necessary dislocation densities. Hertzian contact theory is used to describe the elastic deformation of the material, whereas the critical pop-in load is derived from the theoretical strength of the material. The plastic load after pop-in is calculated from the Taylor relation under the assumption of perfect indenter geometry. Good agreement is found for our model approach with indentation data on Ni, Cu, Al, and W for Berkovich and cube-corner indenters at all length scales. The indentation response of pure metals can thus be modeled from pop-in to macroscopic hardness using uniaxial stress-strain data. © 2006.
Created from Fastlane, Scopus look-up
Keywords: Dislocations; Finite element analysis; Hardness; Modeling; Nanoindentation

Indentation size effect in Ni-Fe solid solutions - Durst, Karsten; Franke, Oliver; Böhner, Andreas; Göken, Mathias (Acta Materialia, 2007)
The indentation size effect observed during indentation testing is studied in pure Ni, Fe and two different Ni-Fe alloys as well as in a Ni-Fe diffusion couple. The hardness as a function of depth in these solid solutions is modeled in terms of geometrically necessary dislocations (GND). It is found that, for indentation depths varying from 50 to 5000 nm, the depth dependence of hardness could be modeled with a parameter f. Parameter f allows scaling of the storage volume of GND with indentation depth, thus yielding the effective contribution of GND to the hardness in a specific alloy. For the alloy studied, parameter f decreases with solid solution strengthening. Frictional stresses or changes in stacking fault energy might reduce the storage volume for GND. Using these observations, it is shown that diffusion couples and nanoindentation allow macroscopic solid solution hardening to be determined in a combinatorial manner. © 2007 Acta Materialia Inc.
Created from Fastlane, Scopus look-up
Keywords: Diffusion; Dislocations; Hardness; Indentation; Size effect

Indentation size effect in spherical and pyramidal indentations - Durst, Karsten; Göken, Mathias; Pharr, George M. (Journal of Physics D-Applied Physics, 2008)
WW1::769

Indium and antimony distribution in a sphalerite from the “burgstaetter gangzug” of the upper harz mountains pb-zn mineralization - Schirmer, Thomas; Ließmann, Wilfried; Macauley, Chandra; Felfer, Peter (Minerals, 2020)
The sphalerite from the Burgstaetter Gangzug, a vein system of the Upper Harz Mountain nearby the town of Clausthal-Zellerfeld, exhibits a very interesting and partly complementary incorporation pattern of Cu, In and Sb, which has not yet been reported for natural sphalerite. A sphalerite specimen was characterized with electron probe micro-analysis (EPMA) and atom probe tomography (APT). Based on the EPMA results and a multilinear regression, a relation expressed as Cu = 0.98In + 1.81Sb + 0.03 can be calculated to describe the correlation between the elements. This indicates, that the incorporation mechanisms of In and Sb in the structure differ substantially. Indium is incorporated with the ratio Cu:In = 1:1 like in roquesite (CuInS2), supporting the coupled substitution mechanism 2Zn2+ → Cu+ + In3+. In contrast, Sb is incorporated with a ratio of Cu:Sb = 1.81:1. APT, which has a much higher spatial resolution indicates a ratio of Cu:Sb = 2.28:1 in the entire captured volume, which is similar to the ratio calculated by EPMA, yet with inhomogeneities at the nanometer-scale. Analysis of the solute distribution shows two distinct sizes of clusters that are rich in Cu, Sb and Ag.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Antimony; APT; Element distribution; EPMA; Indium; Pb-Zn-mineralization; Sphalerite; Upper Harz Mountains

Influence of application technology on the erosion resistance of DLC coatings - Depner-Miller, U.; Ellermeier, J.; Scheerer, H.; Oechsner, M.; Bobzin, K.; Bagcivan, N.; Broegelmann, T.; Weiss, R.; Durst, Karsten; Schmid, Christoph (Surface & Coatings Technology, 2013)
WW1::967

Influence of a Preageing Treatment on the Cluster Formation and the Further Ageing Route in Al–Mg–Si Extrusion Alloys - Ortner, Patrick; Schiffl, Andreas; Höppel, Heinz Werner (Advanced Engineering Materials, 2024)
Herein, the influence of one- and two-step preageing treatments prior to the artificial ageing step to peak age condition for three different 6xxx alloys, from low to high alloy content, is investigated. Analysis of the preaged conditions using atom probe tomography (APT) reveals a broad distribution of Mg and Si clusters, with some instances of Guinier-Preston I zones present. Additionally, the high alloyed system exhibits a growth of precipitates toward a needle-like shaped. These clusters formed during the preageing treatment serve as nucleation sites in the subsequent artificial ageing treatment, leading to an increase in hardness. Microstructural analysis conducted using transmission electron microscopy and APT demonstrates a reduction in the average precipitate length and a more narrow size distribution for T6 condition. This indicates that the preageing treatment results in a decreased portion of already overaged precipitates compared to the direct aged condition. Consequently, the more narrow size distribution of the precipitates leads to more effective hardening of the material, as a higher portion of precipitates is at or close to their optimum size. The investigations highlight the significant influence and positive effect of a preageing treatment at lower temperatures on the subsequent artificial ageing treatment.
CRIS-Team Scopus Importer:2024-06-07
Keywords: 6xxx Al alloys; atom probe tomography; cluster formation; heat treatment strategy; precipitation; transmission electron microscopy

Influence of backpressure during ECAP on the monotonic and cyclic deformation behavior of AA5754 and Cu99.5 - Höppel, Heinz Werner; Kriebel, Florian; Lapovok, Rimma; Boehner, Andreas; Göken, Mathias (2011)
WW1::878

Influence of Co to Ni ratio in γ′-strengthened model alloys on oxidation resistance and the efficacy of the halogen effect at 900 °C - Weiser, Martin; Galetz, Mathias C.; Zschau, Hans Eberhard; Zenk, Christopher; Neumeier, Steffen; Göken, Mathias; Virtanen, Sannakaisa (Corrosion Science, 2019)
The role of base element (Co or Ni) in γ′-strengthened single-crystalline superalloys was elucidated in the present study. Reaction kinetics during oxidation at 900 °C were assessed by thermogravimetry and measurements of individual layer thicknesses in the multilayered oxide scales. The development of diffusion-limiting barrier layers as well as the extent of sub-scale phase transitions could be directly correlated to the Co/Ni ratio in the alloy. For the first time a surface pretreatment with F was applied to Co-base superalloys. Apparent differences in the efficacy of the halogen effect depending on the Co content in the model alloys were observed.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Co/Ni-base model alloys; Diffusion-limiting scales; EPMA; Halogen effect; Oxidation

Influence of cross-rolling on the mechanical properties of an accumulative roll bonded aluminum alloy AA6014 - Ruppert, Mathis; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2014)
Sheets of aluminum AA6014 (AlMgSi) were successfully accumulative roll bonded from T4 condition up to eight cycles. Using the conventional ARB route, processing was on the one hand performed at room temperature. On the other hand, sheets were pre-heated in a furnace for 2.5 min at 210 °C prior to each rolling step. Besides the conventional ARB route an ARB cross-rolling route, where the rolling direction is rotated around 90° after each cycle, was used at room temperature. For all three processing conditions an ultrafine-grained microstructure was obtained. Due to a change in strain path, the ultimate tensile strength and the yield strength of the cross-rolled AA6014 exceed those of the samples processed by conventional ARB. However, a strong decrease in terms of elongation to failure is visible after 6–8 cycles of ARB compared to the pre-heated ARB sheets. Fracture analysis reveals necking of individual layers for the samples processed at room temperature. Therefore, after 7 cycles of cross-rolling at RT, one last cross-rolling step at elevated temperature was performed in order to improve bonding quality. This leads to a high strength of about 475 MPa and a satisfactory elongation to failure of about 10%.
WW1::999

Influence of Cu Addition and Microstructural Configuration on the Creep Resistance and Mechanical Properties of an Fe-Based alpha/alpha '/alpha '' Superalloy - Morales, Luis Angel; Bezold, Andreas; Förner, Andreas; Holz, Hendrik; Merle, Benoit; Neumeier, Steffen; Körner, Carolin; Zenk, Christopher (Advanced Engineering Materials, 2023)
Introducing Cu nanoparticles is an effective mechanism for strengthening and toughening Fe-based materials such as ultra-high-strength steels. Herein, the effect of Cu on the mechanical properties of a novel Fe-based alpha/alpha '/alpha '' superalloy is studied. Compared to a Cu-free reference alloy, nanoindentation reveals an increase in hardness, which was associated with the formation of Cu nanoparticles. Both alloys show room temperature (RT) compressive plastic strain at maximum stress greater than 8%, irrespective of the heat-treatment. At RT and at 750 degrees C, the Cu-containing alloy exhibits a slightly higher strength, but the heat treatment has a more significant impact: A configuration of alpha-matrix and intermetallic alpha '/alpha ''-phases forming an interpenetrating network is superior to a state with isolated precipitates. This difference vanishes in monotonic creep experiments, and under the same conditions, the Cu-containing alloy exhibits a twice as high creep rate despite a slightly higher precipitate fraction. This is linked to a higher lattice misfit and faster-coarsening kinetics. Post-mortem transmission electron microscopy analysis of the creep-deformed specimens identifies dislocation bypass as the dominant deformation mechanism. However, the presence of 110 dislocations in the interfacial networks and evidence of dislocation activity within alpha '/alpha '' precipitates suggest the occurrence of shearing events.
CRIS-Team WoS Importer:2023-03-03

Influence of Different Annealing Atmospheres on the Mechanical Properties of Freestanding MCrAlY Bond Coats Investigated by Micro-Tensile Creep Tests - Giese, Sven; Neumeier, Steffen; Bergholz, Jan; Naumenko, Dmitry; Quadakkers, Willem J.; Vassen, Robert; Göken, Mathias (Metals, 2019)
The mechanical properties of low-pressure plasma sprayed (LPPS) MCrAlY (M = Ni, Co) bond coats, Amdry 386, Amdry 9954 and oxide dispersion strengthened (ODS) Amdry 9954 (named Amdry 9954 + ODS) were investigated after annealing in three atmospheres: Ar-O-2, Ar-H2O, and Ar-H-2-H2O. Freestanding bond coats were investigated to avoid any influence from the substrate. Miniaturized cylindrical tensile specimens were produced by a special grinding process and then tested in a thermomechanical analyzer (TMA) within a temperature range of 900-950 degrees C. Grain size and phase fraction of all bond coats were investigated by EBSD before testing and no difference in microstructure was revealed due to annealing in various atmospheres. The influence of annealing in different atmospheres on the creep strength was not very pronounced for the Co-based bond coats Amdry 9954 and Amdry 9954 + ODS in the tested conditions. The ODS bond coats revealed significantly higher creep strength but a lower strain to failure than the ODS-free Amdry 9954. The Ni-based bond coat Amdry 386 showed higher creep strength than Amdry 9954 due to the higher fraction of the beta -NiAl phase. Additionally, its creep properties at 900 degrees C were much more affected by annealing in different atmospheres. The bond coat Amdry 386 annealed in an Ar-H2O atmosphere showed a significantly lower creep rate than the bond coat annealed in Ar-O-2 and Ar-H-2-H2O atmospheres.
CRIS-Team WoS Importer:2019-07-30

Influence of different homogenization heat treatments on the microstructure and hot flow stress of the aluminum alloy AA6082 - Arnoldt, Aurel Ramon; Schiffl, Andreas; Höppel, Heinz Werner; Oesterreicher, Johannes Albert (Materials Characterization, 2022)
Proper design of the homogenization heat treatment of 6000 series Al wrought alloys is crucial for processes such as hot rolling and extrusion. Important aspects are the precipitation and growth of dispersoids and the dissolution and re-precipitation of Mg-Si-precipitates. Studying these processes is laborious and experimentally demanding, limiting the feasibility of systematic study of variations in the homogenization regime. We conducted in situ differential scanning calorimetry (DSC) experiments of homogenization of AA6082 at different soak temperatures and cooling rates. The resultant heating and cooling curves were interpreted to obtain information on dispersoid number density and Mg-Si-phase dissolution and re-precipitation. Microstructural differences have been evaluated by scanning electron microscopy analysis. The results elucidate the complex relations between dissolution of primary Mg-Si-precipitates, dispersoid precipitation and growth, Mg-Si-re-precipitation, and hot forming behavior while reducing experimental effort compared to semi-industrial furnace trials. Overall, the homogenization soak temperature had the largest influence on these microstructural phenomena while differences due to the cooling rate were less pronounced in an industrially relevant range. In conclusion, in situ DSC can be used as a tool for rapid and inexpensive investigation of homogenization parameters
CRIS-Team WoS Importer:2022-09-30

Influence of dislocation density on the pop-in behavior and indentation size effect in CaF2 single crystals: Experiments and molecular dynamics simulations - Lodes, Matthias; Hartmaier, Alexander; Göken, Mathias; Durst, Karsten (Acta Materialia, 2011)
WW1::879
Keywords: Dislocations; Atomic force microscopy; Nanoindentation; Molecular dynamics

Influence of grain boundaries on the deformation resistance: Insights from an investigation of deformation kinetics and microstructure of copper after predeformation by ECAP - Bach, Jochen; Liebig, Jan Philipp; Höppel, Heinz Werner; Blum, Wolfgang (Philosophical Magazine, 2013)
WW1::968

Influence of grain boundary structure and topology on the plastic deformation of nanocrystalline aluminum as studied by atomistic simulations - Prakash, Aruna; Weygand, D.; Bitzek, Erik (International Journal of Plasticity, 2017)
Nanocrystalline materials, with grain sizes below 100 nm, have been the subject of many research studies in the recent past. At these reduced grain sizes, grain boundaries (GBs) play a very important role in the deformation of such materials. Large scale atomistic simulations that are often used to illuminate the deformation mechanisms in such materials must accurately account for the topology, structure and network of GBs. In this work, we perform atomistic simulations on nanocrystalline aluminum under tensile loading, using a structure with a relaxed GB network obtained from three-dimensional grain growth simulations, and compare the results to that obtained from structures generated using the Voronoi tessellation method. The results show that the grain growth sample results in consistently higher macroscopic stresses when compared to the Voronoi tessellated microstructures. The latter, additionally, tend to overestimate GB deformation, whilst simultaneously underestimating the deformation due to dislocation slip. More importantly, twinning is observed in multiple grains in the grain growth sample, in contrast to the near absence in Voronoi tessellated microstructures. The results are carefully discussed in terms of sample characteristics, stacking fault energies, and GB Structure and network. (c) 2017 Elsevier Ltd. All rights reserved.
Keywords: Grain boundary (GB); Atomistic simulations; Nanocrystalline (NC) aluminum; Grain growth microstructure; Twinning; Voronoi microstructure

Influence of grain size and precipitates on the fatigue lives and deformation mechanisms in the VHCF-regime - Höppel, Heinz Werner; Prell, Michaela; May, Lilia; Göken, Mathias (Procedia Engineering, 2010)
WW1::842

Influence of grain size and precipitation state on the fatigue lives and deformation mechanisms of CP aluminium and AA6082 in the VHCF-regime - Höppel, Heinz Werner; Göken, Mathias; May, Lilia; Prell, M. (2011)
WW1::880

Influence of Grain Size and Volume Fraction of η/δ Precipitates on the Dwell Fatigue Crack Propagation Rate and Creep Resistance of the Nickel-Base Superalloy ATI 718Plus - Kirchmayer, Andreas; Pröbstle, Martin; Huenert, D.; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
Recently, it was found that the orientation of the η/δ plates in the Ni-base superalloys ATI 718Plus has a huge impact on the fatigue crack propagation behavior (Huenert et al. in Superalloys pp.781–792, 2016). However, the targeted alignment of η/δ precipitates in components with complex geometry can be challenging in certain applications. Therefore, the effect of other microstructural features of ATI 718Plus, which are easier to manipulate, is tested with respect to their fatigue crack propagation behavior and creep strength. The grain size, the γ′ precipitate size, as well as the γ′ and η/δ volume fraction are varied by applying different heat treatments. An increase in the η/δ volume fraction as well as the γ′ volume fraction and precipitate size enhanced the crack growth resistance, but worsened the creep properties. On the contrary, increasing the grain size leads to better creep properties and better fatigue crack growth resistance. The impact of the different microstructures investigated in this study on the mechanical properties is smaller compared to microstructures with strongly aligned η/δ plates. These results enable to design the desired microstructures that meet the particular demands of the given application regarding crack propagation and creep resistance.
CRIS-Team Scopus Importer:2023-03-24

Influence of intrinsic strain on irradiation induced damage: the role of threshold displacement and surface binding energies - Guenole, Julien; Prakash, Aruna; Bitzek, Erik (Materials and Design, 2016)
Focused ion beam (FIB) machining has become a standard tool for sample preparation and in combination with digital image correlation (DIC) for the evaluation of local intrinsic stresses by measuring strain relaxation. However, FIB milling always leads to irradiation damage of the material. Current models for the formation of irradiation damage and the sputter yield are based on two key parameters, the threshold displacement energy (TDE) and surface binding energy (SBE), which are usually determined from unstrained systems with idealized surfaces. Here we use atomistic simulations to determine the TDE and SBE for strained silicon and aluminum and compare the results to full cascade simulations. A clear, material class dependent influence of the strain state on the TDE is observed, and surface amorphisation is shown to significantly increase the SBE of 001 surface
Keywords: Atomistic simulation; FIB; Irradiation damage; Surface binding energy; Threshold displacement energy

Influence of iridium on the properties of γ′-strengthened co-base superalloys - Bauer, Alexander; Neumeier, Steffen; Pyczak, Florian; Göken, Mathias (Advanced Engineering Materials, 2015)
The influence of iridium on the phase stability, oxidation behavior, and high temperature creep strength of γ′-hardened Co-base superalloys is discussed. Ir increases the γ′-solvus temperature and γ′-volume fraction since it partitions slightly to the γ′-phase. However, Ir leads also to a discontinuous precipitation transformation of the metastable γ/γ′-microstructure into a lamellar microstructure of Co3W, CoAl, and a Co-rich fcc phase for the W-rich alloys. A reduction of W in presence of Ir leads to a higher phase stability. The constrained lattice misfit between the γ and γ′ phase in the Ir and high W containing alloy is +0.5%. The alloying element Ir strongly increases the creep strength at 850°C as long as the γ/γ′-microstructure is not discontinuously transformed. Furthermore, the oxidation resistance is improved by the addition of iridium. Addition of Iridium to a γ′ strengthened Co-base superalloy leads to increased volume fraction and solvus temperature of the γ′ precipitate phase, as well as to higher solidus and liquidus temperatures. Iridium partitions slightly to the γ′ precipitate phase and the creep strength is improved considerably as long the γ/γ′-microstructure is not discontinuously transforme

Influence of lattice misfit on the internal stress and strain states before and after creep investigated in nickel-base superalloys containing rhenium and ruthenium - Pyczak, Florian; Neumeier, Steffen; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::809

Influence of microstructure on creep strength of MRI 230D Mg alloy - Amberger, D.; Eisenlohr, Philip; Göken, Mathias (Journal of Physics : Conference Series, 2010)
WW1::843

Influence of modulus-to-hardness ratio and harmonic parameters on continuous stiffness measurement during nanoindentation - Merle, Benoit; Maier-Kiener, Verena; Pharr, George M. (Acta Materialia, 2017)
Dynamic nanoindentation is a popular method for continuously probing the mechanical properties of a sample as a function of depth. It is shown here that special caution should be exercised when testing materials with high modulus-to-hardness ratios (E/H) at fast loading rates, as the choice of harmonic parameters can result in a significant underestimation of the contact stiffness and hence the elastic modulus. The origin of this behavior is traced back to a bias occurring during signal processing by the lock-in amplifier. The possible consequences of flawed measurements are highlighted and a practical method for detecting possible occurrence from the phase angle signal is presented. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Nanoindentation; Continuous stiffness measurement; Harmonic parameters; Lock-in amplifier; Stiffness bias

Influence of Nanoparticle Reinforcement on the Mechanical Properties of Ultrafine-Grained Aluminium Produced by ARB - Schmidt, Christian; Knieke, Catharina; Maier, Verena; Höppel, Heinz Werner; Peukert, Wolfgang; Göken, Mathias (Materials Science Forum, 2011)
Dispersed nanoparticles are introduced from stabilized suspensions during the accumulative roll bonding process in aluminium AA1050A by air gun spraying up to a final volume fraction of 0.1 % after eight cycles. Additional strengthening caused by particle insertion is observed and strongly depends on the suspension medium and stabilizing agent as both influence interfacial bonding of the particles to the matrix. The particle insertion furthermore results in reduced peel strength of the sheets irrespective of particle material and size caused by a reduction of effective metal to metal bonding area during rolling through the presence of the particle

Influence of Nb, Ta and Zr on the Interdiffusion Coefficients and Solid Solution Strengthening of γ-TiAl Single Phase Alloys - Haußmann, Lukas; Neumeier, Steffen; Bresler, Johannes; Keim, Simon; Pyczak, Florian; Göken, Mathias (Metals, 2022)
The alloying elements Nb, Ta and Zr improve the creep properties of fully lamellar γ/α2 titanium aluminides significantly. Since high temperature deformation mainly occurs in the γ-phase of γ/α2 titanium aluminides, the diffusivity and the solid solution hardening effect of these three elements in the γ-phase is studied by analyzing the concentration gradients of the alloying elements and the resulting hardness across the interdiffusion zone of diffusion couples by energy dispersive X-ray diffraction and nanoindentation. The results reveal that Zr has the highest interdiffusion coefficient but also the largest solid solution hardening coefficient. The mechanical properties of single γ-phase Ti-54Al-5X alloys were investigated by strain rate jump tests. The addition of 5 at.% Nb or Ta lead to an increased strength compared to a binary γ-Ti-54Al alloy. The Zr-containing γ-TiAl alloy reveals the highest strength at 750°C and 900°C, which is discussed to be due to the strong solid solution hardening effect of Zr. However, in comparison to the other alloys, Ti-54Al-5Zr shows quite brittle behavior up to 900°C. The lower diffusivity of Ta compared to Nb leads to a higher strength of the Ta-modified alloy at 900◦C.
CRIS-Team Scopus Importer:2022-05-13
Keywords: diffusion; solid solution hardening; strain rate jump test; TiAl; γ-phase

Influence of Ni Solute segregation on the intrinsic growth stresses in Cu(Ni) thin films - Kaub, T. M.; Felfer, Peter; Cairney, J. M.; Thompson, G. B. (Scripta Materialia, 2016)
Using intrinsic solute segregation in alloys, the compressive stress in a series of Cu(Ni) thin films has been studied. The highest compressive stress was noted in the 5 at.%Ni alloy, with increasing Ni concentration resulting in a subsequent reduction of stress. Atom probe tomography quantified Ni's Gibbsian interfacial excess in the grain boundaries and confirmed that once grain boundary saturation is achieved, the compressive stress was reduced. This letter provides experimental support in elucidating how interfacial segregation of excess adatoms contributes to the post-coalescence compressive stress generation mechanism in thin films. (C) 2015 Elsevier Ltd. All rights reserve
Keywords: Thin films; Grain boundaries; Atom probe tomography; Sputtering; Residual stress

Influence of refractory and platinum group metals on the microstructure and thermo-physical properties of Co-Al-W-based superalloys - Köbrich, Manuel; Förner, Andreas; Volz, Nicklas; Zenk, Christopher; Fries, S. G.; Göken, Mathias; Neumeier, Steffen (Journal of Alloys and Compounds, 2023)
The influence of various alloying elements on Co-Al-W based superalloys has been investigated in detail since the discovery of the Co3(Al,W) phase. However, a full picture on the role of the refractory and platinum group elements is still lacking. Accordingly, this work covers the microstructural changes and phase stability in Co9Al9W-X superalloys with 2 at% Zr, Ru, Rh, Pd, Hf, Re, Ir, and Pt. The experimental findings are compared with thermodynamic calculations. Generally, alloying with refractory and platinum group elements preserves γ/γ′ microstructures, but causes the formation of additional intermetallic phases. Electron backscatter diffraction and energy dispersive X-ray spectroscopy reveal that Ru, Ir, and Pt cause discontinuous formation of β (B2) and χ (D019) phases whereas in the Re-containing alloy β and µ (D85) precipitates are present along the grain boundaries. Also unidentified Hf- and Zr-rich phases form in the alloys containing these elements. Additionally, differential scanning calorimetry measurements and scanning electron microscopy analysis indicate an increasing γ′ solvus temperature as well as γ′ volume fraction for most of the refractory and platinum group elements. This can be explained by their γ′/γ partitioning behavior, which has been examined by atom probe tomography.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Atom probe tomography; thermodynamic calculations; Co-base superalloys; Differential scanning calorimetry; Electron backscatter diffraction; Energy dispersive X-ray spectroscopy

Influence of rhenium and ruthenium on the local mechanical properties of the c and c0 phases in nickel-base superalloys - Neumeier, Steffen; Pyczaky, F.; Göken, Mathias (Philosophical Magazine, 2011)
WW1::882

Influence of rhenium on γ′-strengthened cobalt-base superalloys - Kolb, Markus; Zenk, Christopher; Kirzinger, Anna; Povstugar, Ivan; Raabe, Dierk; Neumeier, Steffen; Göken, Mathias (Journal of Materials Research, 2017)
The element Re is known to be a very potent strengthener concerning the creep properties of Ni-base superalloys. In this paper the influence of Re on the properties of new gamma'-strengthened Co-base superalloys is addressed. Atom probe tomography reveals that Re partitions preferentially to the gamma phase, but not as pronounced as in ni-base superalloys. Nanoindentation and micro-pillar compression tests of the gamma' phase indicate an increase of the hardness and the critical resolved shear stress caused by a considerable concentration of Re in the gamma' phase. Creep investigations show that the positive effect of Re is by far not as pronounced as in Ni-base superalloys. Several effects, which can contribute to this behavior, such as the lower Re concentration in gamma and hence a slightly reduced effective diffusion coefficient, a smaller diffusion barrier of Re in Cocompared to Ni, a slightly lower lattice misfit and gamma' volume fraction of the Re-containing alloy, are discussed.

Influence of rolling direction on strength and ductility of aluminium and aluminium alloys produced by accumulative roll bonding - Topic, Irena; Höppel, Heinz Werner; Göken, Mathias (Journal of Materials Science, 2008)
WW1::772

Influence of small amounts of Si and Cr on the high temperature oxidation behavior of novel cobalt base superalloys - Liang, Zhida; Göken, Mathias; Lorenz, Uwe; Neumeier, Steffen; Oehring, Michael; Pyczak, Florian; Stark, Andreas; Wang, Li (Corrosion Science, 2021)
The effect of small amounts of Si and Cr on the high temperature oxidation of alloys based on Co-9Al-9W was investigated at 900 °C. The results show that the effect of Si additions on oxidation resistance was more pronounced than for Cr additions. An addition of 4 at.% Cr was insufficient to produce a protective layer, while 2 at.% Si led to the formation of a dense, continuous Al2O3 scale. The thermodynamics and kinetics for Al2O3 layer formation were analyzed by combining CALPHAD and Wagnerʼs theory.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Co-based superalloys; Oxidation; Synchrotron radiation; Thermodynamics and kinetics

Influence of specimen geometry on temperature increase during ultrasonic fatigue testing - Bach, Jochen; Göken, Mathias; Bitzek, Erik; Höppel, Heinz Werner (Ultrasonics, 2013)
During the last decades the interest in fatigue properties of materials subjected to more than 10(7) cycles has strongly increased. To reach such high numbers of cycles the use of ultrasonic fatigue testing systems is a well-established method due to their very high fatigue frequencies. However particular considerations about the specimen design have to be made for ultrasonic fatigue testing. In order to investigate the influence of the specimen design on the fatigue behavior in more detail, two different gauge lengths were chosen. The influence of specimen design was found to be very prominent on the characteristic frequencies which are used for operating ultrasonic fatigue testing systems. As it is already known, with increasing specimen mass the characteristic frequency decreases. Also the amplitude has an influence on the characteristic frequency during an ultrasonic fatigue test. With increasing test amplitude micro-plasticity becomes more pronounced which leads also to a decrease in frequency. Most prominent, a distinct influence of the specimen geometry on the temperature increase during cycling was found. Specimens with a shorter gauge length showed a higher increase in temperature then specimens with the longer gauge length. It is suggested that these observations are caused by an easier and more equal distribution of heat in the specimens with the longer gauge length design. The influence of specimen shape was accomplished by simulation using a finite element metho

Influence of specimen geometry on temperature increase during ultrasonic fatigue testing - Bach, Jochen; Höppel, Heinz Werner; Bitzek, Erik; Göken, Mathias (Ultrasonics, 2013)
Keywords: Ultrasonic fatigue; Characteristic frequency; Very high cycle fatigue; Ultrasonic fatigue specimen design

Influence of specimen geometry on temperature increase during ultrasonic fatigue testing - Bach, Jochen; Höppel, Heinz Werner; Bitzek, Erik; Göken, Mathias (Ultrasonics, 2013)
During the last decades the interest in fatigue properties of materials subjected to more than 107 cycles has strongly increased. To reach such high numbers of cycles the use of ultrasonic fatigue testing systems is a well-established method due to their very high fatigue frequencies. However particular considerations about the specimen design have to be made for ultrasonic fatigue testing. In order to investigate the influence of the specimen design on the fatigue behavior in more detail, two different gauge lengths were chosen. The influence of specimen design was found to be very prominent on the characteristic frequencies which are used for operating ultrasonic fatigue testing systems. As it is already known, with increasing specimen mass the characteristic frequency decreases. Also the amplitude has an influence on the characteristic frequency during an ultrasonic fatigue test. With increasing test amplitude micro-plasticity becomes more pronounced which leads also to a decrease in frequency. Most prominent, a distinct influence of the specimen geometry on the temperature increase during cycling was found. Specimens with a shorter gauge length showed a higher increase in temperature then specimens with the longer gauge length. It is suggested that these observations are caused by an easier and more equal distribution of heat in the specimens with the longer gauge length design. The influence of specimen shape was accomplished by simulation using a finite element method. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Very high cycle fatigue; Ultrasonic fatigue; Ultrasonic fatigue specimen design; Characteristic frequency

Influence of stacking fault energy and dislocation character on slip transfer at coherent twin boundaries studied by micropillar compression - Liebig, Jan Philipp; Krauß, Sebastian; Göken, Mathias; Merle, Benoit (Acta Materialia, 2018)
Copper and alpha-brass micropillars containing a single coherent twin boundary of controlled orientation were compressed to systematically investigate dislocation-twin boundary interactions as a function of the dislocation type and generalized stacking fault energies. For this purpose, bicrystalline micropillars in [112], [110] and [259] orientations were prepared from polycrystalline samples using focused ion beam milling in combination with custom 3D-printed sample holders. Consistent with previous findings, a vertical twin boundary neither resulted in the storage of dislocations at the interface nor in an increase of the sample strength when compressed in the [112] direction. However, the interface proved to be a strong obstacle for the non-screw dislocations promoted by the [259] orientation. In this case, dislocation storage - evidenced by large pile-ups - lead to a strong hardening of the specimens. The strengthening contribution of the interface was further affected by the stacking fault energy of the material. While this could be related to the different permeability of the interface, it is more likely the result of a change in cross-slip frequency within the sample volume. (C) 2018 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Micromechanics; Twin boundary; Stacking fault energy; Slip transfer; Copper alloys

Influence of Surfactant-Mediated Interparticle Contacts on the Mechanical Stability of Supraparticles - Wang, Junwei; Kang, Eunsoo; Sultan, Umair; Merle, Benoit; Inayat, Alexandra; Graczykowski, Bartlomiej; Fytas, George; Vogel, Nicolas (Journal of Physical Chemistry C, 2021)
Colloidal supraparticles are micron-scale spherical assemblies of uniform primary particles, which exhibit emergent properties of a colloidal crystal, yet exist as a dispersible powder. A prerequisite to utilize these emergent functionalities is that the supraparticles maintain their mechanical integrity upon the mechanical impacts that are likely to occur during processing. Understanding how the internal structure relates to the resultant mechanical properties of a supraparticle is therefore of general interest. Here, we take the example of supraparticles templated from water/fluorinated oil emulsions in droplet-based microfluidics and explore the effect of surfactants on their mechanical properties. Stable emulsions can be generated by nonionic block copolymers consisting of a hydrophilic and fluorophilic block and anionic fluorosurfactants widely available under the brand name Krytox. The supraparticles formed in the presence of both types of surfactants appear structurally similar, but differ greatly in their mechanical properties. While the nonionic surfactant induces superior mechanical stability and ductile fracture behavior, the anionic Krytox surfactant leads to weak supraparticles with brittle fracture. We complement this macroscopic picture with Brillouin light spectroscopy that is very sensitive to the interparticle contacts for subnanometer-thick adsorbed layers atop of the nanoparticle. While the anionic Krytox does not significantly affect the interparticle bonds, the amphiphilic nonionic surfactant drastically strengthens these bonds to the point that individual particle vibrations are not resolved in the experimental spectrum. Our results demonstrate that seemingly subtle changes in the physicochemical properties of supraparticles can drastically impact the resultant mechanical propertie
Keywords: Ductile fracture; Emulsification; Fracture mechanics; Nonionic surfactants; Ostwald ripening; Physicochemical properties; Colloidal crystals; Emergent functionality; Emergent property; Internal structure; Interparticle contacts; Mechanical impacts; Mechanical integrity; Micron scale; Primary particles; Spherical assembly; Mechanical stability

Influence of Ta on the oxidation resistance of WB2−z coatings - Fuger, C.; Schwartz, B.; Wojcik, T.; Moraes, V.; Weiss, M.; Limbeck, A.; Macauley, Chandra; Hunold, O.; Polcik, P.; Primetzhofer, D.; Felfer, Peter; Mayrhofer, P. H.; et al. (Journal of Alloys and Compounds, 2020)
Ternary W1−xTaxB2−z is a promising protective coating material possessing enhanced ductile character and phase stability compared to closely related binaries. Here, the oxidation resistance of W1−xTaxB2−z thin films was experimentally investigated at temperatures up to 700 °C. Ta alloying in sputter deposited WB2−z coatings led to decelerated oxide scale growth and a changed growth mode from paralinear to a more linear (but retarded) behavior with increasing Ta content. The corresponding rate constants decrease from kp* = 6.3 ⋅ 10−4 µm2/s for WB2−z, to kp* = 1.1 ⋅ 10−4 µm2/s for W0.66Ta0.34B2−z as well as kl = 2.6 ⋅ 10−5 µm/s for TaB2−z, underlined by decreasing scale thicknesses ranging from 1170 nm (WB2−z), over 610 nm (W0.66Ta0.34B2−z) to 320 nm (TaB2−z) after 10 min at 700 °C. Dense and adherent scales exhibit an increased tantalum content (columnar oxides), which suppresses the volatile character of tungsten-rich as well as boron oxides, hence being a key-factor for enhanced oxidation resistance. Thus, adding Ta (in the range of x = 0.2–0.3) to α-structured WB2−z does not only positively influence the ductile character and thermal stability but also drastically increases the oxidation resistance.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Diborides; Oxidation resistance; Scale growth; Transition metal diborides

Influence of the Co/Ni Ratio and Dendritic Segregations on the High-Temperature Oxidation Resistance of Multinary Co-Rich Superalloys at 850 °C and 1050 °C - Hagen, Sebastian; Weiser, Martin; Abu-Khousa, B.; Virtanen, Sannakaisa (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
Excellent inherent oxidation resistance is a prerequisite for the use of superalloys in many high-temperature applications. To achieve this goal, typically continuous alumina and chromia scale growths are assured through sufficient Cr and Al additions. Since the intended γ/γ′-microstructure of superalloys is only stable within a certain compositional window, the maximum concentrations of these protective scale forming elements are, however, dependent on the overall alloy composition. The latter is a severe drawback, especially for Co-rich superalloys, as for these the maximum content often is insufficient for reaching the desired continuous scale growth. In recent years, the addition of significant Ni levels was identified to improve the high-temperature oxidation properties in the case of simple model alloy systems. In this study, we compare the high-temperature oxidation behavior of two complex Co-rich multinary single-crystalline γ/γ′-strengthened superalloys that only differ regarding their Co/Ni ratios to the commercial Ni-base superalloy CMSX-4. Therefore, time-resolved isothermal gravimetric analysis (TGA) in synthetic air at 850 °C and 1050 °C for 100 hours, scanning electron microscopy analysis (SEM), and electron probe microanalysis (EPMA) were conducted. The results point out that a high Co-content beneficially affects the oxidation resistance at 850 °C, meaning that the Ni-base CMSX-4 is slightly outmatched by the Co-rich competitors. In contrast, at 1050 °C, the commercial (most Ni-rich) alloy performed best and, clearly, an increasing Co-content was identified to deteriorate the oxidation resistance. This temperature-dependent influence of the nominal Co/Ni ratio on oxidation resistance is shown to be especially pronounced for dendritic regions. Consequently, the latter could be identified to especially determine the overall oxidation kinetics.
CRIS-Team Scopus Importer:2022-02-25

Influence of the ECAP processing parameters on the cyclic deformation behavior on ultrafine-grained cubic face centered metals - Böhner, Andreas; Höppel, Heinz Werner; May, Johannes; Göken, Mathias (Advanced Engineering Materials, 2012)
WW1::936

Influence of the W and Ta content on the High-Temperature Oxidation Resistance of Multinary Co/Ni-Based Superalloys at 1050 °C and 1150 °C - Hagen, Sebastian; Haußmann, Lukas; Wahlmann, Benjamin; Gebhardt, Franz; Abu-Khousa, B.; Weiser, Martin; Neumeier, Steffen; Zenk, Christopher; Virtanen, Sannakaisa (High Temperature Corrosion of Materials, 2023)
Outstanding inherent environmental resistance is a precondition for the use of superalloys in high-temperature applications. Besides high Al and Cr levels, also refractory metal concentrations (W and Ta) are reported to affect protective scale formation, as these elements are expected to affect the chemical activity and also the transport of protective scale formers within the alloy. In this study, we elucidate the high-temperature oxidation behavior of 3 Co-based (Co/Ni ratio: 1.4) and 3 Ni-based (Co/Ni ratio: 0.7) superalloys differing in W and Ta levels. Time-resolved thermogravimetric analysis (TGA) in synthetic air at 1050 °C and 1150 °C for 100 h, scanning electron microscopy analysis (SEM), thermodynamic calculations using the CALPHAD software Thermo-Calc, and diffusion couple experiments were conducted to assess the impact of the Co/Ni ratio and the refractory metal content on the oxidation performance. The results indicate that a low W content (3 vs. 5 at.%) and a high Ta content (2.1 vs. 1.5 at.%) beneficially affect the oxidation resistance, as alumina scale formation is facilitated.
Created from Fastlane, Scopus look-up
Keywords: Cobalt-base superalloys; High-temperature oxidation; Protective scales; Refractory metals

Influence of the γ′ Volume Fraction on the High-Temperature Strength of Single Crystalline Co–Al–W–Ta Superalloys - Xue, Fei; Bezold, Andreas; Volz, Nicklas; Kirchmayer, Andreas; Zenk, Christopher; Neumeier, Steffen; Göken, Mathias (Crystals, 2023)
Understanding the influence of γ′ and secondary-phase fractions on the mechanical properties of superalloys is very important to optimize these high-strength materials. So far, this has not been systematically investigated for the novel class of Co-based superalloys. In this study, a Co–Al–W–Ta model alloy series was designed with compositions of γ/γ′ on the tie-line and an increasing γ′ volume fraction of up to 70% after heat treatment at 900 °C, while a few alloys are unexpectedly out of γ/γ′ two-phase region with an additional secondary phase fraction of up to 15%. The high-temperature strength and creep properties were evaluated by compression tests up to 1050 °C and compressive creep experiments at 950 °C, respectively. At temperatures of up to 1050 °C, an increasing γ′ volume fraction consistently increased the yield strength, which was not dramatically changed by the presence of secondary phases. Significant work hardening was found in alloys with γ′ volume fractions of 65–70% during compression testing, but not in alloys with either a lower γ′ volume fraction (<50%) or a high fraction of secondary phases ( 15%). Similar to the yield strength, the creep strength also increased continuously with the γ′ volume fraction, but was greatly reduced with an increasing fraction of secondary phases. The best creep performance at 950 °C and 200 MPa was found in the alloy with the highest γ′ volume fraction and no secondary phases. At higher creep stresses, rafting contributed significantly to the hardening and, again, the alloy with a high γ′ volume fraction and a small amount of secondary phases exhibited the highest strength.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Co-based superalloys; compression test; creep; rafting; stacking faults; transmission electron microscopy

Influence of upscaling accumulative roll bonding on the homogeneity and mechanical properties of AA1050A - Ruppert, Mathis; Böhm, Wolfgang; Nguyen, H.; Höppel, Heinz Werner; Merklein, Marion; Göken, Mathias (Journal of Materials Science, 2013)
Accumulative roll bonding (ARB), as a method for production of ultrafine grained materials, is frequently supposed to be easily transferable to established industrial production lines. In literature, however, common sheet dimensions used for ARB in a laboratory scale are between 20 and 100 mm in width. In order to quantify the potential of upscaling the ARB process to a technological relevant level, sheets of AA1050A with an initial sheet width of 100–450 mm were accumulative roll bonded up to 8 cycles. In this regard, three different rolling mills of distinct dimensions were used for processing of the sheet material. The influence of process parameters and the reproducibility of the process, in terms of mechanical properties and homogeneity of the sheets, were studied by means of mechanical and microstructural characterization. Both appear to be largely independent on the sheet size and the rolling mill utilized for production. Only small deviations after the first cycles could be detected, vanishing in subsequent cycles due to the features of microstructural evolution. The finally obtained results indicate a high potential for industrial application of ARB and illustrate the possibility to upscale the process to a level necessary for that purpose.
WW1::970

Influence of Zn and Sn on the precipitation behavior of new Al-Mg-Si alloys - Glöckel, Felix; Uggowitzer, Peter J.; Felfer, Peter; Pogatscher, Stefan; Höppel, Heinz Werner (Materials, 2019)
In this study, we demonstrate how Zn and Sn influence hardening behavior and cluster formation during pre-aging and paint bake treatment in Al-Mg-Si alloys via hardness tests, tensile tests, and atom probe tomography. Compared to the standard alloy, the Sn-modified variant shows reduced cluster size and yield strength in the pre-aged condition. During the paint bake cycle, the clusters start to grow very fast and the alloy exhibits the highest strength increment. This behavior is attributed to the high vacancy binding energy of Sn. Adding Zn increases the formation kinetics and the size of Mg-Si co-clusters, generating higher yield strength values for both the pre-aged and paint baked conditions. Simultaneous addition of Zn and Sn creates a synergistic effect and produces an alloy that exhibits moderate strength (and good formability) in the pre-aged condition and accelerated hardening behavior during the paint bake cycle.
CRIS-Team Scopus Importer:2019-08-20
Keywords: Al-Mg-Si alloy; Al-Mg-Si-Zn-Sn alloys; Cluster formation; Hardening behavior; Paint bake; Sn; Zn

Influences of residual stresses on the serrated flow in bulk metallic glass under elastostatic four-point bending - A nanoindentation and atomic force microscopy study - Haag, Fabian; Beitelschmidt, Denise; Eckert, Juergen; Durst, Karsten (Acta Materialia, 2014)
WW1::1001

Influencing Hardness and Wear During the Dynamic Tempered Microinjection Molding Process by Considering Isothermal Holding Time - Fischer, Christopher; Seefried, Andreas; Merle, Benoit; Göken, Mathias; Drummer, Dietmar (Polymer Engineering and Science, 2017)
For semicrystalline thermoplastic parts it is well known that increasing isothermal holding temperature can affect inner component properties, respectively, crystalline structure (e.g., morphology, degree of crystallization, crystal modification, etc.) and, therefore, resulting global component properties such as hardness and wear. Nevertheless, in literature there is no explicit focus on the effect of isothermal holding time during dynamically tempered injection molding process. In this article, semicrystalline microcomponents have been injection molded by varying isothermal holding time within the material's crystallization temperature area. As materials, POM-C, as a material with relatively high crystallization kinetic, and PA 12, as a material with medium crystallization kinetic, were used. To evaluate the effects on hardness and wear, nanoindentation measurements as well as pin-on-disc wear tests were performed. Results show that for fast crystallizing POM-C an isothermal holding step has no significant influence on inner component and resulting global component properties. For slower crystallizing PA 12, however, the morphology and the degree of crystallization could be influenced and, as a result, hardness could be increased by 21% while wear could be reduced by 30%.
UnivIS-Import:2017-07-10:Pub.2017.tech.FT.FT-KT.influe

In situ bulge testing in an atomic force microscope: Microdeformation experiments of thin film membranes - Schweitzer, Elmar; Göken, Mathias (Journal of Materials Research, 2007)
A new bulge testing setup for the measurement of the mechanical properties of thin films is presented. This self-built device can be incorporated in an atomic force microscope (AFM), which allows the recording of topographic images of the observed sample membranes under load conditions. Bulge test experiments on different silicon nitride films are presented and compared to nanoindentation experiments. The measured elastic moduli from nanoindentation and bulge testing are in good agreement. Apart from that, the ability to extract stress-strain data from AFM scans is shown, and the results are compared to standard bulge testing experiments. Imaging of the sample microstructure under load conditions is demonstrated on a thin Cu film.
Created from Fastlane, Scopus look-up

In Situ Investigation of TCP Phase Formation, Stress Relaxation and gamma/gamma ' Lattice Misfit Evolution in Fourth Generation Single Crystal Ni-Base Superalloys by X-Ray High Temperature Diffraction - Bezold, Andreas; Stone, H. J.; Rae, C. M. F.; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
In nickel-based superalloys, the lattice misfit between the gamma and gamma' phases and the propensity to TCP phase formation at service temperatures critically influence the microstructural evolution that takes place and hence the resultant mechanical properties. In this work, the lattice misfits of a series of highly alloyed Ru-containing 4th generation Ni-base superalloys are investigated by in situ X-ray diffraction (XRD) at high temperature. While the lattice misfit values of all alloys range between - 0.3 and - 1.3 pct at room temperature, they show an atypical temperature dependence, becoming less negative above 900 degrees C. In situ XRD measurements at 1100 degrees C reveal that the majority of the internal coherency stresses are already relieved after two hours. This is particularly pronounced for the alloys that have both a lattice misfit larger than vertical bar 0.6 vertical bar pct at 1100 degrees C and are prone to TCP phase formation. However, throughout the relaxation of the internal coherency stresses the lattice misfit remains fairly constant. Due to the similar chemical compositions of the alloys studied, qualitative guidelines for an optimum lattice misfit magnitude are developed by comparing the lattice misfit values with previous creep experiments. Our results indicate that no universal optimal lattice misfit value exists for these alloys and the value strongly depends on the applied creep conditions.
CRIS-Team WoS Importer:2022-05-27

In-situ investigation on the deformation and damage behaviour of diamond-like carbon coated thin films under uniaxial loading - Schaufler, Jens; Durst, Karsten; Massler, Orlaw; Göken, Mathias (Thin Solid Films, 2009)
In the present work, the failure behaviour of diamond-like carbon (DLC) coatings on thin steel substrate under uniaxial tensile loading is analyzed in-situ in scanning electron microscopy as well as ex-situ using focused ion beam cross section and transmission electron microscopy. Aim of the work is to find correlations between the failure behaviour of the coating system, the adhesion and the stress–strain behaviour of a DLC coating system under tensile loadings conditions. Therefore thin amorphous DLC films were coated onto thin stainless steel foils using a plasma assisted chemical vapour deposition technique. It is found from the in-situ investigations that at increasing strains cracks were formed in the coating, with decreasing spacing at higher strains. By comparing uncoated steels foils with coated systems the stress–strain behaviour of a DLC coating was determined. The DLC coating, although already strongly cracked, bears loads up to a total strain of 15%. Cross section analyses with a focused ion beam and microscopy techniques supported these investigations. During straining the formation of two deformation bands adjacent to the Cr adhesion layer was observed. This deformation bands also indicate a high interfacial adhesion.
WW1::811

In situ mechanical testing of hard yet tough high entropy nitride coatings deposited on compliant steel substrates - Kuczyk, Martin; Zawischa, Martin; Krülle, Tim; Vollhüter, Jan; Zeiler, Stefan; Leonhardt, Michael; Kaspar, Jörg; Zimmer, Otmar; Göken, Mathias; Leyens, Christoph; Zimmermann, Martina (Thin Solid Films, 2023)
High entropy nitrides are an interesting material class for wear resistant coatings. Their fracture properties and toughness are of particular interest for future application in tool coatings. Therefore, in situ tensile testing and micro-cantilever experiments were performed on (AlCrTaTiZr)N, (AlCrNbSiTiV)N, (HfNbTaTiVZr)N and (AlTi)N coatings inside a scanning electron microscope. Parallel cracks form during tensile testing from which the fracture toughness was determined via a modified Hsueh and Yanaka model. For this the misfit strain between coating and substrate was treated as an unknown parameter and was fitted to the beginning part of the underlying crack density – applied strain curves. The validity of the model was evaluated by comparing the results with fracture toughness values derived via micro-cantilever bending experiments. A good fit between the data could be observed for three out of four tested coatings. The limitations of the underlying analytical model are presented and discussed. The tested high entropy nitride coatings displayed a promising combination of high hardness and fracture toughness.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Fracture toughness; High entropy nitrides; In situ mechanical testing; Micro-cantilever testing; Tensile testing

In situ micro-cantilever tests to study fracture properties of NiAl single crystals - Iqbal, Farasat; Ast, Johannes; Göken, Mathias; Durst, Karsten (Acta Materialia, 2012)
In situ micro-cantilever tests were carried out to determine the anisotropic fracture toughness of NiAl single crystals. Notched micro-cantilever beams with a beam length of 8 extgreekmm, 1.5 extgreekmm thickness and 1.8 extgreekmm width were milled in so-called ``hard'' and ``soft'' orientations of NiAl using a focused ion beam. These cantilevers were loaded in situ with the help of a cantilever-based nanoindenter mounted inside a scanning electron microscope. A fracture toughness of 3.52 ± 0.29 MPa m1/2 was obtained for the ``soft'' orientation and 5.12 ± 0.50 MPa m1/2 for the ``hard'' orientation, which is in good agreement with literature values on the fracture toughness of macroscopic NiAl specimens. Furthermore, nanoindentations were performed for studying the size effects occurring at small length scales for both orientations. The applicability of the small sample geometries for testing the fracture toughness is finally discussed in terms of size effects in the flow stress of the material due to dislocation nucleation and strain gradients at the crack tip.
WW1::933

In-situ observation of dislocation dynamics near heterostructured interfaces - Zhou, Hao; Huang, Chongxiang; Sha, Xuechao; Xiao, Lirong; Ma, Xiaolong; Höppel, Heinz Werner; Göken, Mathias; Wu, Xiaolei; Ameyama, Kei; Han, Xiaodong; Zhu, Yuntian (Materials Research Letters, 2019)
There has been a long-standing controversy on how dislocations interact with interfaces. Here we report in-situ observations that in a Cu-brass heterostructured TEM film Frank-Read sources are the primary dislocation sources. They were dynamically formed and deactivated throughout the deformation in grain interior, which has never been reported before. This observation indicates that strain gradient near interfaces cannot be quantitatively related to the density gradient of geometrically necessary dislocations, and it was primarily produced by Frank-Read source gradient instead of dislocation pile-ups. These findings provide new insights on how to design heterostructured interfaces to enhance mechanical properties.
CRIS-Team WoS Importer:2019-06-28

In-situ observation of the initiation of plasticity by nucleation of prismatic dislocation loops - Lee, Subin; Vaid, Aviral; Im, Jiseong; Kim, Bongsoo; Prakash, Aruna; Guenole, Julien; Kiener, Daniel; Bitzek, Erik; Oh, Sang Ho (Nature Communications, 2020)
The elastic-to-plastic transition during the deformation of a dislocation-free nanoscale volume is accompanied by displacement bursts associated with dislocation nucleation. The dislocations that nucleate during the so-called “pop-in” burst take the form of prismatic dislocation loops (PDLs) and exhibit characteristic burst-like emission and plastic recovery. Here, we report the in-situ transmission electron microscopy (TEM) observation of the initial plasticity ensued by burst-like emission of PDLs on nanoindentation of dislocation-free Au nanowires. The in-situ TEM nanoindentation showed that the nucleation and subsequent cross slip of shear loop(s) are the rate-limiting steps. As the indentation size increases, the cross slip of shear loop becomes favored, resulting in a transition from PDLs to open half-loops to helical dislocations. In the present case of nanoindentation of dislocation-free volumes, the PDLs glide out of the indentation stress field while spreading the plastic zone, as opposed to the underlying assumption of the Nix-Gao model.
CRIS-Team Scopus Importer:2020-05-22

In-situ tensile testing of crystalline diamond coatings using Raman spectroscopy - Ahmed, Furqan; Durst, Karsten; Rosiwal, Stefan; Fandrey, Jan; Schaufler, Jens; Göken, Mathias (Surface & Coatings Technology, 2009)
In the present work, the fracture behaviour of crystalline diamond thin films on titanium substrate has been studied under uniaxial in-situ tensile loading in Micro-Raman spectroscopy. Thin crystalline diamond films were deposited onto thin titanium foils using a hot filament chemical vapour deposition technique. The in-situ investigations in Raman spectroscope indicated that the internal stresses, which were compressive at the beginning, can be reduced by the application of tensile load. At higher strain values, when internal stresses were of tensile nature, cracks were formed in the coating with reduced crack spacing at higher strains and also the tensile stress stayed constant during cracking. Cross-section analyses, across tensile cracks, with a focused ion beam microscopy showed that the crack starts from the surface of the coating, then propagates into the interlayer, stops at the surface of the metallic substrate and opens up on further straining without delamination. This cracking behaviour indicates a good adhesion of the coating to the substrat

In situ X-ray tomography investigation of the crack formation in an intermetallic beta-stabilized TiAl-alloy during a stepwise tensile loading - Löffl, Ch; Saage, H.; Göken, Mathias (International Journal of Fatigue, 2019)
The impact of high temperature exposure on the mechanical damage behavior of the intermetallic TiAl alloy TNM has been investigated by means of high resolution laboratory computer tomography (CT). An in situ testing device was adapted allowing the study of cracking behavior during tensile testing of unnotched samples by CT. Accordingly, failure of exposed and unexposed samples is controlled by the fracture toughness. Unexposed samples reveal crack formation in the interior at only about 1/3 of their plastic elongation to failure. These internal cracks grow gradually with increasing nominal stress and are subjected to significant crack deflection by the microstructure until the crack growth accelerates and the samples fail. After exposure for 1 h at 800 °C cracks originate in the surface region of the samples at almost the same nominal stresses at which internal cracks first appear. However, due to higher fracture mechanical geometry factor, surface cracks become critical almost instantly after their formation resulting in a reduced ductility, which is known as environmental embrittlement in literature. It is supposed that crack formation at the surface after exposure is the result of stress concentrations which are built-up during plastic deformation due to interstitials in the surface layer.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Crack propagation; Environmental effects; In situ X-ray tomography; Titanium aluminides

Instantaneous healing of micro-fractures during coseismic slip: Evidence from microstructure and Ti in quartz geochemistry within an exhumed pseudotachylyte-bearing fault in tonalite - Bestmann, Michel; Pennacchioni, Giorgio; Mostefaoui, Smail; Göken, Mathias; de Wall, Helga (Lithos, 2016)
Exhumed faults within the tonalitic Adamello pluton (Southern Alps) were seismic at depth as indicated by the presence of pseudotachylytes (solidified friction-induced melts). During cooling of tonalite, early-formed joints were first exploited by localized ductile shear zones associated with deposition of quartz veins (at similar to 500 degrees C), and later by pseudotachylyte-bearing cataclastic faults (at similar to 250-300 degrees C ambient temperature). Adjacent to pseudotachylytes, quartz of the host tonalite shows pervasive thin (1-10 mu m wide) healed micro-fractures and ultra-fine (1-2 mu m grain size) recrystallized aggregates along micro-shear zones. Under cathodoluminescence (CL) the healed micro-fractures have a darker gray shade than the host "magmatic" quartz that reflects a change in Ti concentrations ( [Ti]) as indicated by NanoSIMS measurements. [Ti] vary from 35-55 ppm in the CL-lighter host quartz to 10-13 ppm along the CL-darker healed micro-fractures. These [Ti] were inherited by the ultra-fine recrystallized aggregates that overprinted both the magmatic quartz and the healed micro-fractures during the high temperature transient related to frictional seismic slip. Based on Ti-in-quartz thermometry, we infer that micro-fracture healing occurred at higher temperatures than the ambient temperatures of faulting (250-300 degrees C at 0.2 GPa), for which [Ti] <1 ppm would be expected. Micro-fracture healing can be ascribed to the stage of seismic slip of faults on the basis of the observation that: (i) they are absent in the host rock surrounding high-T quartz veins un-exploited by faults; and (ii) they locally occur at the tip of pseudotachylyte injection veins filling new fractures developed during the propagation of the earthquake rupture. The relatively high [Ti] of micro-fractures are therefore interpreted to reflect quartz healing by a fluid overheated during the initial stages of frictional seismic slip and escaping from fault surface through the damage zone. This suggests that, in the presence of fluids, thermal pressurization of the fault did not occur and did not prevent frictional melting. The small-scale microstructures and geochemistry of quartz in the wall of the studied paleo-seismic fault record a complex deformational history, referable to the short-lived (on the order of 10(4) s) thermal anomaly induced by frictional seismic slip, that includes both micro-fracture healing and recrystallization. This microstructural assemblage of the natural exhumed fault provides a key for understanding the mechanics of an earthquake source. (c) 2016 Elsevier B.V. All rights reserved.
Keywords: Titanium in quartz; Cathodoluminescence; Quartz deformation; Pseudotachylyte; NanoSIMS; Micro-fracturing

Instantiations of Multiscale Kinship in Pressing‐Defect Distributions in Yttria‐Stabilized Zirconias by Powder Partitioning - Pereira, Raíssa Monteiro; Lohbauer, Ulrich; Schulbert, Christian; Göken, Mathias; Wurmshuber, Michael; Campos, Tiago Bastos Moreira; Thim, Gilmar Patrocínio; Mieller, Björn; Belli, Renan (Advanced Engineering Materials, 2024)
Modern dry pressing of ceramic powders using spray-dried granulates cannot avoid the occurrence of defects related to persisting inter- and intra-granulate interstitial voids. These constitute the parent defect size population limiting the application of polycrystalline ceramics in high-stress conditions. The mitigation of such defects could widen the range of application in technical and biomedical engineering, reduce the safety range for design, and extend the lifetime of components. Herein, the Weibull size-effect on strength in size-partitioned Yttria-stabilized zirconias (YSZ) feedstocks is used to explore the viability of changing the density distribution of granulate sizes as an effective strategy to obtain a denser particle packing that could reduce the size distribution of strength-limiting pressing defects. In a direct assessment of critical defect size using multiscale strength testing with a dataset of ≈1300 values, the success of such an approach in increasing the strength reliability for small volume components is demonstrated, along with its ultimate failure in altering the defect size distribution in sintered YSZ ceramics across several length scales. Finally, it is shown that granule morphology (spherical or dimpled) fails to affect the defect density and size distribution in YSZ ceramics.<br
Keywords: powder processing; pressing defects; strength; Weibull statistics; zirconia ceramics

Instantiations of Multiscale Kinship in Pressing‐Defect Distributions in Yttria‐Stabilized Zirconias by Powder Partitioning - Pereira, Raíssa Monteiro; Lohbauer, Ulrich; Schulbert, Christian; Göken, Mathias; Wurmshuber, Michael; Campos, Tiago Bastos Moreira; Thim, Gilmar Patrocínio; Mieller, Björn; Belli, Renan (Advanced Engineering Materials, 2024)
Modern dry pressing of ceramic powders using spray-dried granulates cannot avoid the occurrence of defects related to persisting inter- and intra-granulate interstitial voids. These constitute the parent defect size population limiting the application of polycrystalline ceramics in high-stress conditions. The mitigation of such defects could widen the range of application in technical and biomedical engineering, reduce the safety range for design, and extend the lifetime of components. Herein, the Weibull size-effect on strength in size-partitioned Yttria-stabilized zirconias (YSZ) feedstocks is used to explore the viability of changing the density distribution of granulate sizes as an effective strategy to obtain a denser particle packing that could reduce the size distribution of strength-limiting pressing defects. In a direct assessment of critical defect size using multiscale strength testing with a dataset of ≈1300 values, the success of such an approach in increasing the strength reliability for small volume components is demonstrated, along with its ultimate failure in altering the defect size distribution in sintered YSZ ceramics across several length scales. Finally, it is shown that granule morphology (spherical or dimpled) fails to affect the defect density and size distribution in YSZ ceramics.<br

Interaction and passing stress of two threading dislocations of opposite sign in a confined channel - Schwarz, K. W.; Mughrabi, Hael (Philosophical Magazine Letters, 2006)
The binding and unbinding of two threading dislocations in a channel of width d is considered in the context of the persistent slip band (PSB) problem. It is shown that previous analytical estimates of the overall passing stress between two screw-like threading arms have only qualitative validity. In particular, earlier treatments do not recognize the importance of bowing corrections in all limits, and neglect the effects of the opposing dislocation's misfit arms on the passing stress. As an alternative, accurate numerical escape functions are presented for the case of d∈=∈1∈μm, in a form suitable for approximate scaling to other values of d. Although the numerical prediction for the overall passing stress is in good agreement with experimental values of the flow stress observed in the presence of PSBs, we argue that this in fact represents a disagreement, since it is well known that the flow stress in the soft-channel parts of the inhomogeneous PSB structure is reduced by long-range internal back stresses to values significantly below the average macroscopic flow stress of the PSB structure. We suggest that a statistical treatment including the effects of annihilation and of dislocations interacting over a range of separations can account for the discrepancy.
Created from Fastlane, Scopus look-up

Interdiffusion Coefficients and Strengthening Effects of Nb, Ta, and Zr in the α2-Ti3Al Phase - Haußmann, Lukas; Bresler, Johannes; Neumeier, Steffen; Pyczak, F.; Göken, Mathias (Journal of Phase Equilibria and Diffusion, 2024)
The creep properties of fully lamellar γ/α2 titanium aluminides can be significantly improved by alloying with Nb, Ta or Zr. While the influence of these alloying elements on the γ-phase has already been examined, their diffusivity and strengthening properties in the α2-phase are still lacking. In order to study the effect of Nb, Ta and Zr in α2-Ti3Al, the alloys Ti-33Al, Ti-33Al-5Nb, Ti-33Al-5Ta and Ti-33Al-5Zr were investigated using a diffusion couple approach and strain rate jump tests. The results show that Zr diffuses the fastest, followed by Nb and Ta. Furthermore, these alloying elements also increase the strength compared to a binary Ti-33Al alloy, from which Zr leads to the highest strength increase followed by Ta and Nb. The lower diffusivity of Ta becomes increasingly important at higher temperatures and lower strain rates resulting in a higher strengthening potential than Nb and Zr under such conditions.
CRIS-Team Scopus Importer:2024-04-26
Keywords: alloying elements; diffusion; solid solution; strain rate jump test; Ti; titanium aluminides; α

Interface affected zone for optimal strength and ductility in heterogeneous laminate - Huang, C. X.; Wang, Y. F.; Ma, X. L.; Yin, S.; Höppel, Heinz Werner; Göken, Mathias; Wu, X. L.; Gao, H. J.; Zhu, Y. T. (Materials Today, 2018)
Interfaces have been reported to significantly strengthen and toughen metallic materials. However, there has been a long-standing question on whether interface-affected-zone (IAZ) exists, and how it might behave. Here we report in situ high-resolution strain mapping near interfaces in a copper-bronze heterogeneous laminate, which revealed the existence of IAZs. Defined as the zone with strain gradient, the IAZ was found to form by the dislocations emitted from the interface. The IAZ width remained largely constant with a magnitude of a few micrometers with increasing applied strain. Interfaces produced both back stress strengthening and work hardening, which led to both higher strength and higher ductility with decreasing interface spacing until adjacent IAZs started to overlap, after which a tradeoff between strength and ductility occurred, indicating the existence of an optimum interface spacing for the best mechanical properties. These findings are expected to help with designing laminates and other heterogeneous metals and alloys for superior mechanical properties.

Intermediate Co/Ni-base model superalloys - Thermophysical properties, creep and oxidation - Zenk, Christopher; Neumeier, Steffen; Engl, Nicole; Fries, Suzana G.; Dolotko, Oleksandr; Weiser, Martin; Virtanen, Sannakaisa; Göken, Mathias (Scripta Materialia, 2016)
The mechanical properties of gamma'-strengthened Co-Ni-Al-W-Cr model superalloys extending from pure Ni-base to pure Co-base superalloys have been assessed. Differential scanning calorimetry measurements and thermodynamic calculations match well and show that the gamma' solvus temperature decreases with increasing Co-content The gamma/gamma' lattice misfit is negative on the Ni- and positive on the Co-rich side. High Ni-contents decelerate the oxidation kinetics up to a factor of 15. The creep strength of the Ni-base alloy increases by an order of magnitude with additions of Co before it deteriorates strongly upon higher additions despite an increasing gamma' volume fraction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Cobalt; Nickel; Superalloy; Creep; Neutron diffraction

Interpreting Atom Probe Data from Oxide-Metal Interfaces - Mccarroll, Ingrid; Scherrer, Barbara; Felfer, Peter; Moody, Michael P.; Cairney, Julie M. (Microscopy and Microanalysis, 2018)
Understanding oxide-metal interfaces is crucial to the advancement of materials and components for many industries, most notably for semiconductor devices and power generation. Atom probe tomography provides three-dimensional, atomic scale information about chemical composition, making it an excellent technique for interface analysis. However, difficulties arise when analyzing interfacial regions due to trajectory aberrations, such as local magnification, and reconstruction artifacts. Correlative microscopy and field simulation techniques have revealed that nonuniform evolution of the tip geometry, caused by heterogeneous field evaporation, is partly responsible for these artifacts. Here we attempt to understand these trajectory artifacts through a study of the local evaporation field conditions. With a better understanding of the local evaporation field, it may be possible to account for some of the local magnification effects during the reconstruction process, eliminating these artifacts before data analysis.
Keywords: atom probe tomography/APT; reconstruction; interface analysis; high field evaporation

Intrinsic and extrinsic size effects in the deformation of amorphous CuZr/nanocrystalline Cu nanolaminates - Guo, Wei; Jaegle, Eric; Yao, Jiahao; Maier, Verena; Korte, Sandra; Schneider, Jochen M.; Raabe, Dierk (Acta Materialia, 2014)
Introducing a soft crystalline phase into an amorphous alloy can promote the compound's ductility. Here we synthesized multilayered nanolaminates consisting of alternating amorphous Cu54Zr46 and nanocrystalline Cu layers. The Cu layer thickness was systematically varied in different samples. Mechanical loading was imposed by nanoindentation and micropillar compression. Increasing the Cu layer thickness from 10 to 100 am led to a transition from sharp, cross-phase shear banding to gradual bending and co-deformation of the two layer types (amorphous/nanocrystalline). Specimens with a sequence of 100 nm amorphous Cu54Zr46 and 50 nm Cu layers show a compressive flow stress of 2.57 +/- 0.21 GPa, matching the strength of pure CuZr metallic glass, hence exceeding the linear rule of mixtures. In pillar compression, 40% strain without fracture was achieved by the suppression of percolative shear band propagation. The results show that inserting a ductile nanocrystalline phase into a metallic glass prevents catastrophic shear banding. The mechanical response of such nanolaminates can be tuned by adjusting the layer thickness. (C) 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Nanolaminates; Metallic glass; Nanotwins; Shear band

Investigation into the influence of the interlayer temperature on machinability and microstructure of additively manufactured Ti-6Al-4V - Fuchs, Christina; Elitzer, Daniel; Höppel, Heinz Werner; Göken, Mathias; Zaeh, Michael F. (Production Engineering, 2023)
The capability of wire and arc additive manufacturing (WAAM) to produce large, near-net-shaped parts with inexpensive equipment has led to the process being considered as one of the options to significantly decrease the buy-to-fly ratio in aircraft manufacture. Even so, there are several challenges associated with the process: achieving mechanical properties and microstructure similar to wrought material, as well as the low surface quality of the parts. The low surface quality is usually improved by milling. As with the microstructure, here too the question arises as to whether the process is comparable to milling wrought material. A significant factor influencing the microstructure according to literature is the interlayer temperature during the WAAM process. Therefore, the objective of this research was to study the influence of the interlayer temperature on the machinability and the microstructure of wire and arc additively manufactured Ti-6Al-4V. Consequently, the machinability was first determined for Ti-Al6-V4-parts manufactured with three different interlayer temperatures. Then, the macro- and microstructures were analyzed and, finally, the mechanical properties were determined. Contrary to expectations based on the state of the art, the machinability was not influenced by the interlayer temperature. This aligns with the mechanical properties and the macro- and microstructures, which are only slightly affected by the interlayer temperature.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Interlayer temperature; Microstructure; Milling; WAAM

Investigation of the deformation behavior of aluminum micropillars produced by focused ion beam machining using Ga and Xe ions - Xiao, Y.; Wehrs, J.; Ma, Huan; Al-Samman, Talal; Korte-Kerzel, Sandra; Göken, Mathias; Michler, Johann; Spolenak, R.; Wheeler, J. M. (Scripta Materialia, 2017)
Sample geometries for micro-mechanical testing, e.g. micro-pillars and micro-cantilevers are primarily produced using gallium focused ion beam technology. However, the effects of the gallium ions on the mechanical properties of metals which are embrittled by liquid metal gallium are still unknown. In this work, micro-compression samples from single crystalline and ultrafine-grained aluminum are fabricated using both xenon and/or gallium ions. The different ions have little effect on the yield strength of single crystalline aluminum. However, for the ultrafine-grained aluminum, the strength is reduced with increasing Ga dose, and considerable differences in the deformation morphology and resulting microstructures are observed. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Ultrafine-grained aluminum; Focused ion beam; Micro-compression; Gallium

Investigation of the final stages of solidification and eutectic phase formation in Re and Ru containing nickel-base superalloys - Heckl, Astrid; Rettig, Ralf; Cenanovic, S.; Göken, Mathias; Singer, Robert (Journal of Crystal Growth, 2010)
The microstructure resulting from the final stages of solidification-commonly referred to as eutectic islands-has been analysed in detail for three nickel-base superalloys containing Re and Ru. Focused ion beam 3-D reconstruction and EBSD-analysis were used to clarify the origin of different eutectic structure types. One common type of parent 3-D eutectic structure was identified. The solidification process of the final solidifying liquid has been further investigated by electron probe microanalysis mappings along with DICTRA simulations. Two models for diffusion controlled phase transformations are shown to present a fair description of the solidification sequence. (C) 2010 Elsevier B.V. All rights reserve
Keywords: Final stage solidification; Microsegregation; 3-D microstructure; Eutectic island; FIB tomography; Nickel-base superalloys

Investigation of the Hot Deformation Behavior in VDM® Alloy 780 by In Situ High-Energy X-Ray Diffraction - Fritton, Massimo; Kümmel, Frank; Kirchmayer, Andreas; Stark, Andreas; Hafez Haghighat, Masood; Gehrmann, Bodo; Neumeier, Steffen; Gilles, Ralph (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
Ni-based superalloys are indispensable for applications in demanding environments, such as the heavily stressed rotating discs in the hot sections of modern gas turbines or jet engines. In this paper, the microstructure evolution during hot deformation to mimic the forging process was investigated in the polycrystalline VDM® Alloy 780 viain situ X-ray diffraction at temperatures of 950, 1000, and 1050 °C. For the tested temperatures, the hot forming led to subgrain formation, the built-up of a texture by rotation of the matrix grains into preferred orientations, and dynamic recrystallization. The influence of the deformation was analyzed depending on the direction of the lattice plane normals to the load direction, for the first five γ-reflections in the diffraction pattern. During uniaxial compressive deformation intensity, maxima develop in the loading direction solely for the γ-(220) reflections, while intensity minima develop for the other reflections which correspond to the formation of a <110> fiber texture. In the transverse direction, all γ-reflections except the (220) have an increased intensity at the maximum specimen strain of 20 pct. Directly after the hot forming, three different cooling rates of 10, 100, and 1000 °C/min and their influence on the microstructure were investigated. The fast and medium cooling rates lead to low recrystallized fractions and a largely preserved deformation texture, whereas the low cooling rate leads to a high recrystallized fraction and a slight remaining texture. Additionally, the diffraction data are complemented by electron microscopy measurements.
CRIS-Team Scopus Importer:2023-01-27

Investigation of the run-in and corrosion behavior of a PEO-coated aluminum brake disc - Gulden, Florian; Reinhold, B.; Gramstat, S.; Stich, A.; Tetzlaff, U.; Höppel, Heinz Werner (10TH INTERNATIONAL MUNICH CHASSIS SYMPOSIUM 2019 (CHASSIS.TECH PLUS), 2020)
CRIS-Team WoS Importer:2020-12-04

Investigation of the sliding contact properties of WC-Co hard metals using nanoscratch testing - Ndlovu, Siphilisiwe; Durst, Karsten; Göken, Mathias (Wear, 2007)
Nanoscratch tests were performed on a range of WC-Co hard metals with varying cobalt content and WC grain size using a Nanoindenter XP. Single and multiscratch tests were conducted with various loads. The scratch friction coefficient for all the samples was found to be approximately 0.4 and was observed to fluctuate due to the hard and ductile phases in the material. The scratch width and depth were found to increase with increasing load for single scratches. Multiscratching with a constant load resulted in the widening and deepening of the scratches at each load with accumulative damage occurring as more tests were performed. Damage was mainly attributed to a brittle mechanism occurring via the formation and interaction of subsurface cracks and the deformation of WC grains via slip. A deformed layer was formed on the surface of several of the hard metals during multiscratching and this was found to contain WC fragments which were formed during testing. Cobalt extrusion also took place and in the case of the 6 and 6.5% cobalt samples, led to the subsequent loss of loosely anchored WC grains. The scratch depth and width were found to increase linearly with load with more severe grain fracture taking place as the load increased. © 2007 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Multiscratch; Nanoindenter; Nanoscratch; Scratch friction coefficient; Slip

Investigation on the tribological-mechanical behavior of amorphous carbon coatings by load-scanning tests - Hetzner, Harald; Schaufler, Jens; Pejic, Goran; Tremmel, Stephan; Durst, Karsten; Wartzack, Sandro (Materialwissenschaft und Werkstofftechnik, 2012)
Amorphous carbon coatings have a beneficial tribological behaviour since they provide low friction even under dry sliding conditions and at the same time they offer a good wear protection. Under high loads, the applicability of state-of-the-art amorphous carbon coatings is limited by mechanical failure. However, there is still little knowledge concerning the precise failure mechanisms under application-oriented conditions. In the present study, cylindrical specimens of a cold work tool steel were coated with two commercial amorphous carbon coating systems: a WCC coating with an a-C:H:W top layer and a DLC coating which architecture is based on that of the WCC coating, but contains an additional a-C:H top layer. The coated specimens were tested on a load-scanning test rig in dry sliding contact against uncoated specimens of the same steel substrate. In the tests, the specimens were loaded with a normal force in the range of 13 and 350 N, corresponding to a maximum contact pressure of 1 to 3 GPa. The number of load cycles was varied between 1 and 60. Firstly, the load-dependent friction behaviour was monitored. Secondly, the tests were stopped at different total cycle numbers allowing for an evaluation of the progress of wear and damage by scanning electron microscopy. For both coating systems, adhesive pick-up of counter body steel was observed prior to mechanical failure. Whilst the WCC coating system showed first indications of local failure after several load cycles and at contact pressures exceeding 2 GPa, the DLC coating system showed catastrophic failure on a global scale only after few load cycles and over the whole investigated load range.
EAM Import::2019-03-13

Isolating the effect of residual stresses on coating wear by a mechanical stress relaxation technique - Vierneusel, Bernd; Benker, Lisa; Tremmel, Stephan; Göken, Mathias; Merle, Benoit (Thin Solid Films, 2017)
Residual stresses play an essential role for the tribological performance of sputtered coatings since compressive residual stresses yield positive effects on wear resistance. As deposition induced residual stresses are always related to the coating microstructure, a combination of different effects is typically assessed if coatings are validated by tribological testing. Therefore, the real effect of residual stresses on the tribological performance of coatings is not entirely clear. The study aims to examine this issue by isolating the residual stress effect from the microstructural impact by mechanical relaxation of the coating after the deposition process. For this purpose, MoS2 coated substrates are mechanically pre-stretched during the coating process and relaxed again afterwards in order to reduce the coating's macroscopic residual stresses. Other samples, which are not pre-stretched but coated inside the same process with identical distance to the target, serve as a reference material. The proper function of the relaxation technique is demonstrated by applying a recently developed method for residual stress measurement, namely the “Focused Ion Beam – Digital Image Correlation” method. Both samples, the relaxed and as-deposited one, were subjected to a tribological pin-on-disk test. The results show that at high compressive residual stress levels, only mild wear at the upper surface inside the contact area occurs. In contrast, at low compressive residual stress levels, wear results from an abrasive material removal inside the contact track but most significantly from additional coating detachments outside the contact area. The observations can be related, firstly, to a superimposition of harmful bending stresses and beneficial compressive residual stresses beneath the contact area and, secondly, to a stress relaxation effect taking place only inside the tribological contact zone. In summary, owing to the developed stress relaxation technique, a microstructurally independent effect of residual stresses on wear resistance of sputtered MoS2-coatings has been prove
Keywords: Residual stress; Wear; MoS2; Sputtering; Relaxation

Isothermal aging of a γ′-strengthened Co-Al-W alloy coated with vacuum plasma-sprayed MCrAlY bond coats - Terberger, Philipp J.; Sebold, Doris; Webler, Ralf; Ziener, Marco; Neumeier, Steffen; Klein, Leonhard; Virtanen, Sannakaisa; Göken, Mathias; Vassen, Robert (Surface & Coatings Technology, 2015)
WW1::1049
Keywords: High Temperature

JMR early career scholars in materials science annual issue - Messing, Gary L.; Bose, Susmita; Göken, Mathias; Morgan, Sarah E. (Journal of Materials Research, 2022)
CRIS-Team Scopus Importer:2022-01-14

Large chamber scanning electron microscopes: Challenges and Aspects for Materials Science - Göken, Mathias; Höppel, Heinz Werner; et al. (Imaging & Microscopy, 2004)
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.largec

Laser Droplet Brazing for Electrical Contacting of Composite Materials with Integrated Active Elements - Quentin, Ulf-Hermann; Heberle, Johannes; Held, Carolin Constanze; Schmidt, Michael (Procedia Materials Science, 2013)
To be used as actuators or sensors, piezoceramic components have to be electronically contacted. A temperature stable connection can be achieved with brazing techniques. Since piezoceramics are susceptible to damage by high temperatures and temperature gradients, it is important to control the energy input in the brazing process. Therefore, we use a laser droplet brazing method which allows for precise contacting of piezoceramics and avoids thermal damage. The influence of the laser parameters on the brazing process and the contacting accuracy is presented in this pape
Keywords: Laser brazing; Electrical contacting

Laser Droplet Brazing for the Electrical Contacting of Composite Materials with Integrated Active Elements - Held, Carolin Constanze; Quentin, Ulf-Hermann; Heberle, Johannes; Gürtler, Franz-Josef; Weigl, Markus; Schmidt, Michael (Physics Procedia, 2012)
This paper describes a laser droplet brazing method for electrical contacting of sensitive piezoceramic actuator modules. In order to increase the reproducibility of the contacting process, the mass, the energy and the flight path of the braze droplets have to be controlled. For this reason, braze preforms are used which are molten by a single laser pulse. The system technology and first results will be presented, as well as a mechanical and metallurgical analysis of the brazed connection
Keywords: Laser brazing; Piezoceramic actuators; Electrical contacting

Laser-equipped gas reaction chamber for probing environmentally sensitive materials at near atomic scale - Khanchandani, Heena; El-Zoka, Ayman A.; Kim, Se-Ho; Tezins, Uwe; Vogel, Dirk; Sturm, Andreas; Raabe, Dierk; Gault, Baptiste; Stephenson, Leigh T. (PLoS ONE, 2022)

Laser powder bed fusion of FeCoBSiNb-Cu bulk metallic glass composites: Processing, microstructure and mechanical properties - Luo, Ning; Huber, Florian; Ciftci, Nevaf; Wahl, Larissa; Bezold, Andreas; Neumeier, Steffen; Uhlenwinkel, Volker; Travitzky, Nahum; Schmidt, Michael; Zenk, Christopher; Körner, Carolin (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
Fe–Co–B–Si–Nb bulk metallic glasses are prone to the formation of micro-cracks during laser powder bed fusion (LPBF) additive manufacturing. Introducing ductile Cu into Fe–Co–B–Si–Nb bulk metallic glass alloy system rich with Fe and Co could be a promising solution to reduce or even eliminate micro-cracks since there is almost no miscibility of Cu in Fe and Co. In this work, processing, microstructure and mechanical properties of Cu-containing (Fe0.6Co0.4)0.75B0.2Si0.0596Nb4 (at.%) bulk metallic glass composites (BMGCs) under different laser power and scanning speed by LPBF are investigated in detail. A moderate area energy density facilitates the fabrication of highly dense (relative density: up to ∼99.5%) and almost crack-free (crack density: ∼0.1 mm−1) FeCoBSiNb–Cu bulk samples. These bulk samples possess an interpenetrating composite microstructure mainly composed of an amorphous Fe(Co)-rich phase and a crystalline Cu-rich phase. A crystalline Cu-rich phase is distributed relatively homogeneously in an amorphous phase and helps to reduce and even eliminate micro-crack formation during LPBF processing. Also, the Cu-rich phase has the effect of a heat sink and thus speeds up heat dissipation, facilitating the formation of an amorphous phase. The microhardness of the ductile Cu-rich phase and the hard amorphous Fe(Co)-rich phase in the interpenetrating composite microstructure was evaluated. Compressive tests at room temperature indicate that the dense bulk samples exhibit a relatively high fracture strength and a large fracture strain. Additionally, bulk samples with lack-of-fusion pores show a larger fracture strain although their fracture strength is lower than that of dense bulk samples. It is concluded that the LPBF-processed FeCoBSiNb–Cu BMGCs constitute a promising wear-resistant material to be used for example as bearing materials.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Bulk metallic glass composites; Fe-based amorphous alloy; Laser powder bed fusion; Mechanical properties; Microstructure; Solidification

Lattice misfit of high refractory ruthenium containing nickel-base superalloys - Neumeier, Steffen; et al. (Advanced Materials Research, 2011)
The influence of Ru, Co, Mo and W on the lattice misfit of eight highly alloyed Re containing single crystal nickel-base superalloys was investigated. High resolution X-ray diffraction (XRD) was used to relate the elemental partitioning behavior and the Vegard coefficients of the elements under investigation to the measured lattice parameter of the gamma and gamma' phase. The residual chemical segregation and especially the coherency stress-induced tetragonal distortion of the gamma matrix lattice in the high Mo containing alloys results in the observation of two different lattice parameters for the gamma matrix phase. This leads to three overlapping, but clearly distinguishable 002 X-ray reflections.
Keywords: Lattice misfit; X-ray diffraction; Ni-base superalloys; Ruthenium

Laves phase crystal analysis (LaCA): Atomistic identification of lattice defects in C14 and C15 topologically close-packed phases - Xie, Zhuocheng; Chauraud, Dimitri; Bitzek, Erik; Korte-Kerzel, Sandra; Guénolé, Julien (Journal of Materials Research, 2021)
Abstract: The identification of defects in crystal structures is crucial for the analysis of atomistic simulations. Many methods to characterize defects that are based on the classification of local atomic arrangement are available for simple crystalline structures. However, there is currently no method to identify both, the crystal structures and internal defects of topologically close-packed (TCP) phases such as Laves phases. We propose a new method, Laves phase crystal analysis (LaCA), to characterize the atomic arrangement in Laves crystals by interweaving existing structural analysis algorithms. The new method can identify the polytypes C14 and C15 of Laves phases, typical crystallographic defects in these phases, and common deformation mechanisms such as synchroshear and non-basal dislocations. Defects in the C36 Laves phase are detectable through deviations from the periodic arrangement of the C14 and C15 structures that make up this phase. LaCA is robust and extendable to other TCP phases. Graphic abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-05-28

Layer architecture and fatigue life of ultrafine-grained laminated metal composites consisting of different aluminum alloys - Kümmel, Frank; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2017)
The influence of the layer architecture on the fatigue properties of ultrafine-grained laminated metal composites is studied. Composites with different stacking sequences of the aluminum alloys AA1050, AA5005, and AA2024 were produced by accumulative roll bonding and characterized by microstructural analysis and nanoindentation experiments. The fatigue properties were determined by 3-point bending tests performed on a vibraphore testing machine. Subsequently, the crack path was analyzed using a scanning electron microscope. It was observed that the fatigue crack bifurcates close to the interface if the hardness difference between both materials is high. The crack then spreads parallel to the interface within the softer material. This crack branching is more pronounced at high stress amplitudes caused by a significant accumulation of plastic deformation in front of the interface. Consequently, at high stress amplitudes the fatigue lives are significantly higher for composites with a high hardness difference between the layers. At low stress amplitudes, at which crack initiation is the dominating fatigue mechanism, the material of the outer layer mainly determines the fatigue lives. Composites with the same outer layer, but different interlayers, show very similar high cycle fatigue lives. Thus, by an appropriate layer architecture ultrafine-grained laminated metal composites with significantly enhanced fatigue properties can be designed.
Keywords: Accumulative Roll Bonding (ARB); Ultrafine-grained (UFG) laminated metal composites (LMCs); Fatigue life; Fatigue crack path

Life prediction of thermally highly loaded components: Modelling the damage process of a rocket combustion chamber hot wall - Schwarz, W.; Schwub, Sigrid; Quering, K.; Wiedmann, D.; Höppel, Heinz Werner; Göken, Mathias (CEAS Space Journal, 2011)
WW1::885

Limpet teeth microstructure unites auxeticity with extreme strength and high stiffness - Oh, Sang Ho; Kim, Jin-Kyung; Liu, Yue; Wurmshuber, Michael; Peng, Xiang-Long; Seo, Jinsol; Jeong, Jiwon; Wang, Zhen; Wilmers, Jana; Soyarslan, Celal; Kim, Jongil; Kittiwirayanon, Boonsita; et al. (Science Advances, 2022)

Linking stress-driven microstructural evolution in nanocrystalline aluminium with grain boundary doping of oxygen - He, Mo-Rigen; Samudrala, Saritha K.; Kim, Gyuseok; Felfer, Peter; Breen, Andrew J.; Cairney, Julie M.; Gianola, Daniel S. (Nature Communications, 2016)
The large fraction of material residing at grain boundaries in nanocrystalline metals and alloys is responsible for their ultrahigh strength, but also undesirable microstructural instability under thermal and mechanical loads. However, the underlying mechanism of stress-driven microstructural evolution is still poorly understood and precludes rational alloy design. Here we combine quantitative in situ electron microscopy with three-dimensional atom-probe tomography to directly link the mechanics and kinetics of grain boundary migration in nanocrystalline Al films with the excess of O atoms at the boundaries. Site-specific nanoindentation leads to grain growth that is retarded by impurities, and enables quantification of the critical stress for the onset of grain boundary migration. Our results show that a critical excess of impurities is required to stabilize interfaces in nanocrystalline materials against mechanical driving forces, providing new insights to guide control of deformation mechanisms and tailoring of mechanical properties apart from grain size alon

Linking through-thickness cracks in metallic thin films to in-situ electrical resistance peak broadening - Gebhart, David D.; Krapf, Anna; Gammer, Christoph; Merle, Benoit; Cordill, Megan J. (Scripta Materialia, 2022)
Measurements of electrical resistance have been used extensively as a failure criterion in cyclically loaded conductive films. However, not much research has been performed on extracting additional information contained within such resistance data sets. This study shows that an increase in peak width evidences a transition from cracks bridging to through-thickness crack formation. A Au/Cr bilayer system on a polyimide substrate is used for data generation but the method is applicable to any material system where both necking and through-thickness cracks are formed and no immediate formation of electrically insulating oxide layers occurs upon damage initiation. The method is easy to implement, and has the ability to replace time-intensive and destructive inspection methods.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Electrical resistivity; Fatigue; Nanocrystalline metal; Thin films; Through-thickness cracks

Local Fracture Toughness and Residual Stress Measurements on NiAl Bond Coats by Micro Cantilever and FIB Based Bar Milling Tests - Göken, Mathias; Webler, Ralf; Krottenthaler, Markus; Neumeier, Steffen; Durst, Karsten (John Wiley and Sons, 2012)
Keywords: Bond coat; Fracture toughness; FIB; Nanoindentation; Micro cantilever; Residual stress; NiAl; Thermal cycling

Local fracture toughness and residual stress measurements on NiAl bond coats by micro cantilever and fib-based bar milling tests - Neumeier, Steffen; Webler, Ralf; Krottenthaler, Markus; Durst, Karsten; Göken, Mathias (12th International Symposium on Superalloys, Superalloys 2012, 2012)
The mechanical behavior of bond coats depends on their chemical composition. Important for the mechanical behavior is the Al content of β-NiAl based coatings. Additionally, internal stresses are present and change during thermal cycling. Therefore bond coats with different Ni and Al content in the as-coated and thermally cycled state are investigated. For the first time, new small scaled methods are used to obtain fracture toughness and internal stresses of real bond coat systems. Micro cantilever bending and stress relaxation tests were performed on a local scale by employing focused ion beam milling. Additionally, the influence of NiAl composition on Young's modulus and hardness is studied by nanoindentation. Results show an increase of Young's modulus with Al content. In off-stoichiometric NiAl a higher hardness and fracture toughness than in binary NiAl is found. The internal stresses change from tensile in as-coated to compressive stresses in thermally cycled bond coats, respectively.
Keywords: Bond coat; FIB; Fracture toughness; Micro cantilever; Nanoindentation; NiAl; Residual stress; Thermal cycling

Local Heat Transfer and Interdependency of Piston Material, Spray and Combustion in High Power Diesel Engines - Weiß, Lukas; Wensing, Michael; Engl, Nicole; Siegel, Florian; Tilinski, Marco; Zülow, Daniel; Passily, Laetitia (Workshop ENCOM 2019, Waischenfeld, 16./17.10.2019, 2019)
Durch steigende spezifische Leistungen von Dieselmotoren werden die Kolbenwerkstoffe immer stärker belastet. Lokale thermomechanische Überlastungen führen zu Schadensbildern, die mit bisherigen Auslegungsverfahren nicht erfasst werden. Ziel war die Analyse der relevanten Schädigungsmechanismen, eine quantitative Beschreibung des Wandwärmeübergangs (lokal, zeitlich aufgelöst) zum Kolben, dessen Auswirkung im Kolbenmaterial sowie die Rückwirkung der heißen Kolbenoberfläche auf die Gemischbildung, Zündung und wandnahe Verbrennung. Das BFS geförderte Projekt untersuchte die werkstoffwissenschaftlichen und motorischen Wirkzusammenhänge. Anhand der Materialuntersuchungen am AlSi-Kolbenwerkstoff konnte der dominierende Schädigungsmechanismus am Muldenrand identifiziert werden. Darauf aufbauend wurden weitere Materialsysteme untersucht. Belastungstests wurden sowohl im Labor wie am Vollmotor durchgeführt, auch Kolben aus Feldversuchen wurden herangezogen. Auf motorischer Seite wurden in Zusammenarbeit mit experimentellen Untersuchungen Verbrennungs- und FEM-Rechnungen durchgeführt, um die Wärmeübergänge am Kolben zeitlich und örtlich hochaufgelöst zu erfassen. Die thermisch geschädigte Schicht konnte als degradierte Cu-Al Mikrostruktur identifiziert werden, welche erosiv angegriffen war. Die ermittelte Einsatzgrenztemperatur von 440°C stellt für Al-Legierungen ein oberes Limit dar. Für höchstbelastete Kolbenwerkstoffe zeigten Stähle mit hoher Zunderbeständigkeit die größten Potentiale. Schichtsysteme auf Al-Kolben sind zwar geeignet, deren Einsatzgrenzen zu erhöhen, thermodynamisch und kostentechnisch aber den Stahlkolben unterlegen. Die Ergebnisse dienen als Grundlage für eine Modellierung der thermomechanischen Ermüdung unter Berücksichtigung der transienten Oberflächentemperature
Keywords: engines; diesel; spray; heat transfer; piston; material; wall interaction

Local Investigations of the Mechanical Properties of Ultrafine Grained Metals by Nanoindentations - Müller, Johannes; Durst, Karsten; Amberger, Dorothea; Göken, Mathias (Materials Science Forum, 2006)
The mechanical properties of ultrafine-grained metals processed by equal channel angular pressing is investigated by nanoindentations in comparison with measurements on nanocrystalline nickel with a grain size between 20 and 400 nm produced by pulsed electrodeposition. Besides hardness and Young’s modulus measurements, the nanoindentation method allows also controlled experiments on the strain rate sensitivity, which are discussed in detail in this paper. Nanoindentation measurements can be performed at indentation strain rates between 10-3 s-1 and 0.1 s-1. Nanocrystalline and ultrafine-grained fcc metals as Al and Ni show a significant strain rate sensitivity at room temperature in comparison with conventional grain sized materials. In ultrafine-grained bcc Fe the strain rate sensitivity does not change significantly after severe plastic deformation. Inelastic effects are found during repeated unloading-loading experiments in nanoindentations.<br
Keywords: Nanocrystalline Metals; Nanoindentation; Pulsed Electrodeposition; Strain Rate Sensitivity (SRS); Ultra Fine Grained Metal

Localized corrosion of ultrafine-grained Al-Mg model alloys - Brunner, Johannes; May, Johannes; Höppel, Heinz Werner; Göken, Mathias; Virtanen, Sannakaisa (Electrochimica Acta, 2010)
WW1::845

Local Mechanical Properties at the Dendrite Scale of Ni-Based Superalloys Studied by Advanced High Temperature Indentation Creep and Micropillar Compression Tests - Haußmann, Lukas; Neumeier, Steffen; Kolb, Markus; Ast, Johannes; Mohanty, Gaurav; Michler, Johann; Göken, Mathias (Minerals, Metals and Materials Series, 2020)
Chemical inhomogenities due to dendritic solidification of Ni-based superalloys result in different local microstructures with varying mechanical properties. New indentation creep test methods allow probing of the local creep properties at the dendrite scale at high temperatures. The as-cast single crystalline Ni-based superalloy ERBO1A (a derivative alloy of CMSX–4) was investigated and electron-probe microanalysis (EPMA) measurements revealed strong segregation of, e.g., Re and W in the dendritic region and, e.g., Ta in the interdendritic region. Indentation creep experiments at 750 °C and micropillar compression tests at 785 °C were conducted in both regions, and a higher creep strength was found in the dendritic region compared to the interdendritic region. Theoretical models for solid solution hardening as well as γ′ precipitation hardening confirm these results, since they predict a higher strength in the dendritic region than in the interdendritic region. Compared with the fully heat treated state, a smaller difference in the local mechanical properties or even a reverse strength ratio of the dendritic and interdendritic region can be expected.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Dendritic segregations; Indentation creep; Micropillar compression; Ni-based superalloy

Local mechanical properties of the (β0+ω0) composite in multiphase titanium aluminides studied with nanoindentation at room and high temperatures - Kolb, Markus; Wheeler, J. M.; Mathur, H. N.; Neumeier, Steffen; Korte-Kerzel, Sandra; Pyczak, Florian; Michler, J.; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2016)
WW1::1067
Keywords: High Temperature

Long-Chain Terminal Alcohols through Catalytic CO Hydrogenation - Xiang, Yizhi; Chitry, Veronique; Liddicoat, Peter; Felfer, Peter; Cairney, Julie; Ringer, Simon; Kruse, Norbert (Journal of the American Chemical Society, 2013)
We show that long-chain 1-alcohols can be produced with high selectivities using heterogeneous CO hydrogenation catalysis. This breakthrough is achieved through the targeted design of "CoCuMn" nanosized core-shell particles using co-precipitation of metal salts into oxalate precursors and subsequent thermal decomposition. Using stoichiometric CO/H-2 feeds, the selectivities to 1-alcohols or combined 1-alcohols/1-alkenes are usually higher than 60% and occasionally up to 95%. The Anderson-Schulz-Flory chain-lengthening probabilities for these products are higher than 0.6, but usually below 0.9 so as to optimize the C-8-C-14 slate as feedstock for plasticizers, lubricants, or detergent

Long-term effects of ilmenite on a micro-scale bubbling fluidized bed combined heat and power pilot plant for oxygen carrier aided combustion of wood - Schneider, Tanja; Moffitt, Julian; Volz, Nicklas; Müller, Dominik; Karl, Jürgen (Applied Energy, 2022)
Small-scale solutions for the application of solid biomass fuels for the generation of heat and power with fluidized beds are hardly available. The main issues comprise agglomeration and slagging, incomplete burnout of combustibles and low efficiencies. During so-called oxygen carrier aided combustion, an oxygen carrier replaces the conventional bed material and balances the local and temporal oxygen supply in the fluidized bed. This results in a more homogeneous combustion and increased heat release in the fluidized bed area. Especially for small-scale bubbling fluidized bed solutions, these effects require an adapted plant setup. However, applications of oxygen carriers in small-scale bubbling fluidized bed boilers are barely reported. Process parameters differ significantly from large-scale circulating fluidized beds regarding resident times, particle volume fractions and size distributions. Hence, this research examines the enhancing effect of 50 wt% ilmenite in a 45 kWth bubbling fluidized bed fired combined heat and power plant. Long-term measurements in a field test environment promise a potential decrease of the carbon monoxide emissions of up to 75 %. Lower fluidized bed temperatures and apparently poor combustion conditions even enhance the positive effect of ilmenite. Moreover, the porous ilmenite particles interact with ash compounds such as potassium, calcium and magnesium. The migration of potassium into the inner particle mitigates the formation of low-melting layers around the particle. Calcium and magnesium form titanium oxide phases in the outer particle layer, below an iron enriched particle shell. Thereby, ilmenite prevents the formation of sticky particle layers, which addresses agglomeration and slagging issues. The particle shell is subject of ongoing attrition leading to a constant entrainment of active material from the combustion chamber. Therefore, a continuous addition of fresh material is essential to sustain the beneficial impact of the oxygen carrier. The optimal operation period for the oxygen carrier additive is supposed to cover 1–2 weeks.<br
Keywords: Ilmenite; Oxygen carrier; Bubbling fluidized bed; Oxygen carrier aided combustion; Biomass; Ash

Lower hardness than strength: the auxetic composite microstructure of limpet tooth - Wurmshuber, Michael; Wilmers, Jana; Kim, Jongil; Oh, Sang Ho; Kiener, Daniel (Acta Biomaterialia, 2023)
The limpet tooth is widely recognized as nature's strongest material, with reported strength values up to 6.5 GPa. Recently, microscale auxeticity has been discovered in the leading part of the tooth, providing a possible explanation for this extreme strength. Utilizing micromechanical experiments, we find hardness values in nanoindentation that are lower than the respective strength observed in micropillar compression tests. Using micromechanical modeling, we show that this unique behavior is a result of local tensile strains during indentation, originating from the microscale auxeticity. As the limpet tooth lacks ductility, these tensile strains lead to microdamage in the auxetic regions of the microstructure. Consequently, indentation with a sharp indenter always probes a damaged version of the material, explaining the lower hardness and modulus values gained from nanoindentation. Micropillar tests were found to be mostly insensitive to such microdamage due to the lower applied strain and are therefore the suggested method for characterizing auxetic nanocomposites.
Keywords: Biomaterials; Auxetic materials; Nanoindentation; Micromechanical modeling

Low temperature deformation of MoSi2 and the effect of Ta, Nb and Al as alloying elements - Zenk, Carolin; Gibson, James S.K.L.; Maier-Kiener, Verena; Neumeier, Steffen; Göken, Mathias; Korte-Kerzel, Sandra (Acta Materialia, 2019)
Molybdenum disilicide (MoSi2) is a very promising material for high temperature structural applications due to its high melting point (2030∘C), low density, high thermal conductivity and good oxidation resistance. However, MoSi2 has limited ductility below 900∘C due to its anisotropic plastic deformation behaviour and high critical resolved shear stresses on particular slip systems. Nanoindentation of MoSi2 microalloyed with aluminium, niobium or tantalum showed that all alloying elements cause a decrease in hardness. Analysis of surface slip lines indicated the activation of the additional 1 1 0<1 1 1> slip system in microalloyed MoSi2, which is not active below 300∘C in pure MoSi2. This was confirmed by TEM dislocation analysis of the indentation plastic zone. Further micropillar compression experiments comparing pure MoSi2 and the Ta-alloyed sample enabled the determination of the critical resolved shear stresses of individual slip systems even in the most brittle [0 0 1] crystal direction.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Dislocations; Micropillar compression; Molybdenum disilicide; Nanoindentation; Plasticity

Macro- and nanomechanical properties and strain rate sensitivity of accumulative roll bonded and equal channel angular pressed ultrafine-grained materials - Boehner, Andreas; Maier, Verena; Durst, Karsten; Höppel, Heinz Werner; Göken, Mathias (Advanced Engineering Materials, 2011)
Several processes of severe plastic deformation are suitable for the production of materials with ultrafine-grained microstructures which are known to exhibit high strength and often good ductility as well as strain rate sensitive behavior. The most promising ones are equal channel angular pressing (ECAP) for bulk material and accumulative roll bonding (ARB) for the production of sheet material. In order to evaluate the influence of the process on these mechanical properties and the strain rate sensitivity, tensile tests, and nanoindentation tests were performed on material produced up to similar effective plastic strains of extgreekeARB = 6.4 and extgreekeECAP = 6.3. It could be shown that the macroscopic strength is slightly higher for ARB than for ECAP material and vice versa in nanoindentation. Independent of the testing method, the strain rate sensitivities and activation volumes are similar for both materials. Thus, both processes performed up to similar effective plastic strains lead to comparable improvements in the mechanical properties. Additionally it could be shown, that this comparison allows the identification of the dominant deformation mechanism which is responsible for the observed strain rate sensitivity.
WW1::886

Magnetic dilution by severe plastic deformation - Stückler, Martin; Weissitsch, Lukas; Wurster, Stefan; Felfer, Peter; Krenn, Heinz; Pippan, Reinhard; Bachmaier, Andrea (AIP Advances, 2020)
Mixtures of Fe and Cu powders are cold-compacted and subsequently deformed with severe plastic deformation by high-pressure torsion, leading to bulk samples. The dilution of Fe in the Cu matrix is investigated with SQUID-magnetometry, whereas the magnetic properties change as a function of Fe-content from a frustrated regime to a thermal activated behaviour. The magnetic properties are correlated with the microstructure, investigated by synchrotron X-ray diffraction and atom probe tomography. Annealing of the as-deformed states leads to demixing and grain growth, with the coercivity as a function of annealing temperature obeying the random anisotropy model. The presented results show that high-pressure torsion is a technique capable to affect the microstructure even on atomic length scales.
CRIS-Team Scopus Importer:2020-01-28

Mapping interfacial excess in atom probe data - Felfer, Peter; Scherrer, Barbara; Demeulemeester, Jelle; Vandervorst, Wilfried; Cairney, Julie M. (Elsevier, 2015)
Using modern wide-angle atom probes, it is possible to acquire atomic scale 3D data containing 1000 s of nm(2) of interfaces. It is therefore possible to probe the distribution of segregated species across these interfaces. Here, we present techniques that allow the production of models for interfacial excess (IE) mapping and discuss the underlying considerations and sampling statistics. We also show, how the same principles can be used to achieve thickness mapping of thin films. We demonstrate the effectiveness on example applications, including the analysis of segregation to a phase boundary in stainless steel, segregation to a metal-ceramic interface and the assessment of thickness variations of the gate oxide in a fin-FET. (C) 2015 Elsevier B.V. All rights reserve
Keywords: Atom probe tomography; Interface; Grain boundary; Interfacial excess mapping; Data analysis

Martensitic transformation in ultrafine-grained stainless steel AISI 304l under monotonic and cyclic loading - Boehner, Andreas; Niendorf, Thomas; Amberger, Doris; Höppel, Heinz Werner; Göken, Mathias; Maier, Hans Jürgen (Metals, 2012)
Keywords: UFG; Cyclic loading; AISI 304L; Martensitic transformation; Equal channel angular pressing; Tensile test; Stainless steel

Maßgeschneiderte partikelverstärkte Verbundwerkstoffe und Werkstoffverbunde hergestellt durch den akkumulativen Walzprozess (ARB) - Schmidt, Christian; Höppel, Heinz Werner; Göken, Mathias (Tagungsband zum 18. Symposium Verbundwerkstoffe, 2011)
Der akkumulative Walzprozess (ARB) bietet die Möglichkeit ultrafeinkörnige Blechwerkstoffe mit interessanten mechanischen Eigenschaften herzustellen. Durch die kontrollierte Einbringung stabilisierter Nanopartikel während des ARB-Prozesses wurde im Rahmen dieser Arbeit gezeigt, dass der ARB-Prozess auch hervorragend dafür geeignet ist, UFG-Verbundwerkstoffe herzustellen und Eigenschaften maßzuschneidern. Bereits ein sehr geringer Anteil keramischer Nanopartikel von 0,1 vol.-% führt durch zusätzliche, lokale plastische Verformung einerseits zu beschleunigter Kornfeinung, wodurch die hohen spezifischen Festigkeiten ultrafeinkörniger Werkstoffe bereits nach zwei statt acht Walzzyklen erreicht werden können. Andererseits kann gegenüber der reinen UFG-Struktur eine zusätzliche Festigkeitssteigerung erzielt werden.
EAM Import::2019-03-12

Mechanical anisotropy of aluminium laminates produced by ARB - Chekhonin, P.; Beausir, B.; Scharnweber, J.; Oertel, C-G; Jaschinski, J.; Hausöl, Tina; Höppel, Heinz Werner; Brokmeier, H-G; Skrotzki, W. (Materials Science Forum, 2012)
The plastic anisotropy was studied on aluminium sheets with layers of different purity (A: 5N and B: 2N+) produced by accumulative roll bonding (ARB). Both material layers show a contrasting recrystallization behavior where A and B are discontinuously and continuously recrystallized, respectively. Global textures were measured by neutron diffraction. The mechanical anisotropy was measured by tensile testing after different numbers of ARB cycles. The planar anisotropy decreases with the number of ARB cycles while the normal anisotropy reaches a plateau after 4 cycles. Simulations of the Lankford parameters were carried out with the help of the viscoplastic self-consistent scheme (based on the global texture) and compared with the experimental data. Deviations of the simulated values from those of experiment are discussed with regard to through-thickness texture and material heterogeneities.
WW1::940

Mechanical behaviour of novel sintered Co-Al-W alloys at high temperatures - Cartón-Cordero, Marta; Campos, Mónica; Freund, Lisa; Kolb, Markus; Neumeier, Steffen; Göken, Mathias; Torralba, José M. (World Powder Metallurgy 2016 Congress and Exhibition, World PM 2016, 2016)
Keywords: Superalloys; Co-Al-W alloys; Mechanical properties; Mechanical milling; PM route; Nanoindentation

Mechanical characterization of metallic thin films by bulge and scratch testing - Javed, Hassan; Merle, Benoit; Preiß, Eva; Hivet, Romain; Benedetto, Alessandro; Göken, Mathias (Surface & Coatings Technology, 2016)
The mechanical properties of 20-nm thick silver, titanium and nickel-chromium alloy films encapsulated between two silicon nitride ceramic layers are investigated by bulge and scratch tests. Bulge tests are used in order to measure the yield strength of the metallic films. An unexpected strain-softening behavior is observed for a silver sample, which is rationalized as a measurement artifact due to the delamination of the film from its substrate. An experimental workaround is proposed and shown to yield correct measurements. The adhesion strength of the metallic films is measured by scratch tests, and their failure mechanism is characterized by in-situ optical observations. All in all, the poorest mechanical properties are found in the silver. This is probably due to a combination of the low adhesion at the interface between the nitride and the metal and the low yield stress of the silve
Keywords: Bulge test; Scratch test; Silicon nitride; Silver; Thin film

Mechanical performance of doped W–Cu nanocomposites - Wurmshuber, Michael; Burtscher, Michael; Doppermann, Simon; Bodlos, Rishi; Scheiber, Daniel; Romaner, Lorenz; Kiener, Daniel (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
Keywords: kernfusionsrelevant

Mechanical properties and lattice misfit of γ/γ' strengthened Co-base superalloys in the Co-W-Al-Ti quaternary system - Zenk, Christopher; Neumeier, Steffen; Stone, H. J.; Göken, Mathias (Intermetallics, 2014)
A continuous γ/γ' two-phase field has been identified extending between the ternary Co-Al-W system to the binary Co-Ti system. The lattice misfits of two phase γ/γ' alloys from the Co-Al-W-Ti quaternary system were measured by X-ray diffraction and found to be positive and vary linearly with composition. Differential scanning calorimetry measurements showed that the solidus and liquidus temperatures decrease from the W and Al rich end to the Ti rich end, whilst the γ' solvus temperature increases. Long term heat treatments identified the occurrence of discontinuous precipitation at the grain boundaries in many of the alloys studied. The high temperature strength and creep resistance of the quaternary alloys in the intermediate composition range surpassed those of the binary and ternary alloys. © 2014 Elsevier Ltd. All rights reserve
Keywords: B. Age-hardening; B. Thermal stability; B. Yield stress; D. Microstructure; F. Differential scanning calorimetry; F. Diffraction/sacterring (electron; neutron and X-ray)

MECHANICAL PROPERTIES AND MICROSTRUCTURE OF ADVANCED METALLIC ALLOYS IN HONOR OF PROF. HAEL MUGHRABI - PART B - HIGH TEMPERATURE AND NANOMATERIALS Introduction - Göken, Mathias; Eggeler, Gunther; Zhu, Yuntian; Lu, Lei (Journal of Materials Research, 2017)

Mechanical properties, dislocation density and grain structure of ultrafine-grained aluminum and aluminum-magnesium alloys - May, Johannes; Dinkel, Markus; Amberger, Dorothea; Höppel, Heinz Werner; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2007)
The kind and amount of alloying elements strongly affects the formation of ultrafine-grained microstructures. Aluminum alloys with different amounts of the alloying element magnesium, and a commercially pure aluminum alloy, have been investigated in order to evaluate how the obtained microstructures will affect the mechanical properties. X-ray profile analysis has been used to determine grain size and dislocation density. With increasing amounts of alloying elements, a smaller grain size and a higher dislocation density after severe plastic deformation (SPD) are obtained, which lead to higher hardness and improved fatigue properties. © The Minerals, Metals & Materials Society and ASM International 2007.
Created from Fastlane, Scopus look-up

Mechanical properties of aluminium laminates produced by accumulative roll bonding - Chekhonin, P.; Scharnweber, J.; Scharnweber, M.; Oertel, C. -G.; Hausöl, Tina; Höppel, Heinz Werner; Jaschinski, J.; Marr, T.; Skrotzki, W. (Crystal Research and Technology, 2013)
WW1::973

Mechanical properties of copper/bronze laminates: Role of interfaces - Ma, Xiaolong; Huang, Chongxiang; Moering, Jordan; Ruppert, Mathis; Höppel, Heinz Werner; Göken, Mathias; Narayan, Jagdish; Zhu, Yuntian (Acta Materialia, 2016)
Interfaces play a crucial role in mechanical behaviors of both laminated and gradient structured materials. In this work, copper/bronze laminates with varying interface spacing were fabricated by accumulative roll bonding and subsequent annealing to systematically study the interface effect on mechanical properties. Heterogeneities exist in chemical composition, grain size, hardness and texture across the interfaces. Simultaneous improvement of strength and ductility with decreasing interface spacing is found in tensile tests. Extra geometrically necessary dislocations (GNDs) are found to accumulate in the vicinity of interfaces, which is due to mechanical incompatibility across the interfaces. Importantly, an interface-affected zone spanning a few micrometers was found, which is not affected by interface spacing. These observations suggest the existence of an optimum spacing, which may produce the highest hardening capacity and ductility without sacrificing strength. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Interface; Laminate structure; Geometrically necessary dislocation (GND); Interface-affected zone; Back stress hardening

Mechanical properties of dense to porous alumina/lanthanum hexaaluminate composite ceramics - Negahdari, Zahra; Willert-Porada, Monika; Pfeiffer, Carolin (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2010)
For development of new composite materials based on lanthanum hexaaluminate and alumina ceramics, a better understanding of the microstructure-properties relationship is essential. In this paper, attention was focused on the evaluation of mechanical properties of lanthanum hexaaluminate/alumina particulate composite. It was found out that the lanthanum hexaaluminate content plays a critical role in determination of the microstructure and mechanical properties of the composite ceramics. In situ formation of plate-like lanthanum hexaaluminate in the ceramic matrix was accompanied with formation of pores so that the microstructure shifted from dense to porous. Increasing the lanthanum hexaaluminate content up to a certain value enhanced the fracture toughness, increased the hardness, and increased the elastic modulus of the composite materials. Further increase in the lanthanum hexaaluminate content degraded the hardness as well as the elastic modulus of composite ceramics. The influence of lanthanum hexaaluminate on mechanical properties was described by means of microstructure, porosity, and intrinsic characteristics of lanthanum hexaaluminate. © 2010 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Ceramics; Composites; Hardness measurement; Mechanical characterization; Nanoindentation; Porous materials

Mechanical properties of hyaline and repair cartilage studied by nanoindentation - Franke, Oliver; Durst, Karsten; Maier, Verena; Göken, Mathias; Birkholz, Torsten; Schneider, Holm; Hennig, Friedrich; Gelse, Kolja (Acta Biomaterialia, 2007)
Articular cartilage is a highly organized tissue that is well adapted to the functional demands in joints but difficult to replicate via tissue engineering or regeneration. Its viscoelastic properties allow cartilage to adapt to both slow and rapid mechanical loading. Several cartilage repair strategies that aim to restore tissue and protect it from further degeneration have been introduced. The key to their success is the quality of the newly formed tissue. In this study, periosteal cells loaded on a scaffold were used to repair large partial-thickness cartilage defects in the knee joint of miniature pigs. The repair cartilage was analyzed 26 weeks after surgery and compared both morphologically and mechanically with healthy hyaline cartilage. Contact stiffness, reduced modulus and hardness as key mechanical properties were examined in vitro by nanoindentation in phosphate-buffered saline at room temperature. In addition, the influence of tissue fixation with paraformaldehyde on the biomechanical properties was investigated. Although the repair process resulted in the formation of a stable fibrocartilaginous tissue, its contact stiffness was lower than that of hyaline cartilage by a factor of 10. Fixation with paraformaldehyde significantly increased the stiffness of cartilaginous tissue by one order of magnitude, and therefore, should not be used when studying biomechanical properties of cartilage. Our study suggests a sensitive method for measuring the contact stiffness of articular cartilage and demonstrates the importance of mechanical analysis for proper evaluation of the success of cartilage repair strategies.
Created from Fastlane, Scopus look-up
Keywords: Cartilage; Nanoindentation; Soft tissues; Stiffness; Storage effect

Mechanical properties of ultrafine-grained AlZnMg(Cu)-alloys AA7020 and AA7075 processed by accumulative roll bonding - Ruppert, Mathis; Strebl, Michael; Höppel, Heinz Werner; Göken, Mathias (Journal of Materials Science, 2015)
Ultrafine-grained AA7020 (AlZnMg) and AA7075 (AlZnMgCu) were produced by accumulative roll bonding (ARB) with up to 6 cycles. Different pre-heating treatments and their effect on the mechanical performance of the materials were investigated by means of hardness measurements and uniaxial tensile testing. It was found for AA7020 that by pre-heating at 230 degrees C for 2.5 min prior to each rolling step, an UTS of 550 MPa can be achieved, which is 51 % higher compared to the peak-aged T6 reference. For AA7075, pre-heating at 280 degrees C for 2.5 min leads to a very high UTS of 720 MPa after four ARB passes. A negative strain rate sensitivity was found for both alloys, which shifts toward zero with increasing number of ARB cycles. Post-ARB heat treatment was performed in order to overcome the reduced ductility after ARB. This leads to an enhanced strain hardening capacity after 4 cycles, resulting in an increase of the uniform elongation from 1.4 to 2.0 % for AA7020 and from 0.9 to 2.1 % for AA7075.

Mechanical Properties of Ultrafine Grained Metals under Cyclic and Monotonic Loads: An Overview - Höppel, Heinz Werner (Materials Science Forum, 2006)

Mechanics of colloidal supraparticles under compression - Wang, Junwei; Schwenger, Jan; Feldner, Patrick; Ströbel, Andreas; Herre, Patrick; Romeis, Stefan; Peukert, Wolfgang; Merle, Benoit; Vogel, Nicolas (Science Advances, 2021)
Colloidal supraparticles are finite, spherical assemblies of many primary particles. To take advantage of their emergent functionalities, such supraparticles must retain their structural integrity. Here, we investigate their size-dependent mechanical properties via nanoindentation. We find that the deformation resistance inversely scales with the primary particle diameter, while the work of deformation is dependent on the supraparticle diameter. We adopt the Griffith theory to such particulate systems to provide a predictive scaling to relate the fracture stress to the geometry of supraparticles. The interplay between primary particle material and cohesive interparticle forces dictates the mechanical properties of supraparticles. We find that enhanced stability, associated with ductile fracture, can be achieved if supraparticles are engineered to dissipate more energy via deformation of primary particles than breaking of interparticle bonds. Our work provides a coherent framework to analyze, predict, and design the mechanical properties of colloidal supraparticle

Mechanisms of high-temperature corrosion in helium containing small amounts of impurities. II. Corrosion of the nickel-base alloy inconel 617 - Christ, Hans-Jürgen; Künecke, Ulrike; Meyer, K; Sockel, Hans-Georg (Oxidation of Metals, 1988)
Application of the technical nickel-base alloy IN 617 in the primary circuit of the high-temperature gas-cooled reactor is limited essentially by the chemical reactions with the impurities (CO, CO2, H2, CH4, H2O) in the helium coolant. The interactions of the alloy with the reactive impurities in different helium-base gases were investigated by thermogravimetry in a gas-tight microbalance and by simultaneous measurement of the changes in gas composition by a continuous sensitive mass spectrometric analysis. The results demonstrate that the set of six reaction equations deduced in part 1 can be applied to describe the corrosion of the alloy. The occurrence of the various reactions is determined essentially by temperature. For the case of a standardized helium gas (HHT-He), three temperature regions can be distinguished. Below a critical temperature (about 1105 K), the presence of CO can cause simultaneous oxidation and carburization. Above this temperature, this reaction does not reverse itself. Rather, oxidation by CO2 and H2O takes place that shows, after a transient period, the same kinetics observed in undiluted oxygen-containing gases. At temperatures above about 1205 K, decarburization of the alloy accompanied by the production of CO takes place, leading to severe destruction of the carbide microstructure and, therefore, limiting the applicability of the materia
Keywords: decarburization; carburization; mechanisms; kinetics; oxidation; Ni-base alloy IN 617; reactor helium

Metal fused filament fabrication of the nickel-base superalloy IN 718 - Thompson, Yvonne; Zissel, Kai; Förner, Andreas; Gonzalez-Gutierrez, Joamin; Kukla, Christian; Neumeier, Steffen; Felfer, Peter (Journal of Materials Science, 2022)
This study demonstrates metal fused filament fabrication (MF3) as an alternative additive and highly flexible manufacturing method for free-form fabrication of high-performance alloys. This novel processing, which is similar to Metal injection molding (MIM), enables a significant reduction in manufacturing costs for complex geometries, since expensive machining can be avoided. Utilizing existing equipment and reducing material expense, MF3 can pave the way for new and low-cost applications of IN 718, which were previously limited by high manufacturing costs. Iterative process optimization is used to find the most suitable MF3 process parameters. High relative density above 97% after pressureless sintering can be achieved if temperature profiles and atmospheres are well adjusted for thermal debinding and sintering. In this study, the influence of processing parameters on the resulting microstructure of MF3 IN 718 is investigated. Samples sintered in vacuum show coarse-grained microstructure with an area fraction of 0.36% NbC at grain boundaries. Morphology and composition of formed precipitates are analyzed using transmission electron microscopy and atom probe tomography. The gamma/gamma ''/gamma' phases' characteristics for IN 718 were identified. Conventional heat treatment is applied for further tailoring of mechanical properties like hardness, toughness and creep behavior. Fabricated samples achieve mechanical properties similar to MIM IN 718 presented in literature.
CRIS-Team WoS Importer:2022-02-11

Microcantilever bending experiments in NiAl - Evaluation, size effects, and crack tip plasticity - Ast, Johannes; Przybilla, Thomas; Maier, Verena; Durst, Karsten; Göken, Mathias (Journal of Materials Research, 2014)
For a better understanding of the local fracture behavior of semi-brittle materials, we carried out bending experiments on notched microcantilevers of varying sizes in the micrometer range using NiAl single crystals. Smaller and larger beams were milled with a focused ion beam in the so-called soft <110> and hard <100> orientation and were tested in situ in a scanning electron microscope and ex situ with a nanoindenter, respectively. The measurements were evaluated using both linear-elastic fracture mechanics and elastic-plastic fracture mechanics. The results show that (i) the fracture toughness is in the same range as the macroscopically determined one which is around 3.5 MPa/m for the soft orientation and around 8.5 MPa/m for the hard orientation, that (ii) there is a strong influence of the anisotropic behavior of NiAl on the fracture toughness values, and that (iii) the J-integral technique is the most accurate quantification metho
Keywords: fracture; ion beam processing; scanning electron microscopy (SEM)

Microcantilever Fracture Tests of α-Cr Containing NiAl Bond Coats - Gabel, Stefan; Giese, Sven; Webler, Ralf; Neumeier, Steffen; Göken, Mathias (Advanced Engineering Materials, 2022)
MCrAlY bond coats are widely used as oxidation-resistant coatings on superalloys. The major phase is the thermally stable intermetallic β-NiAl phase. The addition of Cr increases the oxidation and corrosion resistance but leads to the formation of α-Cr precipitates. Both phases are brittle and limit the fracture toughness of these coatings. To study the influence of thermal exposure and the resulting changing chemical composition on the fracture properties, the fracture toughness of both phases is measured by notched microcantilever bending, after processing and after oxidation by thermal cycling. The fracture toughness of β-NiAl decreases during thermal cycling due to the depletion in Al, whereas the fracture toughness and the composition of α-Cr stay constant. As the fracture toughness of α-Cr is lower compared with β-NiAl, the formation of α-Cr precipitates is supposed to decrease the fracture toughness of the bond coat.
CRIS-Team Scopus Importer:2022-01-28

Microcantilever Fracture Tests on Eutectic NiAl–Cr(Mo) In Situ Composites - Gabel, Stefan; Giese, Sven; Merle, Benoit; Sprenger, Ioannis; Heilmaier, Martin; Neumeier, Steffen; Bitzek, Erik; Göken, Mathias (Advanced Engineering Materials, 2021)
Lamellar eutectic NiAl–Cr(Mo) alloys show an increased fracture toughness due to different toughening mechanisms. These mechanisms result from the fibrous or lamellar microstructure of the two constituting phases α-Cr(Mo) and β-NiAl. However, the fracture toughness of the individual phases and the evolution from early crack growth to the toughening mechanisms have not yet been systematically studied. Herein, bending tests on focused ion beam (FIB)-notched microcantilever beams are used to characterize the small-scale fracture properties. The micromechanical investigations reveal that the fracture toughness of the α-Cr(Mo) phase ((Formula presented.)) is much higher than the fracture toughness of β-NiAl ((Formula presented.)). Larger cantilevers in the crack arresting orientation show an enhanced fracture toughness with up to (Formula presented.), which is still lower than the one of macroscopic experiments. This is attributed to the small interaction volume of the crack, which hinders the full exploitation of potential extrinsic toughening mechanisms.
CRIS-Team Scopus Importer:2021-03-19
Keywords: eutectic alloys; focused ion beam; fractures; intermetallic; micromechanics

Microimprinting of nanocrystalline metals - Influence of microstructure and work hardening - Durst, Karsten; Backes, Björn; Müller, Johannes; Göken, Mathias; et al. (Journal of Materials Processing Technology, 2010)
The microimprinting behaviour of a wide variety of materials with grain sizes ranging from 25 nm up to a few mm was studied, using a flat punch indenter with a circular cavity with a diameter of 5 extgreekmm and a cavity line width of 350 nm. The flat punch die was fabricated by focussed ion beam machining. The imprinted ring geometry has been evaluated using atomic force microscopy in terms of extrusion height, relative to residual imprinting depth. The experimental work was complemented by Finite Element Analysis (FEA) of the forming process, using experimentally determined stress–strain data of the imprinted materials as input for the finite element simulations. Even so only macroscopic properties of the materials have been used for the modelling, both experiment and simulation yield comparable results. However, the relative extrusion height from FEA are much larger compared to the experimental results. It is found that grain size and the subsequent work hardening behaviour of the material has a strong influence on the local flow behaviour during imprinting. Nanocrystalline materials with nearly ideal-plastic deformation behaviour exhibit the best formability. The influence of the work hardening behaviour on the local flow of the material during microimprinting is moreover confirmed by imprinting of a pre-strained material. A reduction in the work hardenability of the material leads to an increasing microflow during microimprinting.
WW1::847

Micromechanical characterisation of the influence of rhenium on the mechanical properties in nickel-base superalloys - Göken, Mathias; Durst, Karsten (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2004)
Three commercial single-crystalline nickel-base superalloys CMSX-6, CMSX-4 and CMSX-10 which have an increasing amount of rhenium and tungsten were investigated and the micromechanical properties such as hardness and modulus of elasticity of the individual phases were tested in a nanoindenting atomic force microscope. The hardness of the matrix phase increases with the concentration of refractory elements, whereas only a small change in the hardness of the precipitates was found. The hardness ratio of precipitate and matrix decreases significantly with increasing rhenium content in the initial condition and after heat treatment. In the initial condition the hardness ratio ranges from 1.31 for CMSX-10 to 1.41 for CMSX-4 and 1.67 for CMSX-6. Moreover, the modulus of elasticity increases with the concentration of refractory elements. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.microm
Keywords: Hardness; Modulus of elasticity; Nanoindentation; Nickel-base superalloy; Rhenium

Micromechanical characterization of laser consolidated nanoparticle ITO layers - Mikschl, Florian; Merle, Benoit; Baum, Marcus; Heberle, Johannes; Göken, Mathias; Schmidt, Michael (Thin Solid Films, 2017)
Indium tin oxide (ITO) is one of the few materials that combine optical transparency in the visible light spectrum with high electrical conductivity. These properties provide functionality in many optoelectronic applications but their application to certain fields is limited by the need to achieve advanced mechanical properties, hence requiring micromechanical characterization methods. In this paper, ITO coatings of 94-325 nm thickness are produced from spin-coating of nanoparticle ink followed by consolidation by nanosecond UV laser irradiation in ambient air. These ITO layers are investigated by nanoindentation and scratch testing, which provide measurements of their hardness, Young's modulus and scratch resistance. This allows understanding the effect of the process parameters on the mechanical properties of the layers. It is concluded that a laser fluence of 59 mJ/cm(2) provides an effective mechanical consolidation of ITO particles up to 150 nm thickness.
Keywords: Mechanical properties; Indium tin oxide; Nanoparticles; Nanoindentation; Scratch testing; Thin films

Micro-Mechanical Fracture Investigations on Grain Size Tailored Tungsten-Copper Nanocomposites - Schmuck, K.; Burtscher, M.; Alfreider, M.; Wurmshuber, Michael; Kiener, D. (JOM Journal of the Minerals, Metals and Materials Society, 2024)
Tungsten-copper composites are used in harsh environments because of their superior material properties. This work addresses a tungsten-copper composite made of 20 wt.% copper, which was subjected to grain refinement by high-pressure torsion, whereby the deformation temperature was varied between room temperature and 400 °C to tailor the grain size. Deformation was performed up to microstructural saturation and verified by hardness measurement and scanning electron microscopy. From the refined nanostructured material, micro-cantilever bending beams with cross-sections spanning from 5 × 5 to 35 × 35 µm2 were cut to examine possible size effects and the grain size influence on the fracture behavior. Fracture experiments were performed in situ inside a scanning electron microscope by applying a quasi-static loading protocol with partial unloading steps. Inspection of the fracture surfaces showed that all cantilevers failed in an inter-crystalline fashion. Nevertheless, remaining coarser tungsten grains impacted the resultant fracture toughness and morphology. Cantilevers fabricated from the 400 °C specimen exhibited a fracture toughness of 220 ± 50 Jm2 . For the room temperature cantilevers, a fracture toughness of 410 ± 50 Jm2 was observed, which declined to 340 ± 30 Jm2 for cantilevers < 10 × 10 µm2, confirming a size effect. The increased fracture toughness is attributed to the delamination-like structures formed in the room temperature sample.
CRIS-Team Scopus Importer:2024-01-19

Micromechanics and ultrastructure of pyrolysed softwood cell walls - Brandt, Bjoern; Zollfrank, Cordt; Franke, Oliver; Fromm, Joerg; Göken, Mathias; Durst, Karsten (Acta Biomaterialia, 2010)
WW1::848

Microscale High-Cycle Fatigue Testing by Dynamic Micropillar Compression Using Continuous Stiffness Measurement - Merle, Benoit; Höppel, Heinz Werner (Experimental Mechanics, 2018)
The continuous stiffness method (CSM) is used for fatigue testing FIB-fabricated micropillars up to the high cycle fatigue (HCF) range on a commercial nanoindentation platform. The frequency of similar to 40 Hz allows reaching several million (10(6)) cycles within hours under constant nominal stress amplitude testing conditions. It is shown that both the evolution of the strain and plastic strain amplitudes can be evaluated from the harmonic measurements provided by the lock-in amplifier. Defining a custom threshold on strain amplitude decrease as failure criterion further enables the determination of S-N curves. The new method was validated by tests on ECAP copper, which is shown to exhibit the same cyclic softening during micropillar testing as observed macroscopically. The calculated plastic strain amplitude is also well in line with literature data. Generally, the new method has a great potential for studying the local cyclic behavior of individual layers and phases of complex systems and would also be of great advantage for studying local fatigue effects at interfaces.
Keywords: Nanoindentation; Dynamic nanoindentation; Fatigue; High cycle fatigue; Micropillar compression; Continuous stiffness measurement

Microscopic study on the interfacial strength of hydrogenated amorphous carbon coating systems - Spiecker, Erdmann; et al. (Surface & Coatings Technology, 2011)
Slight variation of the coatings in the ramp layer between Cr and a-C:H resulted in a good or poor adhesion behaviour. Both coatings exhibited in the ramp layer a quasi amorphous matrix structure with short-range ordered substructures. No crystalline chromium carbides could be detected in these regions. Focused investigations of the chemical gradients with Energy Filtered TEM (EFTEM) and Energy Dispersive X-Ray (EDX) spectrometry revealed a clear difference in the chemical composition of the ramp layers. Smooth gradients together with a nanocomposite structure seem to provide a high stability of the ramp layer against delamination. (C) 2010 Elsevier B.V. All rights reserve
Keywords: Diamond-like carbon; Interface; Adhesion strength; Cr adhesion layer

Microsegregation and precipitates of an as-cast Co-based superalloy-microstructural characterization and phase stability modelling - Kossmann, J.; Zenk, Carolin; Lopez-Galilea, I.; Neumeier, Steffen; Kostka, A.; Huth, S.; Theisen, W.; Göken, Mathias; Drautz, Ralf; Hammerschmidt, Thomas (Journal of Materials Science, 2015)
The demand for increased efficiency of industrial gas turbines and aero engines drives the search for the next generation of materials. Promising candidates for such new materials are Co-based superalloys. We characterize the microsegregation and solidification of a multi-component Co-based superalloy and compare it to a ternary Co–Al–W compound and to two exemplary Ni-based superalloys by combining the experimental characterization of the as-cast microstructures with complementary modelling of phase stability. On the experimental side, we characterize the microstructure and precipitates by electron microscopy and energy-dispersive X-ray spectroscopy and determine the element distributions and microsegregation coefficients by electron probe microanalysis (EPMA). On the modelling side, we carry out solidification simulations and a structure map analysis in order to relate the local chemical composition with phase stability. We find that the microsegregation coefficients for the individual elements are very similar in the investigated Co-based and Ni-based superalloys. By interpreting the local chemical composition from EPMA with the structure map, we effectively unite the set of element distribution maps to compound maps with very good contrast of the dendritic microstructure. The resulting compound maps of the microstructure in terms of average band filling and atomic-size difference explain the formation of topologically close-packed phases in the interdendritic regions. We identify B2, C14, and D024 precipitates with chemical compositions that are in line with the structure map.<br
WW1::1029
Keywords: Laves Phase; Interdendritic Region; Solidification Path; Dendrite Core; Transmission Electron Microscopy

Microstructural and micromechanical characterisation of a Pt-Al-Cr-Ni-Re alloy by means of transmission electron microscopy and nanoindentation - Nikulina, Elizaveta; Durst, Karsten; Göken, Mathias; Voelkl, Rainer; Glatzel, Uwe (International Journal of Materials Research, 2010)
WW1::849

Microstructural and micromechanical characterisation of TiAl alloys using atomic force microscopy and nanoindentation - Gebhard, Susanne; Pyczak, Florian; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::814

Microstructural Aspects of Cyclic Deformation and Fatigue of Ultrafine-Grained Metals - Mughrabi, Hael; Höppel, Heinz Werner; Kautz, Martin (Nanostructured Materials by High-Pressure Severe Plastic Deformation, 2006)
In recent years, the cyclic deformation and fatigue behaviours of different model and commercial ultrafine-grained (UFG) metals prepared by severe plastic deformation (SPD) techniques have been studied. The present contribution is based largely on the authors’ recent work on fatigued UFG high-purity copper, commercial purity Al, the age-hardenable aluminium alloy AA6061 and α-brass, all prepared by ECAP (equal channel angular pressing). Emphasis is laid on the microstructural mechanisms governing cyclic microplasticity, cyclic deformation, the cyclic stress-strain (CSS) response, as displayed in the CSS-curve, fatigue damage and fatigue life. The roles of fatigue strength, fatigue ductility and microstructural stability of UFG materials in controlling fatigue life in high-cycle and in low-cycle fatigue will be discussed<br
Keywords: Fatigue Life; Severe Plastic Deformation; Equal Channel Angular Pressing; Cyclic Deformation; Plastic Strain Amplitude

Microstructural dependence of the fracture toughness of metallic thin films: A bulge test and atomistic simulation study on single-crystalline and polycrystalline silver films - Preiß, Eva; Lyu, Hao; Liebig, Jan Philipp; Richter, Gunther; Gannott, Florentina; Gruber, Patric A.; Göken, Mathias; Bitzek, Erik; Merle, Benoit (Journal of Materials Research, 2019)
The microstructure contribution to the very low fracture toughness of freestanding metallic thin films was investigated by bulge fracture tests on 200-nm-thick 100 single-crystalline and polycrystalline silver films. The single-crystalline films exhibited a significantly lower fracture toughness value (KIC = 0.88 MPa m1/2) than their polycrystalline counterparts (KIC = 1.45 MPa m1/2), which was rationalized by the observation of an unusual crack initiation behavior - characterized by twinning in front of the notch tip - during in situ testing in the atomic force microscope. Twinning was also observed as a dominant deformation mechanism in atomistic simulations. This twinning tendency is explained by comparing the resolved shear stresses acting on the leading partial dislocation and the full dislocation, which allows to develop a size- and orientation-dependent twinning criterion. The fracture toughness of polycrystalline samples was found to be higher because of the energy dissipation associated with full dislocation plasticity and because of crack meandering along grain boundaries.
CRIS-Team Scopus Importer:2019-09-27
Keywords: atomistic simulations; bulge testing; fracture testing; grain boundaries; silver; thin films; twinning criterion

Microstructural design of Ni-base alloys for high-temperature applications: impact of heat treatment on microstructure and mechanical properties after selective laser melting - Brenne, Florian; Taube, A.; Pröbstle, Martin; Neumeier, Steffen; Schwarze, D.; Schaper, M.; Niendorf, Thomas (Progress in Additive Manufacturing, 2016)
WW1::1071
Keywords: High Temperature

Microstructural evolution and mechanical properties in Zr–Cu–Al–Nb bulk metallic glass composites prepared by laser metal deposition - Luo, Ning; Galgon, Florian; Krauß, Sebastian; Morales, Luis A.; Merle, Benoit; Zenk, Christopher; Körner, Carolin (Intermetallics, 2022)
In this work, laser metal deposition (LMD), a direct energy deposition (DED) additive manufacturing technology, is used to prepare Zr59.3Cu28.8Al10.4Nb1.5 bulk metallic glass composites (BMGCs). Phase constitutions and thermal behavior of LMD-processed Zr–Cu–Al–Nb samples are examined using X-ray diffraction (XRD) and differential scanning calorimetry (DSC). The microstructure evolution parallel to the build direction is characterized in detail utilizing scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), electron probe microscopy analysis (EPMA) and electron backscatter diffraction (EBSD). Young's modulus and hardness in typical microstructures are evaluated employing nanoindentation. Within each deposited layer, a periodic microstructure, exhibiting crystalline features of three distinctly different morphologies, is observed, depending on the location within that layer. Along the build direction, the dominating microstructure of the melt pool evolves from a nearly featureless amorphous state over fine nanocrystals to coarse nanocrystals while the morphology of most micro-scale dendritic crystals changes from flower-shaped to columnar, simultaneously a coarse microstructure appearing in upper layers. The fine Al-rich phases gradually coarsen directionally parallel to the build direction. Furthermore, the correlation between microstructure and mechanical properties is investigated. This work enhances our knowledge about microstructural characteristics and mechanical properties of BMGCs in-situ fabricated by DED additive manufacturing.
Created from Fastlane, Scopus look-up
Keywords: Bulk metallic glass composites; Crystallization; Laser metal deposition; Microstructure; Nanoindentation

Microstructural evolution during creep of Ca-containing AZ91 - Amberger, D.; Eisenlohr, Philip; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::816

Microstructural evolution during deformation of tin dioxide nanoparticles in a comminution process - Armstrong, Patrick; Knieke, Catharina; Mackovic, Mirza; Frank, Gerhard; Hartmaier, Alexander; Göken, Mathias; Peukert, Wolfgang; Mackovic, Mirza (Acta Materialia, 2009)
Nanoparticles can be produced by wet grinding in stirred media mills if agglomeration is prevented by stabilization of the particles. Since the fracture mechanisms at the lower nanoscale are not yet understood, we studied the evolution of the microstructure within tin dioxide particles. Electrostatic stabilization allows the formation of tin dioxide with a mean particle size of 25 nm as measured by dynamic light scattering. High-resolution transmission electron microscopy (HRTEM) images show particles well below 10 nm and mean crystallite sizes of 9 nm were obtained from X-ray diffraction by applying the Rietveld refinement method. Additionally, TEM and HRTEM analyses were conducted to gain detailed insight into the microstructural effects governing the grinding process. Microscopy revealed surprisingly rich phenomena including the formation of shear bands, twinning and stacking faults that directly affect the grinding behavior. Interestingly the ceramic nanoparticles showed not only fracture patterns expected from brittle fracture but also many traces of plastic deformation. For comparison the uniaxial compression of particles up to 30 nm in diameter was simulated using molecular dynamics. The simulated particles shared microstructural details with the real samples, most importantly the shear bands which lead to significant plastic deformation. The internal microstructure produced during multiple particle stressing events in the mill and also observed in the simulations is directly linked to the fracture mechanism and the experimentally observed grinding limit. © 2009 Acta Materialia In
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.micros
Keywords: Molecular dynamics simulations; Nanomechanics; Nanostructure; Shear bands; Transmission electron microscopy (TEM)

Microstructural study of the parameters governing coarsening and cyclic softening in fatigued ultrafine-grained copper - Höppel, Heinz Werner; Mughrabi, Hael; et al. (Philosophical Magazine A, 2002)
The cyclic deformation behaviour of ultrafine-grained (UFG) copper produced by equal-channel angular pressing was investigated. Special attention was paid to the parameters governing cyclic softening and cyclic grain coarsening. UFG copper shows significant cyclic softening for the tests performed at intermediate plastic strain amplitudes Δεpl/2, that is in the range 2 × 10-4 ≤ Δεpl/2 ≤ 1.0 × 10-3. Within this range, the cyclic softening as well as the intensity of grain coarsening increase with decreasing plastic strain amplitude. By contrast, under stress control, corresponding to a plastic strain amplitude range 2.4 × 10-5 ≤ Δεpl/2 ≤ 1.2 × 10-4, cyclic softening as well as the intensity of grain coarsening decrease with decreasing plastic strain amplitude. Furthermore, cyclic softening and grain coarsening were also found to be enhanced by decreasing the deformation rate (and thus increasing the test time) and/or by increasing the temperature. These findings indicate that the responsible microstructural processes are thermally activated. Based on the experimental results, a dynamic 'recrystallization' mechanism is proposed and suggested to be responsible for the cyclic grain coarsening and to some extent also for the cyclic softening.
UnivIS-Import:2015-03-09:Pub.2002.tech.IW.LWAW.micros

Microstructure and compression strength of Co-based superalloys hardened by γ′ and carbide precipitation - Carton-Cordero, Marta; Campos, Monica; Freund, Lisa; Kolb, Markus; Neumeier, Steffen; Göken, Mathias; Torralba, José M. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2018)
A Co-based superalloy, Co-9Al-9W (at%), was processed by mechanical alloying by high-energy milling of elemental powders and consolidated by field assisted hot pressing (FAHP). The milled powder particles mainly consist of undissolved bcc-W as well as WC and an Al and W rich fcc-gamma Co solid solution. After consolidation and heat treatment a fine grained microstructure with a high fraction of carbides and a gamma/gamma' microstructure was obtained. The compressive yield strength at room temperature was found to be 45% higher than that of previously reported results for Co-based superalloys. A similar level of strength was found at 700 degrees C. These extraordinary properties can be explained due to the multitude of hardening mechanisms that sintered Co-based superalloys possess: gamma' precipitation, carbide formation and the ultra-fine se-grain size promoted by the fast consolidation technique.
Keywords: Co-Al-W superalloys; PM route; Mechanical properties; Nanoindentation; Mechanical milling

Microstructure and creep strength of different γ/γ′-strengthened Co-base superalloy variants - Bauer, Alexander; Neumeier, Steffen; Pyczak, Florian; Göken, Mathias (Scripta Materialia, 2010)
WW1::850

Microstructure and creep strength of different γ/γ′- strengthened Co-base superalloy variants - Göken, Mathias; Bauer, Alexander; Pyczak, Florian; Neumeier, Steffen (2010)
Keywords: Cobalt; Superalloy; Creep; Volume fraction; Thermal stability

Microstructure and local mechanical properties of Pt-modified nickel aluminides on nickel-base superalloys after thermo-mechanical fatigue - Franke, Oliver; Durst, Karsten; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2007)
A single-phase and a two-phase platinum modified aluminide coating on the nickel-base superalloy CMSX-6 were investigated with analytical scanning electron microscopy (SEM) and nanoindentation in the as-coated condition and after thermo-mechanical fatigue loading (TMF). The microstructure of the single-phase coating exhibits high stability during TMF-loading and hardly any grain coarsening is observed. The grain size was determined by electron channelling contrast images (ECC) in the SEM to be 45.6 and 39.7 μm, respectively. In the two-phase coating the PtAl2 second phase particles dissolve throughout TMF-loading causing a coarsening of the β-NiAl grains from an original size of 5.5-18.5 μm after TMF. The microstructural evolution is associated with a strong change in the local mechanical properties as determined by nanoindentation. It is found that Young's modulus as well as hardness decrease in both investigated systems. The change in local mechanical properties is related to the microstructural and chemical changes of the coating. As far as the β-NiAl phase is concerned, the Al concentration is found to be the main reason for the decrease in Young's modulus. This behaviour was confirmed by nanoindentation measurements on a Ni-NiAl diffusion couple.
Created from Fastlane, Scopus look-up
Keywords: Hardness; Microstructure; Nanoindentation; NiAl-diffusion coatings; Thermo-mechanical fatigue; Young's modulus

Microstructure and Mechanical Properties of Accumulative Roll-Bonded AA1050A/AA5005 Laminated Metal Composites - Kümmel, Frank; Kreuz, Michael; Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias (Metals, 2016)
Laminated metal composites (LMCs) with alternating layers of commercial pure aluminum AA1050A and aluminum alloy AA5005 were produced by accumulative roll-bonding (ARB). In order to vary the layer thickness and the number of layer interfaces, different numbers of ARB cycles (4, 8, 10, 12, 14 and 16) were performed. The microstructure and mechanical properties were characterized in detail. Up to 8 ARB cycles, the ultrafine-grained (UFG) microstructure of the layers in the LMC evolves almost equally to those in AA1050A and AA5005 mono-material sheets. However, the grain size in the composites tends to have smaller values. Nevertheless, the local mechanical properties of the individual layers in the LMCs are very similar to those of the mono-material sheets, and the macroscopic static mechanical properties of the LMCs can be calculated as the mean value of the mono-material sheets applying a linear rule of mixture. In contrast, for more than 12 ARB cycles, a homogenous microstructure was obtained where the individual layers within the composite cannot be visually separated any longer; thus, the hardness is at one constant and a high level across the whole sheet thickness. This results also in a significant higher strength in tensile testing. It was revealed that, with decreasing layer thickness, the layer interfaces become more and more dominating.
WW1::1066
Keywords: Nanomaterials

Microstructure and mechanical properties of accumulative roll bonded AA6014/AA5754 aluminium laminates - Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias (Materials Science Forum, 2011)
Among the well-known methods of severe plastic deformation the accumulative roll bonding (ARB) process is most promising for producing ultrafine-grained (UFG) materials with extraordinary mechanical properties at an industrial scale. Besides, it has also been shown that the ARB process can be successfully used to produce multi-component materials with tailored properties by reinforcement or grading, respectively. In this work, laminates with alternating layers of the high strength aluminium alloy AA5754 and the AA6014 alloy, well-known for good formability and high surface quality, were produced by ARB at 230 °C. Microstructural and mechanical investigations were performed after 2, 4 and 6 ARB cycles by means of light and electron microscopy, nanoindentation experiments and tensile testing. After ARB processing an ultrafine-grained microstructure is obtained. The UFG microstructure as well as the local mechanical properties alter with the layer composition. With increasing number of ARB cycles the interfaces between the layers become more and more wavy by shear band formation. Compared to the pure accumulative roll bonded AA6014 the yield and ultimate tensile strength of the multi-component laminates are considerably higher and are only slightly reduced in comparison to the high strength AA5754. In terms of elongation to failure no reduction in ductility is found. The serrated yielding effect, clearly visible in AA5754, is shifted to higher strains or fully disappears, respectively, whereas in AA5754 the magnitude of serrations increases with increasing number of ARB cycles. Combining AA5754 and AA6014 sheets by ARB results in well bonded ultrafine-grained laminates which exhibit a combination of the beneficial properties of the single-component materials: high strength of AA5754 and good surface quality of AA6014.
WW1::889

Microstructure and mechanical properties of accumulative roll bonded aluminium alloy AA5754 - Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias (Journal of Physics: Conference Series, 2010)
The aluminium alloy AA5754 is used for many technical applications. In this work, the accumulative roll bonding process is applied to this alloy in order to investigate the potential of an ultrafine-grained structure on the mechanical properties of this Al-Mg alloy. Sheets from AA5754 (AlMg3) were successfully processed by accumulative roll bonding in order to obtain an ultrafine-grained microstructure. The ARB process was performed at 230 °C or 250 °C up to 7 or 8 cycles respectively. Thus the grain size decreased from 10 extgreekmm (initial state) to approximately 80 nm (ultrafine-grained state, normal direction). The microstructural evolution and the mechanical properties have been investigated by means of scanning electron microscopy, hardness measurements and tensile testing. After one ARB cycle the samples showed an increase in hardness by a factor of almost 2 in comparison to the as-received material. Further processing causes a linear increase of hardness with each additional cycle. Yield strength and tensile strength of the roll bonded specimens are highly increased in comparison to the as-received samples whereas the ductility declined. A considerable increase in ductility is obtained by heat treatment of the ARB specimens at 250 °C, but on the expense of a moderate decreased strength. The deformation behaviour is also influenced by the ultrafine-grained structure. The occurrence of the Portevin-Le Chatelier effect is manifested by serrated stress-strain curves. The amplitude of serrations increases with increasing number of ARB cycles but can be reduced by the appliance of a higher strain rate. Lüders strain only occurs at the as-received, i.e. not strained, samples.
EAM Import::2019-03-12

Microstructure and mechanical properties of Cr-Ta-Si Laves phase-based alloys at elevated temperatures - Bhowmik, Ayan; Neumeier, Steffen; Barnard, Jon S.; Zenk, Christopher; Göken, Mathias; Rae, Catherine M. F.; Stone, Howard J. (Philosophical Magazine, 2014)
The microstructure and mechanical properties of a series of Cr-CrTa-based alloys with nominal compositions (90-x)Cr-9Ta-xSi, where x = 4, 6, 10 and 14 at%, have been investigated. The alloys predominantly consisted of a microstructure of primary C14 CrTa Laves phase dendrites and a eutectic intergrowth of an A2 Cr rich solid solution and the Laves phase. The Laves phase was seen to adopt the C14 polytype in all ternary alloys, with no evidence of transformation to the C15 polytype. Fine, solid-state precipitates of the Laves phase were also observed within the solid solution. At higher silicon contents, a third intermetallic phase, CrSi, with the A15 crystal structure, was also identified. The overall hardness of the alloys at room temperature increased with Si content and hence, the volume fraction of the Laves phase. Compression tests were conducted on samples of the alloys at 1000 and 1100 °C under a strain rate of 10 s in air. Amongst the ternary alloys, the alloy with 14 at% Si showed the highest yield strength of 440 MPa at 1000°C and ∼290 MPa at 1100°C. The yield strength of the alloy with 6 at% Si was also found to reduce monotonically with increasing temperature from ambient to 1100°C. Transmission electron microscopy of the post-compression microstructures revealed that deformation was primarily accommodated by the A2 Cr-rich solid solution, with a high density of dislocations in the phase compared to that in the intermetallic phase. Within the C14 Laves phase, deformation was seen to be mediated by the movement of a/3-type synchro-Shockley partial dislocations, consistent with previous studies, bounding stacking faults on the basal plan
Keywords: deformation; dislocation; electron microscopy; intermetallics; Laves phase; transmission

Microstructure and Mechanical Properties of Hypereutectic Al-High Si Alloys up to 70 wt.% Si-Content Produced from Pre-Alloyed and Blended Powder via Laser Powder Bed Fusion - Risse, Jan Henning; Trempa, Matthias; Huber, Florian; Höppel, Heinz Werner; Bartels, Dominic; Schmidt, Michael; Reimann, Christian; Friedrich, Jochen (Materials, 2023)
Hypereutectic Al-high Si alloys are of immense interest for applications in the automotive, space or electronic industries, due their low weight, low thermal expansion, and excellent mechanical and tribological properties. Additionally, their production by laser powder bed fusion (LPBF) technology provides high flexibility in geometrical design and alloy composition. Since, most of the alloy properties could be improved by increasing the Si content, there is much interest in discovering the maximum that could be realized in LBPF Al-high Si alloys, without the appearance of any material failure. For this reason, in this work the production of Al-high Si alloys with extremely high silicon content of up to 70 wt.% was fundamentally investigated with respect to microstructure and mechanical properties. Highly dense (99.3%) and crack-free AlSi50 samples (5 × 5 × 5 mm3), with excellent hardness (225 HV5) and compressive strength (742 MPa), were successfully produced. Further, for the first time, AlSi70 LBPF samples of high density (98.8%) without cracks were demonstrated, using moderate scanning velocities. Simultaneously, the hardness and the compressive strength in the AlSi70 alloys were significantly improved to 350 HV5 and 935 MPa, as a result of the formation of a continuous Si network in the microstructure of the alloy. With respect to the powder source, it was found that the application of powder blends resulted in similar alloy properties as if pre-alloyed powders were used, enabling higher flexibility in prospective application-oriented alloy development.<br
CRIS-Team Scopus Importer:2023-01-27
Keywords: additive manufacturing; hypereutectic Al-high Si alloys; in-situ alloying; laser powder bed fusion; mechanical properties; microstructure

Microstructure-dependent deformation behaviour of bcc-metals - indentation size effect and strain rate sensitivity - Maier, Verena; Schunk, Christopher; Göken, Mathias; Durst, Karsten (Philosophical Magazine, 2015)
In this work, the indentation size effect and the influence of the microstructure on the time-dependent deformation behaviour of body-centred cubic (bcc) metals are studied by performing nanoindentation strain rate jump tests at room temperature. During these experiments, the strain rate is abruptly changed, and from the resulting hardness difference the local strain rate sensitivity has been derived. Single-crystalline materials exhibit a strong indentation size effect; ultrafine-grained metals have nearly a depth-independent hardness. Tungsten as a bcc metal shows the opposite behaviour as generally found for face-centered cubic metals. While for UFG-W only slightly enhanced strain rate sensitivity was observed, SX-W exhibits a pronounced influence of the strain rate on the resulting hardness at room temperature. This is due to the effects of the high lattice friction of bcc metals at low temperatures, where the thermally activated motion of screw dislocations is the dominating deformation mechanisms, which causes the enhanced strain rate sensitivity. For the SX-materials, it was found that the degree of the indentation size effect directly correlates with the homologous testing temperature and thus, the material specific parameter of the critical temperature T-c. However, for the resultant strain rate sensitivity no depth-dependent change was found.
Keywords: nanoindentation; bcc metals; deformation behaviour; strain rate sensitivity; indentation size effect

Microstructure development and hardness of a powder metallurgical multi phase γ-TiAl based alloy - Schloffer, Martin; Iqbal, Farasat; Gabrisch, Heike; Schwaighofer, Emanuel; Schimansky, Frank-Peter; Mayer, Svea; Stark, Andreas; Lippmann, Thomas; Göken, Mathias; Pyczak, Florian; Clemens, Helmut (Intermetallics, 2012)
Keywords: A. Titanium aluminides; C. Powder metallurgy; D. Microstructure; B. Grain growth; B. Phase transformation

Microstructure development and hardness of a powder metallurgical multi phase γ-TiAl based alloy - Schloffer, Martin; Iqbal, Farasat; Gabrisch, Heike; Schwaighofer, Emanuel; Schimansky, Frank-Peter; Mayer, Svea; Stark, Andreas; Lippmann, Thomas; Göken, Mathias; Pyczak, Florian; Clemens, Helmut (Intermetallics, 2012)
WW1::941

Microstructure, Lattice Misfit, and High-Temperature Strength of γ′-Strengthened Co-Al-W-Ge Model Superalloys - Zenk, Christopher; Bauer, Alexander; Goik, Philip; Neumeier, Steffen; Stone, Howard J.; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2016)
WW1::1060
Keywords: High Temperature

Microstructure, mechanical properties and tribological behavior of magnetron-sputtered mos2 solid lubricant coatings deposited under industrial conditions - Seynstahl, Armin; Krauß, Sebastian; Bitzek, Erik; Meyer, Bernd; Merle, Benoit; Tremmel, Stephan (Coatings, 2021)
Depositing MoS2 coatings for industrial applications involves rotating the samples during the PVD magnetron sputtering process. Here, we show that a 3-fold substrate rotation, along a large target–substrate distance given by the deposition unit, introduces porosity inside the coatings. The mechanical properties and wear behavior strongly correlate with the degree of porosity, which, in turn, depends on the temperature and the rotational speed of the substrate. Ball-on-disk tests and nanoindentation wear experiments show a consistent change in tribological behavior; first, a compaction of the porous structure dominates, followed by wear of the compacted material. Compaction was the main contributor to the volume loss during the running-in process. Compared to a dense coating produced without substrate rotation, the initially porous coatings showed lower hardness and a distinct running-in behavior. Tribological lifetime experiments showed good lubrication performance after compaction.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Friction; Microstructure; MoS; Nanoindentation; PVD; Wear mechanisms

Microtensile creep testing of freestanding MCrAlY bond coats - Giese, Sven; Neumeier, Steffen; Amberger-Matschkal, Doris; Bergholz, Jan; Vaßen, Robert; Göken, Mathias (Journal of Materials Research, 2019)
Bond coats are essential in gas turbine technology for oxidation protection. Freestanding MCrAlY (M = Ni, Co) bond coats were investigated with respect to their creep strength at elevated temperatures. Three types of MCrAlY, a Ni-based bond coat Amdry 386, a Co-based bond coat Amdry 9954 and Amdry 9954 + 2 wt% Al2O3 (ODS = oxide dispersion strengthened) produced by low pressure plasma spraying, were analyzed. The two phase microstructure of the bond coats consists of a fcc γ-Ni solid solution and a B2 β-NiAl phase. Constant load experiments were performed in a thermomechanical analyzer at temperatures between 900 and 950 °C. Microtensile test specimens with a diameter of 450 μm were produced by a high-precision grinding and polishing process. Creep rupture was mainly due to void nucleation along the β-γinterfaces and grain boundaries. The time to failure is larger in Ni-based Amdry 386 compared to that in Co-based Amdry 9954 due to a higher fraction of the high-strength β-NiAl phase at test temperatures. The addition of ODS-particles in the Co-based bond coat Amdry 9954 resulted in a better creep resistance but lower ductility in comparison to ODS-particle-free Amdry 9954.
CRIS-Team Scopus Importer:2019-06-04
Keywords: bond coat; creep; MCrAlY; small scale testing

Mikrostruktur und lokale mechanische Eigenschaften von platinmodifizierten Aluminidschichten auf Nickelbasis-Superlegierungen nach thermomechanischer Ermüdung - Durst, Karsten; Höppel, Heinz Werner; Göken, Mathias; et al. (Prakt. Met. Sonderband 36, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IW.LWAW.mikros

Miniaturized bend tests on partially stabilized EB-PVD ZrO2 thermal barrier coatings - Pfeiffer, Carolin; Affeldt, Ernst; Göken, Mathias (Surface & Coatings Technology, 2011)
Keywords: Porosity; Thermal barrier coatings; EB-PVD TBC; Bending; Nanoindentation; Mechanical properties

Miniaturized bend tests on partially stabilized EB-PVD ZrO2 thermal barrier coatings - Pfeiffer, Carolin; Affeldt, Ernst; Göken, Mathias (Surface & Coatings Technology, 2011)
The elastic properties of thermal barrier coatings (TBCs) are important for modelling the lifetime of these coatings. A new test setup has been developed to measure the system modulus of electron-beam enhanced physical vapour deposited (EB-PVD) TBC coatings by miniaturized bend tests. Due to the brittleness, low stiffness and small thickness of the top coat and its complex microstructure, it is difficult to measure its Young's modulus by standard mechanical testing. For this reason, a special sample material has been prepared which consists of a 1 mm thick layer of EB-PVD TBC. This material was isothermally heat treated for different times at 950 °C, 1100 °C and 1200 °C and then tested in a specially developed miniaturized bend test. The bend test setup permits mechanical tests with a high resolution in stress and strain, where the strain is measured by digital image correlation. So the stiffness of the free-standing TBC samples could be measured with a high accuracy and the sintering behaviour of the EB-PVD TBC and the consequent rise of Young's modulus could be determined. The results show a significant increase of the system modulus with heat treatment time and temperature caused by sintering of the coating. An activation energy of 220 kJ/mol for the process has been determined. In addition, the material was tested by nanoindentation in order to measure Young's modulus on a local scale, and the porosity of the samples was determined by quantitative image analysis.
WW1::891

Miniaturized gas exposure devices for atom probe experiments - Ott, Benedict; Heller, Martina; Monajem, Mehrpad; Felfer, Peter (Microscopy research and technique, 2024)
To detect hydrogen in materials at the atomic scale, atom probe tomography is now regularly used. In order to avoid cumbersome cryo-preparation to suppress diffusion, often hydrogen is charged only into the finished specimen. Here, the use of hydrogen gas over electrochemical hydrogen has the advantage that the specimen is not contaminated with an electrolyte. So far, this “charging” has been done in large, expensive systems. Here, we introduce small devices that enable the exposure of atom probe specimens to hydrogen and potentially other gases, using only very small gas volumes. This enables the operation in regular laboratory environments without additional safety measures. These devices can be used to expose the specimen to hydrogen up to 10 bar/90°C. Higher temperatures may be attained with small changes. Validation of the success of charging with these setups is demonstrated through experiments employing deuterium charging of palladium atom probe tips. Research Highlights: Enabling the exposure of atom probe specimens to hydrogen and potentially other gases, using only very small gas volumes. Built setups can be assembled with little money and from freely available parts, making specimen charging much easier. Validation of the success of charging with these setups is demonstrated through experiments employing deuterium charging of palladium atom probe tips.
CRIS-Team Scopus Importer:2024-05-10
Keywords: atom probe; atom probe tomography; deuterium; deuterium gas charging

Mining information from atom probe data - Cairney, Julie M.; Rajan, Krishna; Haley, Daniel; Gault, Baptiste; Bagot, Paula. J.; Choi, Pyuck-Pa; Felfer, Peter; Ringer, Simon P.; Marceau, Ross K. W.; Moody, Michael P. (Ultramicroscopy, 2015)
Whilst atom probe tomography (APT) is a powerful technique with the capacity to gather information containing hundreds of millions of atoms from a single specimen, the ability to effectively use this information creates significant challenges. The main technological bottleneck lies in handling the extremely large amounts of data on spatial-chemical correlations, as well as developing new quantitative computational foundations for image reconstruction that target critical and transformative problems in materials science. The power to explore materials at the atomic scale with the extraordinary level of sensitivity of detection offered by atom probe tomography has not been not fully harnessed due to the challenges of dealing with missing, sparse and often noisy data. Hence there is a profound need to couple the analytical tools to deal with the data challenges with the experimental issues associated with this instrument. In this paper we provide a summary of some key issues associated with the challenges, and solutions to extract or "mine" fundamental materials science information from that dat
Keywords: Atom probe tomography; Clustering; Crystallography; Data mining; Microscopy; Short range order

Modelling the transition from strengthening to softening due to grain boundaries - Zeng, Xiaohui; Eisenlohr, Philip; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2008)
WW1::777

Monitoring the precipitation of the hardening phase in the new VDM® Alloy 780 by in-situ high-temperature small-angle neutron scattering, neutron diffraction and complementary microscopy techniques - Solís, C.; Kirchmayer, Andreas; da Silva, I.; Kümmel, F.; Mühlbauer, S.; Beran, P.; Gehrmann, B.; Haghighat, M. Hafez; Neumeier, Steffen; Gilles, R. (Journal of Alloys and Compounds, 2022)
The hardening phase precipitation process plays an important role in the development of new Ni-base superalloys. In the present work, we apply a powerful combination of complementary characterization techniques to characterize in-situ the γ’ precipitation in the new VDM® Alloy 780. During the whole heat treatment process, in-situ time-of-flight (TOF) neutron diffraction (ND) unambiguously identified the γ’ phase as well as its weight fraction and the misfit with the matrix while in-situ small-angle neutron scattering (SANS) provided precise precipitates’ size analysis. Atom probe tomography (APT) and scanning electron microscopy (SEM) provided detailed microstructural characterization and chemical composition of the phases necessary for a proper neutron scattering data evaluation. This contribution reveals more detailed information on the nucleation, growth, and Ostwald ripening processes starting from the early precipitation stage in bulk samples using the complementary microstructure investigation methods. The nucleation and growth kinetics of precipitates at 720 °C depend on heating rates and the size distribution obtained in the pre-heating history of the sample. A subsequent heat treatment step at 620 °C, typically used in Ni-base superalloys, does not lead to similar progressive precipitation or growth. The expected matrix-diffusion-controlled Ostwald ripening process of the γ’ precipitates was in-situ monitored by SANS on a full precipitation hardened sample at expected operating temperatures (750 °C) showing slower coarsening kinetics than other reported Ni-based superalloys.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Atom probe tomography (APT); Neutron diffraction (ND); Ni-base superalloys; Ostwald ripening; Precipitation; Small-angle neutron scattering (SANS); kernfusionsrelevant

Monotonic and cyclic deformation behaviour of ultrafine-grained aluminium - May, Johannes; Amberger, D.; Dinkel, Markus; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2008)
WW1::778

Morphology evolution of Ti3AlC carbide precipitates in high Nb containing TiAl alloys - Wang, Li; Zenk, Carolin; Stark, Andreas; Felfer, Peter; Gabrisch, Heike; Göken, Mathias; Lorenz, Uwe; Pyczak, Florian (Acta Materialia, 2017)
This work elucidates the morphology evolution of perovskite Ti3AlC carbides in a Ti-45Al-5Nb-0.75C alloy during ageing at 800 °C. The carbides in the g matrix are initially needle-shaped with their long axis parallel to the [001] lattice direction of the g matrix. After extended annealing, they decompose into small carbide sub-particles. By combining different transmission electron microscopy characterization methods and atom probe tomography it has been verified that the carbides first split into several parallel needles that are aligned along the [001]g lattice direction. Later these parallel needles further decompose into numerous small sub-particles, while the matrix phase region between the sub-particles crystallographically reorients. To the authors' knowledge this is the first work which demonstrates such a precipitate splitting process in a matrix with a tetragonal crystal structure. It is proposed that the decomposition into small sub-particles is energetically favourable owing to the elastic interaction energy between the split sub-particle
Keywords: Titanium aluminides; Carbides; Morphology; Splitting; Transmission electron microscopy

Multicomponent materials from machining chips compacted by equal-channel angular pressing - Lapovok, Rimma; Qi, Yuanshen; Ng, Hoi Pang; Maier, Verena; Estrin, Yuri (Journal of Materials Science, 2014)
Al and Mg machining chip blends were compacted by equal-channel angular pressing with back pressure. By varying the weight fraction of the constituent materials, temperature and processing route, as well as employing subsequent heat treatment, the microstructure and the mechanical properties of the compact were varied. The width of the interdiffusion zone and the formation of intermetallic phases near the interfaces between the two metals were studied by energy-dispersive X-ray spectroscopy and nanoindentation. It was shown that substantial improvement of mechanical properties, such as an increase of strength, strain-hardening capability and ductility, can be obtained. This is achieved by changing the processing parameters of equal-channel angular pressing and the annealing temperature, as well as by optimising the weight fraction of the constituent metals.

Multiscale Materials Modeling: Approaches to Full Multiscaling - Möller, Johannes; Prakash, Aruna; Bitzek, Erik (De Gruyter, Berlin, 2016)

Nanoforming behaviour and microstructural evolution during nanoimprinting of ultrafine-grained and nanocrystalline metals - Ast, Johannes; Durst, Karsten (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
The influences of microstructure and the macroscopic material behaviour on the nanoforming behaviour of nickel, copper and aluminium with grain sizes ranging from single crystalline to nanocrystalline were studied using a flat punch indenter with a double ring cavity and with a wheel-shaped die. Of main interest in this work was the flow of crystalline materials in submicron sized cavities during imprinting. The ring cavities which have widths of 650 nm and 80 nm were fabricated by focused ion beam (FIB) machining. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used to evaluate the imprinted ring geometries. The microstructure after imprinting was investigated in detail by FIB cross sections and electron back scatter diffraction (EBSD) as well as by using finite element analysis (FEA) of the forming process. SX-Ni showed the smallest extrusion height together with a sinking-in of the formed region. This is accompanied by strong orientation gradients up to 18° below the cavities. The UFG samples exhibited the best formability, with a subgrain formation inside and around the cavities. The plastic flow is confined to the surface and a pile-up formation occurs. For the nanocrystalline material only a slight elongation of the grains inside the cavity was found, yielding moreover a smooth and homogeneous extruded geometry. These findings can be explained by the grain size to cavity width ratio as well as the yield strength and the work hardening behaviour of the materials.
WW1::976

Nanoindentation and XRD investigations of single crystalline Ni-Ge brazed nickel-base superalloys PWA 1483 and René N5 - Neumeier, Steffen; Dinkel, Markus; Pyczak, Florian; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2011)
WW1::892

Nanoindentation investigations to study solid solution hardening in Ni-based diffusion couples - Franke, Oliver; Durst, Karsten; Göken, Mathias (Journal of Materials Research, 2009)
WW1::819

Nanoindentations as a local probe fort he mechanical properties and alloying influences in nickel-base superalloys and aluminide coatings - Durst, Karsten; Göken, Mathias; Franke, Oliver (Superalloys 2004, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IW.LWAW.nanoin_2

Nanoindentation strain-rate jump tests for determining the local strain-rate sensitivity in nanocrystalline Ni and ultrafine-grained Al - Maier, Verena; Durst, Karsten; Müller, Johannes; Backes, Björn; Höppel, Heinz Werner; Göken, Mathias (Journal of Materials Research, 2011)
A nanoindentation strain-rate jump technique has been developed for determining the local strain-rate sensitivity (SRS) of nanocrystalline and ultrafine-grained (UFG) materials. The results of the new method are compared to conventional constant strain-rate nanoindentation experiments, macroscopic compression tests, and finite element modeling (FEM) simulations. The FEM simulations showed that nanoindentation tests should yield a similar SRS as uniaxial testing and generally a good agreement is found between nanoindentation strain-rate jump experiments and compression tests. However, a higher SRS is found in constant indentation strain-rate tests, which could be caused by the long indentation times required for tests at low indentation strain rates. The nanoindentation strain-rate jump technique thus offers the possibility to use single indentations for determining the SRS at low strain rates with strongly reduced testing times. For UFG-Al, extremely fine-grained regions around a bond layer exhibit a substantial higher SRS than bulk material.
WW1::893

Nanoindentation studies of the mechanical properties of the mu phase in a creep deformed Re containing nickel-based superalloy - Rehman, Hamad Ur; Durst, Karsten; Neumeier, Steffen; Parsa, Alireza B.; Kostka, Aleksander; Eggeler, Gunther; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2015)
WW1::1044
Keywords: Creep and Fatigue; High Temperature; Nanomechanics

Nanoindentierung Eine Sonde für die lokalen mechanischen Eigenschaften - Durst, Karsten; Göken, Mathias (Met. Sonderband 36, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IW.LWAW.nanoin

nanomech 5 - Göken, Mathias; Hangen, Ude D. (International Journal of Materials Research, 2022)
CRIS-Team WoS Importer:2022-02-18

Nanomechanical behaviour of Al-Ti layered composites produced by accumulative roll bonding - Maier, Verena; Höppel, Heinz Werner; Göken, Mathias (Journal of Physics: Conference Series, 2010)
In this study Ti-foils were roll bonded together with commercially pure aluminium AA1050. The laminates were produced by using two 1 mm thick AA1050 sheets at the outer side of the stack combined with 100 extgreekmm thick Ti-foils as an intermediate layer for each accumulative roll bonding process. The samples were rolled up to 4 ARB cycles. Subsequently the sheets were post-process heat treated at 180°C, 400°C or 600°C, respectively, for 24 hours. The local mechanical behaviour of the Al/Ti intermetallic interfaces have been investigated using nanoindentation experiments. A strong dependence between annealing-temperature, – time and deformation grade is detected. While a heat treatment at 180°C only leads to a weak bonding between Al and Ti with a preservation of the UFG structure, temperatures up to 600°C are causing a complete recrystallisation of the microstructure and formation of diffusion layers with different Al and Ti concentrations.
EAM Import::2019-03-12

Nano-mechanical testing in materials research and development - Jennett, Nigel M.; Göken, Mathias; Durst, Karsten (Philosophical Magazine, 2011)
WW1::894

Nanoscaled eutectic NiAl-(Cr,Mo) composites with exceptional mechanical properties processed by electron beam melting - Förner, Andreas; Giese, Sven; Arnold, Christopher; Felfer, Peter; Körner, Carolin; Neumeier, Steffen; Göken, Mathias (Scientific Reports, 2020)
Eutectic NiAl-(Cr,Mo) composites are promising high temperature materials due to their high melting point, excellent oxidation behavior and low density. To enhance the strength, hardness and fracture toughness, high cooling rates are beneficial to obtain a fine cellular-lamellar microstructure. This can be provided by the additive process of selective electron beam melting. The very high temperature gradient achieved in this process leads to the formation of the finest microstructure that has ever been reported for NiAl-(Cr,Mo) in-situ composites. A very high hardness and fracture toughening mechanisms were observed. This represents a feasibility study towards additive manufacturing of eutectic NiAl-(Cr,Mo) in-situ composites by selective electron beam melting.
CRIS-Team Scopus Importer:2020-09-25

Nanosculpt: A methodology for generating complex realistic configurations for atomistic simulations - Prakash, Aruna; Hummel, Martin; Schmauder, Siegfried; Bitzek, Erik (MethodsX, 2016)
Atomistic simulations have now become commonplace in the study of the deformation and failure of materials. Increase in computing power in recent years has made large-scale simulations with billions, or even trillions, of atoms a possibility. Most simulations to-date, however, are still performed with quasi-2D geometries or rather simplistic 3D setups. Although controlled studies on such well-defined structures are often required to obtain quantitative information from atomistic simulations, for qualitative studies focusing on e.g. the identification of mechanisms, researchers would greatly benefit from a methodology that helps realize more realistic configurations. The ideal scenario would be a one-on-one reconstruction of experimentally observed structures. To this end, we propose a new method and software tool called nanosculpt with the following features:The method allows for easy sample generation for atomistic simulations from any arbitrarily shaped 3D enclosed volume.The tool can be used to build atomistic samples from artificial geometries, including CAD geometries and structures obtained from simulation methods other than atomistic simulations.The tool enables the generation of experimentally informed atomistic samples, by e.g. digitization of micrographs or usage of tomography dat
Keywords: 3D materials science; Atom probe tomography; Digitized microstructure; Experimentally informed atomistic simulations; Molecular dynamics simulations; Ni-base superalloy

Nanostructured materials - Höppel, Heinz Werner; Pippan, Reinhard; Motz, Christian; Le Bourhis, Eric (Advanced Engineering Materials, 2012)
WW1::942

Nanostructured Materials - Höppel, Heinz Werner; Pippan, Reinhard; Motz, Christian; Le Bourhis, Eric (Advanced Engineering Materials, 2012)

Nanostructured Metallic Materials and Composites: Processes, Properties and Microstructures - Bachmaier, Andrea; Hohenwarter, Anton; Höppel, Heinz Werner; Ivanisenko, Julia (Advanced Engineering Materials, 2019)

Nanostructuring of Nb-Si-Cr Alloys by Electron Beam Melting to Improve the Mechanical Properties and the Oxidation Behavior - Förner, Andreas; Vollhüter, Jan; Hausmann, D.; Arnold, Christopher; Felfer, Peter; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2021)
Materials processed by additive manufacturing often exhibit a very fine-scaled microstructures due to high cooling rates in the process. In this study, single-layer surface electron beam melting is used to create very high cooling rates similar to additive manufacturing processes to investigate the resulting microstructure. In the case of Nb-Si-Cr in-situ composites, a nano-scaled eutectic microstructure is beneficial for improving the mechanical and oxidational properties. Fast solidification results in the formation of supersaturated phases of Nbss and Cr2Nb with phase diameters down to 10 nm as well as in the stabilization of the metastable Nb9(Cr,Si)5 phase at room temperature. After processing with different solidification rates, the decomposition of the Nb9(Cr,Si)5 phase has been studied in detail with atom probe microscopy. The stabilization of mixed silicide phases by electron beam melting shows a new pathway for improving hardness and enhancing oxidation resistance of nanostructured eutectic in-situ composites, by which the inherent weaknesses of Nb-Si-Cr can be overcome without further alloying elements. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-11-26

Nanotomographie metallischer Gefüge - Göken, Mathias; Durst, Karsten; et al. (Prakt. Met. Sonderband 35, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IW.LWAW.nanoto

New approaches to nanoparticle sample fabrication for atom probe tomography - Felfer, Peter; Li, Tong; Eder, K.; Galinski, H.; Magyar, A. P.; Bell, D. C.; Smith, G. D. W.; Kruse, N.; Ringer, S. P.; Cairney, J. M. (Elsevier, 2015)
Due to their unique properties, nano-sized materials such as nanoparticles and nanowires are receiving considerable attention. However, little data is available about their chemical makeup at the atomic scale, especially in three dimensions (3D). Atom probe tomography is able to answer many important questions about these materials if the challenge of producing a suitable sample can be overcome. In order to achieve this, the nanomaterial needs to be positioned within the end of a tip and fixed there so the sample possesses sufficient structural integrity for analysis. Here we provide a detailed description of various techniques that have been used to position nanoparticles on substrates for atom probe analysis. In some of the approaches, this is combined with deposition techniques to incorporate the particles into a solid matrix, and focused ion beam processing is then used to fabricate atom probe samples from this composite. Using these approaches, data has been achieved from 10-20 nm core-shell nanoparticles that were extracted directly from suspension (i.e. with no chemical modification) with a resolution of better than +/- 1 nm. (C) 2015 Elsevier B.V. All rights reserve
Keywords: Atom probe tomography; Nanoparticles; Sample preparation; Focussed ion beam

New atom probe approaches to studying segregation in nanocrystalline materials - Samudrala, S. K.; Felfer, Peter; Araullo-Peters, V. J.; Cao, Yang; Liao, X. Z.; Cairney, J. M. (Ultramicroscopy, 2013)
Atom probe is a technique that is highly suited to the study of nanocrystalline materials It can provide accurate atomic-scale information about the composition of grain boundaries in three dimensions. In this paper we have analysed the microstructure of a nanocrystalline super-duplex stainless steel prepared by high pressure torsion (HPT). Not all of the grain boundaries in this alloy display obvious segregation, making visualisation of the microstructure challenging. In addition, the grain boundaries present in the atom probe data acquired from this alloy have complex shapes that are curved at the scale of the dataset and the interfacial excess varies considerably over the boundaries, making the accurate characterisation of the distribution of solute challenging using existing analysis techniques. In this paper we present two new data treatment methods that allow the visualisation of boundaries with little or no segregation, the delineation of boundaries for further analysis and the quantitative analysis of Gibbsian interfacial excess at boundaries, including the capability of excess mapping. (C) 2013 Elsevier B.V. All rights reserve
Keywords: Atom probe; Nanocrystalline materials; Stainless steel; Grain boundaries

New boron and silicon free single crystal-diffusion brazing alloys - Dinkel, Markus; Heinz, Paul; Pyczak, Florian; Volek, Andreas; Ott, Michael; Affeldt, Ernst; Vossberg, A.; Göken, Mathias; Singer, Robert (Superalloys 2008: Proceedings of the 11th Intenational Symposium of Superalloys, 2008)
The solidification mechanisms and kinetics were examined and show rather distinct deviations from Transient Liquid Phase Bonding theory for binary systems due to the multicomponent diffusion in the present system. Mechanical testing was performed at room temperature via nanoindentation and at elevated temperatures by hot tensile tests. The nanoindentation results show minor differences in hardness and elastic modulus between brazing joints and parent material. Ultimate tensile strengths of more than 90 % compared to the parent material were obtained in tensile testing at 980 degrees
Keywords: repair; diffusion brazing; single crystalline; transient liquid phase bonding

New flat-punch indentation creep testing approach for characterizing the local creep properties at high temperatures - Matschkal, Dorothea; Kolb, Markus; Neumeier, Steffen; Gao, S.; Hartmaier, A.; Durst, K.; Göken, Mathias (Materials & Design, 2019)
An indentation creep testing approach has been developed which allows measuring creep properties at high temperatures. In contrast to existing indentation or impression creep experiments, the approach described here allows to achieve a quite high spatial resolution, as flat punch indenters with a diameter of only 20 μm are used. First indentation creep tests have been performed on single crystalline nickel and nickel binary solid solution alloys with Re, Ta or W as alloying elements, respectively. The indentation creep tests have been carried out at a temperature of 650 °C and stress levels in the range of 85 to 400 MPa. Using crystal plasticity finite element modeling, the indentation creep response is converted into equivalent uniaxial creep properties. It is shown that the conversion parameters, evaluated for differently oriented single crystals, can be chosen independently of the creep rate exponent in the power law creep regime. It is found that the indentation creep results agree well with conventional uniaxial creep tests. Furthermore, the results show that Ta is the most effective solid solution strengthener of all tested solid-solution strengtheners at 650 °C because of the large atomic size mismatch, followed by W and Re.
CRIS-Team Scopus Importer:2019-08-23
Keywords: Creep testing; Indentation creep testing; Indentation testing; Ni-alloys; Solid solution strengthening

New method of determining stress relaxation behavior in creep machines by controlled unloading - Blum, Wolfgang; Breutinger, Falk (International Journal of Materials Research, 2002)
Conventional measurement of stress relaxation in tests with constant total (elastic plus inelastic plus thermal) strain requires high resolution and excellent control of strain and is perturbed by thermal fluctuations. A new method for measuring the stress relaxation behavior is presented which avoids these experimental problems. It is based on the fact that the stress relaxation behavior is fully contained in the relation between inelastic strain rate and stress at given mechanical strain. Consequently, it should be possible to measure stress relaxation in creep machines when stepwise unloading is performed such that the inelastic strain rate can be determined at constant mechanical strain. This is confirmed by tests on the Mg-base alloy AZ91.
CRIS-Team WoS Importer:2022-01-14

Novel Approach for Assessing Cyclic Thermomechanical Behavior of Multilayered Structures - Seligmann, Benjamin; Alfreider, Markus; Wurmshuber, Michael; Kiener, Daniel (Advanced Engineering Materials, 2023)
Keywords: copper; stress modeling; finite element modeling; thin films; thermomechanical fatigue

Novel Class of Rhenium Borides Based on Hexagonal Boron Networks Interconnected by Short B2Dumbbells - Bykova, Elena; Johansson, Erik; Bykov, Maxim; Chariton, Stella; Fei, Hongzhan; Ovsyannikov, Sergey V.; Aslandukova, Alena; Gabel, Stefan; Holz, Hendrik; Merle, Benoit; Alling, Björn; Abrikosov, Igor A.; et al. (Chemistry of Materials, 2022)
Transition metal borides are known due to their attractive mechanical, electronic, refractive, and other properties. A new class of rhenium borides was identified by synchrotron single-crystal X-ray diffraction experiments in laser-heated diamond anvil cells between 26 and 75 GPa. Recoverable to ambient conditions, compounds rhenium triboride (ReB3) and rhenium tetraboride (ReB4) consist of close-packed single layers of rhenium atoms alternating with boron networks built from puckered hexagonal layers, which link short bonded ( 1.7 Å) axially oriented B2 dumbbells. The short and incompressible Re-B and B-B bonds oriented along the hexagonal c-axis contribute to low axial compressibility comparable with the linear compressibility of diamond. Sub-millimeter samples of ReB3 and ReB4 were synthesized in a large-volume press at pressures as low as 33 GPa and used for material characterization. Crystals of both compounds are metallic and hard (Vickers hardness, HV = 34(3) GPa). Geometrical, crystal-chemical, and theoretical analysis considerations suggest that potential ReBx compounds with x > 4 can be based on the same principle of structural organization as in ReB3 and ReB4 and possess similar mechanical and electronic properties.
CRIS-Team Scopus Importer:2022-09-30

Novel nanoindentation strain rate sweep method for continuously investigating the strain rate sensitivity of materials at the nanoscale - Holz, Hendrik; Merle, Benoit (Materials & Design, 2023)
We introduce a new nanoindentation method to continuously measure the hardness while sweeping through orders of magnitudes of strain rates within a single experiment. While nanoindentation already allows the determination of the strain rate sensitivity of materials by means of strain rate jump tests, these are typically limited to few discrete strain rates. With the new method, the strain rate sensitivity can be measured continuously as a function of the strain rate. Applications to fused silica, Zn-22 %Al superplastic alloy, single crystalline aluminum, various nanocrystalline metals and a palladium-based metallic glass are shown. Besides some discrepancy with the reference measurements, the new method seems only affected by the presence of a strong nanoindentation size effect. Provided this indentation size effect is not excessively large and can be corrected for accurately, the method proves robust, with no suggestion that the direction of the strain rate sweep affects the evaluation of the strain rate sensitivity.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Activation volume; Nanoindentation method; Strain rate history dependence; Strain rate jump tests; Strain rate sensitivity; Strain rate sweep

Novel wrought γ/γ′ cobalt base superalloys with high strength and improved oxidation resistance - Neumeier, Steffen; Freund, Lisa; Göken, Mathias (Scripta Materialia, 2015)
WW1::1033

Numerical Design of CoNi-Base Superalloys With Improved Casting Structure - Wahlmann, Benjamin; Bandorf, Jakob; Volz, Nicklas; Förner, Andreas; Pröbstle, Johannes; Multerer, Kerstin; Göken, Mathias; Markl, Matthias; Neumeier, Steffen; Körner, Carolin (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
Numerical methods can accelerate the design of alloys with improved material properties. One approach is the coupling of multi-criteria optimization with CALPHAD-based models of alloy properties. While this technique has already yielded promising new Nickel-base superalloys, the applicability to CoNi-base alloys has not yet been investigated. These alloys show promising properties for application as wrought high-temperature materials. We designed three CoNi-base superalloys, which were optimized for either high strength or high chemical homogeneity. The alloys were cast, and mechanical and thermophysical properties were characterized. The alloy optimized for strength showed creep performance inferior to a conventionally designed CoNi-alloy but had a much lower density. For developing highly homogeneous alloys, Scheil calculations were implemented in the optimization routine to quantify the severity of segregation. Non-equilibrium phases could be predicted successfully, resulting in a degree of homogeneity that rivaled that of a low-segregation ternary Co-base alloy. A comparison of elemental partitioning behavior and phase transition temperatures with CALPHAD calculations showed that trends are well represented for the most part. Finally, the applicability of the alloy design approach for Co-rich superalloys is evaluated, and possible applications for the optimized alloys are discussed.
CRIS-Team WoS Importer:2022-12-02

Observation of oscillatory radiation induced segregation profiles at grain boundaries in neutron irradiated 316 stainless steel using atom probe tomography - Barr, Christopher M.; Felfer, Peter; Cole, James I.; Taheri, Mitra L. (Journal of Nuclear Materials, 2018)
Radiation induced segregation in austenitic Fe-Ni-Cr stainless steels is a key detrimental microstructural modification experienced in the current generation of light water reactors. In particular, Cr depletion at grain boundaries can be a significant factor in irradiation-assisted stress corrosion cracking. Therefore, having a complete knowledge and mechanistic understanding of radiation induced segregation at high dose and after a long thermal history is desired for continued sustainability of existing reactors. Here, we examine a 12% cold worked AISI 316 stainless steel hexagonal duct exposed in the lower dose, outer blanket region of the EBR-II reactor, by using advanced characterization and analysis techniques including atom probe tomography and analytical scanning transmission electron microscopy. Contrary to existing literature, we observe an oscillatory w-shape Cr and M-shape Ni concentration profile at 31 dpa. The presence and characterization through advanced atom probe tomography analysis of the w-shape Cr RIS profile is discussed in the context of the localized GB plane interfacial excess of the other major and minor alloying elements. The key finding of a co-segregation phenomena coupling Cr, Mo, and C is discussed in the context of the existing solute segregation literature under irradiation with emphasis on improved spatial and chemical resolution of atom probe tomography. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: kernfusionsrelevant

Observing High-Cycle Fatigue Damage in Freestanding Gold Thin Films with Bulge Testing and Intermittent Transmission Electron Microscopy Imaging - Krapf, Anna; Merle, Benoit; Gebhart, David D.; Reiter, Marco; Lassnig, Alice; Göken, Mathias; Cordill, Megan J.; Gammer, Christoph (Advanced Engineering Materials, 2024)
Bulge testing is a potent technique for measuring the mechanical properties of freestanding thin films, but in situ imaging is only possible in limited experimental configurations. This poses a serious limitation for unraveling nanoscale failure mechanisms, such as the deformation mechanisms induced by cyclic loading in freestanding gold thin films of 150 nm thickness. Herein, a new experimental workflow combining standalone bulge cyclic testing with intermittent high-resolution imaging by transmission electron microscopy (TEM) at specific positions of interest is introduced. The observed low dislocation activity in planar areas of the thin films is consistent with the slow strain accumulation during high-cycle fatigue testing. In contrast, notches in the films lead to localized plasticity with sustained dislocation activity, but also grain growth and subgrain formation. At a more advanced stage, cracks proceed along grain boundaries, with crack bridging seemingly slowing down their propagation. The presented setup can be used with a number of TEM-based characterization techniques and has the potential to reveal cyclic deformation mechanisms in several thin-film systems.
CRIS-Team Scopus Importer:2024-04-19
Keywords: bulge test; thin-film fatigue; transmission electron microscopy

On grain boundary segregation in molybdenum materials - Leitner (Babinsky), K.; Felfer, Peter; Holec, D.; Cairney, J.; Knabl, W.; Lorich, A.; Clemens, H.; Primig, Sophie (Materials & Design, 2017)
The character and distribution of grain boundaries (GBs) inmolybdenum materials and their decoration with solutes may lead to strengthening or weakening effects which limits the structural application of Mo, especially in the recrystallized state, as as-deformed materials usually exhibit transgranular failure.Investigations of the structure and chemistry of GBs in Mo materials at the nanoscale are required to answer longstanding questions around their fracture behavior. We present a detailed investigation of segregation at a total of 22 high-angle GBs in Mo materials in their as-deformed and recrystallized states. We reveal the full crystallographic and chemical character of each individual GB by combining transmission Kikuchi diffraction and atom probe microscopy. We demonstrate that the detrimental elements P, N, and O segregate to all random high angle GBs. On the other hand, C-which has a strengthening effect-was only found at low-Sigma GBs in recrystallized materials. We support these experimental observations by first principle calculations. Our results provide an advance on grain boundary segregation engineering in these important technological materials. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Molybdenum; Grain boundary; Segregation engineering; Ductility; Atom probe microscopy; First principles calculations

On localised corrosive attack, stress corrosion cracking and corrosion fatigue effects in a hardmetal cutting-tool material - Pugsley, Victoria; Korn, Gregor; Luyckx, Silvana; Sockel, Hans-Georg (International Journal of Materials Research, 2021)
The influence of corrosion on the strength of a commercial hardmetal and its behaviour under static and cyclic loading has been investigated. Tannic acid was chosen as the corrosive medium in order to simulate the environment to which hardmetal wood-cutting tools are exposed. The results show corrosive attack of unloaded specimens to proceed in a highly localised form, producing defects that reduce the strength of the material by up to 50 %. A further reduction in the maximum endured stress is observed when corrosive attack is combined with a simultaneous static load. This is considered to be due to hydrogen embrittlement. When the hardmetal is subjected to cyclic loading in the presence of the corrosive medium, an increase in the fatigue sensitivity of the material occurs, but noteworthy reductions in lifetime are only observed at low stress amplitudes.
CRIS-Team WoS Importer:2022-01-14

On solution mapping and remeshing in crystal plasticity finite element simulations: application to equal channel angular pressing - Frydrych, Karol; Kowalczyk-Gajewska, Katarzyna; Prakash, Aruna (Modelling and Simulation in Materials Science and Engineering, 2019)
Microstructure evolution in crystalline materials subjected to different loading conditions is regularly studied using crystal plasticity finite element simulations. Accurate and reliable description of the microstructure, particularly in the case of large deformations, requires the usage of remeshing procedures and the mapping of the material state from the distorted mesh onto a new mesh. In this work, we evaluate three different solution mapping schemes, viz. closest point projection (CPP), sequential spherical linear interpolation (SLERP), and weighted spherical averages, all of which are based on the mapping of crystal plasticity variables. The results show that the mapping with CPP is generally acceptable, whilst the sequential SLERP is a more robust method with little additional computing effort.
CRIS-Team WoS Importer:2019-07-23

On the atomic solute diffusional mechanisms during compressive creep deformation of a Co-Al-W-Ta single crystal superalloy - He, Junyang; Zenk, Christopher; Zhou, Xuyang; Neumeier, Steffen; Raabe, Dierk; Gault, Baptiste; Makineni, Surendra Kumar (Acta Materialia, 2020)
We investigated the solute diffusional behavior active during compressive creep deformation at 150 MPa / 975 °C of a Co-Al-W-Ta single crystal superalloy in the [001] orientation. We report the formation of shear-bands that involves re-orientation of γ/γʹ rafts to 111 from 001 planes, referring to as γ/γ′ raft-rotation. In the shear-band regions, we observed abundant micro-twins, stacking faults (SFs), disordered zones within the γʹ termed as ‘γ pockets’ and also few geometrically-close-packed (GCP) phases. We used a correlative approach blending electron microscopy and atom probe tomography to characterize the structure and composition of these features. The SFs were identified as intrinsic and exhibit a W enrichment up to 14.5 at.% and an Al deficiency down to 5.1 at.%, with respect to the surrounding γʹ phase. The micro-twin boundaries show a solute enrichment similar to the SFs with a distinct W compositional profile gradients perpendicular from the boundaries into the twin interior, indicating solute diffusion within the micro-twins. The γ-pockets have a composition close to that of γ but richer in W/Ta. Based on these observations, we propose (i) a solute diffusion mechanism taking place during micro-twinning, (ii) a mechanism for the γ/γʹ raft-rotation process and evaluate their influence on the overall creep deformation of the present Co-based superalloy.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Atom probe tomography; Co-based superalloy; Creep deformation; Transmission electron microscopy; γ/γʹ rafting

On the diffusive phase transformation mechanism assisted by extended dislocations during creep of a single crystal CoNi-based superalloy - Makineni, Surendra Kumar; Kumar, Ankit; Lenz, Malte; Kontis, Paraskevas; Meiners, Thorsten; Zenk, Christopher; Zaefferer, Stefan; Eggeler, Gunther; Neumeier, Steffen; Spiecker, Erdmann; Raabe, Dierk; Gault, Baptiste (Acta Materialia, 2018)
We propose here a deformation-induced diffusive phase transformation mechanism occurring during shearing of γ′ ordered phase in a γ/γ′ single crystalline CoNi-based superalloy. Shearing involved the creation and motion of a high density of planar imperfections. Through correlative electron microscopy and atom probe tomography, we captured a superlattice intrinsic stacking fault (SISF) and its associated moving leading partial dislocation (LPD). The structure and composition of these imperfections reveal characteristic chemical – structural contrast. The SISF locally exhibits a D019 ordered structure coherently embedded in the L12 γ′ and enriched in W and Co. Interestingly, the LPD is enriched with Cr and Co, while the adjoining planes ahead of the LPD are enriched with Al. Quantitative analysis of the three-dimensional compositional field in the vicinity of imperfections sheds light onto a new in-plane diffusion mechanism as the LPD moves on specific 111 planes upon application of stress at high temperature. <p
Keywords: Superalloys; Creep deformation and stacking faults; Electron channeling contrast imaging (ECCI); Transmission electron microscopy (TEM); Atom probe tomography (APT)

On the elevated-temperature deformation behavior of polycrystalline Cu subjected to predeformation by multiple compression - Li, Yujiao; Zeng, Xiaohui; Blum, Wolfgang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2008)
WW1::780

On the grain boundary strengthening effect of boron in γ/γ′ Cobalt-base superalloys - Kolb, Markus; Freund, Lisa; Fischer, Florian; Povstugar, Ivan; Makineni, Surendra Kumar; Gault, Baptiste; Raabe, Dierk; Müller, Julian; Spiecker, Erdmann; Neumeier, Steffen; Göken, Mathias (Acta Materialia, 2018)
Boron is an essential solute element for improving the grain boundary strength in several high temperature metallic alloys especially in Ni- and Co-base superalloys although the detailed strengthening mechanisms are still not well understood. In superalloys, boron leads to the formation of borides and precipitate depleted zones around the grain boundaries and alters the bond strength among the grains directly. In this paper, we explore in detail the role of the boron content in ternary γ/γ′ Co-9Al-9W alloys. Local as well as bulk mechanical properties were evaluated using nanoindentation and compression testing and correlated to near-atomic scale microstructure and compositions obtained from electron microscopy and atom probe tomography. The alloy variant with low B content (0.005 at.% B) reveals an increase in yield strength at room temperature and 600 °C and atom probe tomography investigations show that solute B segregates to the grain boundaries. However, in the bulk B exclusively partitions to the γ′ phase. Additionally, the γ′/γ′ grain boundaries are depleted in W and Al with the concentration locally shifted towards the γ composition forming a very thin γ layer at the γ′/γ′ grain boundaries, which supports dislocation mobility in the γ′/γ′ grain boundary region during deformation. Higher content of B (0.04 at.% B) promotes formation of W-rich borides at the grain boundaries that leads to undesirable precipitate depleted zones adjacent to these borides that decrease the strength of the alloy drastically. However, it was also found that a subsequent annealing heat treatment eliminates these detrimental zones by re-precipitating γ′ and thus elevating the strength of the alloy. This result shows that, if a precipitate depleted zone can be avoided, B significantly improves the mechanical properties of polycrystalline Co-base superalloys by strengthening the γ′ phase and by improving grain boundary cohesion.
Keywords: Cobalt-base superalloys; Borides; Grain boundary; Atom probe tomography (APT); Nanoindentation

On the Hall-Fetch relation between flow stress and grain size - Blum, Wolfgang; Li, Yujiao; Chen, J.; Zeng, Xiaohui; Lu, K. (International Journal of Materials Research, 2006)
Data of flow stresses a for pure Cu with ultrafine grains with grain size d ≈ 0.35 μm produced by severe plastic deformation and grains of conventional size obtained in the range of homologous temperatures T hom from 0.22 (room temperature) to 0.33 are compared to data for hardnesses H for Cu of various grain structures from single crystalline to d = 0.01 μm measured by nanoindentation at room temperature. The two sets of data appear to be consistent when σ ≈ H/3. At room temperature the Hall-Fetch relation holds, i.e., the flow stress increases monotonically with decreasing grain size by Δ σ ∝ d-0.5. At elevated Thom the saturated flow stress decreases when the grains become ultrafine. The transition from hardening to softening by grain boundaries in the saturation stage is discussed on the basis of a simple statistical dislocation model considering the influence of grain boundaries on the balance between generation and annihilation of dislocations.
Created from Fastlane, Scopus look-up
Keywords: Flow stress; Hall-Fetch; Ultra fine grains

On the importance of a connected hard-phase skeleton for the creep resistance of Mg alloys - Amberger, Dorothea; Eisenlohr, Philip; Göken, Mathias (Acta Materialia, 2012)
The low density of Mg alloys renders them attractive for lightweight constructions. However, creep resistance remains an important limitation of Mg alloys for, for example, automotive power train applications. To gain a more detailed understanding of the correlation between microstructure and creep properties in die-castable Mg alloys, AZ91 alloys with nominal additions of 0, 1, 3, and 5 mass% Ca and the commercial alloy MRI 230D have been investigated. Creep tests show an increase in creep strength with increasing Ca addition and increasing cooling rate. Scanning electron microscopy reveals that this is correlated with an increasing interconnectivity of the intermetallic phase skeleton (in addition to the effect of small precipitates within the extgreeka-Mg matrix found in the case of MRI 230D). A simple isostrain composite analysis illustrates that a more interconnected skeleton shields more load from the matrix. Precipitation hardening can additionally strengthen the matrix, and thus the combination of both design approaches results in the highest observed creep resistance.
WW1::943

On the influence of Al-concentration on the fracture toughness of NiAl: Microcantilever fracture tests and atomistic simulations - Webler, Ralf; Baranova, Polina; Karewar, Shivraj; Möller, Johannes; Neumeier, Steffen; Göken, Mathias; Bitzek, Erik (Acta Materialia, 2022)
While the mechanical properties of the stoichiometric B2 β-phase of NiAl are well established, the effect of off-stoichiometric composition on the fracture behavior has not yet been systematically studied over the entire composition range of 40-55% Al. Here we use microbending tests on notched cantilever beams FIB-milled from NiAl single crystals with an aluminized as well as an oxidation-induced composition gradient to determine the influence of the Al concentration on the fracture toughness. Small variations from the stoichiometric composition are shown to lead to drastic changes in fracture behavior. Ni-rich NiAl shows a gradual decrease of fracture toughness and plastic energy dissipation with Ni-concentration that follows the inverse proportionality to the yield stress postulated by the Ritchie, Knott and Rice (RKR) model. Al-rich NiAl, however, shows a concentration-independent low fracture toughness and no signs of accompanying plasticity - both which can not be described by the RKR model. Detailed atomistic simulations show that rather than affecting the theoretical fracture toughness according to the thermodynamic Griffith criterion, structural vacancies in Al-rich NiAl lower the kinetic barrier for crack propagation, explaining the observed different concentration dependence of the fracture toughness. Similar observations are also expected for fracture in other off-stoichiometric B2 aluminides.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Atomistic simulation; Fracture; Intermetallics; Micro cantilever bending; NiAl

On the lattice parameters of silicon carbide - Stockmeier, Matthias; Müller, Robin; Sakwe, Aloysius; Wellmann, Peter; Magerl, Andreas (Journal of Applied Physics, 2009)
The thermal expansion coefficients of the hexagonal SiC polytypes 4H and 6H and with Al and N dopants have been determined for temperatures between 300 and 1770 K. Further, a set of the room temperature lattice parameters in dependence on doping with N, Al, and B has been obtained. Data for the thermal expansion were taken on a triple axis diffractometer for high energy x rays with a photon energy of 60 keV, which allows the use of large single crystals with a volume of at least 6x6x6 mm(3) without the need to consider absorption. The room temperature measurements for samples with different dopants have been performed on a four-circle diffractometer. The thermal expansion coefficients along the a- and c-directions, alpha(11) and alpha(33), increase from 3x10(-6) K(-1) at 300 K to 6x10(-6) K(-1) at 1750 K. It is found that alpha(11) and alpha(33) are isotropic within 10(7) K(-1). At high temperatures both coefficients for doped samples are similar to 0.2x10(-6) and 0.3x10(-6) K(-1) lower than for the undoped material.
Keywords: Silicon Carbide; 4H SiC; 6H SiC; thermal expansion coefficients; x-ray diffraction

On the possibilities to enhance the fatigue properties of ultrafine-grained metals - Höppel, Heinz Werner; et al. (Zeitschrift für Metallkunde, 2002)
Cyclic deformation behaviour of ultrafine-grained (UFG) materials processed by severe plastic deformation is reviewed in the light of possibilities to enhance the fatigue properties of UFG materials. Based on the well-known laws from Coffin-Manson and Basquin the fatigue behaviour of UFG materials for both, the low-cycle fatigue as well as the high-cycle fatigue regimes, are analyzed. The beneficial effects of an annealing heat treatment or a back-pressure modified equal channel angular pressing (ECAP) technique on the fatigue behaviour of UFG materials are demonstrated and critically discussed. In particular, the positive influence of an annealing heat treatment on the fatigue behaviour is explained in terms of an improved cyclic stability of the microstructure after ECAP and of an enhanced ductility. A back-pressure modified ECAP technique was used in order to achieve a ultrafine-grained, high-strength material with increased ductility, which itself is related to a combination of crystallographic slip and grain boundary sliding. The potential of enhancing the fatigue properties of UFG materials by the back-pressure ECAP technique is discussed in the context of the Coffin-Manson and Basquin relations.
UnivIS-Import:2015-03-09:Pub.2002.tech.IW.LWAW.onthep
Keywords: Basquin law; Coffin-Manson law; Copper; Equal channel angular pressing; Fatigue; Fatigue life; Ultrafine-grained materials

On the Precipitation-Strengthening Contribution of the Ta-Containing Co3(Al,W)-Phase to the Creep Properties of γ/γ′ Cobalt-Base Superalloys - Bezold, Andreas; Volz, Nicklas; Xue, Fei; Zenk, Christopher H; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2020)
The creep strength of single-crystalline Co-based superalloys was found to be comparable to first-generation Ni-base superalloys. However, considerable shearing of the γ′ precipitates was observed in the early creep stages. To determine the strengthening contribution of the Ta-containing γ′-Co3(Al,W) precipitates, the creep strength of several single-crystalline Co-Al-W-Ta superalloys was determined as a function of the γ′ volume fraction at 1223 K (950 °C) and stress levels between 25 and 600 MPa. Employing a Lagneborg–Bergman–Reppich (LBR) approach, it is found that the strengthening contribution of the γ′ precipitates increases significantly with increasing γ′ volume fraction. In a Co-base superalloy that exhibits a precipitate volume fraction of about 70 pct, the γ′-strengthening contribution calculated with the LBR approach ranges between the ones observed in first-generation Ni-base superalloy CMSX-6 and second-generation Ni-base superalloy CMSX-4.
CRIS-Team Scopus Importer:2020-02-04

On the pressure dependence of the indentation modulus - Wolf, B.; Göken, Mathias (International Journal of Materials Research, 2005)
The influence of the pressure distribution beneath a spherical indenter onto the resulting penetration depth and consequently its impact onto the derived apparent indentation modulus has been modelled theoretically. It turns out that the pressure distribution has the same effect as a constant hydrostatic pressure of one half of the contact pressure within the entire sample. The effect is particularly important in situations of high contact pressure as during elastic indentation loading before the occurrence of the first popin. Furthermore, for all materials with a high ratio between hardness and elastic modulus the indentation modulus should differ from the "zero-pressure elastic modulus" in an experimentally verifiable way. A quantitative assessment delivers a possible increase up to 15 %.
CRIS-Team WoS Importer:2022-02-18

On the temperature dependent strengthening of nickel by transition metal solutes - Rehman, Hamad Ur; Burst, Karsten; Neumeier, Steffen; Sato, Atsushi; Reed, Roger; Göken, Mathias (Acta Materialia, 2017)
Fundamental insights are presented into the factors influencing the temperature-dependent strengthening of nickel by transition metal solutes. Strain rate jump tests are used using the alloying elements Ta, W and Re which lie beside one another in the d-block. At 800 degrees C, the hardening induced by Ta is significantly greater than that by W and Re. At T >= 1000 degrees C, Re becomes more potent than Ta at slow strain rates; at 1200 degrees C it is the most effective at all the strain rates employed. The results are interpreted using theory for temperature-dependent strengthening that emphasises solute dislocation interaction. It is confirmed that at low temperatures the solute strengthening is controlled by paraelastic interaction the solute with the largest size difference with the host Ni is the most potent. At higher temperatures, the evidence indicates that solutes collect on dislocations such that the slowest diffusing solutes confer maximal resistance to dislocation glide and climb; thus Re is particularly potent. The findings elucidate the role of transition metal solutes in strengthening. Moreover, they provide the necessary quantitative data for ongoing alloy design efforts. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Ni binaries; Superalloys; Solid solution hardening; Re-effect; Diffusion

On the transition from plastic deformation to crack initiation in the high- and very high-cycle fatigue regimes in plain carbon steels - Bach, Jochen; Möller, Johannes; Göken, Mathias; Bitzek, Erik; Höppel, Heinz Werner (International Journal of Fatigue, 2016)
It is well known that fatigue life of metallic materials involves processes at different stages. Two main regimes can be distinguished: The first is governed by plastic deformation and related dislocation processes like cyclic saturation and strain localization. The second regime is mainly dominated by crack initiation and propagation. Whether an infinite fatigue life is obtained or not is therefore ultimately determined by the complex interplay of plastic deformation processes, the formation of small crack nuclei and their subsequent interaction with the surrounding material's microstructure. Thus, it is necessary to investigate the transition from plastic deformation to crack initiation in the high- and very high-cycle fatigue regime in more detail. Three plain carbon steels with different ferrite to pearlite ratios were investigated in order to determine the influence of different microstructures on the transition from cyclic deformation to crack initiation in the high and very high cycle fatigue (VHCF) regime. A new method was developed where the changes in the dissipated energy are used to account for irreversible plastic deformation during ultrasonic fatigue loading. At very small fatigue amplitudes, which still lead to VHCF-failure, the cyclic deformation regime covers the main part of the fatigue life. In this regime dislocation interactions lead to the accumulation of irreversible plastic deformation followed by small crack nuclei that initiate at phase or grain boundaries (GBs), marking the transition to the damage regime. In order to better understand the fundamental mechanisms at the transition between both regimes, idealized atomistic simulations were performed. To model fatigue-induced plastic deformation various defects, i.e. dislocations and vacancies, were placed in the vicinity of a GB. These defects generally decrease the globally applied critical stress for crack initiation whilst the local critical stress stays mainly unchanged in the same range as the theoretical GB strength. Based on the experimental results and on the general findings from the atomistic simulations it is concluded that an infinite fatigue life is obtained either when cyclic irreversible deformation is too small to build up the necessary stresses for crack initiation or when the formed crack nuclei cannot overcome the next microstructural barrier
Keywords: Atomistic simulations; Crack initiation; Steels; Ultrasonic fatigue; VHCF

Open-cell tungsten nanofoams: Scaling behavior and structural disorder dependence of Young's modulus and flow strength - Zhao, Mingyue; Schlueter, Karsten; Wurmshuber, Michael; Reitgruber, Maria; Kiener, Daniel (Materials & Design, 2021)
Keywords: Mechanical properties; Microstructure; Tungsten; Nanoindentation; Nanoporous; kernfusionsrelevant

Optimisation of interface formation by shear inclination: Example of aluminium-cooper hybrid produced by ECAP with back-pressure - Medvedev, Alexander E.; Lapovok, Rimma; Koch, Eric; Höppel, Heinz Werner; Göken, Mathias (Materials & Design, 2018)
Keywords: ECAP; Hybrid material; Diffusion; Intermetallic compounds; TEM

Optimisation of interface formation by shear inclination: Example of aluminium-copper hybrid produced by ECAP with back-pressure - Medvedev, Alexander E.; Lapovok, Rimma; Koch, Eric; Höppel, Heinz Werner; Göken, Mathias (Materials & Design, 2018)
Hybrid materials present a convenient way of combining properties of more than one material in one product. However, there are problems associated with such manufacturing, particularly, in relation to the properties of the interface between components. Intermetallic compounds can potentially form in this area, whose size and composition can have a profound effect on mechanical properties of the product. In this work, we investigate the effect of temperature, mutual arrangement and hydrostatic pressure on the quality of the interface between Al and Cu parts, processed simultaneously by severe plastic deformation. We show that three intermetallic compounds -theta-Al2Cu, zeta(2)-Al3Cu4-delta and gamma(1)-Al4Cu9 - form on the interface. It is shown that the formation of these phases on the interface between aluminium and copper highly depends on the combination of diffusion and recrystallization process. (c) 2018 Elsevier Ltd. All rights reserved.
Keywords: Intermetallic compounds; ECAP; Hybrid material; Diffusion; TEM

Optimization of the heat treatment of additively manufactured Ni-base superalloy IN718 - Diepold, Benedikt; Vorlaufer, Nora; Neumeier, Steffen; Gartner, Thomas; Göken, Mathias (International Journal of Minerals, Metallurgy and Materials, 2020)
Additive manufacturing (AM) of Ni-base superalloy components can lead to a significant reduction of weight in aerospace applications. AM of IN718 by selective laser melting results in a very fine dendritic microstructure with a high dislocation density due to the fast solidification process. The complex phase composition of this alloy, with three different types of precipitates and high residual stresses, necessitates adjustment of the conventional heat treatment for AM parts. To find an optimized heat treatment, the microstructures and mechanical properties of differently solution heat-treated samples were investigated by transmission and scanning electron microscopy, including electron backs-catter diffraction, and compression tests. After a solution heat treatment (SHT), the Nb-rich Laves phase dissolves and the dislocation density is reduced, which eliminates the dendritic substructure. SHT at 930 or 954°C leads to the precipitation of the δ-phase, which reduces the volume fraction of the strengthening γ′- and γ″-phases formed during the subsequent two stage aging treatment. With a higher SHT temperature of 1000°C, where no δ-phase is precipitated, higher γ′ and γ″ volume fractions are achieved, which results in the optimum strength of all of the solution heat treated conditions.
CRIS-Team Scopus Importer:2020-05-22
Keywords: microstructure; Ni-base superalloy; powder bed fusion; selective laser melting; strengthening mechanism

Optimized layer architecture for an extended fatigue life of ultrafine-grained AA1050/AA5005 laminated metal composites - Kümmel, Frank; Tegtmeier, Thea-Simone; Höppel, Heinz Werner; Göken, Mathias (IOP Conference Series: Materials Science and Engineering, 2017)
The influence of interfaces on the fatigue life in AA1050/AA5005 ultrafine-grained laminated metal composites was investigated. At constant sheet thickness, the layer thickness and the number of material interfaces was varied by performing different cycles of accumulative roll bonding. It is found that crack deviation occurs if the crack approaches the soft to hard (AA1050/AA5005) material interface resulting in strongly enhanced fatigue lives compared to the mono-material. The most favourable layer architecture for enhanced fatigue life strongly depends on the applied stress amplitudes. At intermediate stress amplitudes a large layer thickness of 500 extgreekmm (N4) and 8 material interfaces gives the longest fatigue life. In contrast, at low stress amplitudes the sheets with 32 material interfaces and a layer thickness of 125 extgreekmm (N6) shows the longest fatigue life.
EAM Import::2019-03-08

Origins of strengthening and failure in twinned Au nanowires: Insights from in−situ experiments and atomistic simulations - Xie, Zhuocheng; Shin, Jungho; Renner, Jakob; Prakash, Aruna; Gianola, Daniel S.; Bitzek, Erik (Acta Materialia, 2020)
The deformation behavior of ⟨110⟩-oriented twinned Au nanowires (NWs) with multiple longitudinal coherent twin boundaries (CTBs) under tension is studied using in−situ experiments and molecular dynamics (MD) simulations. The twinned NWs show higher yield strength than the single-crystalline NWs with similar diameter. Postmortem observations using electron microscopy and MD simulations show that the presence of CTBs transitions the governing mechanism from twinning-mediated deformation in single-crystalline NWs to strongly localized deformation. MD simulations reveal that the intersection of deposited partial dislocations at the CTB with the free surfaces plays an important role in the transmission of the dislocation, leading to the formation of full dislocations instead of partial dislocations and twinning in the case of single-crystalline NWs. The repeated activation of full dislocation slip leading to localized deformation is furthermore dependent on the relative orientation of surface facets to the activated Burgers vectors. The results of this work enhance the understanding of deformation mechanisms of twinned nano-objects and suggest design strategies for mechanical systems at the nanoscale.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Coherent twin boundary; In−situ tension test; Molecular dynamics; Nanowire; Plasticity

Oxidation Behavior of the Polycrystalline Ni-Base Superalloy VDM® Alloy 780 - Kirchmayer, Andreas; Weiser, Martin; Randelzhofer, Peter; Freund, Lisa; Gehrmann, B.; Haghighat, M. Hafez; Huenert, D.; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
VDM® Alloy 780 is a newly developed polycrystalline Ni-base superalloy with high contents of Co, Cr, and Al intended for operating temperatures up to 750 °C. The alloy is precipitation strengthened by the γ′ phase, which is analyzed by atom probe tomography. Additionally, δ and η phases are utilized for grain boundary pinning. It is shown that the δ and η phases precipitate either plate like or in a fine lamellar structure inside each other. VDM® Alloy 780 shows superior oxidation resistance in comparison with Udimet 720Li and A718Plus, as seen by a lower mass gain and thinner oxide layers at 800 °C and 900 °C. This superior behavior is analyzed in detail by TEM and STEM investigations of the oxide scales from which it is concluded that the Al/Ti ratio in these alloys plays an important role on the oxidation behavior.<br

Oxide scale microstructure and failure mechanism of alloy 601 under varying metal dusting conditions - Schlereth, C.; Weiser, Martin; White, E.; Felfer, Peter; Galetz, M. (Journal of Materials Science, 2024)
Chemical plants which process highly carbonaceous gases at elevated temperatures are prone to catastrophic corrosion by metal dusting. Typically, commercial alloys with high amounts of protective oxide scale formers (Cr, Al, and Si) are used in these environments. However, scale failure is still frequently observed after an incubation time initiating pits. In this study, the microstructure and subsequent metal dusting-induced failure of the oxide scale on the commercial Ni-based alloy 601 was analyzed. Samples were exposed in different aggressive metal dusting gases and characterized using metallographic cross sections, electron beam microanalysis (EPMA), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and transmission electron microscopy (TEM). A thin and protective chromia scale formed in some regions with a continuous silica layer below. Across most of the alloy 601 surfaces, internal oxidation of Al could be linked to metallic particles in the outer scale. Additionally, MnCr2O4 was observed in the outer scale. Together with pores in the chromia, the spinel and metallic particles in the outer scale combined to provide pathways for carbon ingress. After exposure in a gas with a higher driving force for carbon deposition, a higher amount of carbon was incorporated in the growing oxide scale, resulting in earlier scale failure and metal dusting pit initiation. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2024-01-19

Oxide-stabilized microstructure of severe plastically deformed CuCo alloys - Stückler, Martin; Zálešák, Jakub; Müller, Timo; Wurster, Stefan; Weissitsch, Lukas; Meier, Martin; Felfer, Peter; Gammer, Christoph; Pippan, Reinhard; Bachmaier, Andrea (Journal of Alloys and Compounds, 2022)
Nanocrystalline materials are well known for their beneficial mechanical and physical properties. However, it is of utmost importance to stabilize the microstructure at elevated temperatures to broaden the window of application e.g. by pinning grain boundaries through impurities or oxides. CuCo alloys, severe plastically deformed using high-pressure torsion, were used to investigate the evolution of oxides upon annealing. These investigations were performed using electron microscopy, synchrotron high-energy X-ray scattering and atom probe tomography. Monitoring the evolution of oxides by in-situ small angle scattering investigations indicates the growth of primary oxides as well as the formation of another species of oxide at elevated temperatures. Slightly different coarsening can be observed in heat-treated samples, which can be traced back to the influence of different oxide amounts. The initially supersaturated CuCo matrix changes by the decomposition process as well as Co- and Cu-based oxides formation and growth. It has been found that the major number of oxides which are present after annealing, can already be found in the starting materials.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Atom probe tomography; High-pressure torsion; Nanocrystalline material; Severe plastic deformation; Small-angle X-ray scattering; Supersaturation

Paramelaconite-Enriched Copper-Based Material as an Efficient and Robust Catalyst for Electrochemical Carbon Dioxide Reduction - Martić, Nemanja; Reller, Christian; Macauley, Chandra; Löffler, Mario; Schmid, Bernhard; Reinisch, David; Volkova, Elena; Maltenberger, Anna; Rucki, Andreas; Mayrhofer, Karl; Schmid, Günter (Advanced Energy Materials, 2019)
A copper-oxide-based catalyst enriched with paramelaconite (Cu4O3) is presented and investigated as an electrocatalyst for facilitating electroreduction of CO2 to ethylene and other hydrocarbons. Cu4O3 is a member of the copper-oxide family and possesses an intriguing mixed-valance nature, incorporating an equal number of Cu+ and Cu2+ ions in its crystal structure. The material is synthesized using a solvothermal synthesis route and its structure is confirmed via powder X-ray diffraction, transmission electron microscope based selected area electron diffraction, and X-ray photoelectron spectroscopy. A flow reactor equipped with a gas diffusion electrode is utilized to test a copper-based catalyst enriched with the Cu4O3 phase under CO2 reduction conditions. The Cu4O3-rich catalyst (PrC) shows a Faradaic efficiency for ethylene over 40% at 400 mA cm−2. At −0.64 versus reversible hydrogen electrode, the highest C2+/C1 product ratio of 4.8 is achieved, with C2+ Faradaic efficiency over 61%. Additionally, the catalyst exhibits a stable performance for 24 h at a constant current density of 200 mA cm−2.
CRIS-Team Scopus Importer:2019-07-09
Keywords: carbon dioxide electroreduction; Cu; gas diffusion electrodes; mixed-valence; paramelaconite

Particle based alloying by accumulative roll bonding in the system Al-Cu - Schmidt, Christian; et al. (Metals, 2011)
The formation of alloys by particle reinforcement during accumulative roll bonding (ARB), and subsequent annealing, is introduced on the basis of the binary alloy system Al-Cu, where strength and electrical conductivity are examined in different microstructural states. An ultimate tensile strength (UTS) of 430 MPa for Al with 1.4 vol.% Cu was reached after three ARB cycles, which almost equals UTS of the commercially available Al-Cu alloy AA2017A with a similar copper content. Regarding electrical conductivity, the UFG structure had no significant influence. Alloying of aluminum with copper leads to a linear decrease in conductivity of 0.78 µΩ·cm/at.% following the Nordheim rule. On the copper-rich side, alloying with aluminum leads to a slight strengthening, but drastically reduces conductivity. A linear decrease of electrical conductivity of 1.19 µΩ·cm/at.% was obtained.
WW1::895

Particle hardening in creep-resistant Mg-Alloy MRI 230D probed by nanoindenting atomic force microscopy - Backes, Björn; Durst, Karsten; Amberger, Dorothea; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2009)
WW1::822

Partitioning Behavior of Nb, Ta, and Zr in Fully Lamellar gamma/alpha(2) Titanium Aluminides and Its Effect on the Lattice Misfit and Creep Behavior - Neumeier, Steffen; Bresler, Johannes; Zenk, Carolin; Haußmann, Lukas; Stark, Andreas; Pyczak, Florian; Göken, Mathias (Advanced Engineering Materials, 2021)
Previous investigations revealed that Nb, Ta, and Zr improve the creep properties of fully lamellar titanium aluminides significantly. The enhanced creep properties can originate from different potential effects of the alloying elements. Herein, the elements' partitioning between alpha(2)-Ti3Al and gamma-TiAl and their influence on the lattice parameters of ternary Ti-44Al-5X (X = Nb, Ta, Zr) alloys are investigated in comparison with a binary Ti-44Al alloy by atom probe tomography and high-energy X-ray diffraction. Ta partitions nearly equally between alpha(2) and gamma, Nb accumulates slightly in gamma, and Zr enriches strongly in gamma. As all alloying elements have a larger radius than Ti, a stronger partitioning to gamma decreases the lattice misfit more. The synchrotron measurements show a clear influence of the alloying elements on the lattice parameters and resulting lattice misfits in gamma-⟨110] and gamma-⟨101 ] direction as well as the c/a ratio. In accordance with theoretical calculations based on the partitioning behavior, the lattice misfit decreases from Ti-44Al-5Ta over Ti-44Al-5Nb to Ti-44Al-5Zr. The c/a ratio decreases from Ti-44Al-5Nb over Ti-44Al-5Ta to Ti-44Al-5Zr. A correlation between the measured lattice misfits of the ternary Ti-44Al-5X with their primary creep strains is found, as the primary creep strain decreases with decreasing lattice misfit.
CRIS-Team WoS Importer:2021-05-21

Partitioning of Re between γ and γ′ phase in nickel-base superalloys - Volek, Andreas; Pyczak, Florian; Singer, Robert; Mughrabi, Hael (Scripta Materialia, 2005)
The partitioning behavior of the elements W, Mo, Re, Ru and Ir of three experimental nickel-base superalloys was investigated. For comparative studies ternary and quaternary alloys were produced and analyzed. The distribution coefficient of Re is shown to be a function of composition. Ru and Ir do not affect the partitioning behavior of Re. © 2004 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve

Penetration of protective chromia scales by carbon - Young, David J.; Thuan Dinh Nguyen,; Felfer, Peter; Zhang, Jianqiang; Cairney, Julie M. (Scripta Materialia, 2014)
Model Fe-20Cr (wt.%) alloy, exposed to Ar-20CO(2) at 650 degrees C, formed a protective Cr2O3 scale, but nonetheless carburized. Atom probe analysis shows that carbon penetrates the scale via oxide grain boundaries. (C) 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Carbon; Cr2O3; Penetration; Oxidation

Phase equilibria in the ZrO2-YO1.5-TaO2.5 system at 1250 degrees C - Macauley, Chandra; Fernandez, Abel N.; Van Sluytman, Jason S.; Levi, Carlos G. (Journal of the European Ceramic Society, 2018)
The phase relationships in the ZrO2-YO1.5-TaO2.5 (ZYTO) system at 1250 degrees C-a temperature of interest for thermal barrier coatings applications-were investigated using precursor-derived powders. The system is bisected by a quasi-binary joining the tetragonal (t) ZrO2 and monoclinic (M') YTaO4 solid solutions. The mutual solubility limits for these phases differ significantly depending on whether the third phase in equilibrium with t and M' is fluorite or the orthorhombic (O) Zr6Ta2O17. More importantly, the tetragonal phase in equilibrium with fluorite is non-transformable to the monoclinic form upon cooling, whereas that in equilibrium with O, which has lower stabilizer content, is transformable. The behavior contrasts with that previously observed for the equilibrium at 1500 degrees C, wherein the t phase on both sides of the quasi-binary is non-transformable. The fluorite solid solution extends from the ZrO2-YO1.5 binary to the YO1.5-TaO2.5 binary at 1250 degrees C, as previously shown for 1500 degrees C.
Keywords: Thermal barrier coatings; Zirconia; Yttria; Tantala; Phase equilibria

Pinning of extended dislocations in atomically disordered crystals - Vaid, Aviral; Wei, De'An; Bitzek, Erik; Nasiri, Samaneh; Zaiser, Michael (Acta Materialia, 2022)
In recent years there has been renewed interest in the behavior of dislocations in crystals that exhibit strong atomic scale disorder, as typical of compositionally complex single phase alloys. The behavior of dislocations in such crystals has been often studied in the framework of elastic manifold pinning in disordered systems. Here we discuss modifications of this framework that may need to be adapted when dealing with extended dislocations that split into widely separated partials. We demonstrate that the presence of a stacking fault gives rise to an additional stress scale that needs to be compared with the pinning stress of elastic manifold theory to decide whether the partials are pinned individually or the dislocation is pinned as a whole. For the case of weakly interacting partial dislocations, we demonstrate the existence of multiple metastable states at stresses below the depinning threshold and analyze the stress evolution of the stacking fault width during loading. In addition we investigate how geometrical constraints can modulate the dislocation-solute interaction and enhance the pinning stress. We compare our theoretical arguments with results of atomistic and discrete (partial) dislocation dynamics (D(P)DD) simulations. (c) 2022 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2022-07-29

Pitting corrosion-Preferred chloride diffusion pathways in physical vapor deposited AlCrN coatings - Hudak, O. E.; Bahr, A.; Kutrowatz, P.; Wojcik, T.; Bohrn, F.; Solyom, L.; Schuster, R.; Shang, L.; Hunold, O.; Polcik, P.; Heller, Martina; Felfer, Peter; et al. (Corrosion Science, 2023)
Pitting corrosion of sputtered and arc evaportaed fcc-AlCrN coated low-alloy steel substrates was studied in a 0.1 M NaCl solution, using a three-electrode-cell. Depending on the deposition technique, several diffusion mechanisms were identified by high-resolution techniques (i.e. APT, TOF-SIMS). For arc evaporated AlCrN, incoherently embedded macro-particles provided the majority of fast-track diffusion pathways and pit-initiation sites, while their pristine coating matrix proved protective against chloride inward diffusion. Contrarily, the more coarse-grained sputtered AlCrN morphology with a highly orientated crystal growth featured diffusion paths along column boundaries, where chloride permeated the coating structure and initiated pit formations at the coating-substrate interface.
CRIS-Team WoS Importer:2023-01-13

Plane-strain bulge testing of thin films under compressive residual stresses - Ghanem, Maher; Göken, Mathias; Merle, Benoit (Surface & Coatings Technology, 2017)
The Bulge Test is a well-established method for the mechanical testing of freestanding thin films but is generally restricted to the investigation of membranes exhibiting tensile residual stresses. A new procedure based on successively evacuating and pressurizing the membrane from one side is suggested which provides a better estimation of the membrane initial height and extends testing possibilities to compressively stressed or buckled membranes. The robustness of the method is demonstrated by measurements on several material systems, SiO2 and Cu/Nb sputter-deposited onto a thin SiNX substrate. Measurements of the plane-strain modulus of the membranes show good agreement with literature and results of the residual stress levels were reasonable and coincide with the buckled state of the membranes. Moreover, Cu/Nb multilayer membranes show a consistent decrease in the compressive stress level with increasing layer thickness. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Bulge test; Thin film; Residual stress

Plastic anisotropy of ultrafine grained Al alloy AA6016 produced by accumulative roll bonding - Skrotzki, W.; Scharnweber, J.; Oertel, C. -G.; Höppel, Heinz Werner; Topic, Irena; Brokmeier, H. -G.; Jaschinski, J. (Solid State Phenomena, 2010)
In order to quantify the plastic anisotropy of the ultrafine grained aluminium alloy AA6016 produced by accumulative roll-bonding (ARB) the Lankford parameter is measured by tensile testing as a function of the number of ARB cycles. The experimental results are compared with those from texture-based Taylor simulations. Increasing differences between experiment and theory at higher number of ARB cycles may be attributed to highly oriented microstructural features.
WW1::853

Plastic deformation mechanisms in a crept L12 hardened Co-base superalloy - Pyczak, Florian; Bauer, Alexander; Göken, Mathias; Neumeier, Steffen; Lorenz, U.; Oehring, M.; Schell, N.; Schreyer, A.; Stark, A.; Symanzik, F. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
Plastic deformation mechanisms in a crept L1 hardened Co-base superalloy are investigated by transmission electron microscopy. The deformation happens mainly in the cobalt solid solution matrix by slip of ordinary a/2〈101〉111 dislocations and rafting of the γ' precipitates perpendicular to the external compressive stress axis is observed. Dislocation structures are early stages of the development of γ/γ' interfacial dislocation networks. Furthermore, γ' precipitates are sheared by partial dislocations generating stacking faults which sometimes extend over matrix channels and neighbouring γ' precipitates. Due to the positive lattice mismatch at creep temperature the dislocation activity in matrix channels perpendicular to the compressive external stress axis is less pronounced compared to parallel channels. © 2013 Elsevier Ltd.
Keywords: Cobalt based superalloys; Creep; Dislocations; Synchrotron X-ray diffraction; Transmission electron microscopy

Plastic deformation mechanisms in a crept L12 hardened Co-base superalloy - Pyczak, Florian; Bauer, Alexander; Göken, Mathias; Neumeier, Steffen; Lorenz, U.; Oehring, M.; Schell, N.; Schreyer, A.; Stark, Andreas; Symanzik, F. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
Keywords: Cobalt based superalloys; Synchrotron X-ray diffraction; Transmission electron microscopy; Creep; Dislocations

Poly(glycerol sebacate)(butylene succinate-dilinoleate) blends as candidate materials for cardiac tissue engineering - Göken, Mathias; Merle, Benoit; Boccaccini, Aldo R.; Aifantis, K.; Tallawi, Marwa; Rai, Ranjana; R-Gleixner, M.; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; et al. (Macromolecular Symposia, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate‐dilinoleate) (PBS‐DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS‐DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS‐DLA blends were measured and compared. By adding PBS‐DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS‐DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS‐DLA films. Furthermore, addition of PBS‐DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS‐DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS‐DLA addition led to decreased degradation rate of the films. Furthermore the PBS‐DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS‐DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approaches.
Keywords: myoblasts; poly (butylene succinate-dilinoleate); cardiac tissue engineering; mechanobiology; substrate stiffness

Poly(glycerol sebacate){Poly(butylene succinate-dilinoleate) Blends as Candidate Materials for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Ramsperger-Gleixner, Martina; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, Miroslawa; Merle, Benoit; Göken, Mathias; Aifantis, K.; et al. (WILEY-V C H VERLAG GMBH, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate-dilinoleate) (PBS-DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS-DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS-DLA blends were measured and compared. By adding PBS-DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS-DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS-DLA films. Furthermore, addition of PBS-DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS-DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS-DLA addition led to decreased degradation rate of the films. Furthermore the PBS-DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS-DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approaches.
Keywords: cardiac tissue engineering; mechanobiology; myoblasts; poly (butylene succinate-dilinoleate); substrate stiffness

Poly(glycerol sebacate){Poly(butylene succinate-dilinoleate) Blends as Candidate Materials for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Ramsperger-Gleixner, Martina; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, M.; Merle, Benoit; Göken, Mathias; Aifantis, K.; et al. (Macromolecular Symposia, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate-dilinoleate) (PBS-DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS-DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS-DLA blends were measured and compared. By adding PBS-DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS-DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS-DLA films. Furthermore, addition of PBS-DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS-DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS-DLA addition led to decreased degradation rate of the films. Furthermore the PBS-DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS-DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approache
Keywords: cardiac tissue engineering; mechanobiology; myoblasts; poly (butylene succinate-dilinoleate); substrate stiffness

Polysiloxane-derived ceramic foam for the reinforcement of Mg alloy - Greil, Peter; Höppel, Heinz Werner; et al. (Zeitschrift für Metallkunde, 2002)
Magnesium/ceramic composites with an interpenetrating microstructure were made by pressure infiltrating an open cellular ceramic preform. The low-density ceramic preform with a porosity of 82% was prepared by foaming a low-viscous polysiloxane/alumina suspension which formed an SiO2/Al2O3 microcomposite ceramic foam after thermal treatment in air at 1200°C. Foaming was achieved by an in situ blowing process during curing of the polysiloxane precursor at 200-300°C. The open cellular structure was characterized by a mean strut thickness of 130 μm, an average cell diameter of 800 μm and a high pore connectivity. The ceramic preforms were infiltrated with AZ 31 magnesium alloy by squeeze casting at 680°C applying a maximum pressure of 86 MPa. Interface bonding was achieved by the formation of spinel and cordierite in a reaction layer at the metal/ceramic interface. The dense metal/ceramic composite possesses significantly higher elastic modulus, yield strength and creep resistance than the monolithic alloy at room temperature and 135°C. The experimental results suggest that filler-loaded preceramic polymers have a high potential for optimization of lightweight metal cast components.
UnivIS-Import:2015-03-09:Pub.2002.tech.IW.LWAW.polysi
Keywords: Ceramic foam; Interpenetrating phase composites; Squeeze casting

Possibilities for Improving the Heat Resistance of Cylinder Head Alloys based on AlSi7MgCu0.5 and AISi10MgCu0.5 - Schwimmer, Daniel; Stich, Anton; Höppel, Heinz Werner (2017)

Powder content in powder extrusion moulding of tool steel: Dimensional stability, shrinkage and hardness - Gonzalez-Gutierrez, Joamin; Thompson, Yvonne; Handl, David; Cano, Santiago; Schuschnigg, Stephan; Felfer, Peter; Kukla, Christian; Holzer, Clemens; Burkhardt, Carlo (Materials Letters, 2021)
Powder extrusion moulding (PEM) is a versatile and cost-effective technology for producing bidimensional shapes, (e.g. tubes and profiles) from metals, ceramics and cermets. PEM quality is affected by powder content; therefore, three highly-filled polymeric compounds containing 50, 55, 60 vol% tool steel powder were prepared and extruded to profiles. Extruded parts were debound in cyclohexane and sintered in forming gas (Ar + 5% H-2) to obtain dense, sintered parts. The dimensional stability, the shrinkage and the hardness were measured. Minimum shrinkage and higher dimensional stability were obtained when the powder content was the highest (60 vol%). Specimens with 50 vol% powder had the highest hardness due to the initial higher binder content and resulting carbon content. (C) 2020 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2021-01-08

Preface to the special issue on ultrafine grained materials - Zhu, Yuntian T.; Mathaudhu, Suveen N.; Göken, Mathias; Langdon, Terence G.; Lowe, Terry C.; Semiatin, S. Lee; Tsuji, Nobuhiro; Zhao, Yong Hao (Journal of Materials Science, 2010)
WW1::854

Preparation of atom probe tips from (nano)particles in dispersion using (di)electrophoresis and electroplating - Vorlaufer, Nora; Josten, Jan; Carl, Simon; Göbel, Erik; Soegaard, Alexander; Taccardi, Nicola; Spiecker, Erdmann; Felfer, Peter (Microscopy Research and Technique, 2023)
The behavior of catalytic particles depends on their chemical structure and morphology. To reveal this information, the characterization with atom probe tomography has huge potential. Despite progresses and papers proposing various approaches towards the incorporation of particles inside atom probe tips, no single approach has been broadly applicable to date. In this paper, we introduce a workflow that allowed us to prepare atom probe specimens from Ga particles in suspension in the size range of 50 nm up to 2 μm. By combining dielectrophoresis and electrodeposition in a suitable way, we achieve a near-tip shape geometry, without a time-consuming FIB lift-out. This workflow is a simple and quick method to prepare atom probe tips and allows for a high preparation throughput. Also, not using a lift-out allowed us to use a cryo-stage, avoiding melting of the Ga particles, while ensuring a mechanical stable atom probe tip. The specimen prepared by this workflow enable a stable measurement and low fracture rates.<br

Preparation of atom probe tips from (nano)particles in dispersion using (di)electrophoresis and electroplating - Vorlaufer, Nora; Josten, Jan; Carl, Simon; Göbel, Erik; Soegaard, Alexander; Taccardi, Nicola; Spiecker, Erdmann; Felfer, Peter (Microscopy Research and Technique, 2024)
The behavior of catalytic particles depends on their chemical structure and morphology. To reveal this information, the characterization with atom probe tomography has huge potential. Despite progresses and papers proposing various approaches towards the incorporation of particles inside atom probe tips, no single approach has been broadly applicable to date. In this paper, we introduce a workflow that allowed us to prepare atom probe specimens from Ga particles in suspension in the size range of 50 nm up to 2 μm. By combining dielectrophoresis and electrodeposition in a suitable way, we achieve a near-tip shape geometry, without a time-consuming FIB lift-out. This workflow is a simple and quick method to prepare atom probe tips and allows for a high preparation throughput. Also, not using a lift-out allowed us to use a cryo-stage, avoiding melting of the Ga particles, while ensuring a mechanical stable atom probe tip. The specimen prepared by this workflow enable a stable measurement and low fracture rates. Research Highlights: Enabling cryo-preparation of (nano)particles for the atom probe. Characterization of surface and bulk elemental distribution of GaPt model SCALMS.
CRIS-Team Scopus Importer:2024-02-16
Keywords: atom probe tomography; catalyst particles; cryo preparation; nanoparticles

Produktionsmanagement als effizientes Werkzeug zur Vernetzung von Forschungsprojekten - Ziegler, Christian; Stockinger, Andreas; Stoll, Tobias; Wittmann, Stefan; Weickmann, Johannes; Schmidt, Jürgen; Topic, Irena; Schuck, Marcus; Cojutti, Massimo; Al-Sheyyab, Ahmad (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2007)
LFT Import::2019-07-16 (1501)

Progressive changes in crystallographic textures of biominerals generate functionally graded ceramics - Wallis, David; Harris, Joseph; Böhm, Corinna; Wang, Di; Zavattieri, Pablo; Feldner, Patrick; Merle, Benoit; Pipich, Vitaliy; Hurle, Katrin; Leupold, Simon; Hansen, Lars N.; Marin, Frederic; et al. (Materials Advances, 2021)
Biomineralizing organisms are widely praised for their ability to generate structural materials with exceptional crystallographic control. While earlier studies highlighted near-to single-crystalline biominerals, complex polycrystalline features are more widespread yet challenging to account for. Here, we propose that biominerals whose crystal texture varies with depth are functionally graded materials. Using the exemplary case of the nacro-prismatic pearl oyster Pinctada margaritifera, we demonstrate systematic textural changes in a biogenic ceramic. This bivalve employs three synergistic mechanisms to generate a texture gradient across its outer calcitic shell layer. This prismatic layer transitions from an initially weakly-textured to a strongly-textured material. Such changes in texture cause a variation in Young's modulus normal to the shell, owing to the anisotropic mechanical properties of the composing crystallites. Based on finite-element simulations and indentation experiments on the bivalve shell, we conclude that such graded bioceramics yield intrinsic toughening properties similar to those found in compositionally-graded synthetic materials. Notwithstanding, the gradation concept of Pinctada margaritifera is unparalleled among synthetic materials as it rests solely upon elastic anisotropy, making oyster shells potential blueprints for future bioinspired functional materials and damage-resistant ceramics.
CRIS-Team WoS Importer:2022-01-14

Properties and Limitation of an Oxide Coated Aluminum Brake Rotor - Gulden, Florian; Gramstat, Sebastian; Stich, Anton; Höppel, Heinz Werner; Tetzlaff, Ulrich (SAE Technical Papers, 2018)
The electrification of the powertrain and the thereto related recuperation of the electric engine saves the energy in the battery and thus reduces the thermally dissipated brake energy, which leads to lower brake rotor temperatures compared to combustion engine vehicles (ICEVs). These new conditions enable to reconsider brake disc concepts. Including lightweight design in heavy battery electric vehicles (BEVs) and the increasingly reliant corrosion resistance of brake rotors, Aluminum is a promising approach for new brake disc concepts. In the past, Aluminum brake disc concepts have already been deployed. For instance Aluminum Metal-Matrix Composite (Al-MMC) concepts in the Lotus Elise S1 and on the rear axle of the Volvo V40 [1]. The presented concept is a different approach and separates the friction system from the bulk Aluminum brake disc, achieved by coating of the friction rings. By locally reinforcing the friction rings, the good machinability and ductility of the base body is maintained and simultaneously the friction surface is sufficiently protected to resist the frictional loading during a brake application. In this work, fundamental studies on a brake dynamometer were conducted and supplemented by microstructural investigation to identify damage mechanisms and to judge the technical application of the concept.
Created from Fastlane, Scopus look-up

Pseudotachylyte in muscovite-bearing quartzite: Coseismic friction-induced melting and plastic deformation of quartz - Bestmann, Michel; Pennacchioni, Giorgio; Frank, Gerhard; Göken, Mathias; de Wall, Helga (Journal of Structural Geology, 2011)
Thin (0.5–2 mm thick) pseudotachylyte veins occur within muscovite-bearing ( 10% volume), amphibolite-facies quartzites of the Schneeberg Normal Fault Zone (Austroalpine, Southern Tyrol, Italy). Pseudotachylytes are associated with precursor localized plastic microshear zones (50–150 extgreekmm thick) developed sub-parallel to the host-rock foliation and with conjugate sets oriented at a high angle to the foliation. Such microshear zones are characterized by recrystallization to ultrafine-grained (1–2 extgreekmm grain size) mosaic aggregates of quartz showing a transition from a host-controlled to a random crystallographic preferred orientation towards the shear zone interior. Subsequent coseismic slip mainly exploited these microshear zones. Microstructural analysis provides evidence of extensive friction-induced melting of the muscovite-bearing quartzite, producing a bimodal melt composition. First, the host-rock muscovite was completely melted and subsequently crystallized, mainly as K-feldspar. Then, about 60% volume of the ultrafine-grained quartz underwent melting and crystallized as spherulitic rims (mostly consisting of quartz ± Ti ± Fe) around melt-corroded quartz clasts. The two melts show immiscibility structures in the major injection veins exploiting microshear zones at high angles to the quartzite foliation. In contrast, they were mechanically mixed during flow along the main fault veins.
WW1::896

Quantification of dislocation structures at high resolution by atomic force microscopy of dislocation etch pits - Sadrabadi, Peiman; Durst, Karsten; Göken, Mathias; Blum, Wolfgang (Philosophical Magazine Letters, 2009)
WW1::823

Quantification of the temperature-dependent evolution of defect structures in a CoNi-base superalloy - Bezold, Andreas; Volz, Nicklas; Lenz, Malte; Karpstein, Nicolas; Zenk, Christopher; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Acta Materialia, 2022)
Quantifying the individual contributions of specific deformation mechanisms to the total plastic strain is of primary importance to understand the underlying deformation behavior and assess the significance of the different mechanisms. However, this quantification is nearly impossible in Ni-base superalloys due to the inherent difficulties in determining the propagation distances of the respective shearing dislocations. In this study, the occurrence of stacking faults (SFs) at temperatures between 750 °C and 1000 °C in the single crystalline CoNi-base superalloy ERBOCo-4 provides an opportunity to systematically quantify the evolution of the defect structures as a function of temperature and strain after constant strain-rate compressive tests. The quantification approach revealed that deformation is still localized in the matrix at 750 °C. With increasing temperature, the main deformation mechanism changes to SF shearing, which contributes 74% of the total deformation during the initial yielding stage (∼ 0.3% plastic strain) at 900 °C. Deformation spreads significantly more homogeneously across the γ/γ’ microstructure with increasing plastic strain. Extremely high stacking fault densities and frequent fault interactions cause a pronounced work-hardening anomaly at 850 °C. Structural characterization on the atomic scale confirms the strengthening effect of SFs as barriers to partial dislocation propagation. A strong correlation between the possible diffusion length of segregating solutes and the operant shearing mechanisms reveals the significance of segregation on the occurring deformation mechanisms.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Co-base superalloy; Defect structures; High temperature deformation; Transmission electron microscopy; Yielding behavior

Quantifying Co-Deformation Effects in Metallic Laminates by Loading–Unloading–Reloading Tensile Tests - Pohl, Philip; Kuglstatter, Moritz; Göken, Mathias; Höppel, Heinz Werner (Metals, 2023)
Heterostructured materials such as metallic laminates (LMCs) can be specifically tailored to showcase significantly increased mechanical behavior based on the hetero-deformation-induced (HDI) strengthening effect caused by the co-deformation at the vicinity of interfaces. This study introduces a new approach to quantify these co-deformation effects in metallic laminates by characterizing the behavior of inelastic back strain upon unloading. Experimentally, the inelastic back strain (IBS) is determined by cyclic loading–unloading–reloading (LUR) tensile tests. Compared to a linear rule of mixture (ROM) approximation used as a reference, additional amounts of inelastic back strain were measured for different metallic laminate systems, strongly depending on the dissimilarities of yield strength and elastic moduli of constituents and the interface density in the laminates. Conducting finite element analysis, the distribution of residual plastic strain was investigated for the different metallic laminates used in this study. Based on this, a schematic overview of the spatial distribution of the hetero-deformation zone for metallic laminates with dissimilar yield strength and elastic moduli is derived, summarizing the results of this study. As most mechanical components are subject to cyclic stresses during the application, the method provided in this study to characterize the co-deformation behavior of metallic laminates in the microyielding regime enables valuable insights into mechanisms affecting the cyclic deformation behavior of metallic laminates for future applications.<br
Keywords: heterostructured materials; laminated metallic composites (LMCs); interfaces; hetero-deformation zone; cyclic deformation behavior; ultrafine-grained (UFG)

Quantifying eigenstrain distributions induced by focused ion beam damage in silicon - Korsunsky, Alexander; Guenole, Julien; Salvati, Enrico; Sui, Tan; Mousavi, Mahmoud; Prakash, Aruna; Bitzek, Erik (Materials Letters, 2016)
Eigenstrain offers a versatile generic framework for the description of inelastic deformation that acts as the source of residual stresses. Focused ion beam (FIB) milling used for nanoscale machining is accompanied by target material modification by ion beam damage having residual stress consequences that can be described in terms of eigenstrain. Due to the lack of direct means of experimental determination of residual stress or eigenstrain at the nanoscale we adopt a hybrid approach that consists of eigenstrain abstraction from molecular dynamics simulation, its application within a finite element simulation of a flexible silicon cantilever, and satisfactory comparison of the prediction with experimental observation. Directions for further enquiry are briefly discusse
Keywords: Eigenstrain; Focused ion beam milling; Molecular dynamics; Residual stress

Quantifying the distributions of dislocation spacings and cell sizes - Eisenlohr, Philip; Sadrabadi, Peiman; Blum, Wolfgang (Journal of Materials Science, 2008)
WW1::782

Reasons for the enhanced phase stability of Ru-containing nickel-based superalloys - Heckl, Astrid; Neumeier, Steffen; Cenanovic, S.; Göken, Mathias; Singer, Robert (Acta Materialia, 2011)
Improvements in phase stability on the addition of Ru are well known in the field of nickel-based superalloy development. However, the key mechanism of this benefit remains unclear. A new alloy series with stepwise increased additions of Ru was used to systematically investigate the impact of Ru on yopologically close-packed (TCP) phase inhibition. In addition, the investigation was carried out on a less known type of TCP formation, the so-called discontinuous precipitation. This type of TCP phase formation offers two major advantages compared with commonly investigated TCP plates in dendritic regions. First, the microstructure is much coarser than fine TCP plates, allowing reliable and less time consuming investigations. Second, discontinuous precipitation transforms the supersaturated and unstable γ/γ′ microstructure in a condition close to equilibrium, permitting a meaningful insight into the stable alloy constitution. The experimental results for alloy phase stability dependence on Ru are evaluated with respect to all possible effects of TCP phase inhibition by Ru. Furthermore, experimental evidence for increased Re solubility in the γ matrix was found on addition of Ru, which is not seen in corresponding ThermoCalc calculations. This finding is probably the dominant reason for the increased TCP phase capability of Ru-containing alloys. A ternary phase diagram model has been developed to describe the new approach. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Discontinuous precipitation; Phase stability; Ruthenium; ThermoCalc; Topologically close-packed phase inhibition

Recent advances in nanomechanical and in situ testing techniques: Towards extreme conditions - Kiener, Daniel; Wurmshuber, Michael; Alfreider, Markus; Schaffar, Gerald J.K.; Maier-Kiener, Verena (Current Opinion in Solid State & Materials Science, 2023)
Nanoindentation based techniques were significantly enhanced by continuous stiffness monitoring capabilities. In essence, this allowed to expand from point-wise discrete measurement of hardness and elastic modulus towards advanced plastic characterization routines, spanning the whole rate-dependent spectrum from steady state creep properties via quasi static flow curves to impact or brittle fracture. While representing a significant step forwards already, these techniques can tremendously benefit from additional or complementary input provided by in situ or operando experiments. In fact, by combining and merging these approaches, impressive advances were made towards well controlled nanomechanical investigations at various non-ambient conditions. Here we will discuss some novel experimental avenues facilitated by deliberate extreme environments, and also indicate how future improvements and enhancements will potentially provide previously unseen insights into fundamental material behavior at extreme conditions.
Keywords: Nanoindentation; Miniaturized mechanical testing; Fracture mechanics; Continuous stiffness measurement; kernfusionsrelevant

Recovery of superlattice stacking faults at high temperatures - Bezold, Andreas; Amon, L.; Karpstein, Nicolas; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Scripta Materialia, 2023)
Stacking fault shearing is commonly observed in Co-base and CoNi-base superalloys in the intermediate temperature regime between 850 °C to 1000 °C in contrast to Ni-base superalloys. In this work, we report on the significance of recovery processes after aging and creep experiments on predeformed specimens with extreme stacking fault densities. Above 950 °C, superlattice stacking faults start to recover rapidly, whereby intrinsic ones recover more quickly than extrinsic ones. Our results also reveal that the significance of stacking fault shearing in the high temperature creep regime could be higher than that indicated by traditional postmortem investigations due to recovery processes.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Co-base superalloy; Creep; Recovery; Stacking fault; Transmission electron microscopy

Reliability model of LED package regarding the fatigue behavior of gold wires - Altieri-Weimar, P.; Yuan, W.; Annibale, E. S.; Schoemaker, S.; Amberger, D.; Göken, Mathias; Höppel, Heinz Werner (2016)
In this study the mechanical properties and fatigue behavior of ultra-fine gold wires are investigated by experimental tension fatigue tests and finite element (FE) simulation. Hardening behavior, yield criterion and yield surface of gold wire are determined by tensile tests and force controlled tension fatigue tests. The relationship between plastic strain and loading stress amplitude is determined and the cyclic strain hardening coefficient is calculated. The fatigue data are used to develop a predictive crack model for gold wires bonded in LED packages, based on finite element (FE) stress simulation at temperature cycles (TC). The computer model of the gold wire in the LED package used in the simulation is reconstructed from computer tomography (CT) analysis. The predictive crack model is calibrated using on-line monitoring of LED wire cracks during TC tests. Finally, using the reliability model, the impact of LED package design and material on the wire lifetime is investigated.

Reliable identification of the complex or superlattice nature of intrinsic and extrinsic stacking faults in the L12 phase by high-resolution imaging - Karpstein, Nicolas; Lenz, Malte; Bezold, Alexander; Wu, Mingjian; Neumeier, Steffen; Spiecker, Erdmann (Acta Materialia, 2023)
Planar defect-based deformation mechanisms are becoming increasingly important for understanding and tuning the mechanical properties of superalloys. Typically, to elucidate such deformation mechanisms, the type of planar defect is determined by conventional transmission electron microscopy or by high-resolution imaging along 〈110〉 crystallographic directions. However, an unambiguous identification of the complex or non-complex nature of intrinsic and extrinsic stacking faults in the L12 phase may not be possible by analyzing only one projection. To overcome this limitation, we present a straightforward approach to identify the superlattice or complex character of intrinsic and extrinsic faults in the L12 structure in high-resolution scanning transmission electron microscopy by tilting to a different zone axis and examining the shift of superlattice planes. Using this approach, two key aspects of the Kolbe mechanism for the formation of superlattice extrinsic stacking faults are verified for the first time: the presence of a complex intrinsic fault segment at the leading end and the occurrence of re-ordering.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Creep; Dislocation; Electron microscopy; Planar defects; Superalloy

Residual Stresses in Ultrafine-Grained Laminated Metal Composites Analyzed by X-ray Diffraction and the Hole-Drilling Method - Kümmel, Frank; Magnier, Arnauld; Wu, Tao; Niendorf, Thomas; Höppel, Heinz Werner (Advanced Engineering Materials, 2022)
Accumulative roll bonding is an advanced manufacturing process, which is capable of simultaneously refining the grain size into the nanometer regime and bonding different metallic sheet materials. Herein, homogenous aluminum/aluminum as well as heterogeneous aluminum/steel laminated metal composite (LMCs) are fabricated. The residual stresses are experimentally determined by X-ray diffraction and the hole-drilling method. Generally, a complex residual stress profile is found in all LMCs. The level of residual stress strongly depends on the bonded materials. Compressive residual stresses are induced in all sheets in the near surface area. These stresses range from -5 MPa in aluminum to -240 MPa in steel. In the homogenous aluminum/aluminum LMCs, compressive stresses up to -26 MPa in the softer layers and tensile stresses up to 30 MPa in the stronger layers are built up. This is different to heterogeneous aluminum/steel LMCs, where tensile stresses up to 40 MPa in the softer aluminum layers and compressive stresses up to -72 MPa in the inner harder steel layers are present. Based on the results obtained it is possible to directly design the material combination or stacking architecture of ultrafine-grained LMCs to tailor the residual stress profile.
CRIS-Team WoS Importer:2022-05-27

Resistance-curve envelopes for dental lithium disilicate glass-ceramics - Lubauer, Julia; Ast, Johannes; Göken, Mathias; Merle, Benoit; Lohbauer, Ulrich; Belli, Renan (Journal of the European Ceramic Society, 2022)
Recent investigations on the mechanics of dental lithium disilicates have gathered mounting evidences of a probable R-curve behavior. Here we use an indirect approach to obtain the contours of the R-curve using the relationship between strength and initial crack size obtained from quasi-static fracture toughness tests. The tangent condition formed by the multiple K I,appl (ai,j) curves give a smoothened polygonal envelope for the R-curves. The R-curves obtained this way were extended toward an initial value at the onset of stable crack extension, obtained hereusing a microcantilever specimen featuring a sharp notch produced by focused-ion-beam milling. The presence of an R-curve effect was confirmed for the three evaluated lithium disilicates, being more pronounced for the injection-molded material having an oriented elongated Li2Si2O5 microstructural architecture, with crystal fraction playing an important role for low-aspect ratio randomly-oriented microstructures.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Dental ceramics; Focused ion beam milling; Fracture toughness; Lithium silicate; Micro-scale; R-curve

Revealing atomic-scale vacancy-solute interaction in nickel - Morgado, Felipe F.; Katnagallu, Shyam; Freysoldt, Christoph; Klaes, Benjamin; Vurpillot, François; Neugebauer, Jörg; Raabe, Dierk; Neumeier, Steffen; Gault, Baptiste; Stephenson, Leigh T. (Scripta Materialia, 2021)
It is widely accepted that the different types of crystalline imperfections, such as vacancies or dislocations, greatly influence a material's physical and mechanical properties. However, imaging individual vacancies in solids and revealing their atomic neighborhood remains one of the frontiers of microscopy and microanalysis. Here, we study a creep-deformed binary Ni-2 at.% Ta alloy. Atom probe tomography reveals a random distribution of Ta. Field ion microscopy, with contrast interpretation supported by density-functional theory and time-of-flight mass spectrometry, evidences a positive correlation of Ta with vacancies, supporting positive solute-vacancy interactions previously predicted by atomistic simulations.
CRIS-Team Scopus Importer:2021-06-18

Revealing bulk metallic glass crystallization kinetics during laser powder bed fusion by a combination of experimental and numerical methods - Yang, Zerong; Huber, Florian; Krapf, Anna; Merle, Benoit; Markl, Matthias; Schmidt, Michael; Körner, Carolin (Journal of Non-Crystalline Solids, 2023)
Laser powder bed fusion (PBF-LB/M) has been used to fabricate bulk metallic glass (BMG) parts. However, there is still a lack of understanding about the crystallization behavior of BMGs during PBF-LB/M. This article aims to combine experimental and numerical methods to gain a more comprehensive understanding of the BMG crystallization kinetics during PBF-LB/M. The material used in this work is an industrial-grade BMG commercially known as AMZ4 (Zr59.3Cu28.8Al10.4Nb1.5, at.%). The samples prepared by PBF-LB/M were characterized by optical microscopy, scanning electron microscopy, and nanoindentation. Simulations were performed using our in-house developed software with setups mimicking the PBF-LB/M experiment. The experimental and numerical results are compared and discussed in detail. The most important finding is that BMG crystallization in PBF-LB/M is a very localized phenomenon, mainly caused by short-range in situ heat treatment. Here, short-range in-situ heat treatment refers to concomitant heat treatment that occurs during the processing of the current melt line, very few subsequent melt lines, and very few subsequent layers. This work provides insight into the BMG crystallization phenomenon that occurs during PBF-LB/M processing, especially its underlying crystallization kinetics. Furthermore, this work demonstrates the usefulness of our in-house developed simulation software in guiding PBF-LB/M process development for BMGs and BMG composites.<br
Keywords: Bulk metallic glass; Crystallization; Laser powder bed fusion; Additive manufacturing; Numerical simulation

Revealing deformation mechanisms with nanoindentation - Kiener, Daniel; Durst, Karsten; Rester, M.; Minor, A. M. (JOM Journal of the Minerals, Metals and Materials Society, 2009)
WW1::824

Revealing the Distribution of the Atoms within Individual Bimetallic Catalyst Nanoparticles - Felfer, Peter; Benndorf, Paul; Masters, Anthony; Maschmeyer, Thomas; Cairney, Julie M. (Angewandte Chemie International Edition, 2014)
To be able to correlate the catalytic properties of nanoparticles with their structure, detailed knowledge about their make-up on the atomic level is required. Herein, we demonstrate how atom-probe tomography (APT) can be used to quantitatively determine the three-dimensional distribution of atoms within a Au@Ag nanoparticle with near-atomic resolution. We reveal that the elements are not evenly distributed across the surface and that this distribution is related to the surface morphology and residues from the particle synthesi
Keywords: atom-probe tomography; heterogeneous catalysts; nanoparticles; silver; surface analysis

Revealing the local fatigue behavior of bimodal copper laminates by micropillar fatigue tests - Krauß, Sebastian; Schieß, Thomas; Göken, Mathias; Merle, Benoit (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2020)
Cyclic micropillar compression is a powerful technique for characterizing the local fatigue properties of microstructurally complex materials. Here, it was applied to a bimodal copper sample made of alternating ultrafine and coarse grained layers. Micropillars were fabricated from both domains, as well as from the interface between them. The three different areas were investigated from the quasi-static to the high cycle fatigue range (up to 1 million cycles). In line with expectations, the CG micropillars exhibit the smallest fatigue strength and the UFG specimens the highest one. More surprisingly, the micropillars containing a bimodal UFG/CG interface exhibit a slightly shorter fatigue lifetime than plain UFG specimens. The likely reason is their more complex stress state, which alternates between tension and compression and results in the formation of surface extrusions, which lead to eventual failure.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Bimodal microstructure; Copper; High cycle fatigue; Micropillar compression; Nanoindentation

Robocasting of reaction bonded silicon carbide/silicon carbide platelet composites - Wahl, Larissa; Weichelt, Michelle; Goik, Philip; Schmiedeke, Samuel; Travitzky, Nahum (Ceramics International, 2021)
Pastes with a varying amount of uncoated SiC platelets (SiCplatelets) for the fabrication of reaction bonded silicon carbide (RBSC) were developed and the effect of the anisotropic particles on the microstructure and mechanical properties of the fabricated RBSC/SiCplatelets composites was studied. During printing the platelets align in printing direction due to shear forces. This texturization was confirmed by image analysis and EBSD measurement.
CRIS-Team WoS Importer:2021-04-02

Role of Si segregation in the structural, mechanical, and compositional evolution of high-temperature oxidation resistant Cr-Si-B2±z thin films - Zauner, L.; Steiner, A.; Glechner, T.; Bahr, A.; Ott, Benedict; Hahn, R.; Wojcik, T.; Hunold, O.; Ramm, J.; Kolozsvári, S.; Polcik, P.; Felfer, Peter; et al. (Journal of Alloys and Compounds, 2023)
This work investigates the influence of Si-alloying up to 17 at.% on the structural, mechanical, and oxidation properties of magnetron sputtered CrB2±z-based thin films. Density-functional theory calculations combined with atom probe tomography reveal the preferred Si occupation of Cr-lattice sites and an effective solubility limit between 3 to 4 at.% in AlB2-structured solid solutions. The addition of Si results in refinement of the columnar morphology, accompanied by enhanced segregation of excess Si along grain boundaries. The microstructural separation leads to a decrease in both film hardness and Young's modulus from H ∼ 24 to 17 GPa and E ∼ 300 to 240 GPa, respectively, dominated by the inferior mechanical properties of the intergranular Si-rich regions. Dynamic thermogravimetry up to 1400 °C reveals a significant increase in oxidation onset temperature from 600 to 1100 °C above a Si content of 8 at.%. In-situ X-ray diffraction correlates the protective mechanism with thermally activated precipitation of Si from the Cr-Si-B2±z solid solution at 600 °C, enabling the formation of a stable, nanometer-sized SiO2-based scale. Moreover, high-resolution TEM analysis exposes the scale architecture after dynamic oxidation to 1200 °C (10 K/min heating rate) – consisting only of ∼20 nm amorphous SiO2 beneath ∼200 nm of nanocrystalline Cr2O3. In summary, the study provides detailed guidelines connecting the chemical composition with the respective thin film properties of high-temperature oxidation resistant Cr-Si-B2±z coatings.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Borides; Mechanical properties; Oxidation resistance; Phase stability; Segregation; Si alloying; Thin films

Room temperature deposition of functional ceramic films on low-cost metal substrate - Khansur, Neamul Hayet; Eckstein, Udo; Benker, Lisa; Deisinger, Ulrike; Merle, Benoit; Webber, Kyle Grant (Ceramics International, 2018)
In various practical applications, such as high power actuators, high sensitivity sensors, and energy harvesting devices, polycrystalline piezoelectric films of 1-100 mu m thickness and sizes ranging from several mu m(2) to several cm(2) are required. With conventional film deposition processes, such as sol-gel, sputtering, chemical vapor deposition, or pulsed laser deposition, it is difficult to fabricate films with higher thickness due to their low deposition rate and high interfacial stress. The aerosol deposition method (AD), a relatively new deposition technique, can be used to fabricate highly dense thick films at room temperature by the consolidation of sub micrometer-sized ceramic particles on various ceramic, metal, glass, and polymer substrates. Ferroelectric BaTiO3 ceramic films of different thicknesses ranging from 1 to 30 gm were fabricated on a low-cost metallic substrate at room temperature using the AD method. Surface morphology and adhesion of the film were analyzed. Analysis of internal residual stresses revealed an equibiaxial compressive stress state in the as-processed film. Electrical characterization of films annealed at 500 degrees C shows an enhanced polarization value of similar to 14 mu C/cm(2) over that of the as-processed film. This improved property is related to the decreasing internal residual stress. In addition, the BT films prepared in this work were found to withstand electric fields greater than 100 kV/mm, which is possibly related to the inherent relatively defect-free structure of AD films.
Keywords: Functional ceramics; Aerosol deposition; Internal stress; Thick films

Rotating Scan Strategy Induced Anisotropic Microstructural and Mechanical Behavior of Selective Laser Melted Materials and Their Reduction by Heat Treatments - Diepold, Benedikt; Palm, Mathias Sebastian; Wimmer, Andreas; Sebald, Torsten; Höppel, Heinz Werner; Neumeier, Steffen; Göken, Mathias (Advanced Engineering Materials, 2021)
Choosing a properly optimized rotating scan strategy during the selective laser melting (SLM) process is essential to reduce residual stresses and thus to obtain homogeneous properties. Surprisingly, anisotropic material properties are found in several materials that are built with the often applied rotating stripes scan strategy of Electro-Optical Systems (EOS) because the scan strategy avoids possible interactions of the laser beam with process by-products and therefore excludes a range of scanning directions. Herein, the alloys Hastelloy X, Inconel 718, and stainless steel 316L are investigated. Vertically built specimens with a cylindrical gauge geometry show an oval deformation during tensile testing, indicating a mechanical anisotropy in the horizontal x- and y-direction. Tensile tests along the x- and y-direction reveal a deviation of the yield strength of 7% for Hastelloy X. Analyses of the microstructures show differences in the grain morphology, size, and texture in all three coordinate planes of the three materials. This anisotropic behavior can be explained by a detailed study of the texture and the calculated Schmid factors. Heat treatments can reduce the textural and mechanical anisotropy due to recrystallization of grains but requires annealing at sufficiently high temperatures and long times.
CRIS-Team Scopus Importer:2021-08-13
Keywords: microstructures; selective laser melting; stainless steel; superalloys; textures

Scaling of the fracture toughness of freestanding metallic thin films with the yield strength - Preiß, Eva; Gannott, Florentina; Göken, Mathias; Merle, Benoit (Materials Research Letters, 2018)
The influence of the yield strength on the fracture toughness of freestanding metallic films with a thickness of similar to 150 nm was investigated by bulge testing. For this purpose, gold films prepared by thermal evaporation were tested at room temperature and at 100 degrees C. Additionally, different Au-Ag solid-solution strengthened films were studied. The fracture toughness of the films is observed to increase with increasing yield stress. This is at first sight counterintuitive but can be explained by previously observed severe necking leading to a chisel-point type of fracture in freestanding metallic thin films.[GRAPHICS]IMPACT STATEMENTFreestanding metallic thin films exhibit an extremely low fracture toughness. It is shown in this publication that Kic can be significantly improved by increasing the yield strength of the films.
Keywords: Fracture toughness; thin films; AuAg solid solutions; bulge test

Secondary Al-Si-Mg High-pressure Die Casting Alloys with Enhanced Ductility - Bösch, Dominik; Pogatscher, Stefan; Hummel, Marc; Fragner, Werner; Uggowitzer, Peter J.; Göken, Mathias; Höppel, Heinz Werner (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2014)
WW1::1008
Keywords: Nanomaterials

Segregation assisted microtwinning during creep of a polycrystalline L1(2)-hardened Co-base superalloy - Freund, Lisa; Messe, Olivier M. D. M.; Barnard, Jonathan S.; Göken, Mathias; Neumeier, Steffen; Rae, Catherine M. F. (Acta Materialia, 2017)
A polycrystalline L1(2)-hardened Co-base superalloy was creep deformed at 750 degrees C. The investigation of the deformed microstructure in the transmission electron microscope revealed microtwinning to be the prevailing deformation mechanism. The detected twins spanned the entire grain and cut through both, gamma and gamma'. Detailed high-resolution transmission electron microscopy investigations indicated that twin growth takes place by the slip of single a/6 (112) partial dislocations along the twin boundary. Further analysis of the twin boundaries in the gamma' phase revealed segregation of elements known to decrease the stacking fault energy and a local depletion of gamma' forming elements. We propose that this segregation behavior enables subsequent a/6 < 112 > dislocations to easily slip along the twin boundary and further thicken the twins in the process. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Cobalt-base superalloys; Creep; Microtwinning; Stacking faults; Transmission electron microscopy

Segregation-induced strength anomalies in complex single-crystalline superalloys - Bezold, Andreas; Vollhüter, Jan; Karpstein, Nicolas; Lenz, Malte; Subramanyam, Aparna P.A.; Zenk, Christopher; Hammerschmidt, Thomas; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Communications Materials, 2024)
Pushing the maximum service temperature of aircraft engines and industrial gas turbines is the major pathway to improve their energy efficiency and reduce CO2 emissions. This maximum is mostly limited by the temperature capability of key-component materials, including superalloys. In this alloy class, segregation of elements facilitates plastic deformation and is generally considered to cause softening during high-temperature deformation. Here, we show that segregation-assisted processes can also lead to strengthening and induce an anomalous increase of the yield strength. Atomic-resolution transmission electron microscopy and density functional theory calculations reveal a segregation-assisted dissociation process of dislocations at precipitate-matrix interfaces in combination with atomic-scale reordering processes. These processes lead to an inhibition of athermal deformation mechanisms and a transition to stacking fault shearing, which causes the strengthening effect. Unraveling these elementary mechanisms might guide a mechanism-based alloy design of future superalloys with enhanced high-temperature capabilities.
CRIS-Team Scopus Importer:2024-02-02

Segregation of B, P, and C in the ni-based superalloy, Inconel 718 - Alam, Talukder; Felfer, Peter; Chaturvedi, Mahesh; Stephenson, Leigh T.; Kilburn, Matthew R.; Cairney, Julie M. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2012)
Small additions of B, P, and C can result in dramatic changes in the mechanical performance and welding behavior of Inconel 718. Although additions of B and P improve the mechanical properties, they have a detrimental effect on weldability. Adding C mitigates the negative effect on welding while retaining the improvements in mechanical performance. In this study, precise observations of the segregation of B, P, and C to the grain boundaries are made using sitespecific atom probe tomography and NanoSIMS. Changes in the segregation behavior provide a quantitative explanation for the welding response, where hot cracking is attributed to the formation of a eutectic film. Calculations of the relative positions of the B, P, and C revealed that these atoms were less likely to cluster together in the presence of C, providing insight into the likely mechanisms behind the segregation behavior in this complex, multicomponent alloy. © The Minerals, Metals & Materials Society and ASM International 201

Sequence of distinct microyielding stages of the monocrystalline nickel-base superalloy CMSX-6 at high temperatures - Kraft, Stephan; Mughrabi, Hael; et al. (International Journal of Materials Research, 2009)
WW1::826

Shaping the lens of the atom probe: Fabrication of site specific, oriented specimens and application to grain boundary analysis - Felfer, Peter; Ringer, S. P.; Cairney, J. M. (Ultramicroscopy, 2011)
This technique is applied to the analysis of grain boundaries in a high purity iron wire and a strip-cast steel. Lattice resolution is achieved around the boundary in certain areas. Reconstruction of these datasets reveals the distribution of light and heavy elements around the boundary. Issues surrounding the uneven distribution of certain solute elements as a result of field-induced diffusion are discussed. (C) 2011 Elsevier B.V. All rights reserve
Keywords: Atom probe tomography; Grain boundaries; Focussed ion beam; Site specific; Grain boundary segregation

SiC ceramic micropatterns from polycarbosilanes - Jang, Yeon-Suk; Jank, Michael; Maier, Verena; Durst, Karsten; Travitzky, Nahum; Zollfrank, Cordt (Journal of the European Ceramic Society, 2010)
Micropatterned SiC ceramics were fabricated from polycarbosilanes applying a softlithographic replication technique. A polydimethylsiloxane mould replicated from a photolithographic microstructured silicon wafer was used as master structure. The polydimethylsiloxane mould was coated with a solution containing a mixture of two different polycarbosilanes in n-octane. After treatment at 200–400 °C the cross-linked polycarbosilane films were debonded and pyrolysed at 900 °C in nitrogen and subsequently crystallised at temperatures up to 1500 °C in argon. The cross-linking and thermal degradation behaviour of the polycarbosilanes was investigated by Fourier-transform infrared spectroscopy, differential scanning calorimetry and thermogravimetric analysis. X-ray diffractrometry showed the expected development of a nanocrystalline extgreekb-SiC (3 nm) as the main phase with increasing temperature. However, traces of extgreeka-SiO2 derived from the polycarbosilane precursors were also detected by X-ray analysis. Removal of the extgreeka-SiO2 dioxide with hydrofluoric acid in the pyrolysed samples and subsequent increased the crystallite size to 7 nm. The Young's modulus determined by nanoindentation was increased from 3 GPa after cross-linking to 110 GPa after crystallisation. Scanning electron microscopy revealed, that the initial micropatterns were fully retained in the pyrolysed and crystallised SiC ceramics. The micropatterned cross-linked and crystallised extgreekb-SiC based substrates exhibited light scattering characteristics, which qualify them as promising candidates for diffractive optical elements in microoptical applications.
WW1::855

Silicon nitride and intrinsic amorphous silicon double antireflection coatings for thin-film solar cells on foreign substrates - Li, Da; Kunz, Thomas; Wolf, Nadine; Liebig, Jan Philipp; Wittmann, Stephan; Ahmad, Taimoor; Hessmann, Maik T.; Auer, Richard; Göken, Mathias; Brabec, Christoph (Thin Solid Films, 2015)
Hydrogenated intrinsic amorphous silicon (a-Si:H) was investigated as a surface passivationmethod for crystalline silicon thin film solar cells on graphite substrates. The results of the experiments, including quantumefficiency and current density-voltage measurements, show improvements in cell performance. This improvement is due to surface passivation by an a-Si:H(i) layer, which increases the open circuit voltage and the fill factor. In comparison with our previous work, we have achieved an increase of 0.6% absolute cell efficiency for a 40 μm thick 4 cm2 aperture area on the graphite substrate. The optical properties of the SiNx/a-Si:H(i) stack were studied using spectroscopic ellipsometer techniques. Scanning transmission electron microscopy inside a scanning electron microscope was applied to characterize the cross section of the SiNx/a-Si:H(i) stack using focus ion beam preparatio
Keywords: Amorphous silicon; Crystalline silicon thin film; Double layer antireflection coating; Focus ion beam; Graphite substrate; Scanning transmission electron microscopy; Surface passivation

Simulation of fracture in heterogeneous elastic materials with cohesive zone models - Prechtel, Marina; Ronda, Pavel Leiva; Janisch, Rebecca; Hartmaier, Alexander; Leugering, Günter; Steinmann, Paul; Stingl, Michael (International Journal of Fracture, 2010)
In brittle composite materials, failure mechanisms like debonding of the matrix-fiber interface or fiber breakage can result in crack deflection and hence in the improvement of the damage tolerance. More generally it is known that high values of fracture energy dissipation lead to toughening of the material.Ouraimis toinvestigate the influence of material parameters and geometrical aspects of fibers on the fracture energy as well as the crack growth for given load scenarios. Concerning simulations of crack growth the cohesive element method in combination with the Discontinuous Galerkin method provides a framework to model the fracture considering strength, stiffness and failure energy in an integrated manner. Cohesive parameters are directly determined by DFT supercell calculations.We perform studies with prescribed crack paths as well as free crack path simulations. In both cases computational results reveal that fracture energy depends on both the material parameters but also the geometry of the fibers. In particular it is shown that the dissipated energy can be increased by appropriate choices of cohesive parametersof the interface and geometrical aspects of the fiber. In conclusion, our results can help to guide themanufacturing process ofmaterials with a high fracture toughness.
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-TM.simula

Single-crystal nickel-based superalloys developed by numerical multi-criteria optimization techniques: Design based on thermodynamic calculations and experimental validation - Rettig, Ralf; Ritter, Nils; Helmer, Harald; Neumeier, Steffen; Singer, Robert (Modelling and Simulation in Materials Science and Engineering, 2015)
A method for finding the optimum alloy compositions considering a large number of property requirements and constraints by systematic exploration of large composition spaces is proposed. It is based on a numerical multi-criteria global optimization algorithm (multistart solver using Sequential Quadratic Programming), which delivers the exact optimum considering all constraints. The CALPHAD method is used to provide the thermodynamic equilibrium properties, and the creep strength of the alloys is predicted based on a qualitative numerical model considering the solid solution strengthening of the matrix by the elements Re, Mo and W and the optimum morphology and fraction of the γ′-phase. The calculated alloy properties which are required as an input for the optimization algorithm are provided via very fast Kriging surrogate models. This greatly reduces the total calculation time of the optimization to the order of minutes on a personal computer. The capability of the multi-criteria optimization method developed was experimentally verified with two new single crystal superalloys. Their compositions were designed such that the content of expensive elements was reduced. One of the newly designed alloys, termed ERBO/13, is found to possess creep strength of only 14 K below CMSX-4 in the high-temperature/low-stress regime although it is a Re-free allo
Keywords: CALPHAD; Optimization; Rhenium; Superalloy; Surrogate model

Size-dependent fracture toughness of tungsten - Ast, Johannes; Göken, Mathias; Durst, Karsten (Acta Materialia, 2017)
In order to understand the size-dependent fracture behaviour of tungsten at the microscale, micro cantilever tests were performed on single crystalline and ultrafine grained tungsten. The elastic plastic fracture behaviour and crack tip plasticity were found to be strongly influenced by the sample size. The smallest cantilevers with dimensions below one micron failed by pure cleavage fracture at a fracture toughness of 1.5 MPa m(1/2), which agrees well with the Griffith theory for brittle fracture. With increasing specimen size crack tip plasticity was observed, leading to a successive increase in fracture toughness and crack resistance behaviour. Using scanning transmission electron microscopy and electron backscatter diffraction, dislocation densities were analysed and measured. Pronounced plastic strain gradients were found at the crack tip for an intermediate specimen size, which also showed the highest crack resistance. When further increasing the specimen size, large plastic zones were still observed but the gradients in plastic strain vanished, leading to a reduction in the crack resistance behaviour. For those samples, a size independent fracture toughness of ca. 7 MPa m(1/2) was found, which is close to macroscopic literature data. Increasing the initial dislocation density in the single crystals through plastic pre straining led to a reduced stable crack growth behaviour but did not affect the fracture toughness. Furthermore, the effect of grain boundaries on the fracture behaviour was studied by means of ultrafine grained tungsten. A fracture toughness lower than the one reported in literature was found, which is explained by the higher susceptibility to failure once a crack propagates at the micro-scale. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Size effects; Fracture; Tungsten; Micro-cantilever; kernfusionsrelevant

Small-scale fracture mechanical investigations on grain boundary doped ultrafine-grained tungsten - Wurmshuber, Michael; Alfreider, Markus; Wurster, Stefan; Burtscher, Michael; Pippan, Reinhard; Kiener, Daniel (Acta Materialia, 2023)

Small-scale high-cycle fatigue testing by dynamic microcantilever bending - Gabel, Stefan; Merle, Benoit (MRS Communications, 2020)
The lifetime of cyclically loaded devices is often limited by the fatigue resistance of their individual phases. An advanced method is presented for measuring the high-cycle fatigue behavior of materials at the micrometer scale using a nanoindenter. It is based on the cyclic deflection of focused ion beam-fabricated microcantilevers using the continuous stiffness method (CSM). In line with experimental data on bulk nanocrystalline copper, the specimens exhibit grain coarsening followed by the formation of extrusions and a fatigue strength exponent of -0.10. The method is suitable for characterizing single phases and individual components of further complex systems.
CRIS-Team Scopus Importer:2020-05-12

Solid solution strengthening of Mo, Re, Ta and W in Ni during high-temperature creep - Haußmann, Lukas; Rehman, Hamad Ur; Matschkal, Dorothea; Göken, Mathias; Neumeier, Steffen (Metals, 2021)
Solid solution strengthening of the unordered γ matrix phase by alloying elements is of great importance during creep of Ni-based superalloys, particularly at high temperatures above 1000 °C. To study the role of different potent solutes, we have conducted creep experiments on binary Ni-2X alloys (X = Mo, Re, Ta, W) at 1000 °C, 1050 °C, and 1100 °C at a constant stress of 20 MPa. Compared to mechanical tests below 800 °C, where the size of the elements mostly determines the solid solution hardening contribution, the strengthening contribution of the different alloying elements above 1000 °C directly correlates with their diffusivity. Therefore, elements such as Ta that lead to strong solid solution hardening at low temperatures become less effective at higher temperatures and are exceeded by slower diffusing elements, such as Re.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Creep; Diffusion; Nickel; Solid solution hardening

Specific features and mechanisms of fatigue in the ultrahigh-cycle regime - Mughrabi, Hael (International Journal of Fatigue, 2006)
Earlier concepts of ultrahigh-cycle fatigue (UHCF) of both ductile single-phase type I materials that do not contain inclusions and type II materials, e.g., high-strength steels containing non-metallic inclusions as (internal) crack initiation sites, are extended. In particular, the multi-stage fatigue life diagrams with a conventional high-cycle fatigue (HCF) limit and a possible lower fatigue limit in the UHCF range are discussed for both classes of materials in terms of the relevant fatigue cracking mechanisms. In this context, it is emphasized that it is important to consider in both cases details of fatigue crack initiation as a life-determining factor in the HCF and, even more so, in the UHCF regime. Different factors such as the density, size, location and distribution of non-metallic inclusions and details of specimen geometry and surface quality in the case of type II materials are discussed with respect to their influence on the transition stress separating the ranges of surface and internal fatigue cracking and with regard to fatigue lives. © 2006 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Ductile single-phase materials; Fatigue crack initiation; Fatigue life diagrams; Fatigue limit; High-strength steels; Inclusions; Surface versus subsurface failure

Stability and Physical Properties of the L1(2)-gamma ' Phase in the CoNiAlTi-System - Pyczak, F.; Liang, Z.; Neumeier, Steffen; Rao, Z. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
There is a current interest in Co-based superalloys hardened by a L1(2)-gamma ' phase because Co has a higher melting point than Ni and is more resistant against sulfidation attack. However, the Co-Al-W system many of those gamma ' hardened Co-based superalloys are based on, has a number of drawbacks. The gamma ' phase Co-3(Al,W) is not stable at high temperature, the density of the alloys is very high and the oxidation resistance is insufficient. Due to this, there is an ongoing interest to develop gamma '-hardened Co-based superalloys based on other systems. Here, first principles calculations are presented to investigate the properties of the gamma ' L1(2)-(Co-0.5,Ni-0.5)(3)(Al-0.5,Ti-0.5) phase and related L1(2) structures. (Co-0.5,Ni-0.5)(3)(Al-0.5,Ti-0.5) exhibits a lower energy of formation than Co3Ti and Co-3(Al-0.5,W-0.5). Nevertheless, Ni-3(Al-0.5,Ti-0.5) has an even lower energy of formation which is further lowered if Ti is enriched on the second sublattice. This finding is supported by analyzing the electronic densities of states. Ni-3(Al-0.5,Ti-0.5) and especially Ni-3(Al-0.25,Ti-0.75) exhibit Fermi levels close to the gap between binding and antibinding states, which is an indicator for stability. In addition to the stability of the gamma '-phase in dependence on Ni and Ti content, also the elastic properties were calculated. Ni-3(Al-0.25,Ti-0.75) is less elastic anisotropic and has higher Young's and shear modulus compared to Ni-3(Al-0.5,Ti-0.5) and (Co-0.5,Ni-0.5)(3)(Al-0.5,Ti-0.5).
CRIS-Team WoS Importer:2023-02-24

Stability of ultrafine-grained Cu to subgrain coarsening and recrystallization in annealing and deformation at elevated temperatures - Blum, Wolfgang; Li, Yujiao; Durst, Karsten (Acta Materialia, 2009)
WW1::827

Static and cyclic crack growth behavior of ultrafine-grained Al produced by different severe plastic deformation methods - Hübner, Peter; Kiessling, Rene; Biermann, Horst; Hinkel, Thomas; Jungnickel, Werner; Kawalla, Rudolf; Höppel, Heinz Werner; May, Johannes (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2007)
Fracture-mechanics experiments were carried out on ultrafine-grained (UFG) samples of aluminum and two Al alloys to obtain the fracture behavior under static and cyclic loading. The UFG materials investigated show crack resistance behavior under static loading, which was confirmed by ductile fracture surfaces. Under cyclic load, the crack growth rate was described well by the ESACRACK model. The crack propagation results show no influence of the type of the severe plastic deformation method in the Paris region but more effect in the threshold region. © The Minerals, Metals & Materials Society and ASM International 2007.
Created from Fastlane, Scopus look-up

Steel parts produced by material extrusion additive manufacturing, solvent debiding and sintering - Gonzalez-Gutierrez, Joamin; Thompson, Yvonne; Cano, Santiago; Felfer, Peter; Kukla, Christian; Holzer, Clemens (MS and T 2019 - Materials Science and Technology 2019, 2019)
CRIS-Team Scopus Importer:2019-12-03

Strain Rate-Dependent Anomalous Work Hardening of a Single-Crystalline CoNi-Base Superalloy - Vollhüter, Jan; Bezold, Andreas; Karpstein, N.; Köbrich, Manuel; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
The deformation mechanisms operating in superalloys depend on different parameters such as composition, temperature and deformation rate. So far, the transition from shearing by APB-coupled dislocations to shearing under the formation of stacking faults has been studied exclusively as a function of temperature but not as a function of the strain rate. Therefore, interrupted compression tests with strain rates between 10–3 s−1 and 10–5 s−1 were performed on the single-crystalline CoNi-base superalloy ERBOCo-4 at a temperature of 850 °C. The evolution of the defect structures has been analyzed by conventional transmission electron microscopy. A change of the deformation mechanism from APB-coupled dislocation shearing to stacking fault shearing is found to depend on the strain rate. At lower strain rates, an increased stacking fault density is associated with a higher yield strength and higher work hardening rates at the early stages of plastic deformation due to a very high stacking fault density. After approximately 2.0 pct plastic strain, the stress reaches a plateau and decreases subsequently, which is associated with the formation and thickening of twins as shown by high-resolution scanning transmission electron microscopy. At higher strain rates, the work hardening rate is significantly lower in the early deformation stage. The role of segregation to planar defects and the influence of local phase transformations (LPT) at SESFs is further discussed in reference to the influence of the strain rate. The segregation of W as an η stabilizing element is found to be crucial for the formation of a local phase transformation in ERBOCo-4. At higher strain rates the phase transformation is hindered by insufficient W segregation, resulting in a higher twin density.
CRIS-Team Scopus Importer:2023-02-24

Strain rate sensitivity of ultrafine grained aluminium alloy AA6061 - Vevecka-Priftaj, Aferdita; Böhner, Andreas; May, Johannes; Höppel, Heinz Werner; Göken, Mathias (4th International Conference on Nanomaterials by Severe Plastic Deformation, 2008)
The strain rate sensitivity of the aluminium alloy AA6061 has been investigated in a conventional grain sized (CG) state and in two different ultrafine grained (UFG) conditions processed by Equal Channel Angular Pressing (ECAP) for 2 and 6 passes at 100°C. Strain rate jump tests in compression were performed at different temperatures and the strain-rate sensitivity exponent m was determined. The tests were accomplished by microstructural investigations before and after compression testing in CG and UFG conditions. It is shown that all UFG microstructures exhibit strongly increased strain-rate sensitivity (SRS) compared to the CG state. The SRS increases with increasing temperature and is more pronounced for the UFG material processed using 6 ECAP passes. The microstructural investigations show a rather high stability of the grain structure for the UFG conditions up to 250°C. The results are discussed with respect to the relevant deformation mechanisms.
Created from Fastlane, Scopus look-up
Keywords: Equal channel angular pressing (ECAP); Severe plastic deformation; Strain rate sensitivity; Ultrafine-grained metals

Strain Rate Sensitivity of Ultrafine Grained FCC- and BCC-Type Metals - May, Johannes; Höppel, Heinz Werner; Göken, Mathias (Materials Science Forum, 2006)
The dependence of the strain rate sensitivity (SRS) of α-Fe and Al 99.5, as typical representatives of fcc- and bcc-type metals, on the testing temperature and with respect to the microstructure is investigated. In particular, the differences between conventional grain size (CG) and ultrafine grain size (UFG) are pointed out. UFG Al 99.5 generally shows an elevated SRS compared to CG Al 99.5. In case of α-Fe the SRS of the UFG state is decreased at room temperature, but increased at 200 °C, compared to the CG state. It is shown that the SRS also influences the ductility of UFG-metals in tensile tests.<br
Keywords: Ductilit; Equal-Channel Angular Pressing (ECAP); Severe Plastic Deformation (SPD); Strain Rate Sensitivity (SRS); Ultra Fine Grained Metal

Strain-rate sensitivity of ultrafine-grained materials - Höppel, Heinz Werner; May, Johannes; Eisenlohr, Philip; Göken, Mathias (International Journal of Materials Research, 2022)
The strain-rate sensitivity of commercial purity Aluminium (Al 99.5) and of alpha-iron, with both conventional (CG) and ultrafine (UFG) grain sizes, are investigated by compression and tension tests at different temperatures. Microstructural investigations were performed before and after compression testing in order to investigate the microstructural stability. Pronounced strain rate sensitivity was found for UFG Al at room temperature as well as at elevated temperatures, while for UFG alpha-iron an enhanced strain-rate sensitivity was found only at elevated temperatures.
CRIS-Team WoS Importer:2022-02-11

Strain-rate sensitivity (SRS) of nickel by instrumented indentation - Hay, Jennifer; Maier, Verena; Durst, Karsten; Göken, Mathias (2012 Annual Conference on Experimental and Applied Mechanics, 2013)

Strain rate sensitivity (SRS) of Nickel by Instrumented Indentation - Hay, Jennifer; Maier, Verena; Durst, Karsten; Göken, Mathias (Conference Proceedings of the Society for Experimental Mechanics Series 6, 2013)

Strength ranking for interfaces between a TiN hard coating and microstructural constituents of high speed steel determined by micromechanical testing - Gsellmann, Matthias; Klünsner, Thomas; Mitterer, Christian; Krobath, Martin; Wurmshuber, Michael; Leitner, Harald; Ecker, Werner; Marsoner, Stefan; Maier-Kiener, Verena; Kiener, Daniel; Ressel, Gerald (Materials & Design, 2021)
Keywords: FEM simulation; Interface strength; Carbides; Coating adhesion; Micropillar

Stresses to bow edge dislocation segments out of di-/multipolar edge dislocation bundles - Mughrabi, Hael; Pschenitzka, Friedrich (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2008)
WW1::784

Stress evolution and cracking of crystalline diamond thin films on ductile titanium substrate: Analysis by micro-Raman spectroscopy and analytical modelling - Rosiwal, Stefan; et al. (Acta Materialia, 2011)
In this study, the cracking of a brittle diamond coating on a titanium substrate under tensile straining was investigated by micro-Raman spectroscopy and analytical modelling. The in-situ micro-Raman investigations showed that the fracture strength of the coating is ∼1.5 GPa, and it contains an initial compressive residual stress of ∼-5.4 GPa which can be reduced by the application of uniaxial tensile strain. At higher strains, the compressive stress was transformed into the tensile regime and cracks appeared in the coating, followed by a reduction in crack spacing and finally delamination. The stress measurements across different cracked coating segments, using Raman spectroscopy, indicated tensile stresses at the middle and compression near the edges of the segment under tensile load. Coating fragmentation leads to a relaxation of the stress within the cracked coating segment. Further cracking of the smaller segments requires larger strains. Here, the classical shear lag model was extended to derive the stress distribution in the coating bonded to the substrate, considering both residual stress and cracking using a fracture criterion. The effect of substrate plasticity on the evolution of residual stress and on the cracking behaviour of the coating is also introduced. A good agreement is found between the modelling approach and the measured failure behaviour as well as the stress distributions in the fractured diamond segments. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Analytical methods; Fracture; Raman spectroscopy; Residual stresses; Thin films

Structural reorientation and compaction of porous MoS2 coatings during wear testing - Krauß, Sebastian; Seynstahl, Armin; Tremmel, Stephan; Meyer, Bernd; Bitzek, Erik; Göken, Mathias; Yokosawa, Tadahiro; Zubiri, Benjamin Apeleo; Spiecker, Erdmann; Merle, Benoit (Wear, 2022)
Industrial upscaling frequently results in a different coating microstructure than the laboratory prototypes presented in the literature. Here, we investigate the wear behavior of physical vapor deposited (PVD) MoS2 coatings: A dense, nanocrystalline MoS2 coating, and a porous, prismatic-textured MoS2 coating. Transmission electron microscopy (TEM) investigations before and after wear testing evidence a crystallographic reorientation towards a basal texture in both samples. A basal texture is usually desirable due to its low-friction properties. This favorable reorientation is associated to a tribological compaction of the porous specimens. Following running-in, sliding under high contact pressure ultimately leads to a wear rate as small as for an ideal grown bulk MoS2 single crystal grown by chemical vapor deposition (CVD). This suggests that the imperfections of industrial grade MoS2 coatings can be remediated by a suitable pretreatment.
CRIS-Team Scopus Importer:2022-05-13
Keywords: MoS; Nanoindentation; Transmission electron microscopy; Tribology; Wear testing

Structural stability of ultrafine-grained copper - Li, Yujiao; Blum, Wolfgang; et al. (Scripta Materialia, 2008)
WW1::785

Studies on the origin of dropwise condensation of steam on ion implanted metallic surfaces [Untersuchungen zur Ursache der Tropfenkondensation von Wasserdampf an ionenimplantierten Metalloberflächen] - Rausch, Michael Heinrich; Durst, Karsten; Göken, Mathias; Jakobs, Peter-Jürgen; Leipertz, Alfred; Fröba, Andreas Paul (Chemie Ingenieur Technik, 2011)
The origin of dropwise condensation of steam on ion implanted metallic surfaces was fundamentally studied. Condensation experiments and surface analyses showed that chemically inhomogeneous surfaces with topographic microstructures are likely to induce dropwise condensation. These surface characteristics are caused by particulate precipitates. Such particles are formed on ion implanted surfaces by the degradation of the material supersaturation with the doping elements. Similar surfaces showing dropwise condensation also emerged spontaneously on several unimplanted, high-alloyed materials due to oxidation and erosion effects induced by the condensation process. For explaining the observed condensation phenomena on the identified surface characteristics, a new model for the condensation mechanism was developed.
WW1::903
Keywords: Condensation; Ion implantation; Metals; Surface technology; Wettability

Studying plasticity in hard and soft Nb-Co intermetallics - Korte, Sandra; Clegg, William J. (Advanced Engineering Materials, 2012)
It is shown that micropillar compression can be used to study the plastic flow behavior of both a hard, brittle cubic Laves phase, NbCo 2, and a related monoclinic compound, Nb 2Co 7, which is known to be softer, but is also brittle and has, so far, only been prepared in a fine-grained form. Flow in the Laves phase occurs at a shear stress of 3.1 GPa on the 011 111 slip system, consistent with previous observations and estimates from hardness measurement. Micropillar compression and electron microscopy of single crystals of Nb 2Co 7 indicates that flow takes place parallel to the (001) plane, with 100 and 110 type Burgers vectors, at a critical resolved shear stress between 0.1 and 0.5 GPa. It is shown that this is much less than predicted by hardness measurements, consistent with the idea that the hardness of plastically anisotropic materials is determined by flow on the hardest operating slip system. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Created from Fastlane, Scopus look-up

Study of sensitization and different heating cycles on stainless steels used for automotive exhaust components - Yasir, M.; Mori, G.; Wieser, H.; Reller, A.; Höppel, Heinz Werner (Materials and Corrosion-Werkstoffe und Korrosion, 2012)
WW1::944

Study on the deformation mechanics of hard brittle coatings on ductile substrates using in-situ tensile testing and cohesive zone FEM modeling - Rehman, Hamad Ur; Ahmed, Furqan; Schmid, Christoph; Schaufler, Jens; Durst, Karsten (Surface & Coatings Technology, 2012)
In the present work, the mechanics of the stress transfer from a ductile substrate to a brittle coating and the failure of coating segments by normal cracking and delamination are studied using in-situ tensile testing and cohesive zone finite element modeling. The in-situ tensile tests were performed in a scanning electron microscope (SEM) on a diamond coated Ti-substrate and hydrogenated amorphous carbon (a-C:H) coatings on two different steel substrates, with different work hardening behavior. These brittle coatings form cracked coating segments during the in-situ tensile test. The stress transfer from the substrate to the coating segments is dependent on the elastic and elastic/plastic properties of coating and substrate. Furthermore, the segmentation of the coating together with the delamination depends strongly on the film and substrate properties. Using cohesive zone finite element modeling, the influence of substrate and coating properties on the stress transfer, segmentation of the films and on the delamination is discussed. It was found that the saturation in spacing of the cracked coating segments is either cause by a localization of the plastic strain in the substrate or by a delamination of the coating segments. Delamination only occurs, when the flow stress of the substrate is about √3 times larger than the interfacial shear strength.
WW1::945

Study on the indentation size effect in CaF2: Dislocation structure and hardness - Sadrabadi, Peiman; Durst, Karsten; Göken, Mathias (Acta Materialia, 2009)
Keywords: Nanoindentation; Dislocations

Study on the indentation size effect in CaF2: Dislocation structure and hardness - Sadrabadi, Peiman; Durst, Karsten; Göken, Mathias (Acta Materialia, 2009)
WW1::828

Study on the local damage mechanisms in WC-Co hard metals during scratch testing - Ndlovu, Siphilisiwe; Durst, Karsten; Höppel, Heinz Werner; Göken, Mathias (Materials Research Society Symposium - Proceedings, 2007)
The effect of the cobalt content and WC grain size on the deformation behaviour of WC-Co hard metals was investigated by studying materials with a varying WC grain size and cobalt content. The WC grain size ranged from 2.65 to 0.25 µm and the binder content ranged from 6 to 15 wt%. Single and multiple scratch tests were conducted using a Nano indenter with a Berkovich diamond tip and the load ranged from 5 to 500 mN with a tip sliding velocity of 10 µm/s. Several damage mechanisms were observed and these show a combination of ductile and brittle wear. The bulk properties i.e. composite properties of the hard metal determine the wear in the 6 wt% Co samples on the other hand the 15 wt% Co samples exhibited a localised response to the wear i.e. the wear is determined by the individual phases in the hard metal.<br

Superalloys and Their Applications Foreword - Cormier, Jonathan; Rae, Catherine; Neumeier, Steffen; Hardy, Mark; Reed, Roger (2018)

Superior creep strength of a nickel-based super alloy produced by selective laser melting - Pröbstle, Martin; Neumeier, Steffen; Hopfenmüller, Julia; Freund, Lisa; Niendorf, Thomas; Schwarze, D.; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2016)
WW1::1073
Keywords: High Temperature

Superior Mechanical Properties of Aluminum–Titanium Laminates in Terms of Local Hardness and Strength - Schunk, Christopher; Nitschky, Michael; Höppel, Heinz Werner; Göken, Mathias (Advanced Engineering Materials, 2018)
Keywords: ARB; high specific strength; AA2024; titanium grade 1; laminated metallic composites LMC

Superior Mechanical Properties of Aluminum-Titanium Laminates in Terms of Local Hardness and Strength - Schunk, Christopher; Nitschky, Michael; Höppel, Heinz Werner; Göken, Mathias (Advanced Engineering Materials, 2019)
Accumulative roll bonding (ARB) is a very useful method to produce ultrafine-grained (UFG) sheet material with extraordinary mechanical properties. Besides the production of UFG mono-materials, it is possible to create tailored multicomponent materials by stacking different materials. In this work, the aluminum alloy AA2024 and titanium grade1 are roll-bonded in order to achieve laminated metal composites (LMC) with an UFG microstructure. The mechanical properties and microstructural evolution during the ARB process of the LMC are analyzed and compared to that of LMCs. The mono-materials show an ultrafine grain structure after at least three ARB cycles which results in an increased yield and ultimate tensile strength. Most interestingly, the produced LMCs exhibit mechanical properties which are way better than the properties of the UFG mono-materials, when a linear rule of mixture is applied. The strength of the titanium-aluminum laminate is very close to the strength of the UFG titanium. Although, the density is significantly lower. The light-weight potential of the LMC is best expressed by the specific strength. Compared to the specific strength of UFG mono-material titanium of about 168 Nm g(-1) and UFG mono-material aluminum of about 195 Nm g(-1) the ARB laminate exhibits the highest specific strength of about 217 Nm g(-1) after three cycles.
Keywords: AA2024; ARB; high specific strength; laminated metallic composites LMC; titanium grade 1

Superplastic deformation behavior of Zn-22% Al alloy investigated by nanoindentation at elevated temperatures - Feldner, Patrick; Merle, Benoit; Göken, Mathias (Materials & Design, 2018)
Due to their high ductility, superplastic metallic alloys are promising candidates for microforming processes. However, it is not yet clear if the macroscopically observed superplastic material behavior also persists at micrometric length scales. For this reason, the superplastic deformation behavior of the eutectoid alloy Zn-22% Al was investigated at the microscale as a function of temperature, strain-rate and grain-size. Nanoindentation strain-rate jump tests at room temperature and elevated temperatures were correlated with the deformed microstructure. A sigmoidal relationship between the hardness and the strain-rate is evidenced, which is typical for superplastic alloys at the macroscale. In the central part of the sigmoidal curve strong indications for superplastic flow at the microscale are found. Microstructural investigations of the residual indents reveal noticeable intercrystalline deformation processes in combination with some intracrystalline dislocation activity regardless of the applied testing conditions. These experimental findings were further coupled with finite element analysis to determine the size of the plastic zone beneath the indents as a function of the penetration depth. Based on this, a critical cubic material volume of 8 grains over the edge length is found to be sufficient for superplastic flow at local length scales. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Nanoindentation; Superplasticity; Deformation mechanism; Microforming

Surface modification of an alumina-based bioceramic for cement application - Pedimonte, J.; Travitzky, Nahum; Korn, Matthias; Kriegelstein, S.; Greil, Peter (Advanced Engineering Materials, 2011)
Biograde zirconia toughened alumina (ZTA) has found wide application in load bearing endoprosthetic implants due to high strength, fracture toughness, and wear resistance. In order to enhance bonding to acrylic bone cement (BC) for implants, fixation modification of ZTA with a thin layer of porous anodic alumina (PAA) was investigated. An Al-layer of approximately 500 nm was sputtered on the ZTA substrate which subsequently was electrochemically oxidized by anodic polarization in H C O or H PO solution. PAA layers with a total porosity ranging from 11 to 30%, mean pore spacing of 90-200 nm and pore diameters of 30-110 nm were prepared. Compared to unmodified ZTA/BC interface (≈ 30 MPa), the PAA modified specimens (ZTA/PAA/BC) achieved a significantly higher interface bonding strength (≈ 60 MPa) measured by four point bending on composite beam specimens. While crack propagation in the unmodified ZTA/BC specimen was found to proceed along the interface, fracture analysis on the ZTA/PAA/BC specimens showed a mixed mode fracture with part of the fracture propagation localized along the PAA/BC interface and part through BC. Thus, pore structure controlled mechanical interlocking is expected to offer a high potential for applying PAA surface modification to improve biomaterial to BC bonding. Bonding of ZrO toughened Al O (ZTA) to acrylic bone cement (BC) was improved by a PAA film, formed in H C O or H PO by electrochemical anodization of a sputtered Al-layer on the ZTA substrate. Compared to unmodified interface (≈ 30 MPa), the PAA modified specimens achieved a significantly higher interface bonding strength (≈ 60 MPa), due to mixed mode fracture with part of the crack propagation along the PAA/BC interface and part through BC. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Surface strain evolution of ultrafine-grained aluminum alloy laminates under tension-Microscale plastic instabilities and the Portevin-Le Chatelier effect - Kurtovic, A.; Niendorf, Thomas; Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias; Maier, H. J. (Scripta Materialia, 2013)
The surface strain evolution in accumulative roll bonded aluminum alloys was studied in situ using digital image correlation. Laminated multicomponent materials, consisting of two ultrafine-grained aluminum alloys with different layer architectures (laminate and sandwich), were analyzed and compared to the pure alloys after the same number of accumulative roll bonding cycles. The results obtained show differences in the surface strain evolution of the accumulative roll bonded and differently stacked materials, which is attributed to microscale plastic instabilities.
WW1::980

Surface strain evolution of ultrafme-grained aluminum alloy laminates under tension - Microscale plastic instabilities and the Portevin-Le Chatelier effect - Kurtovic, A.; Niendorf, Thomas; Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias; Maier, H. J. (Scripta Materialia, 2013)
The surface strain evolution in accumulative roll bonded aluminum alloys was studied in situ using digital image correlation. Laminated multicomponent materials, consisting of two ultrafine-grained aluminum alloys with different layer architectures (laminate and sandwich), were analyzed and compared to the pure alloys after the same number of accumulative roll bonding cycles. The results obtained show differences in the surface strain evolution of the accumulative roll bonded and differently stacked materials, which is attributed to microscale plastic instabilities. (c) 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Accumulative roll bonding; Ultrafine-grained material; Multicomponent material; Digital image correlation; In situ characterization

Symposium on ultrafine-grained materials: From basics to applications - Maier, Hans Jürgen; Biallas, G.; Eggeler, Gunther; Estrin, J.; Hellmig, R. J.; Göken, Mathias; Höppel, Heinz Werner; Gottstein, G.; Winning, M. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2007)
Created from Fastlane, Scopus look-up

Synthesis, crystal structure, and properties of stoichiometric hard tungsten tetraboride, WB4 - Bykova, Elena; Ovsyannikov, Sergey; Bykov, Maxim; Yin, Yuqing; Fedotenko, Timofey; Holz, Hendrik; Gabel, Stefan; Merle, Benoit; Chariton, Stella; Prakapenka, Vitali B.; Dubrovinskaia, Natalia; Goncharov, Alexander F.; et al. (Journal of Materials Chemistry A, 2022)
Tungsten tetraboride has been known so far as a non-stoichiometric compound with a variable composition (e.g. WB4-x, WB4+x). Its mechanical properties could exceed those of hard tungsten carbide, which is widely used nowadays in science and technology. The existence of stoichiometric WB4 has not been proven yet, and its structure and crystal chemistry remain debatable to date. Here we report the synthesis of single crystals of the stoichiometric WB4 phase under high-pressure high-temperature conditions. The crystal structure of WB4 was determined using synchrotron single-crystal X-ray diffraction. In situ high-pressure compressibility measurements show that the bulk modulus of WB4 is 238.6(2) GPa for B ' = 5.6(0). Measurements of mechanical properties of bulk polycrystalline sub-millimeter size samples under ambient conditions reveal a hardness of similar to 36 GPa, confirming that the material falls in the category of superhard materials.
CRIS-Team WoS Importer:2022-09-09

Tailored heat treated accumulative roll bonded aluminum blanks: failure under bending stresses - Nguyen, H.; Boehm, W.; Tsoupis, Ioannis; Göken, Mathias; Höppel, Heinz Werner; Schmidt, Christian; Hausöl, Tina; Ruppert, Mathis; Merklein, Marion (Production Engineering, 2016)
Ultrafine-grained accumulative roll bonded (ARB) sheet metals of aluminum alloys have a high potential for lightweight construction. The mechanical properties can be enhanced regarding strength and ductility by the combination of ARB and a local heat treatment according to the Tailor Heat Treated Blanks technology. The present investigation focuses on the failure behavior of ultrafine-grained ARB blanks. Due to the low formability of these high-strength ARB metals, a detailed understanding of the failure mechanisms is essential. For this purpose, an established approach to determine the different stages of damage of the material for conventional materials is now applied to multilayered aluminum in the as-received and heat-treated condition. In this context, air bending tests are used to qualify and quantify the bending and forming behavior of ARB sheets of AA1050A and AA6016 aluminum alloys.
Keywords: Tailor Heat Treated Blanks (THTB); Ultrafine-grained microstructure (UFG); Failure; Formability; Bending; Accumulative roll bonding (ARB)

Tailored heat treated accumulative roll bonded aluminum blanks: Microstructure and mechanical behavior - Maier, Verena; Hausöl, Tina; Schmidt, Christian; Böhm, Wolfgang; Hung Nguyen,; Merklein, Marion; Höppel, Heinz Werner; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2012)
Aluminum alloy AA6016 was accumulative roll bonded up to eight cycles and investigated regarding formability by bending tests. Due to the limited bendability of accumulative roll bonding (ARB) processed materials, a tailored laser heat treatment was performed along the bending edge before forming. This tailored laser heat treatment causes a local recrystallization and recovery of the bending samples at the deformation zone, which locally increases ductility and allows higher bending angles achievable with lower forming forces. Between the recrystallized heat treated zone and the unaffected ultrafine-grained (UFG) base material, a gradient in grain size with a bimodal region is formed. This observed microstructural profile is confirmed by local mechanical testing measuring the hardness and strain rate sensitivity by nanoindentation techniques.
WW1::947

Tailored Mechanical Properties and Residual Stresses of a-C:H:W Coatings - Schmid, Christoph; Hetzner, Harald; Tremmel, Stephan; Hilpert, Florian; Durst, Karsten (Advanced Materials Research, 2014)
In this study, three different a-C:H:W coatings with predefined hardness values, ranging from 10 up to 16 GPa, were deposited by selecting suitable parameter set points and adjusting substrate bias voltage of the reactive unbalanced magnetron sputtering process according to a previously created regression model. To obtain this model, the four main process parameters had been varied according to a central composite design and their influence on the mechanical properties of the a-C:H:W coating had been investigated previously by nanoindentation. The three coating variants of this study were investigated in terms of microstructure, mechanical properties and residual stresses. It turned out, that by the use of the regression model, indeed a-C:H:W coatings of tailored mechanical properties can be deposited. Residual stresses were measured by means of focused ion beam milling of a double-slit geometry, which causes the internal stresses to relax, and mapping of the resultant relief strain by digital image correlation. A nearly linear relation between the applied bias voltage and the hardness, the modulus of elasticity of the coating as well as the determined relief strain was observed. Thus, residual stresses of the coatings increase disproportionately with applied bias voltage. The obtained results can be helpful for tailored coating design and further optimization of a-C:H:W coating
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KLMEFK.tailor
Keywords: a-C:H:W; Deposition parameters; Digital image correlation; Focused ion beam; Residual stress; Tailored properties

Tailoring deformation mechanisms in polycrystalline CoNi-base superalloys for enhanced high temperature strength - Bezold, Andreas; Neumeier, Steffen (Scripta Materialia, 2023)
The significance of segregation processes during high temperature deformation in superalloys has become increasingly evident in recent years. Here, the importance of additionally tailoring the active deformation mechanisms is shown by correlating the strain-rate dependent high temperature strength of two slightly different polycrystalline CoNi-base superalloys with their underlying defect structures. Transmission electron microscopy investigations revealed that at high strain-rates shearing by APB-coupled dislocation pairs occurs in both alloys. With decreasing strain-rate, the deformation mechanism in one alloy transitions to stacking fault shearing and at very low strain-rates also to microtwinning, while APB-based shearing remains dominant in the other alloy. In comparison, stacking fault shearing induced a relative increase in strength of 200 MPa, which is diminished to 100 MPa as microtwinning becomes more prevalent implying that the high temperature strength of this alloy system can be significantly increased by tailoring the acting deformation mechanism.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Complex concentrated alloy; Creep; Deformation mechanisms; Stacking fault; Superalloy; Transmission electron microscopy

Tailoring materials properties by accumulative roll bonding - Hausöl, Tina; Maier, Verena; Schmidt, Christian; Winkler, Michael; Höppel, Heinz Werner; Göken, Mathias (Advanced Engineering Materials, 2010)
Accumulative roll bonding (ARB) as a method of severe plastic deformation (SPD) is an interesting established process to produce ultrafine-grained (UFG) sheet materials with high potential for light weight constructions. The ARB process offers a high flexibility for tailored material design. Al_2O_3 particles, carbon fibers and titanium foils are used as reinforcement of aluminum sheets introduced during accumulative roll bonding. Furthermore multicomponent materials are produced by cladding of different aluminum alloys. These sandwich-like structures allow to combine desired properties of the materials involved. Post-ARB heat treatment offers another possibility for tailoring materials properties of graded structures as shown by formation of TiAl_3 in Al/Ti laminates. The tailored materials are investigated by means of SEM, EDX, nanoindentation experiments and tensile testing.
WW1::856

Tailoring materials properties of UFG aluminium alloys by accumulative roll bonded sandwich-like sheets - Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias (Journal of Materials Science, 2010)
Accumulative roll bonding (ARB) as a method of severe plastic deformation is a well-established process to produce ultrafine-grained (UFG) sheet materials with extraordinary mechanical properties. In this work ARB is applied to combine different sheet materials in order to tailor the materials properties by producing sandwich-like structures. The high strength aluminium alloy AA5754, after 4 ARB cycles (N4), is used as a core material. To achieve high corrosion resistance and good visual properties, it is cladded with commercially pure aluminium AA1050A (N4) at room temperature and alternatively with AA6014 (N4) at 230 °C. All materials are UFG and satisfactory bonding between the different layers of aluminium alloys is achieved. Nanoindentation measurements reveal that there is a sharp transition in hardness at the interface. The yield and tensile strength of the core material are fully retained in the case of the AA6014/AA5754 sandwich. The strength of the AA1050A/AA5754 sandwich is slightly lower compared to the core material but still twice as high as the clad material. The serrated yielding effect which is strongly visible in tensile tests on the pure AA5754 alloy completely disappears in the sandwich sheets, which means the surface quality is strongly enhanced.
WW1::857

Tailoring nanostructured, graded, and particle-reinforced Al laminates by accumulative roll bonding - Göken, Mathias; Höppel, Heinz Werner (Advanced Materials, 2011)
Accumulative roll bonding (ARB) is a very attractive process for processing large sheets to achieve ultrafine-grained microstructure and high strength. Commercial purity Al and many Al alloys from the 5xxx and the precipitation strengthened 6xxx alloy series have been successfully processed by the ARB process into an ultrafine-grained state and superior ductility have been achieved for some materials like technical purity Al. It has also been shown that the ARB process can be successfully used to produce multi-component materials with tailored properties by reinforcement or grading, respectively. This allows optimizing the properties based on two or more materials/alloys. For example, to achieve high corrosion resistance and good visual surface properties it is interesting to produce a composite of two different Al alloys, where for example a high strength alloy of the 5xxx series is used as the core material and a 6xxx series alloy as the clad material. It has been shown that such a composite achieves more or less the same strength as the core material although 50% of the composite consists of the significant softer clad alloy. Furthermore, it has been found, that the serrated yielding which typically appears in 5xxx series alloys and limits applications as outer skin materials completely disappears. Moreover, the ARB process allows many other attractive ways to design new composites and graded material structures with unique properties by the introduction of particles, fibres and sheets. Strengthening with nanoparticles for example is a very attractive way to improve the properties and accelerate the grain refining used in the severe plastic deformation process. With an addition of only 0.1 vol.-% Al_2O_3 nanoparticles a significantly accelerated grain refinement has been found which reduces the number of ARB passes necessary to achieve the maximum in strength. The paper provides a short review on recent developments in the field of ARB processing for producing multicomponent ultrafine-grained sheet materials with tailored properties.
WW1::905

Tailoring ultra-strong nanocrystalline tungsten nanofoams by reverse phase dissolution - Zhao, Mingyue; Issa, Inas; Pfeifenberger, Manuel; Wurmshuber, Michael; Kiener, Daniel (Acta Materialia, 2020)
Keywords: Nanoporous tungsten; Selective phase dissolution; Microstructure characterization; Nanoindentation; kernfusionsrelevant

Temperature dependence of element partitioning in rhenium and ruthenium bearing nickel-base superalloys - Pyczak, Florian; Neumeier, Steffen; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2010)
WW1::858

Temperature-Dependent Dynamic Strain Aging in Selective Laser Melted 316L - Diepold, Benedikt; Neumeier, Steffen; Meermeier, Annalena; Höppel, Heinz Werner; Sebald, Torsten; Göken, Mathias (Advanced Engineering Materials, 2021)
Additively manufactured austenitic stainless steel AISI 316L (EN 1.4404, X2CrNiMo17-12-2) is used at higher temperatures, e.g., in space applications. However, the high-temperature properties of such materials have not been analyzed in detail yet. Thus, selective laser melted (SLM) 316L is tested in the solution-annealed condition by compression and tensile tests at temperatures between 25 and 877 °C. The compressive strength of SLM 316L is higher in comparison with the conventionally produced reference material due to hardening by a high dislocation density and a fine substructure. However, tensile tests reveal a loss in ductility of the SLM material at temperatures between 300 and 627 °C, where the elongation to fracture is reduced from 65% to 39%. Alloying elements cause serrated yielding in the affected temperature range. Together with an increased normalized work-hardening rate and a negative strain rate sensitivity, dynamic strain aging is found to cause the reduction of ductility.
CRIS-Team Scopus Importer:2021-07-02
Keywords: dynamic strain aging; laser beam melting; microstructures; Portevin–Le Chatelier effect; serrations; strain rate sensitivity; strengths

Tensile and creep strength of thermally exposed allvac 718Plus - Neumeier, Steffen; Pröbstle, Martin; Huenert, Daniela; Göken, Mathias (Proceedings of 8th International Symposium on Superalloy 718 and Derivatives 2014, 2014)
Keywords: Tensile strength; Creep strength; Thermal stability

Tension/Compression asymmetry of a creep deformed single crystal Co-base superalloy - Lenz, Malte; Eggeler, Yolita; Müller, Julian; Zenk, Christopher; Volz, Nicklas; Wollgramm, Philip; Eggeler, Gunther; Neumeier, Steffen; Göken, Mathias; Spiecker, Erdmann (Acta Materialia, 2019)
The creep behavior of a multinary single crystal Co-base superalloy has been compared for uniaxial tension and compression of 400 MPa applied along [001] at 850 °C. Creep under tensile stress proceeds two times faster than creep under compression. A detailed TEM study shows that already after ∼ 0.3 % creep strain planar faults are formed in both samples. While extended a/2<112> ribbons with SISF loops embedded in ABPs are observed in tension, extrinsic SFs are revealed in compression. At ∼ 5 % creep strain SISFs confined to the γ' phase dominate in tension, whereas extrinsic SFs and microtwins extending across both phases are the prevalent planar faults in compression. In addition, dense networks of regular a/2<101> matrix dislocations develop at the γ/γ' interfaces in both loading scenarios. In tensile creep and early compressive creep the direct contribution of planar faults to plastic deformation is minor and does not exceed 10 % of the measured plastic strain. In contrast, thickening of microtwins appears to become an efficient deformation channel in the later stages of compressive creep. A pronounced asymmetry regarding the rafting kinetics is observed as well resulting in a P-type rafted and topologically inverted microstructure after ∼ 5 % creep in tension while hardly any rafting has occurred under compression. The pronounced rafting and related recovery processes are likely responsible for the inferior creep behavior in tension. Finally, two novel diffusion-assisted degradation mechanisms related to microtwins are shown to be active: an expansion of the γ phase into γ' precipitates along microtwins and the formation of γ phase nuclei at planar fault intersections inside γ'. Both phenomena are hypothesized to be triggered by segregation of γ-formers like Co and Cr to twin boundarie
Keywords: Cobalt-base superalloy; creep; asymmetry; electron microscopy; planar faults

Texture and mechanical anisotropy of ultrafine-grained aluminum alloy AA6016 produced by accumulative roll bonding - Skrotzki, Werner; Hünsche, Ingwar; Hüttenrauch, Juliane; Oertel, C. G.; Brokmeier, H. G.; Höppel, Heinz Werner; Topic, Irena (Texture, Stress, and Microstructure, 2008)
WW1::787

Texture, microstructure and mechanical properties of ultrafine grained aluminum produced by accumulative roll bonding - Scharnweber, Juliane; Skrotzki, Werner; Oertel, Carl-Georg; Brokmeier, Heinz-Guenter; Höppel, Heinz Werner; Topic, Irena; Jaschinski, Joern (Advanced Engineering Materials, 2010)
Texture, microstructure, and tensile behavior of technically pure aluminum AA1050 and of the age-hardening alloy AA6016 produced by accumulative roll bonding (ARB) were studied for different numbers of ARB cycles. After eight cycles an ultrafine grained microstructure with grain sizes of the order of 0.5 µm is reached. The grain size decreases with increasing alloying content. The texture consists of a major copper component and a minor brass component. The latter strengthens with alloying. Due to shear deformation in the surface region also a rotated cube component is found. It is stronger in the pure material and is partly added up in the bulk during ARB. Due to dislocation and grain boundary hardening the tensile strength increases with increasing ARB cycles following the Hall-Petch behavior while a moderate ductility is kept. Within the sheet plane no significant influence of the tensile direction on the observed mechanical properties was found.
WW1::859

The correlation between the internal material length scale and the microstructure in nanoindentation experiments and simulations using the conventional mechanism-based strain gradient plasticity theory - Backes, Björn; Huang, Y. Y.; Göken, Mathias; Durst, Karsten (Journal of Materials Research, 2009)
WW1::830

The Department of Materials Science and Engineering at the Friedrich-Alexander-University of Erlangen-Nürnberg - Travitzky, Nahum; Boccaccini, Aldo R.; Göken, Mathias (Advanced Engineering Materials, 2020)
CRIS-Team Scopus Importer:2022-08-05

The Effect of a Grain Boundary Pinning B2 Phase on Polycrystalline Co-Based Superalloys with Reduced Density - Freund, Lisa; Stark, Andreas; Kirchmayer, Andreas; Schell, Norbert; Pyczak, Florian; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2018)
The Al/W ratio was increased in a new polycrystalline gamma/gamma' Co-based superalloy in order to introduce a grain boundary pinning phase while at the same time reducing the density and increasing the oxidation resistance. The grain boundary pinning phase was identified as beta-phase (B2-(Ni,Co)Al) by high-energy X-ray diffraction. The grain boundary pinning effect was confirmed to be effective up to temperatures of 1050 degrees C by synchrotron radiation in-situ heating experiments. The precipitation of the beta phase led to a reduced gamma' volume fraction thereby decreasing the high-temperature strength. The density was lowered to 8.52 g/cm(3), so the specific strength was equivalent to the strength of the reference alloy up to 750 degrees C. Due to the low gamma' volume fraction and the low W content, the creep resistance was also reduced compared with the reference alloy. The oxidation resistance, however, was improved by the formation of a thin, continuous Al-oxide layer during oxidation at 900 degrees C for 50 hours.

The Effect of Alloying on the Thermophysical and Mechanical Properties of Co–Ti–Cr-Based Superalloys - Zenk, Christopher; Volz, Nicklas; Bezold, Andreas; Huber, Laura-Kristin; Eggeler, Yolita; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Springer International Publishing, 2020)
The system Co–Ti–Cr was recently identified as a very promising base for low mass-density Co-based superalloys. This study presents the influence of quaternary alloying additions on the thermophysical and mechanical properties of a Co–11Ti–15Cr model superalloyModel superalloy. Al, Ta, Re, and W were selected as a starting point for alloy developmentAlloy development as they represent important alloying elements in both Ni-based and Co–Al–W-based superalloys. Microstructure analysis reveals that the addition of only 1 at.% of either of these elements causes the formation of different undesired intermetallic phases in addition to γ and γ′ phases, which is in agreement with thermodynamic calculations. However, a diffusion couple between the Co–Ti–Cr and a Co–Al–W–Ta alloy suggests that the tolerance for alloying elements without destabilizing the γ/γ′ two-phase microstructure is higher when they are present in a certain ratio. Energy-dispersive X-ray spectroscopy shows that Cr and Re are enriched in the γ phase, whereas Ti and W preferentially partition to γ′. All alloying elements increase the yield strength at room temperature, but are disadvantageous at 1000 °C. Re and W retain their strengthening effect up to 900 °C.

The effect of grain size on bubble formation and evolution in helium-irradiated Cu-Fe-Ag - Wurmshuber, Michael; Frazer, David; Balooch, Mehdi; Issa, Inas; Bachmaier, Andrea; Hosemann, Peter; Kiener, Daniel (Materials Characterization, 2021)
Keywords: Nanoindentation; Nanostructured materials; Helium bubbles; Helium implantation; Swelling; kernfusionsrelevant

The effect of hydrogen on the early stages of oxidation of a magnesium alloy - McCarroll, I. E.; Haley, D.; Thomas, S.; Meier, Michael; Bagot, P. A.J.; Moody, M. P.; Birbilis, N.; Cairney, J. M. (Corrosion Science, 2019)
The early stage oxidation of germanium-doped magnesium alloys was investigated via atom probe tomography. A catalytic reaction cell attached to a local electrode atom probe allowed controlled exposure of electropolished specimens to oxygen gas. Prior to exposure, some samples were found to be enriched in hydrogen, thought to be introduced during electropolishing. These samples reacted strongly to form sub-surface phases rich in H and O, while samples with less hydrogen did not. These results suggest that hydrogen in the sample plays an important role as a catalyst to oxidation and may affect the hydrogen evolution rate in Mg alloys.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Atom probe tomography; Corrosion; Hydrogen; Magnesium; Oxidation

The effect of pre-existing defects on the strength and deformation behavior of α-Fe nanopillars - Xie, Kelvin Y.; Shrestha, Sachin; Cao, Yang; Felfer, Peter; Wang, Yanbo; Liao, Xiaozhou; Cairney, Julie M.; Ringer, Simon P. (Acta Materialia, 2013)
The effects of two types of pre-existing defects, dislocations and clusters, on the strength and deformation behavior of body-centered cubic Fe nanopillars with a diameter of ∼150 nm were investigated using in situ nanocompression in a transmission electron microscope. The plastic deformation of nanopillars containing high initial dislocation densities was observed to be relatively continuous, proceeding via a series of small- and intermediate-scale strain bursts that were associated with the movement/escape of dislocations and the formation of slip bands. Mechanical annealing was observed in nanopillars with high dislocation densities. When the dislocation density was reduced by in situ heating, the nanopillars were much stronger and the plastic deformation behavior transformed to a more abrupt and explosive mode. The introduction of a dispersion of solute atom clusters into nanopillars caused further strengthening as a higher stress level is required for dislocations to pass the clusters. The strengthening effect of cluster dispersion in nanopillars is comparable to that observed in the bulk steel. These phenomena are universal for Fe nanopillars with different crystallographic orientations. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Atom probe microscopy; Clustering; Dislocation burst; In situ nanocompression; Transmission electron microscopy

The effect of Re and Ru on γ/γ′ microstructure, γ-solid solution strengthening and creep strength in nickel-base superalloys - Heckl, Astrid; Neumeier, Steffen; Göken, Mathias; Singer, Robert (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2011)
A new in-house designed series of Ni based superalloys with stepwise increased Re and Ru additions has been investigated, to systematically determine the influence of Re and Ru on γ/γ′-microstructure and high temperature creep properties. Improved creep resistance and thus also a higher alloy temperature capability of up to 87. K/at.% was found for additions of Re. Additions of Ru revealed a lower temperature capability improvement of up to 38. K/at.% for low Re-containing second generation alloys. However, in third and fourth generation alloys with higher Re-contents, no significant influence of Ru on creep rupture strength was observed. The creep properties are discussed with respect to the γ′-volume fraction, γ′-size and γ′-coarsening rate, as well as the γ/γ′-lattice misfit and the γ/γ′ partitioning coefficient of the different Re and Ru containing alloys. The presented data shows, that these microstructure parameters are strongly influenced by additions of Re, but only marginally by additions of Ru. A further influence on creep rupture strength is given by the solid solution hardening of the γ-matrix, which is discussed based on solid solution hardener concentrations either experimentally derived or calculated from ThermoCalc data. © 2011 Elsevier B.
Keywords: γ′-Coarsening rate; γ′-Size; γ′-Volume fraction; γ/γ′-Distribution coefficient; Creep resistance; Solid solution strengthening

The effect of tungsten content on the properties of L12-hardened Co-Al-W alloys - Pyczak, Florian; Bauer, Alexander; Göken, Mathias; Lorenz, Uwe; Neumeier, Steffen; Oehring, Michael; Paul, Jonathan; Schell, Norbert; Schreyer, Andreas; Stark, Andreas; Symanzik, Felix (Journal of Alloys and Compounds, 2015)
Ternary Co-Al-W alloys with W contents between 8 and 11 at.% were investigated with respect to element partitioning, γ' solvus, γ' volume fraction, lattice mismatch and creep properties. W is enriched in the γ' precipitates and an increasing W content stabilizes this phase. The lattice mismatch is positive up to 900 °C and rafting occurs during creep with a preferred direction in accordance with this positive lattice mismatc
Keywords: Metals and alloys; Precipitation; Thermodynamic properties; Transmission electron microscopy TEM; X-ray diffraction

The evolution of homogeneity on longitudinal sections during processing by ECAP - Prell, Michaela; Xu, Cheng; Langdon, Terence G. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2008)
An Al-6061 alloy was processed by equal-channel angular pressing at room temperature for one, two, four and six passes and microhardness measurements were recorded along linear traverses on longitudinal planes in the centers of each billet. The results show the average microhardness increases significantly in the first pass although there is a region of lower hardness running in a band near the bottom surface of the billet. Additional but smaller increases in hardness occur in subsequent passes. The hardness values are distributed homogeneously throughout the longitudinal plane after ECAP through six passes although there remains a very narrow region of lower hardness within a distance of ∼0.5 mm adjacent to the bottom surface. When combined with earlier microhardness measurements taken on the Al-6061 alloy on the cross-sectional plane, the results confirm the potential for achieving excellent homogeneity after pressing through a total of six passes. © 2007 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Aluminum alloy; Equal-channel angular pressing; Hardness; Homogeneity; Severe plastic deformation

The grain boundary hardness in austenitic stainless steels studied by nanoindentations - Göken, Mathias; Schweitzer, Elmar (Zeitschrift für Metallkunde, 2004)
The strength of structural materials depends strongly on the structure and properties of grain boundaries. Grain boundaries in crystalline solids are internal surfaces and therefore likely sites for nucleation of precipitates and segregation effects. Nanoindentations are a suitable method to study the influence of grain boundaries on the mechanical properties. The necessary lateral resolution is achieved by combining with an atomic force microscope. Measurements on an austenitic steel after annealing at 650 °C, where the boundary is saturated with carbide precipitates, clearly show a decreasing hardness close to the interface in opposite to the general expected behaviour of strengthening. In this case segregation effects strongly influences the mechanical properties around the boundaries. These results are discussed in comparison with nanoindentation measurements on strongly ordered intermetallics like NiAl where no significant property change at the boundaries was found and with Vickers hardness measurements by Westbrook et al., where a higher grain boundary hardness was found in many metallic and intermetallic materials depending on their composition.
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.thegra
Keywords: Atomic force microscopy; Chromium carbides; Grain boundaries; Hardness; Nanoindentation; Stainless steel

The grain boundary pinning effect of the mu phase in an advanced polycrystalline γ/γ′ Co-base superalloy - Freund, Lisa; Stark, Andreas; Pyczak, Florian; Schell, Norbert; Göken, Mathias; Neumeier, Steffen (Journal of Alloys and Compounds, 2018)
A grain boundary pinning phase was introduced into a gamma/gamma' Co-base superalloy by the addition of Mo. The intermetallic phase was identified as mu phase (Co,Ni,Cr)(7)(W,Mo)6 by high-energy X-ray diffraction and energy-dispersive X-ray spectroscopy in the transmission electron microscope. Synchrotron radiation insitu heating experiments confirmed the stability of the grain structure up to 1050 degrees C and therefore the grain boundary pinning effect of this phase. Recrystallization heat treatments at different temperatures resulted in varying amounts of mu phase. The grain size analysis revealed that at least 1% of the phase is necessary to maintain a pinning effect during recrystallization. Atom probe tomography confirmed that Mo partitioned predominantly to the gamma phase. Since the mu phase and the gamma' phase are competing for W, a lower gamma volume fraction was formed in comparison to a Mo-free polycrystalline gamma/gamma' Co-base superalloy variant. However, the homogeneous distribution of small grains resulted in a higher strength compared to the Mo-free alloy without grain boundary pinning phases. The creep resistance at 750 degrees C was similar to the Mo-free alloy as well as the polycrystalline Ni-base superalloy U720Li with a creep rate minimum of 1.5 x 10(-7) s(-1) at 620 MPa. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Co-base superalloys; Grain boundary pinning; Coarsening; Disc alloys; Synchrotron radiation; High-energy x-ray diffraction

The grain boundary pinning effect of the μ phase in an advanced polycrystalline γ/γ′ Co-base superalloy - Freund, Lisa; Stark, Andreas; Pyczak, Florian; Schell, Norbert; Göken, Mathias; Neumeier, Steffen (Journal of Alloys and Compounds, 2018)
Keywords: Co-base superalloys; Grain boundary pinning; High-energy x-ray diffraction; Coarsening; Disc alloys; Synchrotron radiation

The Hidden Pathways in Dense Energy Materials - Oxygen at Defects in Nanocrystalline Metals - Scherrer, Barbara; Doebeli, Max; Felfer, Peter; Spolenak, Ralph; Cairney, Julie; Galinski, Henning (Advanced Materials, 2015)
Highly abundant oxygen-rich line defects (blue) can act as fast oxygen transport paths. These defects show similar chemistry and therefore similar catalytic activity to the materials surface. These results provide the opportunity to design and produce simple scalable structures as catalysts, whose functionality derives from internal defects rather than from the materials surface
Keywords: multilayers; atom probes; catalysts; nanocrystalline metals; thin films

The Importance of Diffusivity and Partitioning Behavior of Solid Solution Strengthening Elements for the High Temperature Creep Strength of Ni-Base Superalloys - Giese, Sven; Bezold, Alexander; Pröbstle, Martin; Heckl, A.; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2020)
The creep resistance of single-crystalline Ni-base superalloys at elevated temperatures depends among others on solid solution strengthening of the γ-matrix. To study the influence of various solid solution strengtheners on the mechanical properties, a series of Ni-base superalloys with the same content of different alloying elements (Ir, Mo, Re, Rh, Ru, W) or element combinations (MoW, ReMo, ReW) was investigated. Nanoindentation measurements were performed to correlate the partitioning behavior of the solid solution strengtheners with the hardness of the individual phases. The lowest γ′/γ-hardness ratio was observed for the Re-containing alloy with the strongest partitioning of Re to the γ-matrix. As a result of the creep experiments in the high-temperature/low-stress regime (1373 K (1100 °C)/140 MPa), it can be concluded that solid solution hardening in the γ-phase plays an essential role. The stronger the partitioning to the γ-phase and the lower the interdiffusion coefficient of the alloying element, the better the creep resistance. Therefore, the best creep behavior is found for alloys containing high contents of slow-diffusing elements that partition preferably to the γ-phase, particularly Re followed by W and Mo.
CRIS-Team Scopus Importer:2020-10-16

The influence of crack and interface oxidation on dwell fatigue crack propagation behavior of the nickel-base superalloy ATI A718Plus - Kirchmayer, Andreas; Hausmann, Andreas; Gabel, Stefan; Pröbstle, Martin; Giese, Sven; Göken, Mathias; Hünert, Daniela; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
The crack propagation properties are an important and often limiting factor for the commercial application of superalloys in aerospace applications where the oxidation ahead of the crack tip plays an important role. Previous research on the Ni-base superalloy A718Plus revealed that the orientation and the volume fraction of the high temperature grain boundary phases δ and η have a major influence on the dwell fatigue crack propagation rate at 650 °C in ambient air but not in vacuum. In this work, the effect of internal oxidation at the η/δ–matrix interface and its effect on dwell fatigue crack propagation and mechanical properties are examined by advanced microscopic methods and micro-cantilever testing. During crack propagation, the crack tip is exposed to air where a Nb-rich oxide layer forms and embrittles the η/δ–matrix interface causing the cracks to deflect and propagate along the oxidized interfaces. Micro-cantilever tests on the oxidized interface show that these oxide layers also significantly reduce the local strength and fracture toughness of the material. This proves that interfacial oxide layers are the underlying reason for the reduction of the dwell fatigue crack growth resistance at 650 °C, particularly in microstructures whose η/δ–matrix interfaces are oriented parallel to the crack growth direction.<br

The influence of crack and interface oxidation on dwell fatigue crack propagation behavior of the nickel-base superalloy ATI A718Plus - Kirchmayer, Andreas; Hausmann, Daniel; Gabel, Stefan; Pröbstle, Martin; Giese, Sven; Göken, Mathias; Hünert, Daniela; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
The crack propagation properties are an important and often limiting factor for the commercial application of superalloys in aerospace applications where the oxidation ahead of the crack tip plays an important role. Previous research on the Ni-base superalloy A718Plus revealed that the orientation and the volume fraction of the high temperature grain boundary phases δ and η have a major influence on the dwell fatigue crack propagation rate at 650 °C in ambient air but not in vacuum. In this work, the effect of internal oxidation at the η/δ–matrix interface and its effect on dwell fatigue crack propagation and mechanical properties are examined by advanced microscopic methods and micro-cantilever testing. During crack propagation, the crack tip is exposed to air where a Nb-rich oxide layer forms and embrittles the η/δ–matrix interface causing the cracks to deflect and propagate along the oxidized interfaces. Micro-cantilever tests on the oxidized interface show that these oxide layers also significantly reduce the local strength and fracture toughness of the material. This proves that interfacial oxide layers are the underlying reason for the reduction of the dwell fatigue crack growth resistance at 650 °C, particularly in microstructures whose η/δ–matrix interfaces are oriented parallel to the crack growth direction.
CRIS-Team Scopus Importer:2024-02-16

The influence of different alloying elements on the development of the γ/γ′ microstructure of nickel-base superalloys during high-temperature annealing and deformation - Pyczak, Florian; Devrient, Bastian; Neuner, Frank; Mughrabi, Hael (Acta Materialia, 2005)
The development of the γ/γ′ microstructure during high-temperature annealing and deformation is investigated in a series of experimental nickel-base superalloys, with varying contents of alloying elements, in particular rhenium, ruthenium and iridium. Some samples were creep-deformed in compression at 950 °C to different plastic strains εpl, while others were aged at 1000 °C. By investigating the resulting microstructures one can deduce that the development of the γ′ microstructure is influenced in two ways by the alloying elements. The lattice misfit and thereby the coherency stresses between γ′ phase and γ matrix are altered but also the rate of diffusion in the γ matrix. While coherency stresses are the driving force for changes of the γ′ shape at elevated temperatures, the development of the γ′ structure itself is diffusion-controlled. To understand the effects of alloying elements on the development of the γ′ structure, the modifications of both the lattice misfit and the modifications of diffusion rate caused by the alloying elements have to be taken into account. © 2005 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: γ′ Coarsening; γ/γ′ Microstructure; Creep deformation; Microstructural stability; Nickel-base superalloys

The influence of hydrogenated amorphous carbon coatings (a-C:H) on the fatigue life of coated steel specimens - Schaufler, Jens; Durst, Karsten; Haas, Thomas; Nolte, Roland; Höppel, Heinz Werner; Göken, Mathias (International Journal of Fatigue, 2012)
The influence of a hydrogenated amorphous carbon coating on the fatigue life of an austenitic steel was evaluated in this work. The fatigue damage mechanisms have been compared for both coated and uncoated specimens. A strong increase in fatigue life of more than 300% for low total strain amplitudes was found for the coated specimens. The influence of the coating on the fatigue life increases with decreasing total strain amplitude. The damage mechanisms were analyzed using atomic force microscopy and focus ion beam cross sectioning. The coated specimens show a significantly reduced surface roughening. Slip bands in the steel sample could not penetrate the coating and thus slip step formation on the surface was avoided, leading to the enhanced fatigue life. The compressive residual stress in the coating is discussed being the main reason for the enhanced fatigue life of the specimens.
WW1::948

The influence of microstructure on the magnetic properties of WC/Co hardmetals - Topic, Irena; Sockel, Hans-Georg; Wellmann, Peter; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2006)
The magnetic properties of conventional and ultrafine-grained WC/Co hardmetals have been measured and related to the microstructure. The microstructure was characterised using scanning electron and atomic force microscopy. The WC grain size was found to vary between 1.0-2.5 and 0.1-0.3 mu m for conventional and ultrafine-grained hardmetals, respectively. In conventional WC/Co hardmetals the coercivity increases as the WC grain size decreases. In the ultrafine-grained hardmetals with the WC grain size below 0.5 mu m, the coercivity was found to increase strongly and be one order of magnitude higher than in the conventional hardmetals. The relationship between magnetic properties and microstructure in this work can be extended to smaller grain sizes and ties in well with literature results. The developed relationship can be used as a quick method to estimate the WC grain size by measuring the magnetic coercivity. Furthermore, it was confirmed that the coercivity is not only a function of grain size, but also of cobalt content. All results lead to the conclusion that an increase in WC-Co interface area increases the coercivity values. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: WC/Co hardmetals; Ultrafine-grained (UFG); WC–Co interface area; Coercivity; Magnetic saturation; Magnetic domains

The influence of near service environmental conditions on the corrosion and LCF behaviour of a beta-stabilized γ-TiAl alloy - Löffl, Christian; Saage, Holger; Göken, Mathias (Corrosion Science, 2020)
The damage behaviour of the TiAl alloy Ti-43.5Al-4Nb-1Mo-0.1B was investigated by isothermal thermogravimetric-analysis (TGA) and strain controlled low-cycle-fatigue (LCF) experiments at high temperature. Aluminium depletion and the formation of a continuous brittle layer in the subsurface zone takes place in synthetic exhaust gas. Contrary, a continuous ductile γ-phase forms in the subsurface zone in air. Since a continuous TiN layer as diffusion barrier is not formed in the early stages of corrosion, strong hardening is observed in LCF test samples in exhaust gas and a strain amplitude of 0,6 %, leading to a significant reduction of the cycles to failure.
CRIS-Team Scopus Importer:2020-08-07
Keywords: corrosion fatigue; environmental effects; high temperature corrosion; titanium aluminides

The influence of niobium, tantalum and zirconium on the microstructure and creep strength of fully lamellar gamma/alpha(2) titanium aluminides - Bresler, Johannes; Neumeier, Steffen; Ziener, Marco; Pyczak, F.; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2019)
Titanium aluminides are excellent materials for light-weight applications at high temperatures. To enhance their creep strength, various alloying elements are added. In this work the effect of 5 at% Niobium (Nb), Tantalum (Ta) and Zirconium (Zr) on the creep properties of ternary Ti-44Al-5X (X = Nb, Ta, Zr) with a fully lamellar microstructure, is systematically studied. These alloying elements have a high solubility in titanium aluminides, and show a different alpha(2)/gamma partitioning behavior as well as a different influence on the lattice parameters of both phases. The average interface distance between the alpha(2)- and gamma-phase is adjusted to about 300 nm by the cooling rate to evaluate the influence of the three alloying elements. The creep tests reveal that all three alloying elements increase the creep resistance of titanium aluminides, particularly Ta and Zr. Ta seems to extend the pronounced primary creep regime, whereas Zr seems to reduce it The alloying elements decrease also the lamellar spacing compared to the binary alloy. Microstructural investigations after the creep tests show a beneficial effect of the alloying elements on the microstructural stability during creep exposure, since they retard the discontinuous coarsening rate.
Keywords: Titanium aluminides; Microstructure; Alloying elements; Creep

The influence of niobium, tantalum and zirconium on the microstructure and creep strength of fully lamellar γ/α2 titanium aluminides - Bresler, Johannes; Neumeier, Steffen; Ziener, Marco; Pyczak, F.; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2019)
Keywords: Alloying elements; Creep; Microstructure; Titanium aluminides

The influence of particle size on the mechanical properties of dental glass ionomer cements - Brandt, Bjoern; Lohbauer, Ulrich; Göken, Mathias; Durst, Karsten (Advanced Engineering Materials, 2010)
WW1::860

The influence of ruthenium and rhenium on the local properties of the γ- and γ′-phase in nickel-base superalloys and their consequences for alloy behavior - Neumeier, Steffen; Pyczak, Florian; Göken, Mathias (Proceedings of the International Symposium on Superalloys, 2008)
Rhenium and ruthenium are alloyed to modern nickel-base superalloys to gain good high temperature properties combined with acceptable phase stability. Three experimental alloys with varied contents of rhenium and ruthenium were investigated. It was found with transmission electron microscopy (TEM)-based energy dispersive spectroscopy (EDS) that rhenium distributes more homogenously between the γ- and γ′-phase in the presence of ruthenium (reverse partitioning). Other properties of the alloys as the lattice misfit, local hardness of the individual phases and the high temperature evolution of the microstructure were strongly influenced by the partitioning behavior of rhenium and ruthenium. The changes in lattice constants and hardness of the γ- and γ′-phase could be verified by X-ray diffraction and nanoindentation in an atomic force microscope (NI-AFM). The optimum γ′-size with respect to creep properties was found to be dependent on the lattice misfi
Keywords: Creep; Lattice constants; Nanoindentation; Partitioning behavior; Reverse partitioning; Rhenium; Ruthenium

The innovation potential of bulk nanostructured materials - Valiev, Ruslan Z.; Zehetbauer, Michael J.; Estrin, Yuri; Höppel, Heinz Werner; Ivanisenko, Yulia; Hahn, Horst; Wilde, Gerhard; Roven, Hans J.; Sauvage, Xavier; Langdon, Terence G. (Advanced Engineering Materials, 2007)
The innovation potential is high for bulk nanostructured materials (BNM) produced by methods of severe plastic deformation and accordingly this report focuses on very recent developments demonstrating the potential of using BNM for advanced and functional applications in engineering and medicine.
Created from Fastlane, Scopus look-up

The Mechanical Properties in the Vicinity of grain boundaries in ultrafine-grained and Polycrystalline Materials Studied by Nanoindentations - Durst, Karsten; et al. (Materials Research Society Symposium - Proceedings, 2004)
The strength of structural materials strongly depends on the structure and properties of grain boundaries. Interfaces usually act as barriers to dislocation motion and therefore strengthen materials with decreasing grain size, quantitatively described by the well-known Hall-Petch relation. However, interfaces in nanocrystalline materials are often covered with impurities or second phases, which may influence the mechanical properties. With nanoindentation testing it is now possible to probe the strength of interfaces like grain boundaries directly on a nanometer scale. Therefore this method was used to investigate the properties in the vicinity of grain boundaries in polycrystalline materials with conventional grain size and in ultrafine-grained metals prepared by equal channel angular pressing (ECAP), where no impurities are introduced during processing. Measurements on an austenitic steel clearly show a decreasing hardness close to the interface opposite to the general expected behavior of strengthening. In this case segregation effects strongly influence the mechanical properties near the boundaries. The nanoindentation investigations on ultrafine-grained Al and Cu show a strong strain rate sensitivity. Inelastic effects are also found between unloading-loading segments during indentations. © 2004 Materials Research Society.
UnivIS-Import:2015-04-16:Pub.2004.tech.IW.LWAW.themec

The nanoindentation of soft tissue: Current and developing approaches - Franke, Oliver; Göken, Mathias; Hodge, Andrea M. (JOM Journal of the Minerals, Metals and Materials Society, 2008)
WW1::790

The rise of computational techniques in atom probe microscopy - Ceguerra, Anna V.; Breen, Andrew J.; Stephenson, Leigh T.; Felfer, Peter; Araullo-Peters, Vicente J.; Liddicoat, Peter V.; Cui, Xiangyuan; Yao, Lan; Haley, Daniel; Moody, Michael P.; Gault, Baptiste; Cairney, Julie M.; et al. (Current Opinion in Solid State & Materials Science, 2013)
Much effort has been devoted to the development of computational techniques in atom probe microscopy over the past decade. There have been several drivers for this effort. Firstly, there has been effort devoted to addressing the challenges of discerning information from the increasingly large size of the data, and capturing the opportunities that this large data presents. Secondly, there has been significant new effort devoted to the simulation of atom probe data so that pristine datasets that contain microstructural features of increasing complexity can be generated in-silico, and subjected to complex data-mining algorithms. This has enabled the benchmarking of various algorithms, guided the setting of parameters for particular analyses, and exposed the effects of instrumentation parameters such as detector efficiency and aberrations in ionic flight path. The authors are especially interested in the prospects of converging atomic-scale microscopy with atomic-scale materials modelling via first principles approaches. This involves excising parts of the APM data and using these as super-cell inputs to calculations of materials properties via density functional theory. It is our opinion that this represents a major advance for materials science because it enables microscopy to advance microstructure-property relationships to the direct mapping of such relationships based on many-body interactions. As such, this approach has great potential for materials design and development. The final part of this paper focuses on how cloud-based computing represents an exciting frontier of the computational aspects of atom probe microscopy. We discuss the opportunities and the barriers for conducting new materials science through the analysis and visualisation of atom probe data via new generation tools that are cloud-based, and which are managed, curated and governed with significant user-community input and integrated with contemporary electronic laboratory notebook technology. © 2013 Published by Elsevier Ltd. All rights reserve
Keywords: Atom probe microscopy; Atom probe tomography; Computational materials science; Materials informatics

Thermally activated flow in soft and hard regions: Getting information on work hardening strain and recovery strain from rate change tests - Blum, Wolfgang; Eisenlohr, P.; Prell, M.; Durst, K. (Kovove Materialy-Metallic Materials, 2015)
WW1::1037

Thermally activated flow in soft and hard regions: Getting information on work hardening strain and recovery strain from rate change tests - Blum, Wolfgang; Eisenlohr, Philip; Prell, M.; Durst, Karsten (Kovove Materialy-Metallic Materials, 2015)

Thermochemistry and phase stability of the polymorphs of yttrium tantalate, YTaO4 - Lepple, Maren; Ushakov, Sergey V.; Lilova, Kristina; Macauley, Chandra; Fernandez, Abel N.; Levi, Carlos G.; Navrotsky, Alexandra (Journal of the European Ceramic Society, 2020)
Thermodynamic parameters of the three fergusonite-related polymorphs M’, M and T of YTaO4 and their phase stabilities were investigated experimentally. The debate on the relative stability of the M and M’ phases was resolved, and it was shown that the compound does not transform to a cubic polymorph prior to melting. The enthalpies of formation of M and M’ were determined using high temperature oxide melt solution calorimetry, and the heat capacities and heat contents were measured. The enthalpy of the M’ to T phase transition was measured by differential thermal analysis. The stability of the T phase up to its melting at 2090 °C was demonstrated using high temperature X-ray diffraction and thermal analysis. Its enthalpy of fusion was determined using drop-and-catch calorimetry. The thermodynamic properties of YTaO4 assessed in this study enable the thermodynamic modeling of its polymorphs and related materials systems of technological importance.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Calorimetry; Oxide materials; Synchrotron radiation; Thermal analysis; Thermodynamic properties; YTaO; Yttrium tantalate

Thermophysical and Mechanical Properties of Advanced Single Crystalline Co-base Superalloys - Volz, Nicklas; Zenk, Christopher; Cherukuri, Rahul; Kalfhaus, Tobias; Weiser, Martin; Makineni, Surendra Kumar; Betzing, Christian; Lenz, Malte; Gault, Baptiste; Fries, Suzana G.; Schreuer, Juergen; Vassen, Robert; et al. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2018)
A set of advanced single crystalline γ´ strengthened Co-base superalloys with at least nine alloying elements (Co, Ni, Al, W, Ti, Ta, Cr, Si, Hf, Re) has been developed and investigated. The objective was to generate multinary Co-base superalloys with significantly improved properties compared to the original Co-Al-W-based alloys. All alloys show the typical γ/γ´ two-phase microstructure. A γ´ solvus temperature up to 1174 °C and γ´ volume fractions between 40 and 60 pct at 1050 °C could be achieved, which is significantly higher compared to most other Co-Al-W-based superalloys. However, higher contents of Ti, Ta, and the addition of Re decrease the long-term stability. Atom probe tomography revealed that Re does not partition to the γ phase as strongly as in Ni-base superalloys. Compression creep properties were investigated at 1050 °C and 125 MPa in <001> direction. The creep resistance is close to that of first generation Ni-base superalloys. The creep mechanisms of the Re-containing alloy was further investigated and it was found that the deformation is located preferentially in the γ channels although some precipitates are sheared during early stages of creep. The addition of Re did not improve the mechanical properties and is therefore not considered as a crucial element in the design of future Co-base superalloys for high temperature applications. Thermodynamic calculations describe well how the alloying elements influence the transformation temperatures although there is still an offset in the actual values. Furthermore, a full set of elastic constants of one of the multinary alloys is presented, showing increased elastic stiffness leading to a higher Young’s modulus for the investigated alloy, compared to conventional Ni-base superalloys. The oxidation resistance is significantly improved compared to the ternary Co-Al-W compound. A complete thermal barrier coating system was applied successfull

The Role of Interfaces on the Deformation Mechanisms in Bimodal Al Laminates Produced by Accumulative Roll Bonding - Höppel, Heinz Werner; Westermeyer, Martin; Kümmel, Frank; Göken, Mathias (Advanced Engineering Materials, 2020)
Laminated metallic materials with an ultrafine-grained (UFG) microstructure can easily be produced by accumulative roll bonding (ARB). Combining two different Al alloys, commercially pure (CP) and high-purity (HP) aluminum, a layerwise bimodal microstructure is formed, where the CP layers consist of ultrafine grains whereas the HP layers show large grains as these layers undergo dynamic recrystallization during rolling. By applying different numbers of ARB passes and in addition by applying a subsequent heat treatment, the microstructure of the laminate can be changed significantly. Thus, different types of interfaces, specifically the grain boundaries of the ultrafine grains and the interfaces between the different layers of CP and HP aluminum are dominating the deformation behavior and the mechanical properties of these laminates. This article addresses how the UFG boundaries and the layer interfaces affect the mechanical properties under monotonic and cyclic loading, and discusses the relevant deformation mechanisms.
CRIS-Team Scopus Importer:2020-05-02
Keywords: interfaces mechanical properties; metallic laminates; ultrafine-grained and bimodal structures

The role of local chemical composition for TCP phase precipitation in Ni-base and Co-base superalloys - Hammerschmidt, T.; Koßmann, J.; Zenk, Christopher; Neumeier, Steffen; Göken, Mathias; Lopez-Galilea, I.; Mujica Roncery, L.; Huth, S.; Kostka, A.; Theisen, W.; Drautz, R. (13th International Symposium on Superalloys, SUPERALLOYS 2016, 2016)
Keywords: Intermetallic precipitates; Ni-base superalloys; Co-base superalloys; Topologically close-packed phases; Solidification; Structure map

The role of oxygen defects on the electro-chemo-mechanical properties of highly defective gadolinium doped ceria - Kabir, Ahsanul; Kyu Han, Jin; Merle, Benoit; Esposito, Vincenzo (Materials Letters, 2020)
In light of the recent discovery of giant electrostriction in defective fluorites, here we investigate the interplay between mechanical, electrochemical and electromechanical properties of oxygen defective ceria compositions (Ce1−xGdxO2−δ) as the effect of Gd-doping (x = 0.05–0.3) at low temperatures. Highly dense polycrystalline ceramics are prepared as micron-size grains with a minimized grain boundary extent. Electrochemical ionic migration by impedance spectroscopy reveals that dopant content controls the oxygen vacancies association in the samples. Interestingly, we observe that electromechanical activity is strongly controlled by the local oxygen vacancy configuration rather than on its nominal concentration. The primary creep at room temperature indicates a declining viscoelastic trend with increasing oxygen defects.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Blocking barriers; Creep; Defects; Electrostriction; Ionic conductivity

The role of the base element in γ′ strengthened cobalt/nickel-base superalloys - Zenk, Christopher; Neumeier, Steffen; Kolb, Markus; Volz, Nicklas; Fries, S. G.; Dolotko, O.; Povstugar, I.; Raabe, D.; Göken, Mathias (13th International Symposium on Superalloys, SUPERALLOYS 2016, 2016)
Keywords: Creep; Lattice misfit; Atom probe tomography; Co-base superalloys; Partitioning behavior

The Role of Through-Thickness Variation of Texture and Grain Size on Bending Ductility of Al–Mg–Si Profiles - Goik, Philip; Schiffl, A.; Höppel, Heinz Werner; Göken, Mathias (Minerals, Metals and Materials Series, 2023)
Requiring a high strength and concurrently a high ductility in materials is generally a demand for opposing properties in dislocation slip deforming materials, such as Al–Mg–Si wrought alloys. However, these are essential mechanical properties for safety parts in the mobility sector. While the strength of Al–Mg–Si wrought alloys is mainly governed by the state and density of the secondary precipitates, the deformation behavior and ductility are affected by both precipitates and crystallographic texture. The deformation during extrusion leads to the formation of characteristic textures in the bulk, which are distinct to a plane-strain deformation, and a peripheral coarse grain (PCG) layer beneath the surface. This PCG layer can have a detrimental effect on the bending ductility, which assesses the crashworthiness. However, an appropriate texture in the bulk can counteract the detrimental effect of PCG and increases the bending ductility at high strengths. Subsequently, based on EBSD investigations of bending deformed microstructures, a way to enhance bending deformation capability in Al–Mg–Si profiles is proposed.
CRIS-Team Scopus Importer:2023-04-07
Keywords: AA-6xxx; Crystallographic texture; Ductility; EBSD; Extrusion; Peripheral coarse grain; Plate bending

The role of Ti and TiC nanoprecipitates in radiation resistant austenitic steel: A nanoscale study - Cautaerts, Niels; Delville, Rémi; Stergar, Erich; Pakarinen, Janne; Verwerft, Marc; Yang, Yong; Hofer, Christina; Schnitzer, Ronald; Lamm, Steffen; Felfer, Peter; Schryvers, Dominique (Acta Materialia, 2020)
This work encompasses an in-depth transmission electron microscopy and atom probe tomography study of Ti-stabilized austenitic steel irradiated with Fe-ions. The focus is on radiation induced segregation and precipitation, and in particular on how Ti and TiC affect these processes. A 15-15Ti steel (grade: DIN 1.4970) in two thermo-mechanical states (cold-worked and aged) was irradiated at different temperatures up to a dose of 40 dpa. At low irradiation temperatures, the cold-worked and aged materials evolved to a similar microstructure dominated by small Si and Ni clusters, corresponding to segregation to small point defect clusters. TiC precipitates, initially present in the aged material, were found to be unstable under these irradiation conditions. Elevated irradiation temperatures resulted in the nucleation of nanometer sized Cr enriched TiC precipitates surrounded by Si and Ni enriched shells. In addition, nanometer sized Ti- and Mn-enriched G-phase (M6Ni16Si7) precipitates formed, often attached to TiC precipitates. Post irradiation, larger number densities of TiC were observed in the cold-worked material compared to the aged material. This was correlated with a lower volume fraction of G-phase. The findings suggest that at elevated irradiation temperatures, the precipitate-matrix interface is an important point defect sink and contributes to the improved radiation resistance of this material. The study is a first of its kind on stabilized steel and demonstrates the significance of the small Ti addition to the evolution of the microstructure under irradiation.
CRIS-Team Scopus Importer:2020-08-07
Keywords: APT; Austenitic steel; G-phase; Precipitation; Radiation induced segregation; TEM; TiC

The Strengthening Effect of Phase Boundaries in a Severely Plastically Deformed Ti-Al Composite Wire - Marr, Tom; Freudenberger, Jens; Maier, Verena; Höppel, Heinz Werner; Göken, Mathias; Schultz, Ludwig (Metals, 2014)
An accumulative swaging and bundling technique is used to prepare composite wires made of Ti and an Al alloy. These wires show reasonable higher yield stresses than expected from the pure material flow curves. The additional strengthening in the composite is analyzed using nanoindentation measurements, tensile testings and investigations of the microstructure. In addition, these properties are analyzed in relation to the fracture surface of the mechanically tested wires. Additional strengthening due to the presence of phase boundaries could be verified. Indications for residual stresses are found that cause a global hardness gradient from the center to the wire rim. Finally, the yield stress of the wires are calculated based on local hardness measurements.
Keywords: SPD; Ti; Al; nanoindentation; mechanical properties

The temperature dependent lattice misfit of rhenium and ruthenium containing nickel-base superalloys – Experiment and modelling - Neumeier, Steffen; Pyczak, F.; Göken, Mathias (Materials and Design, 2021)
The lattice misfit between γ and γ' phase is a key parameter in Ni-base superalloys. Resulting internal coherency stresses govern the microstructure, its evolution and mechanical properties. Here, the influence of important alloying elements Re and Ru on the misfit up to 1100 °C is investigated. Due to their preferred partitioning to γ, the addition of both leads to a stronger increase of the lattice parameter of γ than of γ' and thus to a more negative misfit. The overall content of Re and Ru influences significantly the evolution of the misfit with temperature. Alloys with high contents show an atypical behavior, where the magnitude of the negative misfit gets smaller at high temperatures. Alloys with a medium content exhibit a rather constant misfit and alloys with a low content or without Re and Ru follow the typical trend of a more negative misfit with increasing temperature. The observed differences are ascribed to different thermal expansion coefficients and particularly to the changing chemical composition of γ due to the dissolution of γ' precipitates. An advanced model for determining the misfit based on thermodynamic calculations is presented. Different approaches for determining lattice parameters and calculating lattice misfits are evaluated in the supplementary.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Lattice misfit; Ni-base superalloy; Rhenium; Ruthenium; X-ray diffraction

The thermal stability of intermetallic compounds in an as-cast SX co-base superalloy - Lopez-Galilea, Inmaculada; Zenk, Christopher; Neumeier, Steffen; Huth, Stephan; Theisen, Werner; Göken, Mathias (Advanced Engineering Materials, 2015)
The nature and stability of intermetallic phases in a multi-component γ/γ′ Co-base superalloy is investigated. At least three kinds of unwanted intermetallic phases form due to the segregation of Al, Ta, Ti, Si, and Hf during casting in the interdendritic areas in addition to γ and γ′. One of the intermetallic phases that shows a blocky shape, contains high content of Ta, Hf, and Ti and has been identified as a topologically close-packed Laves phase. A B2 phase appears as relatively big pools and in some cases contains needle-shaped precipitates with high content of Al and Ti. The thermal stability of these intermetallic phases is studied in this work under defined heat treatments. The needle-shaped precipitates already dissolve at 1000°C, whereas the B2 phase is dissolved only at higher temperatures of 1200°C. Small amounts of Laves phases remained stable during aging at 1200°C for 25h. The prediction of phases as well as their stability is also checked by the CALPHAD method. The TCNi5 database, containing the description of Co3(Al,W), predicts the presence of the observed intermetallic phases; however, the predicted main transformation temperatures for these phases differ from the experimentally obtained values. This work studies the nature and stability of three intermetallic phases - Laves, B2 and needle-shaped precipitates - in a multi-component γ/γ′ Co-base superalloy, named ERBO-Co0. These phases are generated during casting at the interdendritic areas. Experimental characterization of intermetallic phases is contrasted with thermodynamic calculations, which predicts the presence of the identified phase

Thickness and grain size dependence of the strength of copper thin films as investigated with bulge tests and nanoindentations - Merle, Benoit; Schweitzer, Elmar; Göken, Mathias (Philosophical Magazine, 2012)
Thin films have often been reported to exhibit increased strength compared to their bulk counterparts. In this study, copper films with a thickness ranging from 400 to 2400 nm were investigated via bulge testing and nanoindentation, focusing on the influence of thickness and microstructure on the mechanical properties. Bulge tests on freestanding membranes show that the yield strength follows Hall–Petch behaviour, as bulk materials do. This also holds true for films on a substrate, as long as the microstructure contains several grains in the thickness direction. The determined Hall–Petch coefficient of 0.16 MPa m-1/2 is also similar to bulk materials. Texture was found to have very limited influence on mechanical behaviour. Nanoindentation data, evaluated by the Han–Nix method, showed that the hardness of thin films is higher than that of bulk materials with the same grain size.
WW1::949

Ti3C2Tx Solid Lubricant Coatings in Rolling Bearings with Remarkable Performance beyond State-of-the-Art Materials - Marian, Max; Feile, Klara; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Seynstahl, Armin; Tremmel, Stephan; Krauß, Sebastian; Merle, Benoit; Boehm, Thomas; Wang, Bo; Wyatt, Brian C.; et al. (Applied Materials Today, 2021)
Two-dimensional (2D) transition metal carbides, nitrides, and carbonitrides, known as MXenes, are a growing class of 2D materials, which offer great solid lubrication ability for low friction applications due to their weakly bonded multi-layer structure and tribo-layer formation with self-lubricating characteristics. To date, most studies have assessed their tribological response in basic laboratory tests. However, these tests do not adequately reflect the complex geometries, kinematics, and stresses present in machine components. Here, we aim at bridging this gap through assessment of the friction and wear performance of multi-layer Ti3C2Tx MXene solid lubricant coatings used in rolling bearings. MXenes’ tribological response is compared with state-of-the art solid lubricant coatings, which include molybdenum disulfide (MoS2), tungsten-doped hydrogenated amorphous carbon (a‑C:H:W), and hydrogen-free, more graphite-like amorphous carbon (a‑C). Multi-layer Ti3C2Tx MXene coatings reduce wear on the bearing washers by up to 94 %, which can be attributed to the transfer of the lubricious MXene nano-sheets to secondary tribo-contacts of the bearing. While the frictional torque of all solid lubricant coatings is similar during steady-operation, the MXene-coated bearings extend the service life by 30 % and 55 % compared to MoS2 and DLC, respectively. This contribution demonstrates the ability of MXene solid lubricant coatings to outperform state-of-the-art solid lubricants in dry-running machine components such as rolling bearing
Keywords: 2D materials; MXenes; MoS2; DLC; solid lubrication; rolling bearings

Time-dependent deformation behavior of freestanding and SiNx-supported gold thin films investigated by bulge tests - Merle, Benoit; Cassel, Detlev; Göken, Mathias (Journal of Materials Research, 2015)
A novel strain-rate jump method was developed for the plane-strain bulge test and used to investigate the time-dependent deformation behavior of gold thin films in the thickness range 100-400 nm. The experimental method is based on an abrupt variation of the pressurization rate. The evaluated strain-rate sensitivity was found to be five times higher for films in freestanding condition (m = 0.094) than for films tested on a SiNx substrate (m = 0.020). Bulge creep tests confirmed this increased time-dependence. The observation of the surface of the freestanding films after the creep tests provided evidence of apparent grain boundary sliding taking place next to intragranular plastic deformation. The out-of-plane deformation was presumably favored by the columnar microstructure of the samples, with grains extending between both free surfaces. In the case of SiNx-supported films, grain boundary sliding was prevented by the good adhesion of gold to the SiNx substrate.

Transmission electron microscopy study of strain-induced low- and high-angle boundary development in equal-channel angular-pressed commercially pure aluminum - Cabibbo, M.; Blum, Wolfgang; Evangelista, E.; Kassner, M. E.; Meyers, M. A. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2008)
The evolution of the microstructure in a commercially pure aluminum during equal channel angular pressing (ECAP) using route BC was investigated by transmission electron microscopy. Subgrains, or cells, form, which have both high (φ > 15 deg) and low (φ < 15 deg) misorientation. Misorientations and spacings of cell boundaries were determined from about 250 boundaries per pass of ECAP cell boundaries on the basis of Kikuchi patterns and Moiré fringes. The average cell size and misorientation saturate within the first two passes. Misorientations and spacings of high-angle boundaries decrease with the number of passes. After eight passes, the cell size is ≈1.3 μm and the fraction of high-angle boundaries is ≈0.7. The marked differences in the rate of grain structure evolution per pass are linked to differences in the ability of dislocations introduced in new passes to recombine with the existing ones. With increasing ECAP strain, the distribution of misorientations develops strong deviations from the MacKenzie distribution for statistical grain orientation. This is interpreted as a result of the tendency to form equiaxed grains in a textured grain structure. © The Minerals, Metals & Materials Society and ASM International 2007.
Created from Fastlane, Scopus look-up

Transport mechanisms during the high-temperature oxidation of ternary γ/γ′ Co-base model alloys - Weiser, Martin; Chater, Richard J.; Shollock, Barbara A.; Virtanen, Sannakaisa (npj Materials Degradation, 2019)
Over a decade ago, γ′-strengthened Co-base alloys were introduced as potential replacement for conventional Ni-base Superalloys. Insufficient resistance against high-temperature oxidation restricts the number of possible applications. The present study contributes to the understanding of elementary mechanisms such as material transport during extensive oxide scale formation on γ/γ′ Co-base alloys to explain their inferior oxidation behaviour. A clear dependency of the scale growth kinetics on W content and oxidation temperature is demonstrated by thermogravimetry and subsequent analysis of cross-sections. By means of electron backscattered diffraction (EBSD), the evolution of microstructures in the outer oxide layers were examined depending on the oxidation temperature. Sequential exposure of samples in 16O2- and 18O2-containing atmospheres proved counter-current material transport. The combination of focused ion beam (FIB) and secondary ion mass spectroscopy (SIMS) visualised the formation of new oxide phases mainly on the outer and inner interface of the oxide scale. An elaborate review of available transport paths for oxygen is given during the discussion of results. All experimental findings were combined to a coherent explanation of the inferior oxidation resistance of this relatively new class of high-temperature materials at temperatures above 800 °C.<br

Tuning mechanical properties of ultrafine-grained tungsten by manipulating grain boundary chemistry - Wurmshuber, Michael; Jakob, Severin; Doppermann, Simon; Wurster, Stefan; Bodlos, Rishi; Romaner, Lorenz; Maier-Kiener, Verena; Kiener, Daniel (Acta Materialia, 2022)
Keywords: Mechanical properties; Nanoindentation; Atom probe tomography; Grain boundary segregation engineering; Ultrafine-grained metals; Smallscale testing; Tungsten; kernfusionsrelevant

Ultrafine-grained AA6014/AA5754 laminates produced by accumulative roll bonding (ARB) - Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias (Materialwissenschaft und Werkstofftechnik, 2012)
Laminates with alternating AA6014 and AA5754 layers are produced by accumulative roll bonding (ARB). Depending on the number of ARB cycles the microstructure and the mechanical properties are investigated. The microstructure is characterized by scanning electron microscopy and correlated to the local mechanical properties determined by nanoindentation experiments. The overall properties are derived by tensile testing. The ultrafine-grained microstructure and the local mechanical properties alter with the layer composition. With increasing number of ARB cycles a much higher grain refinement is achieved within the AA5754 layers than in the AA6014 layers. The hardness of the individual layers develops similarly. On the macroscopic scale it is shown that the laminates are unifying the desired properties of the materials involved: high strength by a simultaneous suppression of the Portevin-Le Châtelier effect, typically occurring in the AA5754 alloy.
WW1::950

Ultrafine-grained austenitic stainless steels X4CrNi18-12 and X8CrMnNi19-6-3 produced by accumulative roll bonding - Ruppert, Mathis; Freund, Lisa; Wenzl, Thomas; Höppel, Heinz Werner; Göken, Mathias (Metals, 2015)
Austenitic stainless steels X4CrNi18-12 and X8CrMnNi19-6-3 were processed by accumulative roll bonding (ARB). Both materials show an extremely high yield strength of 1.25 GPa accompanied by a satisfactory elongation to failure of up to 14% and a positive strain rate sensitivity after two ARB cycles. The strain-hardening rate of the austenitic steels reveals a stabilization of the stress-strain behavior during tensile testing. Especially for X8CrMnNi19-6-3, which has an elevated manganese content of 6.7 wt.%, necking is prevented up to comparatively high plastic strains. Microstructural investigations showed that the microstructure is separated into ultrafine-grained channel like areas and relatively larger grains where pronounced nano-twinning and martensite formation is observed.
WW1::1039

Ultrafine-Grained Laminated Metal Composites: A New Material Class for Tailoring Cyclically Stressed Components - Kümmel, Frank; Höppel, Heinz Werner; Göken, Mathias (Advanced Engineering Materials, 2021)
The service life of technical components is often limited by the fatigue strength of the deployed materials. The accumulative roll bonding (ARB) process, which has the ability to produce ultrafine-grained (UFG) laminated metal composites with tailored properties, offers a unique method to significantly enhance the fatigue life of materials that are cyclically loaded in three-point bending. Detailed microstructural investigations reveal the material- and load-specific deformation and damage mechanisms. Composites that have a sufficiently high difference in strength between the different constituent layers exhibit a significantly impeded crack growth and therefore an extended fatigue life at high stress amplitudes compared with those laminates with a rather similar strength of the different constituents. In the former composites, the fatigue crack is deflected at the material interface as it propagates from the softer to the harder layer. At low stress amplitudes, a prolonged fatigue life of the composites is mainly because of a significantly increased resistance to crack initiation. On the one side, this is as a result of the introduction of an UFG microstructure. On the other side, a load transfer toward stiffer layers in the interior of the composites also accounts for the enhanced fatigue life, if elastically dissimilar materials are combined in the right manner.
CRIS-Team Scopus Importer:2021-04-23
Keywords: accumulative roll bondings; fatigue crack paths; fatigue life; laminated metal composites; ultrafine-grained materials

Ultrafine-Grained Metals - Höppel, Heinz Werner (Metals, 2015)

Ultrafine-grained Metals - Höppel, Heinz Werner (MDPI Basel, 2017)

Ultrafine-grained Tungsten by High-Pressure Torsion - Bulk precursor versus powder processing route - Wurmshuber, Michael; Doppermann, Simon; Wurster, Stefan; Kiener, Daniel (40th Riso International Symposium on Materials Science: Metal Microstructures in 2D, 3D and 4D, 2019)
Keywords: kernfusionsrelevant

Ultra-high oxidation resistance of nano-structured thin films - Aschauer, E.; Wojcik, T.; Polcik, P.; Hunold, O.; Arndt, M.; Dalbauer, Valentin; Mayrhofer, P. H.; Felfer, Peter; Riedl, H. (Materials & Design, 2021)
Diffusion driven high-temperature oxidation is one of the most important failure mechanisms of protective thin films in industrial applications. Within this study, we investigated the diffusion of oxygen at 800 to 1100 °C through nano-laminated crystalline Ti-Al-N and amorphous Mo-Si-B based multilayer coatings. The most prominent oxygen diffusion pathways, and hence the weakest points for oxidation, were identified by combining 18O tracer diffusion and atom probe tomography. An oxygen inward diffusion along column boundaries within Ti-Al-N layers in front of a visually prevalent oxidation front could be proven, highlighting the importance of these fast diffusion pathways. Furthermore, the amorphous Mo-Si-B layers act as barriers and therefore mitigate the migration of oxygen by accumulating reactive O species at a nanoscale range. Preventing oxygen diffusion along column boundaries – through the implementation of amorphous interlayers – lead to paralinear oxidation behavior and stable scales even after 7 h at 1100 °C. Our results provide a detailed insight on the importance of morphological features such as grain and column boundaries during high-temperature oxidation of protective thin films, in addition to their chemistry.
CRIS-Team Scopus Importer:2021-02-05
Keywords: APT; Fast Diffusion Pathways; Oxidation Mechanism; Ti-Al-N; Tracer Diffusion

Ultrahigh-strength low carbon steel obtained from the martensitic state via high pressure torsion - Mueller, T.; Kapp, M. W.; Bachmaier, A.; Felfer, Peter; Pippan, R. (Acta Materialia, 2019)
A new ultrahigh-strength structure is created by severe plastic deformation of a martensitic 0.1 wt.-% C steel using high pressure torsion (HPT) at room temperature. Tensile tests reveal an ultimate tensile strength of 2.4 +/- 0.1 GPa after an equivalent strain of epsilon(vM) = 7.5 - to our knowledge the highest tensile strength ever reported for a carbon steel with such low carbon content. During HPT, a lamellar microstructure is formed with decreasing lamellar spacing for increasing plastic strain. Micropillar compression tests give crucial insights into the mechanical properties, which are correlated to the deformation behavior of this material. Strong similarities compared to HPT-treated pearlitic steel are found in spite of the large differences concerning both carbon content and phase composition. The possibilities and limits of strength maximization in carbon steels are evaluated and discussed. (C) 2018 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-03-06

Understanding creep of a single-crystalline Co-Al-W-Ta superalloy by studying the deformation mechanism, segregation tendency and stacking fault energy - Volz, Nicklas; Xue, Fei; Zenk, Christopher; Bezold, Andreas; Gabel, Stefan; Subramanyam, A. P.A.; Drautz, R.; Hammerschmidt, T.; Makineni, S. K.; Gault, B.; Göken, Mathias; Neumeier, Steffen (Acta Materialia, 2021)
A systematic study of the compression creep properties of a single-crystalline Co-base superalloy (Co-9Al-7.5W-2Ta) was conducted at 950, 975 and 1000°C to reveal the influence of temperature and the resulting diffusion velocity of solutes like Al, W and Ta on the deformation mechanisms. Two creep rate minima are observed at all temperatures indicating that the deformation mechanisms causing these minima are quite similar. Atom-probe tomography analysis reveals elemental segregation to stacking faults, which had formed in the γ′ phase during creep. Density-functional-theory calculations indicate segregation of W and Ta to the stacking fault and an associated considerable reduction of the stacking fault energy. Since solutes diffuse faster at a higher temperature, segregation can take place more quickly. This results in a significantly faster softening of the alloy, since cutting of the γ′ precipitate phase by partial dislocations is facilitated through segregation already during the early stages of creep. This is confirmed by transmission electron microscopy analysis. Therefore, not only the smaller precipitate fraction at higher temperatures is responsible for the worse creep properties, but also faster diffusion-assisted shearing of the γ′ phase by partial dislocations. The understanding of these mechanisms will help in future alloy development by offering new design criteria.<br
Keywords: Co-base superalloys; Directional coarsening; Creep; Stacking fault energy; DFT

Understanding raft formation and precipitate shearing during double minimum creep in a γ′-strengthened single crystalline Co-base superalloy - Xue, Fei; Zenk, Christopher; Freund, Lisa; Neumeier, Steffen; Göken, Mathias (Philosophical Magazine, 2020)
The compressive creep deformation behavior of a Co-base single-crystalline superalloy is studied in the high temperature / low stress regime at 950°C/150 MPa. Emphasis is placed on the mechanisms causing the double minimum creep behavior consisting of a local and a global creep rate minimum. The local minimum occurs at ∼0.2% strain with dislocation accumulation at γ/γ′ interfaces after bowing out of dislocations in horizontal matrix channels. Plate-like rafting occurring normal to the applied stress axis in the early creep stages is regarded as the primary reason for the decreasing creep rate until the global minimum takes place at ∼0.8% strain. In the final creep stage following the global minimum the creep rate accelerates due to coarsening and extensive precipitate shearing. The shearing by partial dislocations leads to the formation of numerous stacking faults, nano/microtwins, and occasionally to the formation of small amounts of ordered D019-Co3W precipitates. The reasons for twinning and second phase formation as well as differences of the deformation mechanisms between Co- and Ni-base superalloys during double minimum creep are discussed in detail in this work.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Co-base superalloys; creep; deformation; directional coarsening; transmission electron microscopy

Understanding the Extremely Low Fracture Toughness of Freestanding Gold Thin Films by In-situ Bulge Testing in an AFM - Preiß, Eva; Merle, Benoit; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2017)
The fracture toughness of freestanding gold films with thicknesses between 60 nm and 320 nm was determined by bulge testing to be around 2 MPa m1/2. This surprisingly low value confirms the trend also observed for other metals that thin films exhibit only a fraction of the bulk fracture toughness. In order to understand this behavior, the fracture process of freestanding gold films with a crack introduced by focused ion beam (FIB) milling was observed in-situ in an atomic force microscope (AFM). AFM scans of the crack tip region show stable crack growth mainly along grain boundaries. Plastic deformation is localized in a narrow corridor in front of the crack tip. A large plastic zone, as one would typically expect under plane stress, is not observed. Instead, strong local necking is evidenced. We conclude that the spatial confinement of the plastic deformation is the primary reason for the low fracture toughness of metallic thin film
Keywords: Fracture toughness; Thickness effect; Thin films; Bulge testing; Atomic force microscopy; Gold

Understanding the high creep resistance of mri 230d magnesium alloy through nanoindentation and atom probe tomography - Matschkal, Dorothea; Tuengerthal, Patrick; Lamm, Steffen; Göken, Mathias; Höppel, Heinz Werner; Felfer, Peter (Metals, 2021)
Due to their low density, magnesium alloys are very appealing for light-weight construc-tions. However, the use of the most common magnesium alloy, AZ91 (Mg 9 wt.% Al, 1 wt.% Zn), is limited to temperatures below 150◦ C due to creep failure. Several alloys with an improved creep resistance have been developed in the past, for example the alloy MRI 230D or Ca-alloyed AZ91 variants. However, there is an ongoing discussion in the literature regarding the mechanisms of the improved creep resistance. One factor claimed to be responsible for the improved creep resistance is the intermetallic phases which form during casting. Another possible explanation is an increased creep resistance due to the formation of precipitates. To gain more insight into the improved creep resistance of MRI 230D, nanoindentation measurements have been performed on the different phases of as-cast, creep-deformed and heat-treated samples of MRI 230D and Ca-alloyed AZ91 variants. These nanoindentation measurements clearly show that the intermetallic phase (IP) of the alloy MRI 230D does not lose strength during creep deformation in contrast to the Ca-alloyed AZ91 variants. High-temperature nanoindentation measurements performed at 200◦ C clearly show that the intermetallic phases of the MRI 230D alloy maintain their strength. This is in clear contrast to the Ca-alloyed AZ91 variants, where the IP is significantly softer at 200◦ C than at room temperature. Atom probe measurements have been used to gain insight into the differences in terms of chemical composition between the IPs of MRI 230D and the Ca-alloyed AZ91 variants in order to understand the dissimilar behaviour in terms of strength loss with increasing temperature.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Atom probe tomography; Creep; Intermetallic phase; Magnesium alloy; Mechanical properties; Nanoindentation

Understanding the mechanical behavior of nanocrystalline Al-O thin films with complex microstructures - He, Mo-Rigen; Felfer, Peter; Dasgupta, Suman; Samudrala, Saritha K.; Malone, Patrick J.; Feng, Gang; Hemker, Kevin J.; Cairney, Julie M.; Gianola, Daniel S. (Acta Materialia, 2014)
The mechanical behavior of nanocrystalline (NC) metals has attracted widespread interest, though the majority of efforts have focused on (nominally) pure metals. By comparison, the mechanisms of deformation and strengthening in NC alloys, especially those with high segregation propensity and strong chemical interactions, are less well understood. Here we present a quantitative investigation on the mechanical behavior of such an alloy system. NC Al-O thin films are synthesized by means of confocal co-sputtering, which enables a wide-range and quasi-independent control over impurity content and grain size. Detailed characterization combining transmission electron microscopy with three-dimensional atom probe tomography identify the multiple morphologies of O impurities in a composite-like microstructure, including nanosized α-AlO precipitates, O-rich clusters segregated along grain boundaries, and O solute atoms inside Al grains. Individual contributions of these strengthening features to the mechanical properties of NC Al-O thin films, as measured by instrumented nanoindentation, are then well delineated by a microstructure-informed analytical model. Dislocations emitted from grain boundaries are pinned by the stronger obstacles and cut through the weaker, and we show that the strong chemical interactions of this Al-O system play a dominant role in its pronounced strengthening capability. The influence of O impurities on the plasticity and deformation mechanisms in NC Al films is also discussed based on microtensile testing. © 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Alloys; Atom probe tomography; Nanocrystalline; Strengthening mechanisms; Thin films

Understanding the protective ability of the native oxide on an Fe-13 at% Cr alloy at the atomic scale: A combined atom probe and electron microscopy study - Sasidhar, K.N.; Khanchandani, Heena; Zhang, Siyuan; Kwiatkowski da Silva, Alisson; Scheu, Christina; Gault, Baptiste; Ponge, Dirk; Raabe, Dierk (Corrosion Science, 2023)
Keywords: Atom probe tomography; Correlative microscopy; Thermodynamics; Native oxide; Stainless steel

Unraveling the orientation-dependent mechanics of dental enamel in the red-necked wallaby - Wilmers, Jana; Wurmshuber, Michael; Gescher, Christoph; Graupp, Celine-Michele; Kiener, Daniel; Bargmann, Swantje (Acta Biomaterialia, 2024)
Dental enamels of different species exhibit a wide variety of microstructural patterns that are attractive to mimic in bioinspired composites to simultaneously achieve high stiffness and superior toughness. Non-human enamel types, however, have not yet received the deserved attention and their mechanical behaviour is largely unknown. Using nanoindentation tests and finite element modelling, we investigate the mechanical behaviour of Macropus rufogriseus enamel, revealing a dominating influence of the microstructure on the effective mechanical behaviour and allowing insight into structural dependencies. We find a shallow gradient in stiffness and low degree of anisotropy over the enamel thickness that is attributed to the orientation and size of microstructural features. Most notably, M. rufogriseus’s modified radial enamel has a far simpler structural pattern than other species’, but achieves great property amplification. It is therefore a very promising template for biomimetic design.<br

Untersuchung des tribologisch-mechanischen Verhaltens amorpher Kohlenstoffschichten mittels Load Scanner - Wartzack, Sandro; Pejic, Goran; Durst, Karsten; Schaufler, Jens; Hetzner, Harald; Tremmel, Stephan (2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.unters

Untersuchung von mikrostrukturellen Einflussgrößen auf das Reibermüdungsverhalten und auf die Schädigungsmechanismen am Beispiel von Eisenbasislegierungen - Höppel, Heinz Werner; et al. (10. Roell Amsler Symposium 2003, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IW.LWAW.unters

Using Rapid Thermal Annealing for Studying Early Stages of High-Temperature Oxidation of Superalloys - Kubacka, Dorota; Eggeler, Yolita; Volz, Nicklas; Neumeier, Steffen; Spiecker, Erdmann (Springer International Publishing, 2020)
The great potential of Rapid Thermal Annealing (RTA)Rapid Thermal Annealing (RTA), a widespread technique in semiconductor technology, for studying high-temperature properties of superalloys is demonstrated. As an application example, early stages of high-temperature oxidationOxidationof Co/Ni-base superalloysCo/Ni-base superalloysare investigated. Model alloys with different Co/Ni ratio are oxidized in synthetic dry air at 900 °C to understand the differences between the oxidationOxidationbehavior of Ni- and Co-base alloys. Upon short exposure times (below 64 s), the two-phase γ/γ′ microstructure has a pronounced influence on both the morphology and growth kinetics of Al2O3 precipitates. Depending on the base element, Al2O3 nucleates in either the γ′ phase in the form of needles (Ni-base superalloy) or in the γ matrix as lath- and plate-like precipitates (Co-base superalloy) with the latter showing much slower formation kinetics. Observed differences in oxidationOxidationbehavior can be directly correlated to changes in the partitioning of W, which acts as a γ former in Ni- and a γ′ former in Co-base superalloys. We propose that a significant amount of W in γ′ has an inhibitory effect on the diffusionDiffusionof Al, suppressing the formation of Al2O3 in the γ′ phase of Co-base superalloys. Our approach proved to be very successful for oxidationOxidationstudies and opens up new opportunities for superalloys research.

Using scrap in recycling alloys for structural applications in the automotive industry - Fragner, Werner; Baumgartner, Kurt; Suppan, Helmut; Hummel, Marc; Bösch, Dominik; Höppel, Heinz Werner; Uggowitzer, Peter J. (Light Metals 2014 - TMS 2014 Annual Meeting and Exhibition, 2014)
Keywords: Recycling; Scrap; Alloy optimization; Light weight design; Die casting

Using Selective Electron Beam Melting to Enhance the High-Temperature Strength and Creep Resistance of NiAl–28Cr–6Mo In Situ Composites - Förner, Andreas; Vollhüter, Jan; Krapf, Anna; Jamjoom, Abdullah Faisal A; Hausmann, Daniel; Wahlmann, Benjamin; Fu, Zongwen; Körner, Carolin; Neumeier, Steffen; Göken, Mathias (Advanced Engineering Materials, 2023)
By increasing the density of interfaces in NiAl–CrMo in situ composites, the mechanical properties can be significantly improved compared to conventionally cast material. The refined microstructure is achieved by manufacturing through electron beam powder bed fusion (PBF-EB). By varying the process parameters, an equiaxed or columnar cell morphology can be obtained, exhibiting a plate-like or an interconnected network of the (Cr,Mo) reinforcement phase which is embedded in a NiAl matrix. The microstructure of the different cell morphologies is investigated in detail using scanning electron microscope, transmission electron microscopy, and atom probe tomography. For both morphologies, the mechanical properties at elevated temperatures are analyzed by compression and creep experiments parallel and perpendicular to the building direction. In comparison to cast NiAl and NiAl–(Cr, Mo), the yield strength of the PBF-EB fabricated specimens is significantly improved at temperatures up to 1,027 °C. While the columnar morphology exhibits the best improved mechanical properties at high temperatures, the equiaxial morphology shows nearly ideal isotropic mechanical behavior, which is a substantial advantage over directionally solidified material.
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; creep properties; high-temperature strength; in situ composite; intermetallics; NiAl

Verification of a commercial CALPHAD database for Re and Ru containing nickel-base superalloys - Rettig, Ralf; Heckl, Astrid; Neumeier, Steffen; Pyczak, F.; Göken, Mathias; Singer, Robert (Defect and Diffusion Forum, 2009)
The addition of rhenium and ruthenium to single crystal nickel-base superalloys improves the high-temperature properties of the alloys. In this work the applicability of the database TTNi7 (ThermoTech Ltd, UK) for developing 4 generation single crystal superalloys containing rhenium (Re) and ruthenium (Ru) was investigated. We systematically compared experimentally determined alloy properties to the predictions of ThermoCalc with the database TTNi7. The investigated properties were liquidus, solidus and γ′ solvus temperature as well as incipient melting point and segregation. Calculations were based on thermodynamic principles with the assumption of either equilibrium or Scheil-Gulliver conditions, i.e. no diffusion in the solid and complete diffusion in the liquid. Furthermore the composition of the γ and the γ′ phase of a Re- and Ru-containing superalloy was measured and compared to calculations. Our results show that the database is capable of simulating general trends of 4 generation superalloys up to 6 weight percent (wt.-%) Re and 6 wt.-% Ru. The present work shows that Scheil-Gulliver calculations can only be used as a first approximation for nickel-base superalloys. © (2009) Trans Tech Publication
Keywords: CALPHAD; Database; Modelling; Rhenium; Ruthenium; Scheil-Gulliver; Single crystal; Superalloys; ThermoCalc

Visualization Aided Interface Reconstruction - Penk, Dominik; Müller, Jonas; Felfer, Peter; Grosso, Roberto; Stamminger, Marc (VMV 2020, 25th International Symposium on Vision, Modeling, and Visualization, 2020)
Modern atom probe tomography measurements generate large point clouds of atomic locations in solids. A common analysis task in these datasets is to put the location of specific atom types in relation to crystallographic features such as the interface between two crystals (grain boundaries). In cases where these features represent surfaces, their extraction is carried out manually in most cases. In this paper we propose a method for semi automatic extraction of such two dimensional manifold and non-manifold surfaces from a given dataset. We first aid the user to filter the atom data by providing an interactive visualization of the dataset tailored towards enhancing these interfaces. Once a desired set of points representing the interface is found, we provide an automatic surface extraction method to compute an explicit parametric representation of the visualized surface. In case of non-manifold interface structures, this parametric representation is then used to calculate the intersections of the individual manifold parts of the interfaces.<br

Visualizing oxygen transport pathways during intergranular oxidation in Ni-Cr - Weiser, Martin; Olszta, Matthew J.; Engelhard, Mark H.; Zhu, Zihua; Schreiber, Daniel K. (npj Materials Degradation, 2023)
The transport paths of O during intergranular oxidation in binary Ni-Cr were investigated. To isolate the selective oxidation of Cr, oxidation was performed with a CO/CO2 gas mixture in which the oxygen partial pressure was kept under the NiO dissociation pressure. A combination of electron microscopy and atom probe tomography (APT) was used to study the nanometer-scale details of the passivation and penetrative intergranular oxidation processes at high-energy grain boundaries. Oxygen transport towards the terminating oxidation front is elucidated with dedicated usage of oxygen tracer exchange experiments. Secondary ion mass spectroscopy and APT support classical theories of internal oxidation, revealing preferred transport paths at the oxide/alloy interface with sub-nanometer resolution.<br
Keywords: Corrosion; Metals and alloys

Wear Mechanism of Superhard Tetrahedral Amorphous Carbon (ta-C) Coatings for Biomedical Applications - Rothammer, Benedict; Schwendner, Michael; Bartz, Marcel; Wartzack, Sandro; Böhm, Thomas; Krauß, Sebastian; Merle, Benoit; Schroeder, Stefan; Uhler, Maximilian; Kretzer, J. P.; Weihnacht, Volker; Marian, Max (Advanced Materials Interfaces, 2023)
Tetrahedral amorphous carbon (ta-C) coatings have the potential to protect biomedical implants from wear and increase their service life. This study elucidates the biocompatibility, mechanical properties, adhesion, and wear resistance of ta-C coatings fabricated by physical vapor deposition on cobalt-chromium-molybdenum (CoCr) and titanium (Ti64) alloys as well as ultrahigh molecular weight polyethylene (UHMWPE). Satisfactory cytocompatibility is verified using contact angle and surface tension measurements as well as indirect and direct cell testing. Scratch testing demonstrates excellent adhesion to the substrates and as confirmed by nanoindentation, the coatings represent an up to 13-fold and 182-fold increase in hardness on the hard and soft materials. In metal pin-on-UHMWPE disk sliding experiments under simulated body fluid lubrication, the wear rates of the disk are reduced by 48% (against CoCr) and 73% (against Ti64) while the pin wear rates are reduced by factors of 20 (CoCr) and 116 (Ti64) compared to uncoated pairings. From optical and laser scanning microscopy, Raman measurements, and particle analyses, it is shown that the underlying substrates remain well protected. Nonetheless, focused ion beam scanning electron microscopy revealed coating process-related and thermally driven subductions as well as tribologically induced near-surface fatigue, which can potentially constitute critical wear mechanism
Keywords: biotribology; diamond-like carbon; physical vapor deposition coatings; synovial joint; total knee replacements; wear-resistance

Wedge-shaped twins and pseudoelasticity in fcc metallic nanowires under bending - Nöhring, Wolfram Georg; Möller, Johannes; Xie, Zhuocheng; Bitzek, Erik (Extreme Mechanics Letters, 2016)
WW1::1079
Keywords: Simulation and Modeling

XRD profile analysis characterization of ultrafine grained Al-Mg alloys - Dinkel, Markus; Pyczak, Florian; May, Johannes; Höppel, Heinz Werner; Göken, Mathias (Journal of Materials Science, 2008)
WW1::793

Yielding behavior of a single-crystalline γ'-strengthened Co-Ti-Cr superalloy - Bezold, Andreas; Volz, Nicklas; Lenz, Malte; Zenk, Christopher; Spiecker, Erdmann; Mills, M. J.; Göken, Mathias; Neumeier, Steffen (Scripta Materialia, 2021)
The anomalous yielding behavior known from Ni3Al or Ni-base superalloys is explained by the formation of immobile dislocation configurations via cross-slip of the leading superpartial of anti-phase boundary-coupled dislocation pairs. A systematic investigation of the anomalous yielding behavior of a single-crystalline Co-11Ti-15Cr superalloy by transmission electron microscopy revealed the absence of similar sessile dislocation configurations during the initial yielding stage. Shearing of γ' precipitates via superlattice stacking fault formation is the dominant deformation mechanism at the peak temperature. Furthermore, the high density of superlattice stacking faults and their interactions also lead to a pronounced work-hardening anomaly.
Keywords: Superalloy; yield strength anomaly; work hardening; transmission electron microscopy (TEM); high-temperature deformation

110 planar faults in strained bcc metals: Origins and implications of a commonly observed artifact of classical potentials - Möller, Johannes; Mrovec, Matous; Bleskov, Ivan; Neugebauer, Joerg; Hammerschmidt, Thomas; Drautz, Ralf; Elsaesser, Christian; Hickel, Tilmann; Bitzek, Erik (Physical Review Materials, 2018)
Large-scale atomistic simulations with classical potentials can provide valuable insights into microscopic deformation mechanisms and defect-defect interactions in materials. Unfortunately, these assets often come with the uncertainty of whether the observed mechanisms are based on realistic physical phenomena or whether they are artifacts of the employed material models. One such example is the often reported occurrence of stable planar faults (PFs) in body-centered cubic (bcc) metals subjected to high strains, e.g., at crack tips or in strained nano-objects. In this paper, we study the strain dependence of the generalized stacking fault energy (GSFE) of 110 planes in various bcc metals with material models of increasing sophistication, i.e., (modified) embedded atom method, angular-dependent, Tersoff, and bond-order potentials as well as density functional theory. We show that under applied tensile strains the GSFE curves of many classical potentials exhibit a local minimum which gives rise to the formation of stable PFs. These PFs do not appear when more sophisticated material models are used and have thus to be regarded as artifacts of the potentials. We demonstrate that the local GSFE minimum is not formed for reasons of symmetry and we recommend including the determination of the strain-dependent (110) GSFE as a benchmark for newly developed potentials.

A Bela Melusina - Rautenberg, Ursula (Livro : revista do Núcleo de Estudos do Livro e da Edição, 2013)
BUCHWISS::art-257

Ab initio investigation of diamond coatings on steel - Boehner, Andreas; Janisch, Rebecca; Hartmaier, Alexander (Scripta Materialia, 2009)
WW1::795

Alumina effect on the structure and properties of calcium aluminosilicate in the percalcic region: A molecular dynamics investigation - Atila, Achraf; Ghardi, El Mehdi; Hasnaoui, Abdellatif; Ouaskit, Said (Journal of Non-Crystalline Solids, 2019)
We rely on molecular dynamics simulations to investigate and discuss the effect of alumina content on the thermodynamic, elastic and structural properties of calcium aluminosilicate glasses in the light of available experimental data. The alumina content varies from low to intermediate ranges by considering compositions of (CaO [sbnd] SiO2)(1−x)(Al2O3)x where x = 0–30 mol%. The glass transition temperature was found by referring to the concept of inherent structure energy while elastic properties were computed using two methods: the first is via molecular statics using energy minimization and the second one by performing molecular dynamics at a finite temperature. We suggest a correlation between structural changes, mechanical properties and glass transition temperature, through an analysis of the short and medium range orders. The results show that by increasing Al2O3 content, an increase in the population of bridging oxygens and oxygen tricluster is observed while free oxygens tend to vanish. Regions with rich Al [sbnd] O [sbnd] Al linkages start to appear as shown by the aluminium avoidance parameter, which is also accompanied with an increase of the glass transition temperature and elastic moduli.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Aluminium avoidance parameter; Calcium aluminosilicate; Elastic properties; Glass transition; Molecular dynamics

Analyzing crack-tip dislocations and their shielding effect on fracture toughness - Higashida, K.; Tanaka, Masaki; Hartmaier, Alexander; Hoshino, Y. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2008)
WW1::751

A simple dislocation model of the influence of high-angle boundaries on the deformation behavior of ultrafine-grained materials - Blum, Wolfgang; Eisenlohr, Philip (Journal of Physics : Conference Series, 2010)
WW1::832

Atomistic aspects of fracture - Bitzek, Erik; Kermode, James R.; Gumbsch, Peter (International Journal of Fatigue, 2015)
Any fracture process ultimately involves the rupture of atomic bonds. Processes at the atomic scale therefore critically influence the toughness and overall fracture behavior of materials. Atomistic simulation methods including large-scale molecular dynamics simulations with classical potentials, density functional theory calculations and advanced concurrent multiscale methods have led to new insights e.g. on the role of bond trapping, dynamic effects, crack-microstructure interactions and chemical aspects on the fracture toughness and crack propagation patterns in metals and ceramics. This review focuses on atomistic aspects of fracture in crystalline materials where significant advances have been achieved over the last ten years and provides an outlook on future perspectives for atomistic modelling of fracture.
WW1::1020

Atomistic insights into the impact of charge balancing cations on the structure and properties of aluminosilicate glasses - Atila, Achraf; Ghardi, El Mehdi; Ouaskit, Said; Hasnaoui, A. (Physical Review B, 2019)
Ternary aluminosilicate glasses are of great interest in glass and earth sciences. The structural role of the non-network cations is not fully understood until now. Understanding the structural effect of the non-network cations is necessary for explaining their impact on the macroscopic properties of aluminosilicate glasses. In this work, we use molecular dynamics to investigate physical properties of a series of charge balanced aluminosilicate glasses. Elastic properties and the glass transition temperature were calculated. Our results are in accordance with the experimental data found in the literature. We found that elastic moduli increase with the charge balancing cations field strength (FS), while the glass transition temperature is negatively correlated to FS. The effect of the charge balancing cations field strength on the calculated properties is discussed and explained using the change in the structural properties, energetic environment of atoms, and two-body excess entropy. This allows us to get an overview of the effect of cations nature on the properties of the glass.
CRIS-Team WoS Importer:2019-11-15

Atomistic simulation of dislocation-void interactions under cyclic loading - Cheng, Y.; Bitzek, Erik; Weygand, Daniel; Gumbsch, Peter (Modelling and Simulation in Materials Science and Engineering, 2010)
WW1::833

Atomistic Simulations of Compression Tests on Ni3Al Nanocubes - Amodeo, Jonathan; Begau, C.; Bitzek, Erik (Materials Research Letters, 2014)
The deformation behaviour of nano-sized Ni3Al cubes with 100 side surfaces is investigated under uniaxial compression using constant-temperature molecular dynamics simulations at 300 K. The simulations reproduce key features of recently performed nanocompression experiments, namely the lack of strain hardening, homogeneous deformation of the entire sample and overall high stress levels of the order of 3-5 GPa. According to the simulations, the critical initial step is the formation of a pseudo-twin structure, which then further deforms by Shockley partial dislocations. These deformation mechanisms differ significantly from bulk Ni3Al and are rationalized in terms of generalized stacking fault energies and resolved shear stresses.
Keywords: Small-Scale Plasticity; MD Simulations; Ni3Al; Dislocations; Twinning

A tribute to Claude Bathias – Highlights of his pioneering work in Gigacycle Fatigue - Mughrabi, Hael; Antolovich, Stephen D. (International Journal of Fatigue, 2016)
WW1::1085

BDA: A novel method for identifying defects in body-centered cubic crystals - Möller, Johannes; Bitzek, Erik (MethodsX, 2016)
The accurate and fast identification of crystallographic defects plays a key role for the analysis of atomistic simulation output data. For face-centered cubic (fcc) metals, most existing structure analysis tools allow for the direct distinction of common defects, such as stacking faults or certain low-index surfaces. For body-centered cubic (bcc) metals, on the other hand, a robust way to identify such defects is currently not easily available. We therefore introduce a new method for analyzing atomistic configurations of bcc metals, the BCC Defect Analysis (BDA). It uses existing structure analysis algorithms and combines their results to uniquely distinguish between typical defects in bcc metals. In essence, the BDA method offers the following features: Identification of typical defect structures in bcc metals. Reduction of erroneously identified defects by iterative comparison to the defects in the atom's neighborhood. Availability as ready-to-use Python script for the widespread visualization tool OVITO [http://ovito.org
Keywords: Atomistic simulations; bcc materials; Defectanalysis; Molecular dynamics

Close up on crystal plasticity - Mughrabi, Hael; Ungár, Tamas (Nature Materials, 2006)
A novel X-ray diffraction technique opens the way to investigate deformation-induced dislocation microstructures with submicrometre resolution.<br

Combining atomistic simulation and x-ray diffraction for the characterization of nanostructures: A case study on fivefold twinned nanowires - Niekiel, Florian; Bitzek, Erik; Spiecker, Erdmann (Acs Nano, 2014)
Recent progress in achieving high degrees of monodispersity in chemical synthesis of complex nanostructures creates the unique situation in which individual nanostructures become representative for the whole ensemble. Under these conditions, atomistic simulations can play a completely new role in interpreting structural data obtained from averaging techniques. We apply this approach to fivefold twinned Ag nanowires for which the existence of an ambient-stable tetragonal phase in the nanowire core has been recently proposed. Quantitative comparison of experimental X-ray diffraction data with atomistic calculations unequivocally shows that the diffractograms can be fully explained by the complex strain state and defect structure of fivefold twinned Ag nanowires with fcc crystal structure. In addition, our approach enables rapid and accurate determination of wire diameters by a modified Scherrer analysis which uses a database generated by atomistic simulations. © 2014 American Chemical Societ
Keywords: atomistic simulation; disclination; fivefold twinned nanowires; X-ray diffraction

Comment on 'Constant intermittent flow of dislocations: Central problems in plasticity' by L. M. Brown - Mughrabi, Hael (Journal of Materials Science & Technology, 2014)
WW1::990

Computational insights into the structure of barium titanosilicate glasses - Ghardi, El Mehdi; Atila, Achraf; Badawi, Michael; Hasnaoui, Abdellatif; Ouaskit, Said (Journal of the American Ceramic Society, 2019)
Understanding the role of TiO2 in BaO-TiO2-SiO2 (BTS) glasses is one of the keys to develop new glasses and glass-ceramics for different technological applications. For the first time, molecular dynamics simulations were conducted to get new insights into the atomic structure of the BTS glasses and their elastic moduli. Various compositions are studied where SiO2 have been replaced by TiO2. The calculated mechanical properties of our models are observed to depend linearly on TiO2 content. However, the structure-induced changes are far from such dependence. The structural results indicate that BTS glasses are mainly built on four types of basic units: SiO4, TiO4, TiO5 and TiO6. This high structural heterogeneity induced by the three coordination states of Ti is found to have an impact on the medium range order by increasing the rings number, the polymerized regions, and by transforming Q3-Q4 and Q2 without neglecting the increase in Q5 and Q6 species. Those structural modifications of the BTS glass network features have been found to be consistent with available experimental data.
CRIS-Team Scopus Importer:2019-06-04
Keywords: BaO-TiO; elastic properties; molecular dynamics; structural properties; titanosilicate glass

Controlled Evolution of Coincidence Site Lattice Related Grain Boundaries - Vaid, Aviral; Mittal, Kalpi; Sahu, Sandeep; Shekhar, Shashank (Transactions of the Indian Institute of Metals, 2016)
Modification in grain boundary character distribution has been known to improve the functional and mechanical properties of low stacking fault energy, face centered cubic materials. In this work, thermomechanical processing has been employed on nickel alloy using iterative and single-step, non-iterative routes to gain an insight into the role of processing path on the generation of low-σ coincidence site lattice (CSL) boundaries. A low amount of strain ( 4 %) has been used in iterative processing in order to obtain CSL boundaries with less deviation. Evolution of σ1 and σ3 boundaries showed different trends during iterative and non-iterative processing. Also, iterative processing resulted in low-σ CSL fraction (σ ≤ 29) as high as 0.9 consisting of significant fraction from both σ1 and σ3 boundaries. Non-iterative processing yielded low-σ CSL fraction of 0.73 but with significant contribution only from σ3 boundarie
Keywords: Coincidence site lattice; Electron back scattered diffraction; Grain boundary character distribution; Inconel 600 alloy; Thermomechanical processing

Controlling the diameter of aligned single-walled carbon nanotubes on quartz via catalyst reduction time - Schweiger, Manuel; Schaudig, Maximilian; Gannott, Florentina; Killian, Manuela; Bitzek, Erik; Schmuki, Patrik; Zaumseil, Jana (Carbon, 2015)
One of the main objectives of chemical vapor deposition (CVD) growth of single-walled carbon nanotubes (SWCNT) is control over their diameter and type (metallic or semiconducting). Here, we investigate the evolution of iron catalyst particles on quartz substrates depending on the duration of the reduction step with hydrogen and its effect on the growth of horizontally aligned SWCNT. We find a strong dependence of catalyst particle size and size distribution on the initial iron film thickness and the reduction time at 630 °C. Initial decrease of the particle size is followed by an unexpected increase. Statistical analysis of the Raman radial breathing modes of the SWCNT over large areas gave reliable and reproducible diameter distributions that correlated directly with the catalyst particle size distributions. By changing the reduction time it was possible to reproducibly shift the average SWCNT diameter from 1.5 (±0.3) nm to 1.2 (±0.2) nm while maintaining a nanotube density of 5–6 SWCNT/ extgreekmm. In order to describe the evolution of the particle size during the reduction process at this particular temperature, we propose a model that includes the diffusion of iron into the quartz and its re-emergence.
WW1::1053
Keywords: Simulation and Modeling

Correct Interpretation of Creep Rates: A Case Study of Cu - Blum, Wolfgang; Dvorak, J.; Kral, P.; Eisenlohr, Philip; Sklenicka, V. (Journal of Materials Science & Technology, 2015)
WW1::1050
Keywords: Creep and Fatigue

Corrigendum to “A simple dislocation model of deformation resistance of ultrafine-grained materials explaining Hall-Petch strengthening and enhanced strain rate sensitivity” (Acta Materialia (2009) 57 (1966-1974)) - Blum, Wolfgang; Zeng, X. H. (Acta Materialia, 2011)
WW1::912
Keywords: Creep and Fatigue; Simulation and Modeling; Nanomaterials

Cyclic slip irreversibilities and the evolution of fatigue damage - Mughrabi, Hael (Metallurgical and Materials Transactions B-Process Metallurgy and Materials Processing Science, 2009)
WW1::799

Cyclic slip irreversibility and fatigue life: A microstructure-based analysis - Mughrabi, Hael (Acta Materialia, 2013)
The evolution of fatigue damage is intimately related to different types of more or less pronounced irreversible cyclic slip, associated with gradual permanent microstructural and topological changes which ultimately can cause fatigue failure. Only in a few cases has it been possible to assess quantitatively the cyclic slip irreversibility. Based on a limited amount of available experimental data amenable to analysis, an attempt is made in this work to explore whether there exists an explicit relationship between the cyclic slip irreversibility and fatigue life. The existence of such a relationship is suggested by a microstructure-based reformulation of the Coffin-Manson fatigue life law, which involves the cyclic slip irreversibility. The analysis of the experimental data in two adequately documented cases indicates that the cyclic slip irreversibility is related very satisfactorily to fatigue life via a power law which contains two constants. These two constants can be expressed in terms of the fatigue ductility coefficient and the fatigue ductility exponent of the Coffin-Manson fatigue life law. (C) 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
WW1::957
Keywords: Cyclic deformation; Cyclic slip irreversibility; Fatigue damage; Fatigue life; Coffin-Manson fatigue life law

Cyclic strain rate effects in fatigued face-centred and body-centred cubic metals - Mughrabi, Hael (Philosophical Magazine, 2013)
WW1::958

Damage mechanisms and fatigue lives: From the low to the very high cycle regime - Mughrabi, Hael (Procedia Engineering, 2013)
WW1::959

Deformation of silicon - Insights from microcompression testing at 25-500 °c - Korte, Sandra; Barnard, J. S.; Stearn, R. J.; Clegg, W. J. (International Journal of Plasticity, 2011)
The plastic deformation of silicon and other brittle materials near room temperature has conventionally been studied under high confining pressures, although it has been suggested that these may modify the dislocation core structure. Here, the possibility of using microcompression has been studied. Using this method the yield stress of silicon micropillars was measured for different pillar diameters and between 25 and 500 °C for a constant diameter of 2 μm. No pronounced effect of size on the yield stress was found, but the transition from failure by cracking to predominately plastic deformation was shown to be consistent with a previously proposed simple model for axial splitting. Deformed specimens were analysed by transmission electron microscopy to elucidate the operative dislocation mechanisms. This showed that at 500 °C deformation occurs by twinning and formation of partial dislocations, whereas at 100 °C it is associated with micro-cracking and only weakly dissociated dislocations.
Created from Fastlane, Scopus look-up
Keywords: Ceramic material; Dislocations; Fracture; Mechanical testing; Silicon

Deformation resistance in the transition from coarse-grained to ultrafine-grained Cu by severe plastic deformation up to 24 passes of ECAP - Blum, Wolfgang; Li, Y. J.; Zhang, Y.; Wang, J. T. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2011)
WW1::868

Diffusive molecular dynamics and its application to nanoindentation and sintering - Li, Ju; Sarkar, Sanket; Cox, William T.; Lenosky, Thomas J.; Bitzek, Erik; Wang, Yunzhi (Physical Review B, 2011)
WW1::869

Diplomarbeit: Verformungswiderstand von TiAlV6 bei mittleren Temperaturen - Deserno, Frank (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2000)

Discrete dislocation dynamics simulations of surface induced size effects in plasticity - Han, Chung-Souk; Hartmaier, Alexander; Gao, Huajian; Huang, Yonggang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2006)
Experiments have shown that the presence of free surfaces may induce harder as well as softer deformation behaviors in a crystalline solid. In order to shed some light on these apparently contradictory findings, two-dimensional discrete dislocation dynamics simulations are performed to investigate the surface induced size effects. The simulations indicate that, depending on the surface density of dislocation sources, a free surface may act either as a dislocation sink or as a net dislocation source, and can accordingly exert opposite effects on dislocation density over a boundary layer thickness of up to 500nm into the bulk. This finding provides a possible explanation for the apparent contradictions in experimental observations. © 2005 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Discrete dislocation dynamics; Plasticity; Size effects; Surface effects

Discussion: Activation volumes of plastic deformation of crystals - Blum, Wolfgang (Scripta Materialia, 2018)
Two data sets reporting apparent activation volumes V-app of plastic deformation of ultrafine-grained Cu are compared. They differ strongly in magnitude and stress dependence of Vapp. It is suggested that the difference results from differences in testing method. While Vapp from stress relaxations appears to be consistent with expectations for the activation of thermally activated glide of dislocations in the bulk of the material, Vapp from rate change tests appears to characterize the quasi-stationary deformation where dynamic recovery plays a major role. This underscores the necessity to specify which of the various thermally activated subprocesses of deformation are tested. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.

Dislocation glide velocity in creep of Mg alloys derived from dip tests - Eisenlohr, Philip; Blum, Wolfgang; Milicka, K. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::802

Dislocation mechanics of creep - Blum, Wolfgang; Eisenlohr, Philip (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::803

Dynamic recovery in nanocrystalline Ni - Sun, Z.; Van Petegem, Steven; Cervellino, A.; Durst, Karsten; Blum, Wolfgang; Van Swygenhoven, H. (Acta Materialia, 2015)
WW1::1022

Effect of frequency on dielectric properties of liquid crystal doped with side-chain liquid crystalline polymer - Göken, M.; Köysal, O. (Materials Chemistry and Physics, 2011)
The frequency and applied bias voltage dependence of the dielectric properties and dielectric anisotropy of liquid crystal (LC) doped with side-chain liquid crystalline polymer (SLCP) mixture have been investigated using the admittance spectroscopy method (C-V and G/ω-V) in the frequency range of 10 kHz to 10 MHz at room temperature. The liquid crystal used in this experiment is E63. The doping material used in this study is SLCP and its concentration is ensured 1 wt % in E63. Dielectric constant (ε′), dielectric loss (ε), dielectric loss tangent (tan δ) and real and imaginary parts of electrical modulus (M′ and M″) of the E63/SLCP mixture was also calculated. Moreover, dielectric anisotropy (Δε) as a function of frequency was obtained. Results show that the values of the all dielectric parameters are strong functions of frequency and applied bias voltage. After a critical frequency, dielectric anisotropy has negative values according to p/n type changing. © 2011 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: A. Liquid crystals; C. Electronic characterization; D. Dielectric properties; D. Electrical properties

Effect of grain refinement by ECAP on creep of pure Cu - Blum, Wolfgang; Dvorak, J.; Kral, Petr; Eisenlohr, Philip; Sklenicka, V. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2014)
WW1::994

Effect of rolling-assisted deformation on the formation of an ultrafine-grained structure in a two-phase titanium alloy subjected to severe plastic deformation - Demakov, S. L.; Elkina, O. A.; Illarionov, A. G.; Karabanalov, M. S.; Popov, A. A.; Semenova, I. P.; Saitova, L. R.; Shchetnikov, N. V. (Physics of Metals and Metallography, 2008)
The effect of rolling in the temperature range 450-650°C on the fragmentation of the primary phase in a hot-rolled VT6 alloy rod preliminarily subjected to severe plastic deformation by equal-channel angular pressing at 700°C (scheme B c, the angle between the channels is 135°, 12 passes) is studied. Rolling at 450°C without preliminary ECAP is shown not to cause α-phase fragmentation and to favor intense cold working of the alloy due to multiple slip. ECAP provides partial fragmentation of the initial structure of the α phase and changes the morphology of the retained β phase: it transforms from a continuous matrix phase into separated precipitates located between α particles. This transformation activates the fragmentation of the α phase during rolling at 550°C owing to the development of twinning and polygonization processes apart from multiple slip. Both a decrease (to 450°C) and an increase (to 625-650°C) in the rolling temperature as compared to 550°C lead to the formation of a less homogeneous and fragmented structure because of weakly developed recovery and intense cold working in the former case and because of the beginning of recrystallization and the suppression of twinning in the latter case. A relation between the structure that forms upon SPD followed by rolling and the set of its properties is found. A general scheme is proposed for the structural transformations that occur during ECAP followed by rolling at various temperatures. © 2008 Pleiades Publishing, Ltd.
Created from Fastlane, Scopus look-up

Enhancement of strain-rate sensitivity and shear yield strength of a magnesium alloy processed by high-pressure torsion - Choi, In-Chul; Lee, Dong-Hyun; Ahn, Byungmin; Durst, Karsten; Kawasaki, Megumi; Langdon, Terence G.; Jang, Jae-Il (Scripta Materialia, 2015)
WW1::1023

Ermüdungsverhalten des Hartmetalls G55 Co bei Raumtemperatur - Deserno, Frank (1999)

Erratum: A simple dislocation model of deformation resistance of ultrafine-grained materials explaining Hall-Petch strengthening and enhanced strain rate sensitivity (Acta Materialia (2009) 57 (1966-1974)) - Blum, Wolfgang; Zeng, X. H. (Acta Materialia, 2011)
WW1::872

Es werde Strom - Dietrich, Simon; Trägler, Horst; Otto, Andreas (Design & Elektronik, 2007)
LFT Import::2019-07-16 (1398)

Existence of two twinning-mediated plastic deformation modes in Au nanowhiskers - Sedlmayr, Andreas; Bitzek, Erik; Gianola, Daniel S.; Richter, Gunther; Moenig, Reiner; Kraft, Oliver (Acta Materialia, 2012)
WW1::924

Fatigue, an everlasting materials problem - Still en vogue - Mughrabi, Hael (Procedia Engineering, 2010)
WW1::839

Finding activation pathway of coupled displacive-diffusional defect processes in atomistics: Dislocation climb in fcc copper - Sarkar, Sanket; Li, Ju; Cox, William T.; Bitzek, Erik; Lenosky, Thomas J.; Wang, Yunzhi (Physical Review B, 2012)
WW1::928

Fracture modes in micropillar compression of brittle crystals - Howie, Philip R.; Korte, Sandra; Clegg, William J. (Journal of Materials Research, 2012)
This article describes cracking during microcompression of Si, InAs, MgO, and MgAl 2O 4 crystals and compares this with previous observations on Si and GaAs micropillars. The most common mode of cracking was through-thickness axial splitting, the crack growing downward from intersecting slip bands in pillars above a critical size. The splitting behavior observed in all of these materials was quantitatively consistent with a previous analysis, despite the differences in properties and slip geometry between the different materials. Cracking above the slip bands also occurred either in the side or in the top surface of some pillars. The driving forces for these modes of cracking are described and compared with observations. However, only through-thickness axial splitting was observed to give complete failure of the pillar; it is, therefore, considered to be the most important in determining the brittle-to-ductile transitions that have been observed. © 2011 Materials Research Society.
Created from Fastlane, Scopus look-up
Keywords: Ceramic; Fracture; Toughness

Fracture toughness and bond trapping of grain boundary cracks - Möller, Johannes; Bitzek, Erik (Acta Materialia, 2014)
The fracture toughness of materials in which brittle cracks initiate and propagate along grain boundaries (GBs) depends not only on the energy of the GB, but also on its microscopic structure. Exactly how and to what degree brittle GB fracture is affected by the local atomic structure at the crack tip has not yet been studied in detail. Here, we use molecular static simulations to study the atomic-scale fracture behavior of six large-angle tilt GBs in tungsten bicrystals. The fracture toughness depends critically on the propagation direction and on the position of the crack tip within the structural units of the GB. Furthermore, the GB fracture toughness can be significantly larger than for single crystals in the same orientation. These results cannot be explained by the usual thermodynamic approach in continuum-scale fracture mechanics but can be understood by considering the effect of bond trapping of GB cracks. © 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Atomistic simulation; Bond trapping; Fracture; Grain boundary; Tungsten

Fracture toughness of layered structures: Embrittlement due to confinement of plasticity - Broedling, Nils C.; Hartmaier, Alexander; Gao, Huajian (Engineering Fracture Mechanics, 2008)
WW1::766

Großbritannien - Sturm, Roland (Informationen zur politischen Bildung, 2008)
UnivIS-Import:2015-03-09:Pub.2008.phil.dsp.ipowi.lpowi1.grobri

Harper-Dorn creep - Kassner, Michael E.; Kumar, Praveen; Blum, Wolfgang (International Journal of Plasticity, 2007)
The fundamental mechanism of time-dependent plasticity, or creep, of crystalline materials at very low stress is, at present, particularly controversial. At "moderate" stresses above about 0.6 Tm, over a wide range of stresses, five-power-law creep is observed that is widely believed to be dislocation climb-controlled, with the activation energy for creep to be close to that of vacancy diffusion. Steady-state creep (Stage II or secondary creep) is usually described by the steady-state stress exponent, n, which is typically 4-7. At lower stresses, Harper-Dorn has usually been the mechanism suggested to occur. The relation between the applied stress and the steady-state creep-rate for Harper-Dorn creep is phenomenologically described byover(ε, ̇)ss = AHD fenced(frac(Dsd Gb, kT)) fenced(frac(σ, G))1where AHD is a constant. Since these early observations, Harper-Dorn creep has been reported to occur in many materials. Recent observations have suggested that in Al (the most extensively studied system) and all other systems, Harper-Dorn may be artificial in that the high creep rates may be a consequence of additional or unusual restoration mechanisms that do not normally occur in five-power-law creep or tensile fracture. These restoration mechanisms include dynamic recrystallization and/or grain growth. Others have suggested that Harper-Dorn is also artificial but because the strain-rates reported were not genuinely steady-state and, consequently, as much as an order of magnitude higher than genuine steady-state behavior. Others also found that they could not reproduce the original Al data of Harper and Dorn, for unknown reasons. The analysis of other materials in which Harper-Dorn has been proposed to occur has been placed in question. © 2006 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Ceramics; Creep; Harper-Dorn

Heterostructured materials: superior properties from hetero-zone interaction - Zhu, Yuntian; Ameyama, Kei; Anderson, Peter M.; Beyerlein, Irene J.; Gao, Huajian; Kim, Hyoung Seop; Lavernia, Enrique; Mathaudhu, Suveen; Mughrabi, Hael; Ritchie, Robert O.; Tsuji, Nobuhiro; Zhang, Xiangyi; et al. (Materials Research Letters, 2021)
Heterostructured materials are an emerging class of materials with superior performances that are unattainable by their conventional homogeneous counterparts. They consist of heterogeneous zones with dramatic (>100%) variations in mechanical and/or physical properties. The interaction in these hetero-zones produces a synergistic effect where the integrated property exceeds the prediction by the rule-of-mixtures. The heterostructured materials field explores heterostructures to control defect distributions, long-range internal stresses, and nonlinear inter-zone interactions for unprecedented performances. This paper is aimed to provide perspectives on this novel field, describe the state-of-the-art of heterostructured materials, and identify and discuss key issues that deserve additional studies.
CRIS-Team Scopus Importer:2020-10-09
Keywords: back stress; forward stress; hetero-deformation induced (HDI) hardening; Heterostructured materials; heterostructures; synergy

High temperature microcompression and nanoindentation in vacuum - Korte, Sandra; Stearn, Robert J.; Wheeler, Jeffrey M.; Clegg, William J. (Journal of Materials Research, 2012)
In small-scale testing at elevated temperatures, impurities in inert gases can pose problems so that testing in vacuum would be desirable. However, previous experiments have indicated difficulties with thermal stability and instrument noise. To investigate this, measurements of the temperature changes in a modified nanoindenter have been made and their influence on the displacement and load measurements is discussed. It is shown that controlling the temperatures of the indenter tip and the sample enabled flat punch indentations of gold, a good thermal conductor, to be carried out over several minutes at 665 °C in vacuum, as well as permitting thermal stability to be quickly re-established in site-specific microcompression experiments. This allowed compression of nickel superalloy micropillars up to sample temperatures of 630 °C with very low levels of oxidation after 48 h. Furthermore, the measured Young moduli, yield and flow stresses were consistent with literature data. © 2011 Materials Research Society.
Created from Fastlane, Scopus look-up
Keywords: Au; Nanoindentation; Stress/strain relationship

Impact of twin boundaries on bulk elastic constants: Density-functional theory data for Young's modulus of Ag - Klöffel, Tobias; Bitzek, Erik; Meyer, Bernd (Data in Brief, 2015)
Experimental and theoretical studies on nanowires have reported a size-dependence of the Young's modulus in the axial direction, which has been attributed to the increasing influence of surface stresses with decreasing wire diameter. Internal interfaces and their associated interface stresses could lead to similar changes in the elastic properties. In Kobler et al., however, we reported results from atomistic calculations which showed for Ag that twin boundaries have a negligible effect on the Young's modulus. Here, we present data of density-functional theory calculations of elastic constants and Young's modulus for defect-free bulk Ag as well as for bulk Ag containing dense arrays of twin boundaries. It is shown that rigorous convergence tests are required in order to be able to deduce changes in the elastic properties due to bulk defects in a reliable way.
WW1::1026

Impurity levels and fatigue lives of pseudoelastic NiTi shape memory alloys - Rahim, M.; Frenzel, Jan; Frotscher, M.; Pfetzing-Micklich, J.; Steegmueller, R.; Wohlschloegel, M.; Mughrabi, Hael; Eggeler, Gunther (Acta Materialia, 2013)
WW1::966

Influence of anisotropic elasticity on the mechanical properties of fivefold twinned nanowires - Niekiel, Florian; Spiecker, Erdmann; Bitzek, Erik (Journal of the Mechanics and Physics of Solids, 2015)
Previous atomistic simulations and experiments have shown an increased Young's modulus and yield strength of fivefold twinned (FT) face-centered cubic metal nanowires (NWs) when compared to single crystalline (SC) NWs of the same orientation. Here we report the results of atomistic simulations of SC and FT Ag, Al, Au, Cu and Ni NWs with diameters between 2 and 50 nm under tension and compression. The simulations show that the differences in Young's modulus between SC and FT NWs are correlated with the elastic anisotropy of the metal, with Al showing a decreased Young's modulus. We develop a simple analytical model based on disclination theory and constraint anisotropic elasticity to explain the trend in the difference of Young's modulus between SC and FT NWs. Taking into account the role of surface stresses and the elastic properties of twin boundaries allows to account for the observed size effect in Young's modulus. The model furthermore explains the different relative yield strengths in tension and compression as well as the material and loading dependent failure mechanisms in FTNWs. (C) 2015 Elsevier Ltd. All rights reserve
Keywords: Fivefold twinning; Numerical algorithms; Anisotropic material; Microstructures; Strengthening and mechanisms

Influence of Atomic-scale Heterogeneties on Fracture Behavior of B2 NiAl - Baranova, Polina; Bitzek, Erik (14th International Conference on Fracture (ICF 14), 2017)

In Memoriam Claude Bathias 1938–2015 - Antolovich, Stephen D.; Mughrabi, Hael (International Journal of Fatigue, 2016)
WW1::1082

In situ mechanical quenching of nanoscale silica spheres in the transmission electron microscope - Mackovic, Mirza; Niekiel, Florian; Wondraczek, Lothar; Bitzek, Erik; Spiecker, Erdmann (Scripta Materialia, 2016)
A novel approach for in situ mechanical quenching experiments of nanoscale silica spheres inside the transmission electron microscope is presented. Electron irradiation is used to mimic temperature by mediating plastic flow. Quenching under load is achieved by switching-off the electron beam. This is employed in different loading scenarios. Complementary finite element method simulations underline a change of Young's modulus, which strongly depends on the interplay of electron irradiation and mechanical load. We attribute the reduction in Young's modulus to compression-induced structural anisotropy which is frozen-in by rapid quenching and propose a model on how structural anisotropy develops in nanoscale silic
Keywords: Amorphous materials; Compression test; In situ mechanical testing; Silica glass; Transmission electron microscopy

In situ study of microstructure and strength of severely predeformed pure Cu in deformation at 573K - Blum, Wolfgang; Dvorak, J.; Kral, P.; Petrenec, M.; Eisenlohr, Philip; Sklenicka, V. (Philosophical Magazine, 2015)
WW1::1052
Keywords: Nanomaterials

In situ TEM observations of reverse dislocation motion upon unloading in tensile-deformed UFG aluminium - Mompiou, Frederic; Caillard, Daniel; Legros, Marc; Mughrabi, Hael (Acta Materialia, 2012)
WW1::934

In situ TEM observations of reverse dislocation motion upon unloading of tensile-deformed UFG aluminium - Mompiou, F.; Legros, M.; Caillard, D.; Mughrabi, Hael (Journal of Physics : Conference Series, 2010)
WW1::841

Interpretation of unloading tests on nanocrystalline Cu in terms of two mechanisms of deformation - Blum, Wolfgang; Eisenlohr, Philip; Hu, Jiangjiang (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2016)
WW1::1064

Ionic self-diffusion and the glass transition anomaly in aluminosilicates - Atila, Achraf; Ouaskit, Said; Hasnaoui, Abdellatif (Physical Chemistry Chemical Physics, 2020)
The glass transition temperature (Tg) is the temperature after which a supercooled liquid undergoes a dynamical arrest. Usually, glass network modifiers (e.g., Na2O) affect the behavior of Tg. However, in aluminosilicate glasses, the effect of different modifiers on Tg is still unclear and shows an anomalous behavior. Here, based on molecular dynamics simulations, we show that Tg decreases with increasing charge balancing cation field strength (FS) in the aluminosilicate glasses, which is an anomalous behavior as compared to other oxide glasses. The results show that the origins of this anomaly come from the dynamics of the supercooled liquid above Tg, which in turn is correlated to pair excess entropy. Our results deepen our understanding of the effect of different modifiers on the properties of the aluminosilicate glasses.
CRIS-Team Scopus Importer:2020-08-21

Kafkas Tiere - Ortlieb, Cornelia (Zeitschrift für deutsche Philologie, 2007)

Life time and cyclic slip of copper in the VHCF regime - Stanzl-Tschegg, Stefanie; Mughrabi, Hael; Schoenbauer, Bernd (International Journal of Fatigue, 2007)
Studies were performed on the fatigue properties of polycrystalline copper at very low cyclic stress amplitudes and very high numbers of cycles. The experiments were carried out with the time-saving ultrasonic fatigue technique. Thus, experiments up to more than 1010 cycles could be performed within reasonable testing time. Main result is that below the PSB threshold, irreversible cyclic slip along crystallographic planes still occurs, as evidenced by changes in the surface slip line pattern down to strain and stress amplitudes that are as low as approximately only half of the PSB threshold values. These values are named SB (slip band) thresholds. No fatigue limit in the conventional sense could be detected below 1 × 1010 cycles. Thus, a threshold value at 1 × 1010 cycles is defined (named fatigue life threshold in this study) which is roughly 50% higher than the PSB threshold. The question whether the SBs are actually PSBs or whether continued cycling below the PSB threshold would ultimately lead to PSB formation and finally failure after extremely long testing has to be answered in future studies. © 2007 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Fatigue limit; Irreversible slip; Persistent slip band (PSB); Surface roughness; Very high cycle fatigue (VHCF)

Mechanisms of creep deformation in steel - Blum, Wolfgang (Creep-Resistant Steels, 2008)
Created from Fastlane, Scopus look-up

Mechanisms of dislocation multiplication at crack tips - Bitzek, Erik; Gumbsch, Peter (Acta Materialia, 2013)
Whether a stressed material fractures by brittle cleavage or ductile rupture is determined by its ability to convert elastic strain energy to plastic deformation through the generation and motion of dislocations. Although it is known that pre-existing dislocations play a crucial role in crack tip plasticity, the involved mechanisms are unclear. Here it is demonstrated by atomistic simulations that individual pre-existing dislocations may lead to the generation of large numbers of dislocations at the crack tip. The newly generated dislocations are usually of different types. The processes involved are fundamentally different for stationary cracks and propagating cracks. Whereas local crack front reorientation plays an important role in propagating cracks, the multiplication mechanism at stationary cracks is connected with cross-slip in the highly inhomogeneous stress field of the crack. Analysis of the forces acting on the dislocations allows to determine which dislocations multiply and the slip systems they activate. These results provide the necessary physical link between pre-existing dislocations and the generation of dislocations at crack tips.
WW1::974

Microstructural aspects of high temperature deformation of monocrystalline nickel base superalloys: Some open problems - Mughrabi, Hael (Journal of Materials Science & Technology, 2009)
WW1::815

Microstructural fatigue mechanisms: Cyclic slip irreversibility, crack initiation, non-linear elastic damage analysis - Mughrabi, Hael (International Journal of Fatigue, 2013)
WW1::975

Microstructural features of failure surfaces and low-temperature mechanical properties of Ti-6Al-4V ELI ultra-fine grained alloy - Tabachnikova, E. D.; Podolskiy, A. V.; Bengus, V. Z.; Smirnov, S. N.; Csach, K.; Miškuf, J.; Saitova, L. R.; Semenova, I. P.; Valiev, R. Z. (STRENGTH MATER+, 2008)
Microstructural regularities of failure surfaces and low-temperature mechanical characteristics in quasistatic uniaxial tension and compression have been studied for ultra-fine grained structural states of Ti-6Al-4V ELI alloy processed by equal channel angular pressing. Values of the yield stress and uniform strain at 300, 77, and 4.2 K have been compared for structural states of the Ti-6Al-4V ELI alloy that differ in the average grain size and the morphology of α and β phases. Statistical distributions of dimple sizes on the failure surfaces have been studied for different structural states and temperatures. © Springer Science+Business Media, Inc. 2008.
Created from Fastlane, Scopus look-up
Keywords: Equal channel angular pressing; Low temperatures; Mechanical properties

Microstructural mechanisms of cyclic deformation, fatigue crack initiation and early crack growth - Mughrabi, Hael (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2015)
WW1::1030

Microstructure and oxidation resistance of Cr-Ta-Si alloys - Bhowmik, Ayan; Pang, Hon Tong; Neumeier, Steffen; Stone, Howard J.; Edmonds, Ian (Materials Research Society Symposium Proceedings, 2011)
The phase equilibria and oxidation resistance of alloys lying near the Cr-rich end of the Cr-Ta-Si system have been investigated. Samples were prepared by arc-melting and homogenized at 1300°C for 500hrs. Identification of the phases present and their compositions were carried out using x-ray diffraction and electron probe micro-analysis and the ternary phase diagram on the Cr-rich end was plotted. A three-phase equilibria was found to exist between an A2 Cr-solid solution, a hexagonal Laves phase and the A15 Cr3Si intermetallic phase for alloys with higher contents of Si. Thermo-gravimetric analysis of the alloys at 1100°C demonstrated an improvement in the oxidation resistance of the ternary alloys with increasing Si-content. The microstructures of the oxidized samples revealed the formation of a thick chromia layer on top of a Cr,Ta-mixed oxide layer and an internal oxidation zone for all the alloys. A protective silica layer was not observed to form in any of the alloys tested. © 2011 Materials Research Society.
Created from Fastlane, Scopus look-up

Microstructure features of failure and mechanical properties of ultra-fine grained Ti-6AL-4V ELI alloy at 300-77 K - Tabachnikova, Elena D.; Bengus, Vladimir Z.; Podolskiy, Aleksey V.; Smirnov, Sergey N.; Csach, Kornel; Miskuf, Jozef; Saitova, Lilya R.; Semenova, Irina P.; Valiev, Ruslan Z. (International Journal of Mechanics and Materials in Design, 2008)
Experimental investigation of mechanical characteristics and failure regularities of the ultra-fine grained Ti-6Al-4V ELI alloy, produced by equal channel angular pressing (ECAP), have been carried out under the uniaxial tension at 300 and 77 K. These characteristics have been compared for the different structural states of the Ti-6Al-4V ELI alloy, distinguished by the average grain size and by the morphology of α and β phases. It has been established that the combination of the heat treatment, ECAP, and the extrusion of the Ti-6Al-4V ELI alloy leads to a considerable increase of the alloy's strength in comparison with the initial state (54% at 300 K and 78% at 77 K) with preserving the reasonable values of the ductility (3-4% elongation to the neck beginning and 5-10% to the failure). For all investigated structural states of the Ti-6Al-4V ELI alloy only ductile failure was observed at 300 and 77 K. The fracture surface consists of regions failed under normal and shear stresses. In shear failure regions of fracture surface only elongated dimples were present. © 2007 Springer Science+Business Media B.V.
Created from Fastlane, Scopus look-up
Keywords: ECAP; Failure regularities; Tensile testing; Ti-6Al-4V ELI alloy; Ultra dispersed structures

Multiscale modeling of fracture and plasticity in layered structures - Hartmaier, Alexander; Brodling, Nils; Gao, Huajian (Fracture of Nano and Engineering Materials and Structures - Proceedings of the 16th European Conference of Fracture, 2006)
Created from Fastlane, Scopus look-up

Nanotwinned silver nanowires: Structure and mechanical properties - Kobler, Aaron; Beuth, Thorsten; Klöffel, Tobias; Prang, Robby; Moosmann, Markus; Seherer, Torsten; Walheim, Stefan; Hahn, Horst; Kuebel, Christian; Meyer, Bernd; Schimmel, Thomas; Bitzek, Erik (Acta Materialia, 2015)
Ag nanowires have been manufactured with the ultrathin layer electrochemical deposition method. Transmission electron microscopy revealed a multiple twinned nanostructure that has not been reported in comparable structures using a non-template self-assembling preparation method. The [1 1 1] twin planes are oriented parallel to the 〈1 1 2〉 wire axis. The influence of the twin boundaries on the elastic and plastic properties of these wires has been investigated. Atomistic calculations revealed no influence of the twin boundaries on the Young's modulus of the wire for this geometry and along the 〈1 1 2〉 direction. However, the twin boundaries exhibited a strong orientation-dependent influence on the plastic deformation when indented orthogonal (〈1 1 1〉 direction) or parallel (〈1 1 0〉 direction) to the twin boundaries, reflecting the interaction between the glide systems active in fcc metals and the stress direction. Heating experiments showed a high heat resistance for the twin boundaries till sublimation in an in situ TEM heating experiment. Sublimation followed the twin boundaries, indicating the lower binding energy of hcp stacking in comparison to fcc stacking.
WW1::1032

New observations on high-temperature creep at very low stresses - Kumar, Praveen; Kassner, Michael E.; Blum, Wolfgang; Eisenlohr, Philip; Langdon, Terence G. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2009)
WW1::820

On the influence of crack front curvature on the fracture behavior of nanoscale cracks - Möller, Johannes; Bitzek, Erik (Engineering Fracture Mechanics, 2015)
Atomic-scale fracture processes are traditionally investigated in quasi-2D models of straight, infinite cracks. This approach neglects crack front curvature effects, which might be particularly important for nanoscale crack nuclei in semi-brittle materials. Here we use 3D atomistic simulations to study penny-shaped cracks in body-centered cubic metals. Our results show extensive crack tip plasticity initiated by deformation twinning and followed by emission of screw dislocations which cross-slip along the crack front. Together with the interactions of dislocations and/or twins that are nucleated at differently oriented parts of the crack, these processes determine the fracture behavior of highly curved nanoscale crack
WW1::1006
Keywords: Cross-slip; Molecular dynamics simulation; Penny-shaped crack; Semi-brittle fracture; Twinning

On the presence of nanoscale heterogeneity in Al70Ni15Co15 metallic glass under pressure - Atila, Achraf; Kbirou, Meryem; Ouaskit, Said; Hasnaoui, Abdellatif (Journal of Non-Crystalline Solids, 2020)
We used molecular dynamics simulations to investigate the dependence of the atomic-scale structure on the temperature and pressure conditions of Al70Ni15Co15 metallic glass. The effect of pressure variations on the glass transition temperature was also studied, showing an increase with pressure. Moreover, radial distribution function, coordination number, and Voronoi tessellation analysis indicate that the applied pressure affects the local structure of glassy Al70Ni15Co15. We used a local symmetry parameter to access the glass-forming ability of the metallic glasses cooled under different pressures. The glasses cooled under high-pressures showed a significant fraction of embedded crystalline structure, which was found to be surrounded by a region of mixed-like clusters playing the role of an interface between the crystalline region and the glassy region. The correlation length, as calculated from the full width at half maximum of the first sharp diffraction peak, indicated an increase of the medium-range order with the increase of pressure. The evolution of the heterogeneity with pressure was highlighted by the existence of nanoscale crystals (1 to 4 nm in size)embedded in the amorphous zone. Finally, we discuss the results by referring to the atomic potential energy and stress.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Correlation length; Glass transition; Heterogeneity; Local atomic structure; Medium-range order

Pair vs many-body potentials: Influence on elastic and plastic behavior in nanoindentation of fcc metals - Ziegenhain, Gerolf; Hartmaier, Alexander; Urbassek, Herbert M. (Journal of the Mechanics and Physics of Solids, 2009)
WW1::821

Preface - Götz-Votteler, Katrin; Herbst, Thomas; Bergenholtz, Henning (Zeitschrift für Anglistik und Amerikanistik, 2009)

Preface - Mossakowski, Till; Roggenbach, Markus; Schröder, Lutz (Electronic Communications of the EASST, 2013)

Preface - Shaw, Leon L.; Larsen, James M.; Liaw, Peter K.; Mughrabi, Hael; Endo, Masahiro; Kostorz, Gernot (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2007)

Psalmlieder - Klek, Konrad (Quatember, 2014)

Quasi-Stationary Strength of ECAP-Processed Cu-Zr at 0.5 T-m - Blum, Wolfgang; Dvorak, Jiri; Kral, Petr; Eisenlohr, Philip; Sklenicka, Vaclav (Metals, 2019)
The influence of the grain structure on the tensile deformation strength is studied for precipitation-strengthened Cu-0.2%Zr at 673K. Subgrains and grains are formed by equal channel angular pressing (ECAP) and annealing. The fraction of high-angle boundaries increases with prestrain. Subgrains and grains coarsen during deformation. This leads to softening in the quasi-stationary state. The initial quasi-stationary state of severely predeformed, ultrafine-grained material exhibits relatively high rate-sensitivity at relatively high stresses. This is interpreted as a result of the stress dependences of the quasi-stationary subgrain size and the volume fraction of subgrain-free grains.
CRIS-Team WoS Importer:2020-01-10

Reversible cyclic deformation mechanism of gold nanowires by twinning-detwinning transition evidenced from in situ TEM - Lee, Subin; Im, Jiseong; Yoo, Youngdong; Bitzek, Erik; Kiener, Daniel; Richter, Gunther; Kim, Bongsoo; Oh, Sang Ho (Nature Communications, 2014)
Mechanical response of metal nanowires has recently attracted a lot of interest due to their ultra-high strengths and unique deformation behaviours. Atomistic simulations have predicted that face-centered cubic metal nanowires deform in different modes depending on the orientation between wire axis and loading direction. Here we report, by combination of in situ transmission electron microscopy and molecular dynamic simulation, the conditions under which particular deformation mechanisms take place during the uniaxial loading of [110]-oriented Au nanowires. Furthermore, by performing cyclic uniaxial loading, we show reversible plastic deformation by twinning and consecutive detwinning in tension and compression, respectively. Molecular dynamics simulations rationalize the observed behaviours in terms of the orientation-dependent resolved shear stress on the leading and trailing partial dislocations, their potential nucleation sites and energy barriers. This reversible twinning-detwinning process accommodates large strains that can be beneficially utilized in applications requiring high ductility in addition to ultra-high strength.

Revisiting “Steady-State” Monotonic and Cyclic Deformation: Emphasizing the Quasi-Stationary State of Deformation - Mughrabi, Hael (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2020)
High-temperature creep, cyclic deformation in saturation, and a number of technologically important processes are typical examples of the so-called “steady-state” deformation. These cases are usually defined in terms of the constancy of the mechanical parameters. Moreover, it is usually assumed that the deformation-induced microstructure undergoes no further changes. However, clear evidence shows that non-negligible microstructural changes continue to occur in the so-defined steady-state high-temperature creep and in cyclic saturation. It can be shown that the so-called “steady-state” deformation is actually a quasi-stationary deformation which is characterized by the initial development of a “mechanical steady state”, which is followed with a delay by a “microstructural steady state.” Only the latter can then be considered as a true steady state. A deeper analysis reveals a persistent slight increase of the dislocation density, with geometrically necessary dislocations in the cell walls/subgrain boundaries, causing the latter to transform gradually into sharper boundaries with higher misorientations. These findings, based on a detailed analysis of a wide range of experimental studies, are found to be almost identical for both high-temperature creep and cyclic deformation in saturation and are hence considered as characteristic of quasi-stationary deformation. The analysis clarifies, as a by-product, specific effects which arise from the increasing heterogeneity of the dislocation pattern (patterning). Thus, a marked decrease of the arrangement factor “alpha” in the Taylor flow stress is noted, as patterning proceeds, in agreement with predictions of the so-called composite model. Since this effect is compensated partially by the increase of the dislocation density, the flow stress remains rather insensitive to subtle microstructural changes. Based on these facts, the need for revision of current flow-stress formulations in future dislocation modeling is emphasized.
CRIS-Team Scopus Importer:2020-02-14

Rezension - Pirner, Manfred (Zeitschrift für Pädagogik und Theologie, 2012)

Role of boundaries in control of deformation rate and strength of crystalline materials - Blum, Wolfgang (Materials Science Forum, 2009)
Plastic deformation of crystalline materials is not controlled by interaction among free dislocations only, but the interaction of free dislocations with internal boundaries. i) Low-angle boundaries: Modeling of deformation of pure materials with conventional grain size on the basis of structure evolution indicates that low-angle boundaries act as obstacles of free dislocations. The migration of the low-angle boundaries constitutes an essential recovery process determining the deformation resistance in the steady state. ii) High-angle boundaries: Severe plastic deformation transforms low-angle boundaries into high-angle ones. They differ in obstacle and recovery characteristics from low-angle boundaries, which explains the special properties of ultrafine-grained and nanocrystalline materials with regard to strength, strain rate sensitivity and ductility. iii) Phase boundaries in Ni-base superalloys enhance the strengthening by hard phases with strengthening by dense dislocation networks serving to reduce coherency stresses. It is concluded that internal boundaries play a crucial role in controlling the evolution of structure and strength in crystalline materials. © (2009) Trans Tech Publications.
Created from Fastlane, Scopus look-up
Keywords: Annihilation of dislocations; Creep rate; Deformation resistance; Dislocation structure; Flow stress; Generation of dislocations; High-angle boundaries; Low-angle boundaries; Nanostructured materials; Phase boundaries; Steady state deformation

Role of boundaries in control of deformation rate and strength of crystalline materials - Blum, Wolfgang (Materials Science Forum, 2009)
WW1::825

Sinne und Künste - Zirfas, Jörg (Modulør : Architektur, Immobilien, Recht, 2012)

Size-Dependent Brittle-to-Ductile Transition in Silica Glass Nanofibers - Luo, Junhang; Wang, Jianwei; Bitzek, Erik; Huang, Jian Yu; Zheng, He; Tong, Limin; Yang, Qing; Li, Ju; Mao, Scott X. (Nano Letters, 2016)
WW1::1057
Keywords: Simulation and Modeling

Sol LeWitt - Dickel, Hans (Texte zur Kunst, 2007)

Solving Material Mechanics and Multiphysics Problems of Metals with Complex Microstructures Using DAMASK—The Düsseldorf Advanced Material Simulation Kit - Diehl, Martin; Wang, Ding; Liu, Chuanlai; Rezaei Mianroodi, Jaber; Han, Fengbo; Ma, Duancheng; Kok, Piet J.J.; Roters, Franz; Shanthraj, Pratheek (Advanced Engineering Materials, 2020)
Predicting process–structure and structure–property relationships are the key tasks in materials science and engineering. Central to both research directions is the internal material structure. In the case of metallic materials for structural applications, this internal structure, the microstructure, is the collective ensemble of all equilibrium and nonequilibrium lattice imperfections. Continuum models to derive process–structure and structure–property relationships are based on two ingredients: 1) quantitative state variables that capture the essential features of the material's state and 2) kinetic equations for the state that describe its evolution under load. Successful models, that is, models that are of practical use, depend on state variables and corresponding evolution laws that are sufficiently representative for the microstructure and that are able to describe the phenomena of interest. The development of software tools capable to integrate these different aspects to get a holistic view of process–structure–property relationships requires joint efforts from specialists in different disciplines and a long-term perspective. The Düsseldorf Advanced Material Simulation Kit (DAMASK) is such a tool. In this overview article published on the occasion of Advanced Engineering Materials' 20th anniversary, some representative application examples which demonstrate how DAMASK can be used to study metallic microstructures at different length scales are presented.
CRIS-Team Scopus Importer:2020-02-25
Keywords: crystal plasticity; multiphysics; open-source software; simulation

Strain Rate Contribution due to Dynamic Recovery of Ultrafine-Grained Cu-Zr as Evidenced by Load Reductions during Quasi-Stationary Deformation at 0.5 T-m - Blum, Wolfgang; Dvorak, Jiri; Kral, Petr; Eisenlohr, Philip; Sklencka, Vaclav (Metals, 2019)
During quasi-stationary tensile deformation of ultrafine-grained Cu-0.2 mass%Zr at 673 K and a deformation rate of about 10(-4) s(-1) load changes were performed. Reductions of relative load by more than about 25% initiate anelastic back flow. Subsequently, the creep rate turns positive again and goes through a relative maximum. This is interpreted by a strain rate component E- associated with dynamic recovery of dislocations. Back extrapolation indicates that E- contributes the same fraction of (20 +/- 10)% to the quasi-stationary strain rate that has been reported for coarse-grained materials with high fraction of low-angle boundaries; this suggests that dynamic recovery of dislocations is generally mediated by boundaries. The influence of anelastic back flow on E- is discussed. Comparison of E- to the quasi-stationary rate points to enhancement of dynamic recovery by internal stresses. Subtraction of
CRIS-Team WoS Importer:2020-01-10

Structure evolution and deformation resistance in production and application of ultrafine-grained materials - The concept of steady-state grains - Blum, Wolfgang; Eisenlohr, Philip (Materials Science Forum, 2011)
WW1::902

Synthesis and high-temperature evolution of polysilylcarbodiimide-derived SiCN ceramic coatings - Klausmann, Amon; Morita, Koji; Johanns, Kurt E.; Fasel, Claudia; Durst, Karsten; Mera, Gabriela; Riedel, Ralf; Ionescu, Emanuel (Journal of the European Ceramic Society, 2015)
WW1::1035

Tag, you're it - Costanzo, A.; Masotti, D.; Ußmüller, Thomas; Weigel, Robert (IEEE Microwave Magazine, 2013)
elib2cris::1512001600,costanzo2013

Temperature dependence of the strength of fine- and ultrafine-grained materials - Schneibel, J. H.; et al. (Acta Materialia, 2011)
WW1::906

The a-factor in the Taylor flow-stress law in monotonic, cyclic and quasi stationary deformations: Dependence on slip mode, dislocation arrangement and density - Mughrabi, Hael (Current Opinion in Solid State & Materials Science, 2016)
WW1::1072

The importance of sign and magnitude of γ/γ′ lattice misfit in superalloys - With special reference to the new γ′-hardened cobalt-base superalloys - Mughrabi, Hael (Acta Materialia, 2014)
WW1::1012

The influence of long-term annealing at room temperature on creep behaviour of ECAP-processed copper - Blum, Wolfgang; et al. (Materials Letters, 2017)
Present work investigates the effect of long-term annealing at low homologous temperature (similar to 0.22 T-m) on creep behaviour of pure copper (99.99%) processed by equal-channel angular pressing (ECAP). Coarse-grained pure copper was processed by 1 and 8 ECAP passes at room temperature. The ECAP-processed specimens were annealed at room temperature for 3 years. Microstructures of ECAP-processed specimens and their room temperature-annealed states were investigated by electron back scatter diffraction (EBSD) technique. Tensile tests were performed at room temperature under constant rate and at 373 Kin creep under constant load. It was found that long-term annealing at room temperature led to occurrence of large grains in microstructure which influenced the strength. The influence grew with number of ECAP passes.
Keywords: Equal-channel angular pressing (ECAP); Ultrafine-grained microstructure; Creep behaviour; Microstructure stability

The strength limit in a bio-inspired metallic nanocomposite - Broedling, Nils C.; Hartmaier, Alexander; Buehler, Markus J.; Gao, Huajian (Journal of the Mechanics and Physics of Solids, 2008)
WW1::791

Three-dimensional electron backscattered diffraction analysis of deformation in MgO micropillars - Korte, Sandra; Ritter, M.; Jiao, C.; Midgley, P. A.; Clegg, W. J. (Acta Materialia, 2011)
Small-scale testing is extensively used to study the effects of size on plasticity or characterise plastic deformation of brittle materials, where cracking is suppressed on the microscale. Geometrical and experimental constraints have been shown to affect small-scale deformation and efforts are underway to understand these better. However, current analytical techniques tend to possess high resolution in only one or two dimensions, impeding a detailed analysis of the entire deformed volume. Here electron backscattered diffraction in three dimensions is presented as a way of characterising three-dimensional (3-D) deformation at high spatial resolution. It is shown that, by reconstruction of compressed and then successively sliced and indexed MgO micropillars, this 3-D technique yields information complementary to μ-Laue diffraction or electron microscopy, allowing a correlation of experimental artefacts and the distribution of plasticity. In addition, deformation features which are difficult to visualise by standard scanning electron microscopy are easily detected, for example where only small surface traces are produced or minimal plastic strain can be introduced before failure in brittle materials. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Compression test; Crystalline oxides; Electron backscattering diffraction; Plastic deformation; Scanning electron microscopy

Transdifference - Breinig, Helmbrecht; Lösch, Klaus (Journal for the study of British cultures, 2006)

Using Supercritical Carbon Dioxide for Physical Foaming of Advanced Polymer Materials - Wolff, Friederich; Zirkel, Larissa; Sarah, Betzold; Jakob, Matthias; Verena, Maier; Nachtrab, Frank; Ceron Nicolat, Bruno; Fey, Tobias; Münstädt, Helmut (International Polymer Processing, 2011)
Foams from high performance polymers find more and more interest. The processes to generate them can be difficult, however. It is shown how physical foaming with CO2 can be used as a first step to assess the potentials of such materials. For investigations of such kind an autoclave on a laboratory scale which allows pressure variations up to 300 bars and temperatures up to 300 degrees C was set up. The samples are saturated with supercritical carbon dioxide (s.c. CO2) which acts as a foaming agent. Depending on the process and material parameters different foam characteristics and cell morphologies were obtained and characterised. The potential of this method is demonstrated for two different classes of advanced polymer materials, thermoplastic fluoropolymers (PEP), and a silicone resin. In the case of the fluoropolymer, previously prepared films were foamed and the effects of various process parameters on the foam characteristics were investigated. Besides the general potential of foams from fluoropolymers, they are candidates for polymeric piezoelectric materials with a relatively high temperature stability. Silicone polymers possess some properties superior to common organic polymers. First results on the foaming behaviour of a silicone resin are presented.

Very high cycle fatigue for single phase ductile materials: Comparison between α-iron, copper and α-brass polycrystals - Favier, Veronique; Blanche, Antoine; Wang, Chong; Ngoc Lam Phung,; Ranc, Nicolas; Wagner, Daniele; Bathias, Claude; Chrysochoos, Andre; Mughrabi, Hael (International Journal of Fatigue, 2016)
WW1::1083

Very high cycle fatigue of copper: Evolution, morphology and locations of surface slip markings - Phung, N. L.; Favier, V.; Ranc, N.; Vales, F.; Mughrabi, Hael (International Journal of Fatigue, 2014)
WW1::1015

What is "stationary" deformation of pure Cu? - Blum, Wolfgang; Dvorak, J.; Kral, Petr; Eisenlohr, Philip; Sklenicka, V. (Journal of Materials Science, 2014)
WW1::1016